12dB of noise reduction by a NOLM based 2-R regenerator - Schmauß, Bernhard; Rösch, Matthias; et al. (IEEE Photonics Technology Letters, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.12dbof

12 dB of Noise Reduction by a NOLM based all optical all passive Regenerator - Meißner, Markus; Rösch, Matthias; Schmauß, Bernhard; Leuchs, Gerd (CLEO Europe, June, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.12dbof_5

2D Carbon Allotrope with Incorporated Au-Ag Nanoclusters - Laser-Induced Synthesis and Optical Characterization - Manshina, Alina; Petrov, Yuriy; Kolesnikov, I.; Mitetelo, N. V.; Murzina, T. V.; Butt, M. A.; Neugebauer, M.; Banzer, Peter; Leuchs, Gerd (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
We discuss the laser-induced fabrication and detailed structural and optical characterization of a novel carbon allotrope intercalated with bimetallic nanoclusters.
CRIS-Team Scopus Importer:2019-05-21

2R-Regeneration of an 80-Gb/s RZ-DQPSK signal by a nonlinear amplifying loop mirror - Cvecek, Kristian; Sponsel, Klaus; Ludwig, R.; Schubert, C.; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2007)
The performance of a nonlinear amplifying loop mirror as a 2R-regenerator for an 80-Gb/s return-to-zero differential-quadrature-phase-shift-keyed signal has been investigated experimentally. A significant eye-opening improvement and a negative power penalty of up to 2.6 dB were obtained. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.2rrege
Keywords: 2R-regeneration; All-optical regeneration; Differential quadrature phase-shift keying (DQPSK); Nonlinear amplifying loop mirror (NALM)

2R-Regeneration of an RZ-DPSK Signal Using a Nonlinear Amplifying Loop Mirror - Cvecek, K; Sponsel, K; Onishchukov, G; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2007)
The performance of a nonlinear amplifying loop mirror as a 2R-regenerator for return-to-zero differential-phase-shift-keyed signals has been investigated experimentally. The measured power characteristics and phase functions show that the signal amplitude is regenerated while the signal phase is preserved in the setup. A significant eye-opening improvement and a negative power penalty of about 1.5 dB were obtain
lhft_intern.bib::cvecek07

>30 dB Suppression of Intrinsic Backscattering in Whispering-Gallery-Mode Microresonators - Svela, Andreas O.; Silver, Jonathan M.; Del Bino, Leonardo; Zhang, Shuangyou; Woodley, Michael T.M.; Vanner, Michael R.; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We demonstrate a technique for suppressing backscattered light in a whispering-gallery-mode resonator by positioning a sub-wavelength-size scatterer within its evanescent field, achieving at least 34 dB suppression compared to the intrinsic backscattering.
CRIS-Team Scopus Importer:2021-12-24

30 years of squeezed light generation - Andersen, Ulrik L.; Gehring, Tobias; Marquardt, Christoph; Leuchs, Gerd (Physica Scripta, 2016)
Squeezed light generation has come of age. Significant advances on squeezed light generation have been made over the last 30 years - from the initial, conceptual experiment in 1985 till today's top-tuned, application-oriented setups. Here we review the main experimental platforms for generating quadrature squeezed light that have been investigated in the last 30 years.
CRIS-Team Scopus Importer:2022-06-05
Keywords: entanglement; quantum optics; squeezed light

3.9-dB OSNR Gain by an NOLM-Based 2-R Regenerator - Meißner, Markus; Sponsel, Klaus; Cvecek, Kristian; Benz, S.; Weisser, B.; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2004)
We experimentally demonstrate bit-error-rate (BER) improvement of more than nine decades by an asymmetric nonlinear optical loop mirror (NOLM). This can be related to an optical signal-to-noise ratio (OSNR) gain of up to 3.9 dB with respect to the NOLM input OSNR at a bit rate of 40 GB/s. The principle of operation of NOLM-based 2-R regeneration with respect to BER improvement is investigated and it is experimentally shown that BER improvement cannot be detected directly at the regenerator's output. © 2004 IEEE.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.39dbos

3D-imaging of human skin - optical in vivo tomography and topology by short coherence interferometry - Häusler, Gerd; et al. (Proceedings of SPIE, 1997)
We discuss different modifications of white light interferometry, for the acquisition of human skin morphology. In a first experiment we display the diffusion of light within tissue, versus time. Light is focused onto the surface of the sample, penetrates the sample, is scattered and partly emerges from the surface again. For each point of the surface we can measure a certain run time profile of the emerging photons, via the speckle contrast. The local scattering behavior of the skin is encoded in the run time profile. Further we present a sensor for the acquisition of cross-sectional images of volume scatterers, we call it "spectral radar." The scattering amplitude a(z) along one vertical axis from the surface into the bulk can be measured within one exposure. No reference arm scanning is necessary, hence a short measurement time is possible. The depth uncertainty within a range of 1000 μm is about 10 μm. In first measurements we distinguished a melanoma maligna from healthy skin, in vitro and we measured the thickness of a fingernail in vivo. We further demonstrate a third method, the "coherence radar" for in vivo measurements of skin surface topology, with an accuracy of a few micrometers, and a field of 512 x 512 pixels. ©2004 Copyright SPIE - The International Society for Optical Engineering.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.3dimag
Keywords: Coherence radar; Human skin; Multiple scattering; Oct; Short coherence interferometry; Skin cancer; Spectral radar; Texture analysis; Volume scatterer

3D-Opto-MID Coupling Concept Using Printed Waveguides - Lorenz, Lukas; Backhaus, Carsten; Bock, Karlheinz; Lindlein, Norbert (Springer International Publishing, 2022)
The central question for Chap. 6 is how to connect optical multimode waveguides without interruption. Such systems are needed in device communication for the bus coupling of 3D-Opto-MID. A novel coupling concept (AOBC: asymmetrical optical bus coupler) is presented in this chapter. By coupling two cores at the side surfaces, it is possible to realize a bidirectional connection. The most important innovation of the presented principle is the possibility of asymmetric coupling, depending on the coupling direction. This makes it possible to couple less power from the bus into the module than vice versa. This ensures that enough optical power remains in the bus to provide the signal for all connected modules. On the other hand, it ensures that a module signal can also be reliably detected. This functionality is missing in known principles and has so far prevented purely optical bus systems from gaining acceptance in extended structures.
CRIS-Team Scopus Importer:2024-12-16

3D Real Time Camera - Häusler, Gerd; et al. (Proc. of the 3rd Int. Workshop on Automatic Processing of Fringe Patterns, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.3dreal

8 QAM regeneration using a phase-sensitive amplifier with dual-conjugated pumps - Stiller, Birgit; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
CRIS-Team Scopus Importer:2021-06-29

Abandoned Functionality of Thin-Film Opal Photonic Crystals - Kuechenmeister, Jens; Wolff, Christian; Busch, Kurt; Peschel, Ulf; Romanov, Sergey (Advanced Optical Materials, 2013)
Angle-resolved polarized transmission spectra of thin-film opals are studied experimentally and theoretically as a function of the azimuthal rotation of the plane of incidence at different angles of light incidence. In such 3-dimensional lattices, the refraction acquires the form of diffraction orders, each with a distinct spectrum, that propagate simultaneously along different directions. The corresponding continuous and patchy stop-bands in the photonic energy band structure of the opal photonic crystal are determined numerically. For diffraction at high Miller index planes, the diffraction pattern is often distorted due to multiple-wave diffraction. The finite stacking of hexagonally close-packed layers leads to an intrinsic 3-fold rotation symmetry of these spectra, which is particularly pronounced in transmission for frequencies that correspond to wave vectors within the 1st Brillouin zone. Despite the cubic symmetry of the opal lattice, cross-polarization coupling effects occur in the volume of the opal crystal. These effects are associated with the fact that, the opal eigenmodes are Bloch waves whose electromagnetic field distributions and dispersion relations are markedly different from plane waves.
EAM Import::2019-03-13

About the scaling behavior of optical range sensors - Häusler, Gerd (Proc. of the 3rd Int. Workshop on Automatic Processing of Fringe Patterns, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.aboutt

Absolute calibration in grazing incidence interferometry via rotational averaging. - Mantel, Klaus Peter; Lamprecht, Jürgen; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2006)
Interferometry in grazing incidence can be used to test cylindrical mantle surfaces. The absolute accuracy of the resulting surface profiles is limited by systematic wavefront aberrations caused in the interferometer, in particular due to an inversion of the test wavefront in an interferometer using diffractive beam splitters. For cylindrical specimens, a calibration method using four positions has therefore been investigated. This test is combined with another method of optical metrology: the rotational averaging procedure. The implementation for grazing incidence is described and measurement results for hollow cylinders are presented. The gain in accuracy is demonstrated.
UnivIS-Import:2015-04-14:Pub.2006.nat.dphy.optik.1optik.absolu

Absolute sphericity measurement: a comparative study of the use of interferometry and a Shack-Hartmann sensor - Lindlein, Norbert; et al. (Optics Letters, 1998)
A comparison of absolute sphericity measurements with a Shack-Hartmann sensor and a Twyman-Green interferometer is presented. The absolute deviations of a test sphere from its ideal shape were calculated in both cases from the measured wave aberrations of three different positions. Very good qualitative and quantitative agreement of the results was achieved. The difference of the root-mean-square values of the two methods was 1/1000 of a wavelength. © 1998 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.absolu

Absolute sphericity measurement: a comparative study on the use of interferometry and a Shack-Hartmann sensor - Lindlein, Norbert; et al. (Proceedings of the 1998 International Symposium on Information Theory, CLEO/EUROPE'98, 1998)
A comparative study of the performance of the Shack-Hartmann sensor (SHS) and interferometry in absolute sphericity tests was conducted. The absolute sphericity test was carried out with an existing TWG using the phase shifting technology. The same set-up and identical measurements were used to measure the wave fields in front of the SHS. For the SHS measurements, the reference arm of the TWG was obscured. The measured concave surface had a diameter of 40mm and a radius of curvature of 41mm. The used wavelength was λ=632.8nm and the distance of the contours in the plots is 0.050λ.

Absolute testing of aspherics in transmitted light using an amplitude DOE - Lindlein, Norbert; et al. (6th International Workshop on Advanced Optical Metrology, Fringe 2009, 2009)

Absolute testing of the reference surface of a Fizeau interferometer through even/odd decompositions - Schreiner, Roland; Schwider, Johannes; Lindlein, Norbert; Mantel, Klaus Peter (Applied Optics, 2008)
Absolute testing of spherical surfaces is a technological necessity because of increased accuracy requirements. In a Fizeau setup, the main part of the interferometer deviations thereby comes from the reference surface. We demonstrate the validity of an absolute testing procedure for the reference surface that has been proposed earlier. The procedure relies on the decomposition of the surface deviations into odd and even parts and could be used in partially coherent illumination. The odd deviations are obtained from a basic and a 180°-rotated position of an auxiliary sphere, and the even deviations can be measured with the help of a cat's eye position in double pass using an opaque half screen in the interferometer aperture. © 2008 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2008.nat.dphy.optik.1optik.absolu

Absoluttest von rotationssymmetrischen Asphären mittels radialem Shearing - Mantel, Klaus; Geist, Eduard; Harder, Irina; Lindlein, Norbert (DGAO-Proceedings, 2010)

Absolutverfahren zum Nulltest asphärischer Linsen im Durchlicht - Berger, Andreas; Mantel, Klaus; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Acceptance Tests of more than 10 000 Photomultiplier Tubes for the multi-PMT Digital Optical Modules of the IceCube Upgrade - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
More than 10 000 photomultiplier tubes (PMTs) with a diameter of 80 mm will be installed in multi-PMT Digital Optical Modules (mDOMs) of the IceCube Upgrade. These have been tested and pre-calibrated at two sites. A throughput of more than 1000 PMTs per week with both sites was achieved with a modular design of the testing facilities and highly automated testing procedures. The testing facilities can easily be adapted to other PMTs, such that they can, e.g., be re-used for testing the PMTs for IceCube-Gen2. Single photoelectron response, high voltage dependence, time resolution, prepulse, late pulse, afterpulse probabilities, and dark rates were measured for each PMT. We describe the design of the testing facilities, the testing procedures, and the results of the acceptance tests.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cherenkov detectors; Neutrino detectors; Photon detectors for UV; HPDs; others); visible and IR photons (vacuum) (photomultipliers

Accessing the Phase Quadrature of Intense Non-Classical Light States - Leuchs, Gerd; et al. (Quantum Information with continuous variables of atoms and light, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dphy.optik.1optik.access

Accounting for changing snow over 10 years of IceTop, and its impact on the all-particle cosmic ray spectrum - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceTop surface detector of the IceCube Neutrino Observatory measures extensive air showers (EAS). Coincident signals in both tanks of an IceTop station result primarily from the electromagnetic component of the EAS, and events which trigger at least 5 stations correspond to energies roughly above the knee, with an energy threshold and reconstruction behavior that changes over time as snow accumulates above the array. We present a status report of an analysis of ≥ 5-station events in IceTop from 2011-2021, which will be used to measure the all-particle spectrum of cosmic rays in the transition region from galactic to extragalactic sources up to EeV range, using updated simulations and improved treatments of snow attenuation. In particular, a snow model has been developed which takes the non-attenuating muon content of tank signals, as well as their saturation behavior, into account.
CRIS-Team Scopus Importer:2025-02-04

Achieving Gaussian outputs from large-mode-area higher-order-mode fibers - Lindlein, Norbert; Leuchs, Gerd; Ramachandran, Srinivasan (Applied Optics, 2007)
We describe an alternative to fiber-gratings for converting higher-order LP0om (m > 1) fiber modes into a nearly fundamental Gaussian shape at the output of a fiber. This schematic enables the use of light propagation in higher-order modes of a fiber, a fiber-platform that has recently shown great promise for achieving very large mode areas needed for future high-power lasers and amplifiers. The conversion will be done by using a binary phase plate in the near field of the fiber, which emits the LPom mode. Since the binary phase plate alone cannot increase the quality factor M2 of the laser beam because of some broad sidebands, a filtering of the sidebands is done in the Fourier plane of a telescope. Of course, this will cost some of the total light power, but on the other side the M2 factor can be reduced to nearly the ideal value near 1.0, and it is shown that ∼76% of the total light power can be conserved for all investigated modes (2≤m≤8). A tolerance analysis for the phase plate and its adjustment is made, and different optical imaging systems to form a magnified image of the fiber mode on the phase plate are discussed in order to have more tolerance for the adjustment of the phase plate. © 2007 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.achiev

Achromatic diffractive fan-out systems - Lindlein, Norbert; et al. (Proceedings of SPIE, 1994)
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.optik.1optik.achrom

A complete basis of generalized Bell states - Sych, Denis; Leuchs, Gerd (New Journal of Physics, 2009)
A generalization of the Bell states and Pauli matrices to dimensions which are powers of 2 is considered. A basis of maximally entangled multidimensional bipartite states (MEMBS) is chosen very similar to the standard Bell states and constructed of only symmetric and antisymmetric states. This special basis of MEMBS preserves all basic properties of the standard Bell states. We present a recursive and non-recursive method for the construction of MEMBS and discuss their properties. The antisymmetric MEMBS possess the property of rotationally invariant exclusive correlations which is a generalization of the rotational invariance of the antisymmetric singlet Bell state. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.acompl

A confocal profilometer using microlens arrays - Lindlein, Norbert; et al. (Technical digest / Optical Society of America, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.aconfo

Adaptive frequency comb illumination for interferometry in the case of nested two-beam cavities - Harder, Irina; Leuchs, Gerd; Mantel, Klaus Peter; Schwider, Johannes (Applied Optics, 2011)

Addressing RB and CS transitions with a tunable source of photon pairs - Schunk, Gerhard; Vogl, Ulrich; Förtsch, Michael; Strekalov, Dmitry; Sedlmeir, Florian; Schwefel, Harald G.L.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2014)
CRIS-Team Scopus Importer:2022-06-05

A Fibre-Optical Implementation of Range Sensors, based on the 'Spectral Radar' - Häusler, Gerd; et al. (Proceedings of the EOS Topical Meeting Free Space Micro-Optical Systems, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.afibre

After-gate attack on a quantum cryptosystem - Wiechers, C.; Lydersen, L.; Wittmann, C.; Elser, Dominique Alexander; Skaar, Johannes; Marquardt, Christoph; Makarov, V.; Leuchs, Gerd (New Journal of Physics, 2011)
We present a method to control the detection events in quantum key distribution systems that use gated single-photon detectors. We employ bright pulses as faked states, timed to arrive at the avalanche photodiodes outside the activation time. The attack can remain unnoticed, since the faked states do not increase the error rate per se. This allows for an intercept-resend attack, where an eavesdropper transfers her detection events to the legitimate receiver without causing any errors. As a side effect, afterpulses, originating from accumulated charge carriers in the detectors, increase the error rate. We have experimentally tested detectors of the system id3110 (Clavis2) from ID Quantique. We identify the parameter regime in which the attack is feasible despite the side effect. Furthermore, we outline how simple modifications in the implementation can make the device immune to this attack. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

A generator for unique quantum random numbers based on vacuum states - Gabriel, Christian; Wittmann, Christoffer; Sych, Denis; Dong, Ruifang; Mauerer, Wolfgang; Andersen, Ulrik L.; Marquardt, Christoph; Leuchs, Gerd (Nature Photonics, 2010)
Random numbers are a valuable component in diverse applications that range from simulations1 over gambling to cryptography2,3. The quest for true randomness in these applications has engendered a large variety of different proposals for producing random numbers based on the foundational unpredictability of quantum mechanics4-11. However, most approaches do not consider that a potential adversary could have knowledge about the generated numbers, so the numbers are not verifiably random and unique 12-15. Here we present a simple experimental setup based on homodyne measurements that uses the purity of a continuous-variable quantum vacuum state to generate unique random numbers. We use the intrinsic randomness in measuring the quadratures of a mode in the lowest energy vacuum state, which cannot be correlated to any other state. The simplicity of our source, combined with its verifiably unique randomness, are important attributes for achieving high-reliability, high-speed and lowcost quantum random number generators. © 2010 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Agile and Versatile Quantum Communication: Signatures and Secrets - Richter, Stefan; Thornton, Matthew; Khan, Imran; Scott, Hannah; Jaksch, Kevin; Vogl, Ulrich; Stiller, Birgit; Leuchs, Gerd; Marquardt, Christoph; Korolkova, Natalia (Physical Review X, 2021)
Agile cryptography allows for a resource-efficient swap of a cryptographic core in case the security of an underlying classical cryptographic algorithm becomes compromised. Conversely, versatile cryptography allows the user to switch the cryptographic task without requiring any knowledge of its inner workings. In this paper, we suggest how these related principles can be applied to the field of quantum cryptography by explicitly demonstrating two quantum cryptographic protocols, quantum digital signatures (QDS) and quantum secret sharing (QSS), on the same hardware sender and receiver platform. Crucially, the protocols differ only in their classical postprocessing. The system is also suitable for quantum key distribution (QKD) and is highly compatible with deployed telecommunication infrastructures, since it uses standard quadrature phase-shift keying encoding and heterodyne detection. For the first time, QDS protocols are modified to allow for postselection at the receiver, enhancing protocol performance. The cryptographic primitives QDS and QSS are inherently multipartite, and we prove that they are secure not only when a player internal to the task is dishonest, but also when (external) eavesdropping on the quantum channel is allowed. In our first proof-of-principle demonstration of an agile and versatile quantum communication system, the quantum states are distributed at GHz rates. A 1-bit message may be securely signed using our QDS protocols in less than 0.05 ms over a 2-km fiber link and in less than 0.2 s over a 20-km fiber link. To our knowledge, this also marks the first demonstration of a continuous-variable direct QSS protocol.
CRIS-Team Scopus Importer:2021-03-19

A highly miniaturized satellite payload based on a spatial heterodyne spectrometer for atmospheric temperature measurements in the mesosphere and lower thermosphere - Kaufmann, Martin; Olschewski, Friedhelm; Mantel, Klaus; Solheim, Brian; Shepherd, Gordon; Deiml, Michael; Liu, Jilin; Song, Rui; Chen, Qiuyu; Wroblowski, Oliver; Wei, Daikang; Zhu, Yajun; et al. (Atmospheric Measurement Techniques, 2018)
A highly miniaturized limb sounder for the observation of the O2 A-Band to derive temperatures in the mesosphere and lower thermosphere is presented. The instrument consists of a monolithic spatial heterodyne spectrometer (SHS), which is able to resolve the rotational structure of the R-branch of that band. The relative intensities of the emission lines follow a Boltzmann distribution and the ratio of the lines can be used to derive the kinetic temperature. The SHS operates at a Littrow wavelength of 761.8 nm and heterodynes a wavelength regime between 761.9 nm and 765.3 nm with a resolving power of about 8000 considering apodization effects. The size of the SHS is 38 × 38 × 27 mm3 and its acceptance angle is ±5°. It has an etendue of 0.014 cm2 sr. Complemented by a front optics with a solid angle of 0.65° and a detector optics, the entire optical system fits into a volume of about 1.5 liters. This allows to fly this instrument on a 3 or 6 unit CubeSat. The vertical field of view of the instrument is about 60 km at the Earth's limb if operated in a typical low Earth orbit. Integration times to obtain an entire altitude profile of nighttime temperatures are in the order of one minute for a vertical resolution of 1.5 km and a random noise level of 1.5 K. Daytime integration times are one order of magnitude shorter. This work presents the design parameters of the optics and a radiometric assessment of the instrument. Furthermore it gives an overview of the required characterization and calibration steps. This includes the characterization of image distortions in the different parts of the optics, flat fielding and the spectral power estimatio

A High-Rate Receiver for Satellite Quantum Key Distribution - Rößler, Conrad; Günthner, Kevin; Hacker, Bastian; Leuchs, Gerd; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2022)
We present a high-rate fiber-integrated quantum receiver for phase-encoded satellite-based QKD. We highlight concepts for time synchronization as well as compensation of the Doppler shift and optimized quantum signal processing.
CRIS-Team Scopus Importer:2022-09-02

A high-speed secure quantum random number generator based on vacuum states - Gabriel, Christian; Wittmann, Christoffer; Hacker, Bastian; Mauerer, Wolfgang; Huntington, Elanor; Sabuncu, Metin; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
A high-speed continuous-variable quantum random bit generator with an expected effective bit generation rate of up to 10 GBit/s is presented. The obtained bit sequences are truly random and unique, i.e. they cannot be known by an adversary. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

A Holography-Based Modal Wavefront Sensor for the Precise Positioning of a Light Emitter Using a High-Resolution Computer-Generated Hologram - Loosen, Florian; Stehr, Johannes; Alber, Lucas; Harder, Irina; Lindlein, Norbert (Ieee Photonics Journal, 2018)
In certain applications, modal wavefront sensors (MWFSs) can outperform zonal wavefront sensors, which are widely used due to their high ﬂexibility. In this paper, a holography-based MWFS as described is developed for the fast position control of a light emitter in a deep parabolic mirror. The light source is located in the vicinity of the focal point. Instead of Zernike polynomials, more complex phase functions, which are related to certain dislocations of the light source are used as detector modes. The performance of the sensor is veriﬁed with a test setup, where the test wavefront is generated by a spatial light modulator instead of a real parabolic mirror. The design and fabrication of the required high-resolution holographic element is described and an easy way of multiplexing several single mode sensors is demonstrated.
Keywords: advanced optics design; diffractive optics; holography

Akquisition und Verarbeitung von 3D-Daten für die angewandte Messtechnik - Häusler, Gerd; et al. (Bildverarbeitung '97: Forschen, Entwickeln, Anwenden, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.akquis

Algorithm for expanding the dynamic range of a Shack-Hartmann sensor by using a spatial light modulator array - Lindlein, Norbert; et al. (Optical Engineering, 2001)
Normally, the dynamic range of a Shack-Hartmann sensor is limited by the foci leaving their respective subapertures, thus a definite attachment of the foci to their subapertures is difficult. By using an array of spatial light modulators in front of the microlenses of the sensor to switch on and off the subapertures, a definite assignment of the spots to their subapertures is possible. We present a coding algorithm that needs only log2 N+1 frames to assign N spots unequivocal to their subapertures. © 2001 Society of Photo-Optical Instrumentation Engineers.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.algori
Keywords: Coding algorithm; Microlenses; Shack-Hartmann sensor; Spatial light modulator

All-fibre source of amplitude squeezed lightpulses - Meißner, Markus; Marquardt, Christoph; Heersink, Joel; Gaber, Tobias; Wietfeld, André; Leuchs, Gerd; Andersen, Ulrik Lund (Journal of Optics B Quantum and Semiclassical Optics, 2004)
An all-fibre source of amplitude squeezed solitons utilizing the self-phase modulation in an asymmetric Sagnac interferometer is experimentally demonstrated. The asymmetry of the interferometer is passively controlled by an integrated fibre coupler, allowing for the optimization of the noise reduction. We have carefully studied the dependence of the amplitude noise on the asymmetry and the power launched into the Sagnac interferometer. Qualitatively, we find good agreement between the experimental results, a semi-classical theory and earlier numerical calculations (Schmitt et al 1998 Phys. Rev. Lett. 81 2446). The stability and flexibility of this all-fibre source makes it particularly well suited to applications in quantum information science.<br
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.allfib

All-fibre source of continuous variable entangled light - Leuchs, Gerd; et al. (International Journal of Modern Physics B, 2006)
We experimentally demonstrate the production of continuous variable entanglement of femto second laser pulses from an all-fibre asymmetric Sagnac interferometer exploiting the Kerr effect. Contrary to the experiment of Silberhorn et al. [Phys. Rev. Lett. 86,4267 (2001)], the asymmetric coupler in the Sagnac loop is fully integrated in the fibre, making the source extremely compact, reliable and robust. Employing a simple detection scheme, comprising a beam splitter and two intensity detectors, we clearly observe quantum correlations of conjugate quadratures, hereby witnessing entanglement. © World Scientific Publishing Company.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.allfib
Keywords: Continuous variables; Entanglement; Sagnac interferometer

All-optical DPSK-Signal-Regeneration based on a NOLM-Setup - Striegler, Arne; Meißner, Markus; Cvecek, Kristian; Sponsel, Klaus; Schmauß, Bernhard (Optical Fiber Technology, 2005)
We present a novel concept for all-optical DPSK signal regeneration based on a directionally attenuated non linear loop mirror (DA-NOLM). © 2005 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2005.tech.IE.LEH.allopt

All-Optical Multilevel Amplitude and Phase Regeneration - Röthlingshöfer, Tobias; Richter, T.; Onishchukov, Georgy; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (2014 IEEE Photonics Society Summer Topical Meeting Series, 2014)
Using a cascade of an amplitude and a phase regenerator, multilevel signal processing is demonstrated experimentally for a 25-GBd star-8QAM. Improvements in the signal quality by up to 2 dB are obtaine
lhft_intern.bib::Roethlingshoefer2014_6

All-optical phase-preserving multilevel amplitude regeneration - Röthlingshöfer, Tobias; Richter, Thomas; Schubert, Colja; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
The possibility of all-optical phase-preserving amplitude regeneration for star-8QAM is demonstrated using a modified nonlinear optical loop mirror. Experiments show a reduction in amplitude noise on both amplitude levels simultaneously, considering two different types of signal distortions: deterministic low-frequency amplitude modulation and broadband amplitude noise. Furthermore, using this amplitude regeneration, the robustness against nonlinear phase noise from fiber nonlinearity in a transmission line is increased. The scheme suppresses the conversion of amplitude noise to nonlinear phase noise. This is shown for simultaneous amplitude regeneration of the two amplitude states as well as for amplitude regeneration of the high-power states only. If the transmission is limited by nonlinear phase noise, single-level operation at the more critical higher-power state will benefit because of the wider plateau region. Numerical simulations confirm the experimental result

All-optical signal regeneration of advanced modulation formats - Röthlingshöfer, Tobias; Richter, Thomas; Stiller, Birgit; Onishchukov, Georgy; Schubert, Colja; Schmauß, Bernhard; Leuchs, Gerd (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIII, 2014)
With growing demand on transmission capacity, spectral-efficient multilevel modulation formats such as quadrature amplitude modulation (QAM) become of great interest. One of their weaknesses is high sensitivity to noise accumulation, especially in long-haul transmission systems. Our investigations have shown the possibility of all-optical regeneration of multiple amplitude and phase states. Processing of amplitude noise in several amplitude states is based on periodicity of interference conditions in modified nonlinear fiber Sagnac interferometers. Their staircase-like power transfer characteristic can be used for phase-preserving amplitude regeneration of multiple amplitude states. Processing of QAM with up to three non-zero amplitude states, e.g. 16QAM, has been demonstrated in numerical simulations. Furthermore, simultaneous amplitude regeneration of a star-8QAM format with two amplitude states was performed experimentally. Recently, it has also been shown that phase-sensitive amplification for multiple phase states can be realized in fiber optical parametric amplifiers using four-wave mixing (FWM) with a high-order idler. Our numerical simulations and experimental results for star-8QAM revealed that with some modifications, this approach can be used not only for reduction of phase noise in multilevel phase-shift keying but also for signals with multiple amplitude states. The transmission improvement using a cascade of these two regenerator types has been demonstrated in numerical simulations and experiments. Numerical investigations confirm also the possibility to combine both approaches in a single device by using the highly nonlinear fiber in the Sagnac interferometer loop simultaneously for phase-sensitive amplification in one propagation direction. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Roethlingshoefer2014_8

All-Optical Simultaneous Multilevel Amplitude and Phase Regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2014)
Simultaneous amplitude and phase noise reduction of multiple signal states using a nonlinear amplifying loop mirror with integrated directional phase-sensitive amplifier are presented for the star-eight quadrature amplitude modulation transmission format as an example. The performance of this combined regenerator scheme is compared with that of a cascade of separate phase and amplitude regenerators. It could be shown that an improvement in the error vector magnitude of 4 dB for the high-power states with simultaneous improvement of 5 dB for the low-power states is possible in both cases. Transmission improvement by regeneration is considered for two noise types: 1) amplified spontaneous emission and 2) nonlinear phase noise. Both schemes can either improve the bit error rate by an order of magnitude or enable an increase of the fiber launch power by 3 d
lhft_intern.bib::Roethlingshoefer2014a

All-sky Measurement of the Anisotropy of Cosmic Rays at 10 TeV and Mapping of the Local Interstellar Magnetic Field - Abeysekara, A. U.; Alfaro, R.; Alvarez, C.; Arceo, R.; Arteaga-Velazquez, J. C.; Avila Rojas, D.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Capistran, T.; Carramiana, A.; Casanova, S.; et al. (Astrophysical Journal, 2019)
We present the first full-sky analysis of the cosmic ray arrival direction distribution with data collected by the High-Altitude Water Cherenkov and IceCube observatories in the northern and southern hemispheres at the same median primary particle energy of 10 TeV. The combined sky map and angular power spectrum largely eliminate biases that result from partial sky coverage and present a key to probe into the propagation properties of TeV cosmic rays through our local interstellar medium and the interaction between the interstellar and heliospheric magnetic fields. From the map, we determine the horizontal dipole components of the anisotropy δ 0h = 9.16 ×10 -4 and δ 6h = 7.25 ×10 -4 (±0.04 × 10 -4 ). In addition, we infer the direction (229.°2 ± 3.°5 R.A., 11.°4 ± 3.°0 decl.) of the interstellar magnetic field from the boundary between large-scale excess and deficit regions from which we estimate the missing corresponding vertical dipole component of the large-scale anisotropy to be δN ∼ -3.97 +1.0 -2.0 × 10 -4 .
CRIS-Team Scopus Importer:2019-05-02
Keywords: astroparticle physics; cosmic rays; ISM: magnetic fields

A miniaturized satellite payload hosting a spatial heterodyne spectrometer for remote sensing of atmospheric temperature - Kaufmann, Martin; Deiml, Michael; Olschewski, Friedhelm; Mantel, Klaus; Wagner, Fritz; Loosen, Florian; Fröhlich, Denis; Rongen, Heinz; Neubert, Tom; Rottland, Björn; Schneider, Herbert; Riese, Martin; et al. (Proceeding, 11. IAA Symposium on Small Satellites for Earth Observation, 2017)
In this paper we present a concept study for a highly miniaturized interferometer for the deployment  on  micro-  and  nano-satellites  to  measure  atmospheric  temperature.  The  selected technology  is  a  Spatial  Heterodyne  Spectrometer  (SHS).  It  is  known  since  1958,  but  its manufacturability  gained  increasing  attention  during  the  last  decade  because  of  improvements  in detector and computer technology. The throughput of a SHS is orders of magnitude larger than of a conventional  grating  spectrometer  of  the  same  size.  It  can  be  designed  to  deliver  extraordinary spectral  resolution  to  resolve  individual  emission  or  absorption  lines,  or  even  Doppler  shifts.  We introduce the SHS technology and an instrument design to measure the ro-vibrational structure of the O2  atmospheric band at 762 nm in limb viewing geometry. Design considerations of a potential SHS spectrometer and of the overall optical system are discussed. Requirements for a potential satellite platform hosting this instrument are presented, in particular in view of the utilization of CubeSats or other  nano-satellite  platforms.  Potential  mission  scenarios  for  three-dimensional  sounding  of   the atmosphere taking advantage of the agility of small satellites are given.

Amplification of Microwave Signals at the Quantum Limit - Eichler, Christopher (Meeting of the CCQED fellows, 2014)
Keywords: wwwqudev

Amplitude noise reduction in multilevel QAM formats using a nonlinear amplifying loop mirror with a saturable amplifier - Roethlingshoefer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Lasers and Electro-Optics Europe (CLEO EUROPE/EQEC), 2011 Conference on and 12th European Quantum Electronics Conference, 2011)
lhft_intern.bib::Roethlingshoefer2011

Analysis and optimization of coupling to external cavities in feedback experiments with vertical-cavity surface-emitting lasers - Jentsch, Karl Friedrich; Sondermann, Markus; Ackemann, Thorsten (Optics Communications, 2008)
The feedback strength is a crucial parameter for feedback experiments using semiconductor lasers. In this article, the coupling efficiency of the field of vertical-cavity surface-emitting lasers (VCSELs) to external cavities containing one collimating lens has been analyzed in detail using ABCD-matrix methods. It is found that for a given set of parameters there are two distinct, experimentally realizable positions of the collimating lens which allow for optimal coupling, if the cavity length is sufficiently small. The predictions are verified in experiments using single-transverse-mode VCSELs. The obtained coupling efficiencies exceed 70%. © 2007 Elsevier B.V. All rights reserved.
Keywords: Coupling efficiency; Feedback; Vertical-cavity surface-emitting lasers

Analysis of additive manufactured polymer optical waveguides: measurement and simulation of their waviness - Backhaus, Carsten; Hoffmann, Gerd-Albert; Reitberger, Thomas; Eiche, Yannic; Overmeyer, Ludger; Franke, Jörg; Lindlein, Norbert (Integrated Optics: Devices, Materials, and Technologies XXIV, 2020)
This paper analyzes an approach for additively manufacturing polymer optical waveguides. The production process includes flexographic printing of conditioning lines (5 μm height) on a substrate, which are used as guiding barriers in the subsequent printing of the optical core. The core is additively printed (up to 50 μm in height) with an aerosol jet printer, filling the gap between the conditioning lines. The conditioning lines do not only enhance the contact angle of the polymer, which results in a higher cross section of the waveguides, but also improve the straight edges of the printed waveguides. We show that the quality of the conditioning lines is directly correlated to the waviness of the waveguides. Consequently, the analyses of the waviness of the conditioning lines classifies the quality of the fabricated waveguides. However, the waviness of the waveguides can also be considered in optical simulations. In this paper we show how we derive a waveguide model with waviness by fitting a single sine function onto the topological data of the conditioning lines. With this model a variation of the waviness can easily be simulated and goals for fabrication can be set. With the simulations it is possible to verify that the measured waviness (period of 559.5 μm and an amplitude of 4.99 μm) does not affect the optical quality of the waveguide
Keywords: Polymer Optical Waveguides; Waviness; Additive Manufacturing; Waveguide Simulation; Aerosol Jet Printing

Analysis of the disturbing diffraction orders of computer-generated holograms used for testing optical aspherics - Lindlein, Norbert (Applied Optics, 2001)
Aspheric surfaces are increasingly used in the design of high-quality optical imaging systems. Therefore accurate testing methods for aspherics are also necessary. One possibility is to use a computer-generated hologram (CGH) as a part of a null lens in an interferometric testing device. However, CGHs normally have more than one diffraction order, thus causing disturbing areas in the interferogram. Here a simple approximative analytical expression is given for the spatial frequencies of the disturbing light in the interferogram coming from the different diffraction orders of the CGH. This expression also enables one to calculate the size and the shape of the disturbing areas in the interferogram. Some design examples for CGHs are given in an application of the expression. © 2001 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.analys

Analytical circuit model for split ring resonators in the far infrared and optical frequency range - Delgado, V.; Sydoruk, Oleksiy; Tatartschuk, Eugen; Marqués, R.; Freire, M. J.; Jelinek, L. (Metamaterials, 2009)
The article proposes an LC-circuit model for single split ring resonators (SRRs) operating at far infrared and optical frequencies. Taking the effects of magnetic and kinetic inductances as well as gap and surface capacitances into account, we obtain analytical expressions for the resonant frequency of the singly, doubly, and quadruply split SRRs. Comparing the analytical results with numerical simulations, we show that the numerical simulations agree better with the present model than with the models reported previously. We also discuss a size dependent correction to the electron collision frequency which takes into account electron collisions with SRR walls.
EAM Import::2019-03-13

Analytical formulation for the resonant frequency of split rings - Sydoruk, Oleksiy; Tatartschuk, Eugen; Shamonina, E.; Solymar, L. (Journal of Applied Physics, 2009)
A simple approximate expression is derived for the resonant frequency of a singly split single ring that is among the first microwave resonators designed to be small relative to the wavelength. In addition to the usual gap capacitance the concept of surface capacitance is introduced. The surface capacitance is determined analytically by two different methods, first using analytical expressions for the electric field of a split cylinder, and second by using conformal mapping. Taking two practical examples the resonant frequency, found analytically, is shown to agree with that obtained by numerical simulations. The model could be used for studies of the resonant properties of split rings in the terahertz region.
EAM Import::2019-03-13

An efficient source of continuous variable polarization entanglement - Leuchs, Gerd; et al. (New Journal of Physics, 2007)
We have experimentally demonstrated the efficient creation of highly entangled bipartite continuous variable polarization states. Exploiting an optimized scheme for the production of squeezing using the Kerr non-linearity of a glass fibre we generated polarization squeezed pulses with a mean classical excitation in Ŝ3. Polarization entanglement was generated by interfering two independent polarization squeezed fields on a symmetric beam splitter. The resultant beams exhibit strong quantum noise correlations in the dark Ŝ1-Ŝ2 polarization plane. To verify entanglement generation, we characterized the quantum correlations of the system for two different sets of conjugate Stokes parameters. The quantum correlations along the squeezed and the anti-squeezed Stokes parameters were observed to be -4.1 ±0.3 and -2.6 ±0.3 dB below the shot noise level, respectively. The degree of correlations was found to depend critically on the beam-splitting ratio of the entangling beam splitter. Carrying out measurements on a different set of conjugate Stokes parameters, correlations of -3.6 ±0.3 and -3.4 ±0.3 dB have been observed. This result is more robust against asymmetries in the entangling beam splitter, even in the presence of excess noise. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.aneffi

A new 4 pi geometry optimized for focusing on an atom with a dipole-like radiation pattern - Lindlein, Norbert; Maiwald, Robert; Konermann, Hildegard; Sondermann, Markus; Peschel, Ulf; Leuchs, Gerd (Laser Physics, 2007)
Focusing electromagnetic radiation efficiently onto an atom requires an open geometry, which is as close to the full solid angle as possible. Additionally, the radiant intensity should be as close as possible to a dipole radiation in order to have a similar field distribution as in the emission process. Here, we propose to make use of a novel combination of a parabolic mirror and a diffractive optical element. © 2007 MAIK "Nauka/ Interperiodica".
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.anew4p

A new approach for modeling and smoothing of scattered 3D data - Häusler, Gerd; et al. (Proceedings of SPIE, 1998)
In order to digitize the whole surface of a three-dimensional object by means of an optical range sensor, usually multiple range images are acquired from different viewpoints and merged into a single surface description. The simplest and most accurate way is to generate a polyhedral surface. The data are usually distorted by measuring errors like noise, aliasing, outliers, calibration and registration errors, etc., so that they have to be filtered. Calibration and registration errors first appear after merging of different views. As the merged data are no longer represented on a grid, conventional filters for digital signal processing are not applicable. We introduce a new approach for modeling and smoothing scattered data based on an approximation of a mesh of circular arcs. This new method enables interpolation of curved surfaces using solely the vertex position and the associated vertex normals of a polyhedral mesh. The new smoothing filter is specifically adapted to the requirements of geometric data, as it minimizes curvature variations. In contrast to linear filters, undesired surface undulations are avoided, which is an important pre-condition for NC milling and rendering.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.anewap
Keywords: Geometric modeling; Reverse engineering; Scattered data interpolation; Scattered data modeling; Smoothing of polyhedral surfaces; Surface approximation; Surface interpolation; Surface reconstruction; Surface smoothing

A new method of short-coherence interferometry in human skin (in vivo) and in solid volume scatterers - Häusler, Gerd; et al. (SPIE j, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.anewme

A new method to reduce the spot size at a focused laser beam - Leuchs, Gerd; et al. (EOS Topical Meetings Digest, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.anewme

An improved infrastructure for the IceCube realtime system - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube realtime alert system has been operating since 2016. It provides prompt alerts on high-energy neutrino events to the astroparticle physics community. The localization regions for the incoming direction of neutrinos are published through NASA’s Gamma-ray Coordinate Network (GCN). The IceCube realtime system consists of infrastructure dedicated to the selection of alert events, the reconstruction of their topology and arrival direction, the calculation of directional uncertainty contours and the distribution of the event information through public alert networks. Using a message-based workflow management system, a dedicated software (SkyDriver) provides a representational state transfer (REST) interface to parallelized reconstruction algorithms. In this contribution, we outline the improvements of the internal infrastructure of the IceCube realtime system that aims to streamline the internal handling of neutrino events, their distribution to the SkyDriver interface, the collection of the reconstruction results as well as their conversion into human- and machine-readable alerts to be publicly distributed through different alert networks. An approach for the long-term storage and cataloging of alert events according to findability, accessibility, interoperability and reusability (FAIR) principles is outlined.
CRIS-Team Scopus Importer:2025-02-04

A Non-linear Subdivision Scheme for Triangle Meshes - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visualization 2000, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dphy.optik.1optik.anonli

A novel method for polarization squeezing with Photonic Crystal Fibers - Leuchs, Gerd; et al. (Optics Express, 2010)
Photonic Crystal Fibers can be tailored to increase the effective Kerr nonlinearity, while producing smaller amounts of excess noise compared to standard silicon fibers. Using these features of Photonic Crystal Fibers we create polarization squeezed states with increased purity compared to standard fiber squeezing experiments. Explicit we produce squeezed states in counter propagating pulses along the same fiber axis to achieve near identical dispersion properties. This enables the production of polarization squeezing through interference in a polarization type Sagnac interferometer. We observe Stokes parameter squeezing of -3.9 ± 0.3dB andanti-squeezingof 16.2 ±0.3dB. © 2010 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.optik.1optik.anovel

Anticaustics in a Fabry-Perot interferometer - Sanchez-Soto, Luis L.; Monzon, Juan J.; Leuchs, Gerd (Journal of the Optical Society of America A-Optics Image Science and Vision, 2022)
We address the response of a Fabry-Perot interferometer to a monochromatic point source. We calculate the anti -caustics (that is, the virtual wavefronts of null path difference) resulting from the successive internal reflections occurring in the system. They turn out to be a family of ellipsoids (or hyperboloids) of revolution, which allows us to reinterpret the operation of the Fabry-Perot interferometer from a geometrical point of view that facilitates comparison with other apparently disparate arrangements, such as Young's double slit. (c) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement
CRIS-Team WoS Importer:2023-01-06

Anwendung von Beam-Propagation-Method und Wave-Propagation-Method zur Simulation innovativ gedruckter Lichtwellenleiter - Backhaus, Carsten; Loosen, Florian; Vögl, Christian; Mansuroglu, Refik; Lindlein, Norbert (DGaO Proceedings 2018, 2018)
In der DFG-finanzierten Forschergruppe OPTAVER wurden Lichtwellenleiter mittels eines Aerosol-Druck-Verfahrens hergestellt. Eine dadurch ermöglichte Koppelstelle kann jedoch nicht mehr mittels Raytracing simuliert werden, da Interferenzeffekte nicht berücksichtigt werden. Eine Anwendung wellenoptischer Methoden auf die Problemstellung wird im Folgenden untersucht und dargestellt.<br
Keywords: Optische Systeme; Faseroptik; Optische Informationsübertragung

Approach for the production chain of printed polymer optical waveguides–an overview - Loosen, Florian; Backhaus, Carsten; Zeitler, Jochen; Hoffmann, Gerd-Albert; Reitberger, Thomas; Lorenz, Lukas; Lindlein, Norbert; Franke, Jörg; Overmeyer, Ludger; Suttmann, Oliver; Wolter, Klaus-Jürgen; Bock, Karlheinz (Applied Optics, 2017)
Research for new production chains in the field of waveguide fabrication is a challenging task. Realizing a cost efficient manufacturing process allows integrating optical data communication in arbitrary structures, for example, the wing of an airplane or the body of a car. The production chain described in this paper contains the design, simulation, and fabrication process of printed polymer optical waveguides (POWs).

A primary radiation standard based on quantum nonlinear optics - Lemieux, Samuel; Giese, Enno; Fickler, Robert; Chekhova, Maria; Boyd, Robert W. (Nature Physics, 2019)
The black body remains the most prominent source of light for absolute radiometry(1). Its main alternative, synchrotron radiation, requires costly and large facilities(2). Quantum optics offers a new radiometric source: parametric down-conversion (PDC), a nonlinear optical process, in which pairwise photon correlations enable absolute calibration of photodetectors(3-6). Since the emission rate crucially depends on the brightness of the electromagnetic field, quantum-mechanical fluctuations of the vacuum(7) can be seen as a seed of spontaneous PDC, and their amplitude is a natural radiometric standard. Thus, they allow for the calibration of the spectral radiance of light sources(8-11) by measuring the ratio between seeded and unseeded PDC. Here, we directly use the frequency spectrum of the electromagnetic vacuum to trigger spontaneous PDC and employ the generated light to infer the spectral response of a spectrometer over a broad spectral range. Then, we deduce the absolute quantum efficiency from the spectral shape of PDC in the high-gain regime, without relying on a seed or reference detector. Our results compare well with the ones obtained with a reference lamp, demonstrating a promising primary radiation standard.
CRIS-Team WoS Importer:2019-06-18

A pulsed source of continuous variable polarization entanglement - Leuchs, Gerd; et al. (Journal of Optics B Quantum and Semiclassical Optics, 2003)
We have experimentally demonstrated polarization entanglement using continuous variables in an ultra-short pulsed laser system at the telecommunications wavelength of 1.5 μm. Exploiting the Kerr non-linearity of a glass fibre we generated polarization squeezed pulses with Ŝ2 as the only non-zero Stokes parameter, thus Ŝ1 and Ŝ3 being the conjugate pair. Polarization entanglement was generated by interference of the polarization squeezed field with a vacuum on a 50:50 beamsplitter. The two resultant beams exhibit strong quantum noise correlations in Ŝ1 and Ŝ3. The sum noise signal of Ŝ3 was at the respective shot noise level and the difference noise signal of Ŝ1 fell -2.9 dB below this value.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.apulse
Keywords: Continuous variables; Entanglement; Nonlinear optics; Polarization

A quantitative comparison of amplitude versus intensity interferometry for astronomy - Bojer, Manuel; Huang, Zixin; Karl, Sebastian; Richter, Stefan; Kok, Pieter; von Zanthier, Joachim (New Journal of Physics, 2022)
Astronomical imaging can be broadly classified into two types. The first type is amplitude interferometry, which includes conventional optical telescopes and very large baseline interferometry (VLBI). The second type is intensity interferometry, which relies on Hanbury Brown and Twiss-type measurements. At optical frequencies, where direct phase measurements are impossible, amplitude interferometry has an effective numerical aperture that is limited by the distance from which photons can coherently interfere. Intensity interferometry, on the other hand, correlates only photon fluxes and can thus support much larger numerical apertures, but suffers from a reduced signal due to the low average photon number per mode in thermal light. It has hitherto not been clear which method is superior under realistic conditions. Here, we give a comparative analysis of the performance of amplitude and intensity interferometry, and we relate this to the fundamental resolution limit that can be achieved in any physical measurement. Using the benchmark problem of determining the separation between two distant thermal point sources, e.g., two adjacent stars, we give a short tutorial on optimal estimation theory and apply it to stellar interferometry. We find that for very small angular separations the large baseline achievable in intensity interferometry can more than compensate for the reduced signal strength. We also explore options for practical implementations of very large baseline intensity interferometry (VLBII).
CRIS-Team WoS Importer:2022-04-29

A Robust Multiresolution Registration Approach - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visualization '99, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.arobus

Artiffcial wave plates made from subwavelength structures - Rothau, Sergej; Ghadyani, Zahra; Harder, Irina; Lindlein, Norbert (113. Jahrestagung der DGaO, 2012)

Aspherical surface testing by using spherical compensation - Lindlein, Norbert; et al. (Proceedings of SPIE, 1999)
A technique for testing aspherical surfaces without the use of a null-corrector is described. The wave-front sensor for the detection of the aspherical wave-front is a Shack-Hartmann sensor which has a significantly expanded range of measurable wave-front slopes. The optical testing set-up, the used algorithm for the dynamic range expansion, and experimental results are presented in this paper.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.optik.1optik.aspher

Assessing the polarization of a quantum field from stokes fluctuations - Klimov, A. B.; Bjoerk, G.; Soederholm, J.; Madsen, L. S.; Lassen, M.; Andersen, U. L.; Heersink, J.; Dong, Ruifang; Marquardt, Christoph; Leuchs, Gerd; Sanchez-Soto, L. L. (Physical Review Letters, 2010)
We propose an operational degree of polarization in terms of the variance of the Stokes vector minimized over all the directions of the Poincaré sphere. We examine the properties of this second-order definition and carry out its experimental determination. Quantum states with the same standard (first-order) degree of polarization are correctly discriminated by this new measure. We argue that a comprehensive quantum characterization of polarization properties requires a whole hierarchy of higher-order degrees. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

A Sub-Atomic Subdivision Approach - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visulaisation, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.asubat

Asymmetric broadcasting of quantum correlations - Jain, Aditya; Chakrabarty, Ndranil; Chatterjee, Sourav (Physical Review A, 2019)
In this work, we exhaustively investigate 1→2 local and nonlocal broadcasting of entanglement as well as correlations beyond entanglement (geometric discord) using asymmetric Pauli cloners with the most general two-qubit state as the resource. We exemplify asymmetric broadcasting of entanglement using "maximally entangled mixed states." We demonstrate the variation of broadcasting range with the amount of entanglement present in the resource state as well as with the asymmetry in the cloner. We show that it is impossible to optimally broadcast geometric discord with the help of these asymmetric Pauli cloning machines. We also study the problem of 1→3 broadcasting of entanglement using nonmaximally entangled state as the resource. For this task, we introduce a method we call successive broadcasting which involves application of 1→2 optimal cloning machines multiple times. We compare and contrast the performance of this method with the application of direct 1→3 optimal cloning machines. We show that 1→3 optimal cloner does a better job at broadcasting than the successive application of 1→2 cloners and the successive method can be beneficial in the absence of 1→3 cloners. We also bring out the fundamental difference between the tasks of cloning and broadcasting in the final part of the paper. We create examples to show that there exist local unitaries which can be employed to give a better range for broadcasting. Such unitary operations are not only economical, but also surpass the best possible range obtained using existing cloning machines enabling broadcasting of lesser entangled states. This result opens up a direction in exploration of methods to facilitate broadcasting which may outperform the standard strategies implemented through cloning transformations.
CRIS-Team Scopus Importer:2021-04-20

A telecentric line scanning system: requirements in the macroscopic and microscopic regime - Loosen, Florian; Lindlein, Norbert; Donner, Klaus (Proceeding, 116. DGaO-Jahrestagung, 2015)
Last year (lecture A28 - 115th DGaO annual meeting), we presented the concept of a compact and modular telecentric line scanning system, capable of measuring large surfaces, e.g. for deformation and scratch detection of aluminium rolled sheets. In this particular construction, a circular scan curve is imaged onto one line. Because of the modular design of the system, this system could be considered in an inline process as well. To be applicable either in macroscopic or microscopic regime, both single components (torus mirror and imaging system) as well as the complete system have to be configured accordingly. Using optical simulation tools, the characteristic parameters of the line scanner can be determined accurately. Due to field curvature and distortion, off-axis beams can distort the image on the detector (line camera) significantly. Therefore, a special interest was paid to the influence of the quality of the image points concerning the enlargement of the field angle and the imaging on the detector plane.
Keywords: Optisches Design; Optische Systeme; Messtechnik

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, Bettina; Elser, Dominique Alexander; Bartley, Tim; Sabuncu, Metin; Wittmann, Christoffer; Sych, Denis; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2010)
We investigate the properties of an atmospheric channel for free space quantum communication with continuous polarization variables. In our prepare-and-measure setup, coherent polarization states are transmitted through an atmospheric quantum channel of 100 m length on the flat roof of our institute's building. The signal states are measured by homodyne detection with the help of a local oscillator (LO) which propagates in the same spatial mode as the signal, orthogonally polarized to it. Thus the interference of signal and LO is excellent and atmospheric fluctuations are auto-compensated. The LO also acts as a spatial and spectral filter, which allows for unrestrained daylight operation. Important characteristics for our system are atmospheric channel influences that could cause polarization, intensity and position excess noise. Therefore we study these influences in detail. Our results indicate that the channel is suitable for our quantum communication system in most weather condition
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.optik.1optik.atmosp

Atmospheric continuous-variable quantum communication - Heim, B.; Peuntinger, Christian; Killoran, N.; Khan, Imran; Wittmann, C.; Marquardt, Christoph; Leuchs, Gerd (New Journal of Physics, 2014)
We present a quantum communication experiment conducted over a point-to-point free-space link of 1.6 km in urban conditions. We study atmospheric influences on the capability of the link to act as a continuous-variable (CV) quantum channel. Continuous polarization states (that contain the signal encoding as well as a local oscillator (LO) in the same spatial mode) are prepared and sent over the link in a polarization multiplexed setting. Both signal and LO undergo the same atmospheric fluctuations. These are intrinsically auto-compensated which removes detrimental influences on the interferometric visibility. At the receiver, we measure the Q-function and interpret the data using the framework of effective entanglement (EE). We compare different state amplitudes and alphabets (two-state and four-state) and determine their optimal working points with respect to the distributed EE. Based on the high entanglement transmission rates achieved, our system indicates the high potential of atmospheric links in the field of CV quantum key distribution.
CRIS-Team Scopus Importer:2022-06-05
Keywords: atmospheric turbulence; polarization in atmospheric optics; quantum communication

Atomic mercury vapor inside a hollow-core photonic crystal fiber - Vogl, Ulrich; Peuntinger, Christian; Joly, Nicolas Y.; Russell, Philip St. J.; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2014)
We demonstrate high atomic mercury vapor pressure in a kagomé-style hollow-core photonic crystal fiber at room temperature. After a few days of exposure to mercury vapor the fiber is homogeneously filled and the optical depth achieved remains constant. With incoherent optical pumping from the ground state we achieve an optical depth of 114 at the 63P2 - 63D3 transition, corresponding to an atomic mercury number density of 6 × 1010cm-3. The use of mercury vapor in quasi one-dimensional confinement may be advantageous compared to chemically more active alkali vapor, while offering strong optical nonlinearities in the ultraviolet region of the optical spectrum.
CRIS-Team Scopus Importer:2022-06-05

Attacks on practical quantum key distribution systems (and how to prevent them) - Jain, Nitin; Stiller, Birgit; Khan, Imran; Elser, Dominique Alexander; Marquardt, Christoph; Leuchs, Gerd (Contemporary Physics, 2016)
With the emergence of an information society, the idea of protecting sensitive data is steadily gaining importance. Conventional encryption methods may not be sufficient to guarantee data protection in the future. Quantum key distribution (QKD) is an emerging technology that exploits fundamental physical properties to guarantee perfect security in theory. However, it is not easy to ensure in practice that the implementations of QKD systems are exactly in line with the theoretical specifications. Such theory–practice deviations can open loopholes and compromise security. Several such loopholes have been discovered and investigated in the last decade. These activities have motivated the proposal and implementation of appropriate countermeasures, thereby preventing future attacks and enhancing the practical security of QKD. This article introduces the so-called field of quantum hacking by summarising a variety of attacks and their prevention mechanisms.
CRIS-Team Scopus Importer:2021-06-29
Keywords: countermeasures; practical data security; quantum computer; Quantum cryptography; quantum hacking; quantum key distribution

Aufbereitung von 3D-Sensordaten für Reverse Engineering mit Slim3D - Häusler, Gerd; et al. (Optische 3D-Formerfassung, 1998)
UnivIS-Import:2015-04-16:Pub.1998.nat.dphy.optik.1optik.aufber

Automatic Coarse Registration of 3D Surface Data in Oral and Maxillofacial Surgery - Nkenke, Emeka; Neukam, Friedrich Wilhelm; Häusler, Gerd; et al. (Perspective in Image-Guided Surgery, Proceedings of the Scientific Workshop on Medical Robotics, Navigation and Visualizatiom, 2004)
UnivIS-Import:2015-04-16:Pub.2004.nat.dphy.optik.1optik.autima

Automatic registration method for multisensor datasets adopted for dimensional measurements on cutting tools - Shaw, Laura; Ettl, Svenja; Mehari, Fanuel; Weckenmann, Albert; Häusler, Gerd (Measurement Science & Technology, 2013)
Multisensor systems with optical 3D sensors are frequently employed to capture complete surface information by measuring workpieces from different views. During coarse and fine registration the resulting datasets are afterward transformed into one common coordinate system. Automatic fine registration methods are well established in dimensional metrology, whereas there is a deficit in automatic coarse registration methods. The advantage of a fully automatic registration procedure is twofold: it enables a fast and contact-free alignment and further a flexible application to datasets of any kind of optical 3D sensor. In this paper, an algorithm adapted for a robust automatic coarse registration is presented. The method was originally developed for the field of object reconstruction or localization. It is based on a segmentation of planes in the datasets to calculate the transformation parameters. The rotation is defined by the normals of three corresponding segmented planes of two overlapping datasets, while the translation is calculated via the intersection point of the segmented planes. First results have shown that the translation is strongly shape dependent: 3D data of objects with non-orthogonal planar flanks cannot be registered with the current method. In the novel supplement for the algorithm, the translation is additionally calculated via the distance between centroids of corresponding segmented planes, which results in more than one option for the transformation. A newly introduced measure considering the distance between the datasets after coarse registration evaluates the best possible transformation. Results of the robust automatic registration method are presented on the example of datasets taken from a cutting tool with a fringe-projection system and a focus-variation system. The successful application in dimensional metrology is proven with evaluations of shape parameters based on the registered datasets of a calibrated workpiece. © 2013 IOP Publishing Ltd.
UnivIS-Import:2015-04-14:Pub.2013.tech.FT.FT-QMFMT.automa
Keywords: automatic registration; cutting tools; three-dimensional metrology

Automatische Porenfindung in 3D-CT Daten - Häusler, Gerd; et al. (2001)
UnivIS-Import:2015-04-14:Pub.2001.forsch.gradui.gradui_6.automa

Automatische Segmentierung der Gewebegrenzen in 2D-Ultraschalldaten aus der Mund-Kiefer- und Gesichtschirurgie - Häusler, Gerd; Wittenberg, Thomas; Nkenke, Emeka; Ettl, Svenja; et al. (Informatik aktuell, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.automa

Autonomous absolute calibration of an ICCD camera in single-photon detection regime - Qi, Luo; Just, Felix; Leuchs, Gerd; Chekhova, Maria V. (Optics Express, 2016)
Intensified charge coupled device (ICCD) cameras are widely used in various applications such as microscopy, astronomy, spectroscopy. Often they are used as single-photon detectors, with thresholding being an essential part of the readout. In this paper, we measure the quantum efficiency of an ICCD camera in the single-photon detection mode using the Klyshko absolute calibration technique. The quantum efficiency is obtained as a function of the threshold value and of the wavelength of the detected light. In addition, we study the homogeneity of the photon sensitivity over the camera chip area. The experiment is performed in the autonomous regime, without using any additional detectors. We therefore demonstrate the self-calibration of an ICCD camera.

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Leuchs, Gerd; Silberhorn, Christine; Marquardt, Christoph (Nature Communications, 2013)
The generation of high-quality single-photon states with controllable narrow spectral bandwidths and central frequencies is key to facilitate efficient coupling of any atomic system to non-classical light fields. Such an interaction is essential in numerous experiments for fundamental science and applications in quantum communication and information processing, as well as in quantum metrology. Here we implement a fully tunable, narrow-band and efficient single-photon source based on a whispering gallery mode resonator. Our disk-shaped, monolithic and intrinsically stable resonator is made of lithium niobate and supports a cavity-assisted spontaneous parametric down-conversion process. The generated photon pairs are emitted into two highly tunable resonator modes. We verify wavelength tuning over 100 nm of both modes with controllable bandwidth between 7.2 and 13 MHz. Heralding of single photons yields anti-bunching with g (2) (0)<0.2. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Axicon-type test interferometer for cylindrical surfaces: systematic error assessment - Lindlein, Norbert; et al. (Applied Optics, 1997)
The principle and the alignment aberration functions are described for an axicon-type test interferometer for measuring cylindrical mantle surfaces. Additionally, we show that the derived systematic alignment functions fulfill for reasonably small misalignments the requirements for measurements in the range of approximately 1/100 of a fringe. We verify this with optical path-length calculations, using ray tracing. © 1997 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.axicon
Keywords: Alignment aberration functions; Axicon-type test interferometer; Cylinder test; Ray tracing

Balancing ballistic and hopping light transport by purposive arraying of colloidal particles - Romanov, Sergei G.; Orlov, Sergej; Vogel, Nicolas; Bley, Karina; Landfester, Katharina; Weiss, Clemens K.; Peschel, Ulf (Photonic Crystal Materials and Devices XI, 2014)
Keywords: 2-dimensional slab photonic crystal; Diffraction; Disorder; Etching; Mie resonance; Optical spectra; Photon hopping

Beeinflussung der optischen Eigenschaften von Polymer Optischen Wellenleitern durch das Druckpfad-Design - Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (DGaO Proceedings, 2019)
In der DFG-finanzierten Forschergruppe OPTAVER (Optische Aufbau- und Verbindungstechnik für baugruppenintegrierte Bussysteme) wurden erfolgreich Lichtwellenleiter mittels eines Aerosol-Druck-Verfahrens mit vorheriger Konditionierung hergestellt sowie ein virtuelles Abbild der gesamten Prozesskette erstellt. Dieses Verfahren ermöglicht nahezu beliebige Druckpfade, sodass dies den Weg frei macht für neue Realisationen von optischen Buskopplungen.Ein nun möglicher Druckpfad ist jedoch nicht zwangsweise eine Verbesserung in Bezug auf die optischen Eigenschaften des Lichtwellenleiters. Die besondere Geometrie des Querschnitts der Polymer Optischen Wellenleiter (POW) beeinflusst das Design des Druckpfades. Ein Beispiel dafür ist der minimale Radius, den eine Kurve haben darf, damit kein Licht aus dem Wellenleiter auskoppelt. Um nun Vorschriften für das Druckpfad-Design ableiten zu können, benötigt es einer Charakterisierung der POWs bezüglich verschiedenster Druckpfade. Diese Charakterisierung wird vorgestellt und die daraus abgeleiteten Druckpfad-Design Vorschriften aufgezeigt. Des Weiteren werden neue Realisierungsmöglichkeiten von optischen Buskopplungen vorgestellt
Keywords: Additive Fertigung; Polymer Optische Wellenleiter; optische Eigenschaften

Benchmark for optical simulation tools in the european network of excellence on micro-optics NEMO - Lindlein, Norbert; et al. (Optical Design and Engineering II, 2005)
The European Network of Excellence on Micro-Optics (NEMO) is a consortium of about 30 European institutes and companies which are working on micro-optics. The network is supported by the European Commission for a period of four years. One of its work packages is the Centre for Modelling and Design consisting of about 20 partners. In this work package a benchmark of the capabilities of commercial and internal software tools which are available among the partners will be made. The ten test systems which are used for the benchmarking range from seemingly simple things like calculating the intensity distribution in the focus of a microlens to complete systems like for example an optical interconnect system with microlenses, DOEs and a prism. The paper will present some of the benchmark systems. First results of the benchmarking itself cannot be presented in this proceeding because the benchmarking just ends at the end of August (after the deadline of this proceeding). But, hopefully first results can be presented during the talk.
Keywords: Benchmarking; Micro-optics; Optical design tools; Ray tracing; Simulation; Wave-optical simulation

Binary Homodyne Detection for Observing Quadrature Squeezing in Satellite Links - Müller, Christian R.; Seshadreesan, Kaushik P.; Peuntinger, Christian; Marquardt, Christoph (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
Optical satellite links open up new prospects for realizing quantum physical experiments over unprecedented length scales. We demonstrate the feasibility of quadrature squeezing detection in satellite links using optical communication technology already in orbit. The detection process is complicated by the fact that the homo dyne detectors aboard of satellites often provide an efficient resolution of only one bit. We show experimentally, that despite this extremal constraint quantum squeezing can still be detected efficiently. The required sample overhead compared to an ideal homo dyne detector is only a factor of 3.3.
CRIS-Team Scopus Importer:2019-05-21

Binary homodyne detection for observing quadrature squeezing in satellite links - Müller, Christian; Seshadreesan, Kaushik P.; Peuntinger, Christian; Marquardt, Christoph (Physical Review Research, 2020)
Optical satellite links open up new prospects for realizing quantum physical experiments over unprecedented length scales. We analyze and affirm the feasibility of detecting quantum squeezing in an optical mode with homodyne detection of only one bit resolution, as is found in satellites already in orbit. We show experimentally that, in combination with a coherent displacement, a binary homodyne detector can still detect quantum squeezing efficiently even under high loss. The sample overhead in comparison to nondiscretized homodyne detection is merely a factor of 3.3.
CRIS-Team WoS Importer:2021-01-22

Binding Kinetics of Self-Assembled Monolayers of Fluorinated Phosphate Ester on Metal Oxides for Underwater Aerophilicity - Mazare, Anca Valentina; Kim, Hyesung; Ulubas, Mahmut Hakan; Fomicheva, Iana; Sarau, George; Christiansen, Silke H.; Goldmann, Wolfgang; Tesler, Alexander (Langmuir, 2025)
The term “aerophilic surface” is used to describe superhydrophobic surfaces in the Cassie-Baxter wetting state that can trap air underwater. To create aerophilic surfaces, it is essential to achieve a synergy between a low surface energy coating and substrate surface roughness. While a variety of techniques have been established to create surface roughness, the development of rapid, scalable, low-cost, waste-free, efficient, and substrate-geometry-independent processes for depositing low surface energy coatings remains a challenge. This study demonstrates that fluorinated phosphate ester, with a surface tension as low as 15.31 mN m-1, can form a self-assembled monolayer on metal oxide substrates within seconds using a facile wet-chemical approach. X-ray photoelectron spectroscopy was used to analyze the formed self-assembled monolayers. Using nanotubular morphology as a rough substrate, we demonstrate the rapid formation of a superhydrophobic surface with a trapped air layer underwater.
CRIS-Team Scopus Importer:2025-02-14

Birefringence and dispersion of cylindrically polarized modes in nanobore photonic crystal fiber - Euser, T. G.; Schmidt, M. A.; Joly, N. Y.; Gabriel, C.; Marquardt, Christoph; Zang, L. Y.; Foertsch, M.; Banzer, Peter; Brenn, A.; Elser, Dominique; Scharrer, Michael G; Leuchs, Gerd; et al. (Journal of the Optical Society of America B-Optical Physics, 2011)
We demonstrate experimentally and theoretically that a nanoscale hollow channel placed centrally in the solidglass core of a photonic crystal fiber strongly enhances the cylindrical birefringence (the modal index difference between radially and azimuthally polarized modes). Furthermore, it causes a large split in group velocity and group velocity dispersion. We show analytically that all three parameters can be varied over a wide range by tuning the diameters of the nanobore and the core.© 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Birth, death, and revival of spontaneous emission in a three-atom system - Mährlein, Simon; Götzendörfer, Lukas; Günthner, Kevin; Evers, Jorg; von Zanthier, Joachim (Physical Review Research, 2020)
Three identical two-level atoms in free space prepared in particular entangled single-photon excited states display a "birth," "death," and a nonperiodic "revival" of spontaneous emission in selected directions. Instead of recording the spontaneously emitted photon with a maximum probability at t = 0 as for a single atom, a "birth" manifests itself in an initially zero photon detection probability, increasing thereafter in particular directions. Alternatively, the photon detection probability decreases in particular directions from an initially maximal value to completely disappear ("death") and to reappear again ("revival"). We show how these phenomena can be induced in the fully excited system, by projecting the atomic ensemble into the required entangled single-photon excited state via detection of the first two spontaneously emitted photons. To observe death and revival of spontaneous emission it is necessary to provide both spatial and temporal interference for which a minimum of three atoms is required. Hereby, the third atom, located at a large distance with respect to the other two atoms, can be used to tune the time and direction of the death of the photon. From this manipulation of spontaneous decay at a distance, we anticipate multiple applications, in fundamental science as well as in quantum technologies.
CRIS-Team WoS Importer:2021-01-22

Bright EPR-entangled beams for quantum communication - Leuchs, Gerd; et al. (Quantum Communication, Measurement and Computing 3, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dphy.optik.1optik.bright

Broadband, Lensless, and Optomechanically Stabilized Coupling into Microfluidic Hollow-Core Photonic Crystal Fiber Using Glass Nanospike - Zeltner, Richard; Xie, Shangran; Pennetta, Riccardo; Russell, Philip St. John (ACS Photonics, 2017)
We report a novel technique for launching broadband laser light into liquid-filled hollow-core photonic crystal fiber (HC-PCF). It uniquely offers self-alignment and self-stabilization via optomechanical trapping of a fused silica nanospike, fabricated by thermally tapering and chemically etching a single mode fiber into a tip diameter of 350 nm. We show that a trapping laser, delivering ∼300 mW at 1064 nm, can be used to optically align and stably maintain the nanospike at the core center. Once this is done, a weak broadband supercontinuum signal (∼575–1064 nm) can be efficiently and close to achromatically launched in the HC-PCF. The system is robust against liquid-flow in either direction inside the HC-PCF, and the Fresnel back-reflections are reduced to negligible levels compared to free-space launching or butt-coupling. The results are of potential relevance for any application where the efficient delivery of broadband light into liquid-core waveguides is desired.
EAM Import::2019-03-13

Broadband Omnidirectional Diversion of Light in Hybrid Plasmonic-Photonic Heterocrystals - Ding, Boyang; Bardosova, Maria; Pemble, Martyn E.; Korovin, Alexander V.; Peschel, Ulf; Romanov, Sergei G. (Advanced Functional Materials, 2011)
Broadband, omnidirectional, and polarization-independent diversion has been achieved of more than 90% of the light flow intensity off its incidence direction using hybrid metal–dielectric plasmonic-photonic heterocrystals. These architectures were prepared by depositing metal film on the interface between two photonic crystals of different parameters. The magnitude of light losses was extracted from angle-resolved measurements of transmission and reflectance spectra. Comparing these data for different stages of constructing the complex architecture, the diffraction in colloidal crystals, the excitation and radiative decay of short-living surface plasmon polaritons in a corrugated metal film and the eigenmode mismatch at the interface between two different photonic crystals were identified as corroborating physical mechanisms behind the light diversion.
EAM Import::2019-03-13

Broadband Operation of a Gain Switched TI:Sapphire Laser for Coherence Radar Measurements - Häusler, Gerd; et al. (Proceedings of SPIE, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.optik.1optik.broadb

Broadcasting of entanglement via orthogonal and non-orthogonal state-dependent cloners - Shukla, Manish Kumar; Chakrabarty, Indranil; Chatterjee, Sourav (Quantum Information Processing, 2020)
In this work, we extensively study the problem of broadcasting of entanglement as state-dependent versus state-independent cloners. We start by re-conceptualizing the idea of state-dependent quantum cloning machine (SD-QCM), and in that process, we introduce different types of SD-QCMs, namely orthogonal and non-orthogonal cloners. We derive the conditions for which the fidelity of these cloners will become independent of the input state. We note that such a construction allows us to maximize the cloning fidelity at the cost of having partial information of the input state. In the discussion on broadcasting of entanglement, we start with a general two-qubit state as our resource and later we consider a specific example of Bell diagonal state. We apply both state-dependent and state-independent cloners (orthogonal and non-orthogonal), locally and non-locally, on input resource state and obtain a range for broadcasting of entanglement in terms of the input state parameters. Our results highlight several instances where the state-dependent cloners outperform their state-independent counterparts in broadcasting entanglement. Our study provides a comparative perspective on the broadcasting of entanglement via cloning in two-qubit scenario, when we have some knowledge of the resource ensemble versus a situation when we have no such information.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Broadcasting; Cloning; Entanglement

Broadcasting of quantum correlations in qubit-qudit systems - Mundra, Rounak; Patel, Dhrumil; Chakrabarty, Indranil; Ganguly, Nirman; Chatterjee, Sourav (Physical Review A, 2019)
Quantum mechanical properties like entanglement, discord, and coherence act as fundamental resources in various quantum information processing tasks. Consequently, the technique of generating more resources from a few, typically termed as broadcasting, serves as a promising candidate for the design of quantum networks. One way to broadcast resources could be using a cloning operation. In this article, broadcasting of quantum resources beyond 2 - 2 systems is investigated. In particular, in 2 - 3 dimensions, a class of states not useful for broadcasting of entanglement is characterized considering an optimal universal Heisenberg cloning machine. The broadcasting ranges for maximally entangled mixed states and two-parameter class of states are obtained to exemplify our protocol. A significant derivative of our protocol is that the cloning operation generates a qutrit (3 - 3) entangled pair with positive partial transpose on one of the local sides, and an absolutely separable qubit (2 - 2) pair on the other side of the input bipartite 2 - 3-dimensional resource state. Moving beyond entanglement, in 2 - d dimensions, the impossibility to optimally broadcast quantum discord and quantum coherence (l1 norm) is established. However, some significant illustrations are provided to highlight that nonoptimal broadcasting of discord and coherence is still possible.
CRIS-Team Scopus Importer:2021-04-20

Building and Controlling Superconducting Quantum Hardware towards Error-Corrected Quantum Computing - Eichler, Christopher (MQV Colloquium, 2022)
Keywords: wwwquantum

Building Superconducting Quantum Hardware towards Error-Corrected Quantum Computing - Eichler, Christopher (APS March Meeting: Quantum Computing Hardware, 2023)
Keywords: wwwquantum

Building Superconducting Quantum Hardware towards Error-Corrected Quantum Computing - Eichler, Christopher (2023)
Quantum Computers will ultimately rely on near-perfect logical gates, implemented while correcting errors at the physical level. The need for developing quantum hardware optimized for performing fast, repeatable, and high-fidelity syndrome measurements in quantum error-correcting codes such as the surface code therefore becomes increasingly important. In my talk, I will present advances in performing qubit readout and two-qubit gates in multi-qubit superconducting quantum processors, which enabled the recent experimental demonstration of repeated quantum error correction in surfaces codes. I will show how quantum processors optimized for quantum error correction can also serve as a testbed to explore noisy intermediate-scale quantum algorithms. The talk will conclude with a discussion about open challenges and opportunities to advance the speed and fidelity of syndrome detection in scalable device architectures by exploiting tunable coupling elements.
Keywords: wwwquantum

Building Superconducting Quantum Processors to exploreQuantum Error Correction and Quantum Neural Networks - Eichler, Christopher (Seminar hosted by Per Delsing, Chalmers University, 2021)
Keywords: wwwqudev

Bulk Er:Yb:glass soliton femtosecond laser - Leuchs, Gerd; et al. (CLEO Technical digest, 2001)
A bulk solid state Erbium glass laser used to generate ultrashort laser pulses in the femtosecond regime was presented using soliton dynamics. Intracavity self-phase modulation was used to achieve soliton mode-locking. The dependence of pulse shaping dynamics on the pump power and intracavity dispersion was investigated, and the results were compared with the soliton mode-locking model.
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.bulker

Calibration for cylindrical specimens in grazing-incidence interferometry via integration of difference measurements. - Lindlein, Norbert; et al. (Applied Optics, 2006)
Cylindrical specimens may be tested advantageously by using grazing-incidence interferometry. A multiple positions test in combination with rotational averaging has recently been used to separate the surface deviations of the specimen from the interferometric aberrations. To reduce the measuring time and to check whether the results are reliable, a second procedure is now investigated, which uses the principle of the multiple positions test to determine quantities proportional to the difference quotients of the surface deviations. After numerical integration, the results can be compared with those obtained previously by rotational averaging. The measurement principle is described, and calibration results are presented.

Cascaded Phase-Preserving Amplitude Regeneration in a DPSK Transmission System - Schmauß, Bernhard; Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Leuchs, Gerd (ECOC 2009, Vienna, Austria, 20-24 September, 2009)
Experimental results obtained on 10 Gb/s RZ-DPSK transmission in a recirculating fiber-loop setup show that nonlinear amplifying loop mirrors can efficiently enhance system performance. Main limiting factor is amplified Rayleigh backscattering in highly nonlinear fiber. © VDE VERLAG GMBH.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.cascad

Cascaded phase-preserving multilevel amplitude regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
The performance of cascaded in-line phase-preserving amplitude regeneration using nonlinear amplifying loop mirrors has been studied in numerical simulations. As an example of a spectrally efficient modulation format with two amplitude states and multiple phase states, the regeneration performance of a star-16QAM format, basically an 8PSK format with two amplitude levels, was evaluated. An increased robustness against amplified spontaneous emission and nonlinear phase noise was observed resulting in a significantly increased transmission distance.
lhft_intern.bib::Roethlingshoefer2014_4

Cavity optomechanics in a levitated helium drop - Childress, Lilian; Schmidt, M. P.; Kashkanova, A. D.; Brown, C. D.; Harris, G. I.; Aiello, Andrea; Marquardt, Florian; Harris, J. G. E. (Physical Review A, 2017)
We describe a proposal for a type of optomechanical system based on a drop of liquid helium that is magnetically levitated in vacuum. In the proposed device, the drop would serve three roles: its optical whispering-gallery modes would provide the optical cavity, its surface vibrations would constitute the mechanical element, and evaporation of He atoms from its surface would provide continuous refrigeration. We analyze the feasibility of such a system in light of previous experimental demonstrations of its essential components: magnetic levitation of mm-scale and cm-scale drops of liquid He, evaporative cooling of He droplets in vacuum, and coupling to high-quality optical whispering-gallery modes in a wide range of liquids. We find that the combination of these features could result in a device that approaches the single-photon strong-coupling regime, due to the high optical quality factors attainable at low temperatures. Moreover, the system offers a unique opportunity to use optical techniques to study the motion of a superfluid that is freely levitating in vacuum (in the case of He4). Alternatively, for a normal fluid drop of He3, we propose to exploit the coupling between the drop's rotations and vibrations to perform quantum nondemolition measurements of angular momentum.
CRIS-Team Scopus Importer:2023-03-27

Characteristics of the Diffuse Astrophysical Electron and Tau Neutrino Flux with Six Years of IceCube High Energy Cascade Data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau,; Anton, Gisela; Arguelles, C.; et al. (Physical Review Letters, 2020)
We report on the first measurement of the astrophysical neutrino flux using particle showers (cascades) in IceCube data from 2010-2015. Assuming standard oscillations, the astrophysical neutrinos in this dedicated cascade sample are dominated (similar to 90%) by electron and tau flavors. The flux, observed in the sensitive energy range from 16 TeV to 2.6 PeV, is consistent with a single power-law model as expected from Fermi-type acceleration of high energy particles at astrophysical sources. We find the flux spectral index to be gamma = 2.53 +/- 0.07 and a flux normalization for each neutrino flavor of phi(astro) = 1.66(-0.27)(+0.25) at E-0 = 100 TeV, in agreement with IceCube's complementary muon neutrino results and with all-neutrino flavor fit results. In the measured energy range we reject spectral indices gamma <= 2.28 at >= 3 sigma significance level. Because of high neutrino energy resolution and low atmospheric neutrino backgrounds, this analysis provides the most detailed characterization of the neutrino flux at energies below similar to 100 TeV compared to previous IceCube results. Results from fits assuming more complex neutrino flux models suggest a flux softening at high energies and a flux hardening at low energies (p value >= 0.06). The sizable and smooth flux measured below similar to 100 TeV remains a puzzle. In order to not violate the isotropic diffuse gamma-ray background as measured by the Fermi Large Area Telescope, it suggests the existence of astrophysical neutrino sources characterized by dense environments which are opaque to gamma rays.
CRIS-Team WoS Importer:2020-10-02

Characterization and application of continuous variable quantum states of light - Marquardt, Christoph (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2007)
The aim of this thesis was the characterization of continuous variable quantum states of light and their application in quantum information processing protocols. The photo current statistics of squeezed and entangled states from a nonlinear fiber Sagnac interferometer were analyzed and can be regarded as Gaussian states within the measurement accuracy. In addition, instead of the usual variance, the covariance was experimentally investigated as a relative measure of squeezing, using a balanced self-homodyne system. As an application in a quantum information protocol the experimental distillation of squeezed states has been shown. The undistilled squeezed states suffered from non-Gaussian classical excess noise. In the experiment nearly the complete squeezing could be recovered by a probabilistic selection method. The Cavalcanti-Reid criterion to prove intrinsic macroscopic superposition states in continuous variables was experimentally applied for the first time. With this criterion generalized superposition states were proven in vacuum and intense coherent states with a distance in phase space of 0.51+/-0.02 shot noise units. For squeezed states from an optical parametric oscillator generalized superposition states were proven with a distance of up to 0.83+/-0.02 shot noise units. At the same time the dependence of the criterion on squeezing and purity of the states was investigated. To reconstruct the quantum state of the polarization variables of light, a theory was developed, that is based on the su(2) algebra and at the same time takes into account the possibility, that the photon number is not fixed. It was found that for high photon numbers the quantum state reconstruction of the SU(2) Q function in Poincare space is an inverse 3D Radon transformation. With this method the Q function of a polarization squeezed state was reconstructed from measured data. In the dark plane of a polarization squeezed state the Wigner function of an intense Kerr squeezed state was reconstructed for the first time.<br
Keywords: quantum state reconstruction; quantum state distillation; photon statistics; Squeezed state

Characterization of cylindrical lenses with the help of grazing incidence interferometry for micro- and macro-optics - Lindlein, Norbert; et al. (19th Congress of the International Commisssion for Optics Optics for the Quality of Life, 2003)
The cylinder geometry allows for grazing incidence tests of optical surfaces let it be micro- or macro cylinder lenses. By using diffiactive beam splitter and beam shaping elements a grazing incidence interferometer can be built where the zero diffraction order is used as reference beam and one of the first orders as probe beam for the cylinder surface. Circular as well as noncircular meridian curves can be dealt with by shaping the DOE structure accordingly. The structure of the DOE are parallel curves to the meridian providing a constant spatial frequency which alleviates the lithographic process. The fringes indicate surface deviations from fringe to fringe by p/2 where p is the pitch of the DOE. A description of a micro- and a macro-interferometer together with measuring results will be given.
Keywords: Computer generated holograms; Grazing incidence interferometry; Micro-optics; Optical Physics

Characterization of cylindrical micro-lenses in transmitted light and with grazing incidence interferometry in reflected light - Lindlein, Norbert; et al. (Optical Micro- and Nanometrology in Microsystems Technology, 2006)
High numerical aperture cylindrical micro-lenses are needed in collimating the laser light from laser bars in the near infrared. Diffraction limited performance of such collimation lenses can only be obtained if the surface shape deviates strongly from circular symmetry. Therefore, null tests make the use of diffractive optical elements (DOE) necessary. For performance test at the design wavelength the reference DOE produces an ideal cylinder wave which enables the compensation of the wave front coming from the micro-lens to a plane wave. The use of a DOE-master enables beside the null test geometry also a removal of the anamorphic distortion due to the cylinder geometry. The DOEs having a numerical aperture of 0.8 are produced on an e-beam machine. The measurement of the wave aberrations is done with the help of the phase shifting technique. Alignment aberrations are eliminated by a least square fit of suitable misalignment functionals derived from an analytic approximation. The shape of the micro-lenses is tested in reflected light showing surface defects directly. The cylinder symmetry allows for a grazing incidence test using two DOE with nearly constant spatial frequency. There are no limitations concerning the test of high numerical aperture surfaces since the structure of the diffractive elements are parallel curves to the profile curve. The mean spatial frequency of the DOE defines the effective wavelength. Since we use a diffractive interferometer the effective wavelength is identical to the pitch of the DOE. Usually pitches between 4-10 μm are used resulting in a fringe sensitivity of 2-5 μm. The test delivers the deviation of the surface from the ideal form. In the case of non-circular symmetry the DOE deviates from the axicon type DOE. In addition to the shape deviations also the radius of curvature at the vertex can be measured. The stage for the cylindrical micro-lens is equipped with a length measuring device using grating references from Renishaw providing a length increment of 0.1 μm. With the axicon DOE there are two positions where nearly fluffed out fringes can be observed. Starting from the basic test position the lens can be moved until the vertex of the lens coincides with the focal line of the wave generated by the central part of the DOE. The distance between these two positions gives the radius of curvature for the vertex. Modern manufacturing of micro-lenses comprises also hot embossing in plastics or even into glass. Because of the small dimensions of the lenses and the required accuracy of the surface shape also tests of the impressing mould have to be carried out. The DOE approach enables also the test of the embossing form with the same sensitivity as the final test of the lens. Measuring results for the two test methods will be given.
Keywords: Cylindrical micro lens; Diffractive optics; Grazing incidence; Null test; Phase shifting interferometry

Characterization of microlenses using a phase-shifting shearing interferometer - Lindlein, Norbert; et al. (Optical Engineering, 1994)
A shearing interferometer is proposed for the characterization of microlenses. The optical configuration of the test system enables the measurement of the wave aberrations, the focal length, and the deviations of the lens surface from an ideal sphere. In addition, a quantitative evaluation method is given that enables the calculation of the wave aberrations (e.g., the phase function) from the shearing interferometer data.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.optik.1optik.charac

Characterization of microoptical components - Lindlein, Norbert (2003 Conference on Lasers and Electro-Optics Europe, CLEO/EUROPE 2003, 2003)
Microoptical components are more and more important in technical applications due to the miniaturization of optical systems for communication, sensors, visualization devices and other purposes. Since the quality in the fabrication of an optical element cannot be better than the measurement accuracy with which the element can be tested, it is very important that also microoptical components can be characterized with sufficient accuracy. In this paper several measurement devices for microoptical components like rotationally symmetric microlenses and cylindrical microlenses will be presented. © 2003 IEEE.

Characterization of sub-wavelength structures usingphase-singularities - Leuchs, Gerd; et al. (Proc. Vol. XV,Industrial Systems: Part II, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.charac

Characterization of the astrophysical diffuse neutrino flux using starting track events in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2024)
A measurement of the diffuse astrophysical neutrino spectrum is presented using IceCube data collected from 2011-2022 (10.3 years). We developed novel detection techniques to search for events with a contained vertex and exiting track induced by muon neutrinos undergoing a charged-current interaction. Searching for these starting track events allows us to not only more effectively reject atmospheric muons but also atmospheric neutrino backgrounds in the southern sky, opening a new window to the sub-100 TeV astrophysical neutrino sky. The event selection is constructed using a dynamic starting track veto and machine learning algorithms. We use this data to measure the astrophysical diffuse flux as a single power law flux (SPL) with a best-fit spectral index of γ=2.58-0.09+0.10 and per-flavor normalization of φper-flavorAstro=1.68-0.22+0.19×10-18×GeV-1 cm-2 s-1 sr-1 (at 100 TeV). The sensitive energy range for this dataset is 3-550 TeV under the SPL assumption. This data was also used to measure the flux under a broken power law, however we did not find any evidence of a low energy cutoff.
CRIS-Team Scopus Importer:2024-07-19

Chiral optical response of planar and symmetric nanotrimers enabled by heteromaterial selection - Banzer, Peter; Wozniak, Pawel; Mick, Uwe; De Leon, Israel; Boyd, Robert W. (Nature Communications, 2016)
Chirality is an intriguing property of certain molecules, materials or artificial nanostructures, which allows them to interact with the spin angular momentum of the impinging light field. Due to their chiral geometry, they can distinguish between left-and right-hand circular polarization states or convert them into each other. Here we introduce an approach towards optical chirality, which is observed in individual two-dimensional and geometrically mirror-symmetric nanostructures. In this scheme, the chiral optical response is induced by the chosen heterogeneous material composition of a particle assembly and the corresponding resonance behaviour of the constituents it is built from, which breaks the symmetry of the system. As a proof of principle, we investigate such a structure composed of individual silicon and gold nanoparticles both experimentally, as well as numerically. Our proposed concept constitutes an approach for designing two-dimensional chiral media tailored at the nanoscale, allowing for high tunability of their optical response.

Citizen science for IceCube: Name that Neutrino - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (European Physical Journal Plus, 2024)
Name that Neutrino is a citizen science project where volunteers aid in classification of events for the IceCube Neutrino Observatory, an immense particle detector at the geographic South Pole. From March 2023 to September 2023, volunteers did classifications of videos produced from simulated data of both neutrino signal and background interactions. Name that Neutrino obtained more than 128,000 classifications by over 1800 registered volunteers that were compared to results obtained by a deep neural network machine-learning algorithm. Possible improvements for both Name that Neutrino and the deep neural network are discussed.
CRIS-Team Scopus Importer:2024-06-28

Classical and quantum properties of cylindrically polarized beams of light via a poincaré sphere representation - Holleczek, A.; Aiello, A.; Gabriel, C.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Classical and quantum properties of cylindrically polarized states of light - Holleczek, Annemarie; Aiello, Andrea; Gabriel, Christian; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2011)
We investigate theoretical properties of beams of light with non-uniform polarization patterns. Specifically, we determine all possible configurations of cylindrically polarized modes (CPMs) of the electromagnetic field, calculate their total angular momentum and highlight the subtleties of their structure. Furthermore, a hybrid spatio-polarization description for such modes is introduced and developed. In particular, two independent Poincaré spheres have been introduced to represent simultaneously the polarization and spatial degree of freedom of CPMs. Possible mode-to-mode transformations accomplishable with the help of Bconventional polarization and spatial phase retarders are shown within this representation. Moreover, the importance of these CPMs in the quantum optics domain due to their classical features is highlighted. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Classically entangled optical beams for high-speed kinematic sensing - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, Marco; Giacobino, Elisabeth; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optica, 2015)
Tracking the kinematics of fast-moving objects is an important diagnostic tool for science and engineering. Here, we demonstrate an approach to positional and directional sensing based on the concept of classical entanglement in vector beams of light [Found. Phys. 28, 361–374 (1998)]. The measurement principle relies on the intrinsic correlations existing in such beams between transverse spatial modes and polarization. The latter can be determined from intensity measurements with only a few fast photodiodes, greatly outperforming the bandwidth of current CCD/CMOS devices. In this way, our setup enables two-dimensional real-time sensing with temporal resolution in the GHz range. We expect the concept to open up new directions in metrology and sensing.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Classical and quantum physics; Optical sensing and sensors

Cluster state generation with quadrature squeezed cylindrically polarized modes - Gabriel, Christian; Rigas, Ioannes; Aiello, Andrea; Berg-Johansen, Stefan; van Loock, Peter; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We present schemes which exploit the hybrid-entanglement in quadrature squeezed cylindrically polarized modes to generate cluster states. Such states are essential for one-way quantum computing. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Coherence Radar and Spectral Radar - New Tools for Dermatological Diagnosis - Häusler, Gerd; et al. (Journal of Biomedical Optics, 1998)
"Coherence radar," an optical 3-D sensor based on short coherence interferometry, is used to measure skin surface topology. This method is called optical coherence profilometry (OCP) and it may be a useful tool for medical diagnosis in dermatology because different medical conditions show distinct alterations of the skin surface. The measuring uncertainty is less than 2 μm. The measuring time is about 4 s. in vivo 3-D mapping of naked skin was performed without preparation. For clinical application, a fiber optical implementation was introduced. Spectral radar is an optical sensor for the acquisition of skin morphology based on OCT techniques. The scattering amplitude a(z) along one vertical axis from the surface into the bulk can be measured within one exposure. No reference arm scanning is necessary. The theory of the sensor, including the dynamic range, is discussed and in vivo measurements of human skin by a fiber optical implementation of the sensor are demonstrated. © 1998 Society of Photo-Optical Instrumentation Engineer
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.cohere
Keywords: Coherence radar; Fourier spectroscopy; Human skin; In vivo measurements; Melanoma maligna; Optical coherence profilometry; Optical coherence tomography; Speckle interferometry; Spectral radar; Volume scatterers

'Coherence Radar' - New Modifications of White Light Interferometry for Large Objects Shape Acquisition - Häusler, Gerd; et al. (Proc. of the EOS Topical Meeting on Optoelectronics Distance Measurements and Applications, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.cohere

"Coherence Radar, Spectral Radar, Dispersion Radar": Modifications of Broad Band Interferometry for High Accuracy 3D-Measurements in Medicine and Industry - Häusler, Gerd; et al. (Proc. of ODIMAP II, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.cohere

Coherent Conversion Between Microwave and Optical Photons-An Overview of Physical Implementations - Lambert, Nicholas J.; Rueda, Alfredo; Sedlmeir, Florian; Schwefel, Harald G. L. (Advanced Quantum Technologies, 2020)
Quantum information technology based on solid state qubits has created much interest in converting quantum states from the microwave to the optical domain. Optical photons, unlike microwave photons, can be transmitted by fiber, making them suitable for long distance quantum communication. Moreover, the optical domain offers access to a large set of very well-developed quantum optical tools, such as highly efficient single-photon detectors and long-lived quantum memories. For a high fidelity microwave to optical transducer, efficient conversion at single photon level and low added noise is needed. Currently, the most promising approaches to build such systems are based on second-order nonlinear phenomena such as optomechanical and electro-optic interactions. Alternative approaches, although not yet as efficient, include magneto-optical coupling and schemes based on isolated quantum systems like atoms, ions, or quantum dots. Herein, the necessary theoretical foundations for the most important microwave-to-optical conversion experiments are provided, their implementations are described, and the current limitations and future prospects are discussed.
CRIS-Team WoS Importer:2020-07-31

Collecting more than half the fluorescence photons from a single ion - Maiwald, Robert; Golla, Andrea; Fischer, Martin; Bader, Marianne; Heugel, Simon Tobias; Chalopin, Benoit; Sondermann, Markus; Leuchs, Gerd (Physical Review A, 2012)
We demonstrate the trapping of a single ion in the focus of a deep parabolic mirror that covers 81% of the solid angle surrounding the ion. Accounting for the reflectivity of the mirror we infer a photon collection efficiency of 54.8% for our setup. The underlying experimentally detected maximum fluorescence rate is 1.91×106 s 1 from a single 174Yb ion, mainly limited by the quantum efficiency of our photon detector. Besides the high collection efficiency, the integration of an ion trap into a parabolic mirror is a key ingredient for efficient coupling of light to a single ion in free space. © 2012 American Physical Society.

Collectively Enhanced Giant Circular Dichroism of Germanium Nanohelix Square Lattice Arrays - Ellrott, Günter; Beck, Paul; Sultanov, Vitaliy; Rothau, Sergej; Lindlein, Norbert; Chekhova, Maria; Krstic, Vojislav (Advanced Photonics Research, 2023)
Circular dichroism is a unique chiroptical signature of the chirality of a system and is a prevalent way to characterize and distinguish systems on a fundamental level and for their technological applicability. Thus, engineering and maximizing the chiroptical response of a single chiral object or a metasurface composed of chiral entities is a formidable task. Current efforts strongly focus on individual metallic nanostructures and their periodic ensembles to harvest on (resonant) plasmonic properties and interactions. This route, however, waives the advantages of high-refractive-index nanoscale materials embracing low dissipative losses at optical wavelengths and electromagnetic fields penetrating and propagating in such materials. Herein, a strong circular dichroism is demonstrated in square lattices of nanohelices made of the high-refractive-index semiconductor germanium, with dissymmetry factors outperforming metal-based ensembles. The observation of a much higher dissymmetry emerges for illumination with spatially coherent light, in comparison to spatially incoherent light. High dissymmetry is attributed to cooperative coupling between single helices, resulting from the combination of dielectric resonances of both the individual helical building blocks and the highly ordered lattice.<br

Colloquium: The Einstein-Podolsky-Rosen paradox: From concepts to applications - Leuchs, Gerd; et al. (Reviews of Modern Physics, 2009)
This Colloquium examines the field of the Einstein, Podolsky, and Rosen (EPR) gedanken experiment, from the original paper of Einstein, Podolsky, and Rosen, through to modern theoretical proposals of how to realize both the continuous-variable and discrete versions of the EPR paradox. The relationship with entanglement and Bell's theorem are analyzed, and the progress to date towards experimental confirmation of the EPR paradox is summarized, with a detailed treatment of the continuous-variable paradox in laser-based experiments. Practical techniques covered include continuous-wave parametric amplifier and optical fiber quantum soliton experiments. Current proposals for extending EPR experiments to massive-particle systems are discussed, including spin squeezing, atomic position entanglement, and quadrature entanglement in ultracold atoms. Finally, applications of this technology to quantum key distribution, quantum teleportation, and entanglement swapping are examined. © 2009 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.colloq

Combined diffractive optical elements for quasi-absolute testing of aspherics - Lindlein, Norbert; et al. (Optical Fabrication and Testing, OFT 2006, 2006)
Three position quasi-absolute test for aspherics by using combined-diffractive optical elements is presented. We discuss the effects of substrate quality of DOE on the proposed calibration procedure and present an optimised design of the DOE. © 2006 Optical Society of America.

Combined search for neutrinos from dark matter self-annihilation in the Galactic Center with ANTARES and IceCube - Albert, A.; Andre, M.; Domi, Alba; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, Simone; et al. (Physical Review D, 2020)
We present the results of the first combined dark matter search targeting the Galactic Center using the ANTARES and IceCube neutrino telescopes. For dark matter particles with masses from 50 to 1000 GeV, the sensitivities on the self-annihilation cross section set by ANTARES and IceCube are comparable, making this mass range particularly interesting for a joint analysis. Dark matter self-annihilation through the tau(+)tau(-) , mu(+)mu(-) , b (b) over bar, and W+W- channels is considered for both the Navarro-Frenk-White and Burkert halo profiles. In the combination of 2101.6 days of ANTARES data and 1007 days of IceCube data, no excess over the expected background is observed. Limits on the thermally averaged dark matter annihilation cross section are set. These limits present an improvement of up to a factor of 2 in the studied dark matter mass range with respect to the individual limits published by both collaborations. When considering dark matter particles with a mass of 200 GeV annihilating through the tau(+)tau(-)channel, the value obtained for the limit is 7.44 x 10(-24) cm(3) s(-1 )for the Navarro-Frenk-White halo profile. For the purpose of this joint analysis, the model parameters and the likelihood are unified, providing a benchmark for forthcoming dark matter searches performed by neutrino telescopes.
CRIS-Team WoS Importer:2020-11-13

Comparison of phase unwrapping algorithms applied to singular phase fields - Seifert, Kristina Johanna; Berger, Andreas; Mantel, Klaus Peter; Nercissian, Vanusch; Lindlein, Norbert (DGaO Proceedings, 2012)

Compensation for Anamorphotic Distortion in Grazing-Incidence Interferometry Testing Planar Specimes - Schneider, Jessica; Mantel, Klaus Peter; Schreiner, Roland; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2003)
UnivIS-Import:2015-04-14:Pub.2003.nat.dphy.optik.1optik.compen

Compensation of Nonlinear Phase Noise Using the Effective Negative Nonlinearity of a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Journal of Selected Topics in Quantum Electronics, 2012)
The nonlinear amplifying loop mirror (NALM) has been explored for use as a nonlinear phase-shift compensator (NPSC). Operation conditions for a tunable effective negative nonlinearity are considered and the NALM parameter optimization is discussed for direct bit-error-ratio (BER) improvement by postcompensation after a nonlinear transmission line. In this configuration, the fundamental limits for NPSC are estimated for differential quadrature phase-shift keying (DQPSK) using a simplified model. Numerical simulations of a 20 Gb/s RZ-DQPSK transmission system confirmed the applicability of this model and showed a significant BER improvement in a realistic transmission line. Alternatively, the fiber launch power per span could be increased by 2 dB for the same BE
lhft_intern.bib::Sponsel2012

Compensation of the wavelength dependence in diffractive star couplers - Lindlein, Norbert; et al. (Journal of the Optical Society of America A-Optics Image Science and Vision, 1995)
A space-variant and a space-invariant approach for decreasing the wavelength dependence of diffractive fan-out systems was presented. Applying diffractive optical elements (DOEs) for the wave-front correction in the space-variant system, the spot sizes were lessened by half the spot sizes over a wavelength range of 20 nm. The paraxial design of the space-invariant system revealed that at least two diffractive lenses were needed. The resulting space-invariant system gave a nearly diffraction-limited performance for a wavelength range from 830 to 850 nm. A summary of the results for all three system designs were also provided.
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.optik.1optik.compen

Complex source beam: A tool to describe highly focused vector beams analytically - Orlov, S.; Peschel, Ulf (Physical Review A, 2010)
The scalar-complex-source model is used to develop an accurate description of highly focused radially, azimuthally, linearly, and circularly polarized monochromatic vector beams. We investigate the power and full beam widths at half maximum of vigorous Maxwell equation solutions. The analytical expressions are employed to compare the vector complex source beams with the real beams produced by various high-numerical-aperture (NA) focusing systems. We find a parameter set for which the spatial extents of the analytical beams are the same as those of experimentally realized ones. We ensure the same shape of the considered beams by investigating an overlap of the complex source beams with high-NA beams. We demonstrate that the analytical expressions are good approximations for realistic highly focused beams.
EAM Import::2019-03-13

Computer-Aided Design and Simulation of Spatial Opto-Mechatronic Interconnect Devices - Zeitler, Jochen; Reichle, Andreas; Franke, Jörg; Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert (26th CIRP Design Conference, 2016, 2016)
Optical technologies become increasingly important in modern sensor and communication applications. Nevertheless, manufacturing and design methods in the field of spatial opto-electronics have not been investigated intensively yet. A new approach is to print polymer waveguides on spatial carriers to use the full design freedom of opto-mechatronic assemblies. Up to now, no specific design tools and validation methods are available. The article describes possible technology-specific methods for designing spatial opto-mechatronic applications with the focus on computer-aided design (CAD) and raytracing simulation of spatial waveguides.
Keywords: computer-aided design (CAD); design method; optical communication; opto-electronics; simulation

Computer generiertes Hologramm als punktsymmetrische Streuplatte - Hampp, Heiko; Harder, Irina; Lano, Maik; Lindlein, Norbert (DGaO-Proceedings 2010 - http://www.dgao-proceedings.de - ISSN: 1614-8436, 2010)

Concentration of phase-information - Usuga, Mario; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Andersen, Ulrik L.A.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2010)
We demonstrate a probabilistic scheme capable of increasing the phase information of weak coherent states by addition of thermal noise and subsequent photon-counting based postselection. We present experimental and theoretical results. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Concentric ring metal grating for generating radially polarized light - Ghadyani, Zahra; Harder, Irina; Lindlein, Norbert; Berger, Andreas; Iff, Wolfgang; Vartiainen, Ismo; Kuittinen, M (Applied Optics, 2011)

Concepts for the design and optimization process of printed polymer-based optical waveguides (scattering processes) - Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (Proceeding, 4th doctoral students conference on optics (DoKDoK), 2015)

Confocal Microscopy with a Refractive Microlens/Pinhole Array - Lindlein, Norbert; et al. (Optics Letters, 1998)
The stable setup of a confocal arrangement consisting of a combination of a refractive microlens and a pinhole array is presented. The focal plane of the microlenses lies at the rear surface of the substrate in the pinhole plane. By using a microscope objective one can image the stop array onto the object at a reduced size. Surface profiles of refractive and diffractive optical elements were measured with the help of this confocal microscope. © 1998 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.confoc

Conical-shaped titania nanotubes for optimized light management in DSSCs reach back-side illumination efficiencies > 8% - So, Seulgi; Kriesch, Arian; Peschel, Ulf; Schmuki, Patrik (Journal of Materials Chemistry A, 2015)
In the present work, we introduce the anodic growth of conical shaped TiO2 nanotube arrays. These titania nanocones provide a scaffold for dye-sensitized solar cell (DSSC) structures with significantly improved photon management, providing an optimized absorption profile compared with conventional cylindrical nanotube arrays. Finite difference time domain (FDTD) modelling demonstrates a drastically changed power-absorption characteristic over the tube length. When used in a back-side illumination DSSC configuration, nanocone structures can reach over 60% higher solar cell conversion efficiency ( extgreekh) than conventional tubes. The resulting extgreekh ≈ 8% represents one of the highest reported values for Grätzel type DSSCs used under back-side illumination.
EAM Import::2019-03-13

Continuous Variable Entanglement and Squeezing of Orbital Angular Momentum States - Lassen, Mikael Ostergaard; Leuchs, Gerd; Andersen, Ulrik Lund (Physical Review Letters, 2009)
We report the first experimental characterization of the first-order continuous variable orbital angular momentum states. Using a spatially nondegenerate optical parametric oscillator (OPO) we produce quadrature entanglement between the two first-order Laguerre-Gauss modes. The family of orbital angular momentum modes is mapped on an orbital Poincaré sphere, where the mode's position on the sphere is spanned by the three orbital parameters. Using a nondegenerate OPO we produce squeezing of these parameters, and as an illustration, we reconstruct the "cigar-shaped" uncertainty volume on the orbital Poincaré sphere. © 2009 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.contin

Continuous variable entanglement between frequency modes - Leuchs, Gerd; et al. (Fortschritte Der Physik-Progress of Physics, 2006)
The pairwise production of photons in nonlinear optical processes ensures entanglement to occur between two photons. E.g. when the Kerr effect is exploited, the photons are produced in different frequency modes, which are symmetric with respect to the pump frequency. Since these photons are produced into the same spatial mode, the quadrature entanglement can be witnessed only by the use of a frequency selective device which transforms the adjacent frequency modes into two different spatial modes. We use a Mach-Zehnder interferometer with a large path length difference to separate symmetric frequency modes located 10.25 MHz from the carrier. We measure correlations of the quadrature components of 1.6 ± 0.1dB below the shot noise in the amplitude and 1.4 ± 0.1dB in the phase. © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.contin

Continuous-variable entanglement distillation of non-Gaussian mixed states - Dong, Ruifang; Lassen, Mikael; Heersink, Joel; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd; Andersen, Ulrik L. (Physical Review A - Atomic, Molecular, and Optical Physics, 2010)
Many different quantum-information communication protocols such as teleportation, dense coding, and entanglement-based quantum key distribution are based on the faithful transmission of entanglement between distant location in an optical network. The distribution of entanglement in such a network is, however, hampered by loss and noise that is inherent in all practical quantum channels. Thus, to enable faithful transmission one must resort to the protocol of entanglement distillation. In this paper we present a detailed theoretical analysis and an experimental realization of continuous variable entanglement distillation in a channel that is inflicted by different kinds of non-Gaussian noise. The continuous variable entangled states are generated by exploiting the third order nonlinearity in optical fibers, and the states are sent through a free-space laboratory channel in which the losses are altered to simulate a free-space atmospheric channel with varying losses. We use linear optical components, homodyne measurements, and classical communication to distill the entanglement, and we find that by using this method the entanglement can be probabilistically increased for some specific non-Gaussian noise channels. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Continuous variable entanglement distillation of non-gaussian states - Lassen, Mikael Ostergaard; Dong, Ruifang; Heersink, Joel; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd; Ulrik, L. Andersen (AIP Conference Proceedings, 2009)
We experimentally demonstrate distillation of continuous variable entangled light that has undergone non-Gaussian attenuation loss. The continuous variable entanglement is generated with optical fibers and sent through a lossy channel, where the transmission is varying in time. By employing simple linear optical components, a measurement induced operation and classical communication, we demonstrate that the entanglement is probabilistically increased. © 2009 American Institute of Physics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Distillation; Entanglement; Quantum information

Continuous variable quantum communication - Andersen, Ulrik Lund; Leuchs, Gerd (Lectures on Quantum Information, 2006)
UnivIS-Import:2015-04-20:Pub.2006.nat.dphy.optik.1optik.contin_6

Continuous Variable Quantum Communication with Gaussian States - Andersen, Ulrik Lund; Leuchs, Gerd (Quantum Information: From Foundations to Quantum Technology Applications, 2019)
CRIS-Team WoS Importer:2020-09-25

Continuous Variable Quantum Cryptography - beating the 3dB loss limit - Leuchs, Gerd; et al. (Physical Review Letters, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.contin

Continuous variable quantum key distribution using polarization encoding and post selection - Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 2004)
We present an experimental demonstration of a quantum key distribution protocol using coherent polarization states. Post selection is used to ensure a low error rate and security against beam-splitting attacks even in the presence of high losses. Signal encoding and readout in polarization bases avoids the difficult task of sending a local oscillator with the quantum channel. This makes our setup robust and easy to implement. A shared key was established for losses up to 64%.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.contin

Controlling the quantum properties of optical solitons in fibres - Leuchs, Gerd; et al. (Molecular Crystals and Liquid Crystals Science and Technology Section B: Nonlinear Optics, 2000)
Solitons in optical fibres are stable objects when described classically. The quantum properties,[1] however, change with propagation distance due to Kerr and Raman induced intrapulse correlations. It is demonstrated that spectral filters and interferometers can be used to control the quantum properties of 130 fs solitons. This lends to the generation of many photon states of the light field with non-classical noise reduction and quantum entanglement for application in quantum communication.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.contro

Correlation measurement of squeezed light - Leuchs, Gerd; et al. (Physical Review A, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.correl

Corrupting coherence - ubquitous inthe metrologists daily life - Häusler, Gerd (Proc. of 3rd Topical Meeting onOptoelectronic Distance Measurement and Applications (ODIMAP III), 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.corrup

Counterpropagating light in ring resonators: Switching fronts, plateaus, and oscillations - Campbell, Graeme N.; Zhang, Shuangyou; Del Bino, Leonardo; Del'Haye, Pascal; Oppo, Gian-Luca (Physical Review A, 2022)
We characterize the formation of robust stationary states formed by light plateaus separated by two local switching fronts in only one of two counterpropagating fields in ring resonators with normal dispersion. Such states are due to global cross coupling and allow for frequency combs to switch from one field to the other by simply tuning the input laser frequency. Exact expressions for the distance between fronts and for plateau powers are provided in excellent agreement with simulations. These demonstrate an unusual high degree of control over pulse and plateau duration in one of the fields upon changes of one of the input laser frequencies. We identify a wide parameter region in which light plateaus are self-starting and are the only stable solution. For certain values of the detunings we find multistable states of plateaus with switching fronts, slowly oscillating homogeneous states and nonoscillating homogeneous states of the counterpropagating fields. Robustness and multistability of these unusual single-field front solutions are provided in parameter ranges that are experimentally achievable in a wide variety of ring resonators.
CRIS-Team WoS Importer:2022-11-18

Covariant constructive gravity: A step-by-step guide towards alternative theories of gravity - Alex, Nils; Reinhart, Tobias (Physical Review D, 2020)
We propose a step-by-step manual for the construction of alternative theories of gravity, perturbatively as well as nonperturbatively. The construction is guided by no more than two fundamental principles that we impose on the gravitational dynamics: invariance under spacetime diffeomorphisms and causal compatibility with given matter dynamics, provided that spacetime is additionally endowed with matter fields. The developed framework then guides the computation of the most general, alternative theory of gravity that is consistent with the two fundamental requirements. Utilizing this framework we recover the cosmological sector of general relativity solely from assuming that spacetime is a spatially homogeneous and isotropic metric manifold. On top of that, we explicitly test the perturbative framework by deriving the most general third-order expansion of a metric theory of gravity that is causally compatible with a Klein-Gordon scalar field. Thereby we recover the perturbative expansion of general relativity. To demonstrate how new physics emerges from our approach, we finally construct the most comprehensive third-order expansion of a theory of gravity that supports general (not necessarily Maxwellian) linear electrodynamics.
CRIS-Team WoS Importer:2020-04-24

Covariant constructive gravity - Reinhart, Tobias; Alex, Nils (15th Marcel Grossmann Meeting on Recent Developments in Theoretical and Experimental General Relativity, Astrophysics, and Relativistic Field Theories, MG 2018, 2022)
We present a method of constructing perturbative equations of motion for the geometric background of any given tensorial field theory. Requiring invariance of the gravitational dynamics under spacetime diffeomorphisms leads to a PDE system for the gravitational Lagrangian that can be solved by means of a power series ansatz. Furthermore, in each order we pose conditions on the causality of the gravitational equations, that en- sure coevolution of the matter fields and the gravitational background is possible, i.e. gravitational equations and matter equations share the same initial data hypersurfaces.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Causality; Constructive gravity; Diffeomorphism invariance

Critical dynamics of an asymmetrically bidirectionally pumped optical microresonator - Silver, Jonathan M.; Grattan, Kenneth T.; Del'Haye, Pascal (Physical Review A, 2021)
An optical ring resonator with third-order, or Kerr, nonlinearity will exhibit symmetry breaking between the two counterpropagating circulating powers when pumped with sufficient power in both the clockwise and counterclockwise directions. This is due to the effects of self- and cross-phase modulation on the resonance frequencies in the two directions. The critical point of this symmetry breaking exhibits universal behaviors including divergent responsivity to external perturbations, critical slowing down, and scaling invariance. Here we derive a model for the critical dynamics of this system, first for a symmetrically pumped resonator and then for the general case of asymmetric pumping conditions and self- and cross-phase modulation coefficients. This theory not only provides a detailed understanding of the dynamical response of critical-point-enhanced optical gyroscopes and near-field sensors, but is also applicable to nonlinear critical points in a wide range of systems.
CRIS-Team Scopus Importer:2021-10-29

Dark-Bright Soliton Bound States in a Microresonator - Zhang, Shuangyou; Bi, Toby; Ghalanos, George N.; Moroney, Niall P.; Del Bino, Leonardo; Del'Haye, Pascal (Physical Review Letters, 2022)
Dissipative Kerr solitons in microresonators have facilitated the development of fully coherent, chipscale frequency combs. In addition, dark soliton pulses have been observed in microresonators in the normal dispersion regime. Here, we report bound states of mutually trapped dark-bright soliton pairs in a microresonator. The soliton pairs are generated seeding two modes with opposite dispersion but with similar group velocities. One laser operating in the anomalous dispersion regime generates a bright soliton microcomb, while the other laser in the normal dispersion regime creates a dark soliton via Kerr-induced cross-phase modulation with the bright soliton. Numerical simulations agree well with experimental results and reveal a novel mechanism to generate dark soliton pulses. The trapping of dark and bright solitons can lead to light states with the intriguing property of constant output power while spectrally resembling a frequency comb. These results can be of interest for telecommunication systems, frequency comb applications, and ultrafast optics.
CRIS-Team WoS Importer:2022-02-11

Data-based evaluation of direction reconstruction for IceCube cascade events by utilizing starting tracks - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube Neutrino Observatory instruments a cubic-kilometer of glacial ice and has been the first experiment to identify high-energy astrophysical neutrinos. There are two main morphologies of IceCube events: tracks and cascades. Tracks result from muons, while cascades result from particle showers induced by in-ice interactions. The directional reconstruction of cascades is less precise than that of tracks, which limits the sensitivity of astrophysical neutrino analyses with cascade events. In order to improve the directional reconstruction of cascade events, accurate ice modeling is essential. However, potential biases might exist in data stemming from unconstrained systematic uncertainties. In this work, feasibility studies to better understand the ice using a data-driven approach are performed, where photons that are likely to have been induced by the hadronic cascade part of muon neutrino charged-current interactions are categorized using probability density functions in time, distance and angle, and the reconstructed direction with this pseudo-cascade is compared with the track direction. In this proceedings, methodology and results are detailed and a path towards better understanding of the ice is discussed.
CRIS-Team Scopus Importer:2025-02-04

Demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
We demonstrate and discuss a state of light with purely transverse angular momentum - a photonic wheel - generated by tight focusing of polarization tailored light. We use an experimental nanoprobing technique to measure the corresponding distribution.
CRIS-Team Scopus Importer:2022-06-05

Demonstration of Near-Optimal Discrimination of Optical Coherent States - Leuchs, Gerd; et al. (Physical Review Letters, 2008)
The optimal discrimination of nonorthogonal quantum states with minimum error probability is a fundamental task in quantum measurement theory as well as an important primitive in optical communication. In this work, we propose and experimentally realize a new and simple quantum measurement strategy capable of discriminating two coherent states with smaller error probabilities than can be obtained using the standard measurement devices: the Kennedy receiver and the homodyne receiver. © 2008 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.demons

Demonstration of the spatial separation of the entangled quantum side-bands of an optical field - Leuchs, Gerd; et al. (Physical Review A, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.demons

Depolarized guided acoustic wave Brillouin scattering in hollow-core photonic crystal fibers - Zhong, Wenjia; Stiller, Birgit; Elser, Dominique Alexander; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2015)
By performing quantum-noise-limited optical heterodyne detection, we observe polarization noise in light after propagation through a hollow-core photonic crystal fiber (PCF). We compare the noise spectrum to the one of a standard fiber and find an increase of noise even though the light is mainly transmitted in air in a hollow-core PCF. Combined with our simulation of the acoustic vibrational modes in the hollow-core PCF, we are offering an explanation for the polarization noise with a variation of guided acoustic wave Brillouin scattering (GAWBS). Here, instead of modulating the strain in the fiber core as in a solid core fiber, the acoustic vibrations in hollow-core PCF influence the effective refractive index by modulating the geometry of the photonic crystal structure. This induces polarization noise in the light guided by the photonic crystal structure.
CRIS-Team Scopus Importer:2021-06-29

Design and fabrication of nanowire metal grating polarizers for a shearing interferometer using polarization marking - Ghadyani, Zahra; Harder, Irina; Rusina, Olga; Iff, Wolfgang; Nercissian, Vanusch; Mantel, Klaus Peter; Lindlein, Norbert; Leuchs, Gerd (Proceedings of the EOS Topical Meeting on Diffractive Optics 2010, 2010)

Design and modeling of a miniature system containing micro-optics - Lindlein, Norbert; et al. (Proceedings of SPIE, 2001)
The design and modeling of micro-optical systems is still a challenging task because classical methods like ray tracing do not take into account diffraction effects and other coherent effects which appear e.g. in the presence of micro-optical array systems. On the other side, there exist scalar or rigorous diffraction theories to model optical systems. But they are also limited in their applications because they either neglect non-paraxial effects or the calculation time is too high for a practical use. In this paper we will therefore give an overview about existing (scalar) theories to model optical systems, especially systems containing micro-optics: a simple paraxial matrix theory, ray tracing, Gaussian beam propagation and the propagation of a wave using the angular spectrum of plane waves. The advantages and disadvantages of these theories will be shown and compared. At the end we will describe a combination of ray tracing and wave propagation methods to give a more realistic simulation of micro-optical systems.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.design
Keywords: Angular spectrum of plane waves; Diffraction theories; Gaussian beams; Micro-optics; Modeling of optical systems; Optical design; Ray tracing

Design and simulation rules for printed optical waveguides with implemented scattering methods in CAD and raytracing software - Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (Proceeding, 117. DGaO-Jahrestagung, 2016)
The printing process of polymer optical waveguides is a new and uncharted research topic, which the research group OPTAVER is principally involved in. A main consequence of the printing process is the roughness of the interface between core and cladding. This surface between the dielectric media creates scattering in printed waveguides. To simulate this behaviour, standard non-sequential raytracing methods have to be extended with scattering algorithms. Here, scattering power spectra for each incident ray interacting with the rough surface are generated using the perturbation theory. Another task is to connect MID-speciﬁc CAD tools with raytracing simulations to create a holistic tool for design and validation of light propagation. This tool is specifically prepared to analyze the manufacturing process of polymer optical waveguides. This technique facilitates new applications in different research and development fields. Comparing the performances of real printed and simulated polymer optical waveguides is one of the major links between the different researchers of this DFG research group.
Keywords: Optisches Design; Optische Systeme; Optische Informationsübertragung

Design considerations for the absolute testing approach of aspherics using combined diffractive optical elements - Lindlein, Norbert; Schwider, Johannes; Harder, Irina; Mantel, Klaus Peter; Khan, Gufran S. (Applied Optics, 2007)
Aspheric optical surfaces are often tested using diffractive optics as null elements. For precise measurements, the errors caused by the diffractive optical element must be calibrated. Recently, we reported first experimental results of a three position quasi-absolute test for rotationally invariant aspherics by using combined-diffractive optical elements (combo-DOEs). Here we investigate the effects of the DOE substrate errors on the proposed calibration procedure and present a set of criteria for designing an optimized combo-DOE. It is demonstrated that this optimized design enhances the overall consistency of the procedure. Furthermore, the rotationally varying part of the surface deviations is compared with the rotationally varying deviations obtained by an N-position averaging procedure and is found to be in good agreement. © 2007 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2007.nat.dphy.optik.1optik.design_9

Design criteria for combined diffractive optical elements for quasi-absolute testing of aspherics - Lindlein, Norbert; et al. (Frontiers in Optics, FiO 2007, 2007)
Recently, we reported first experimental results of a three position quasi-absolute test for rotationally symmetric aspherics by using combined diffractive optical elements (Combo-DOEs). Here we investigate several systematic error sources and present an optimised Combo-DOE. © 2007 Optical Society of America.

Design of a mode converter for efficient light-atom coupling in free space - Sondermann, Markus; Maiwald, Robert; Konermann, Hildegard; Lindlein, Norbert; Peschel, Ulf; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2007)
In this article, we describe how to develop a mode converter that transforms a plane electromagnetic wave into an inward-moving dipole wave. The latter one is intended to bring a single atom or ion from its ground state to an excited state by absorption of a single photon wave packet with near-100% efficiency. © 2007 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.design

Design und Herstellung eines CGH-basierten Modalen Wellenfrontsensors - Stehr, Johannes; Loosen, Florian; Lindlein, Norbert; Alber, Lucas (118. DGaO-Jahrestagung, 2017)
Modale Wellenfrontsensoren können gegenüber einer zonalen Wellenfrontdetektion von Vorteil sein. Etwa, wenn in einem optischen Element fabrikationsbedingt nur spezielle Aberrationsmoden zu erwarten sind. Der Hauptvorteil eines modalen Sensors ist die geringe Auswertekomplexität und folglich ein Geschwindigkeitsvorteil bei der Wellenfrontmessung. Als modale Basis können die Zernike-Polynome dienen, deren Koeffizienten durch Messung der Phasenfront bestimmt werden können. Sind die zu erwartenden Aberrationen für ein optisches Element bekannt, kann die Funktionsweise diesbezüglich optimiert werden. Unser Ziel ist es, einen Wellenfrontsensor auf Basis eines Computer-Generierten Hologramms zu realisieren (Neil et al. 2000). Das Prinzip des Sensors basiert auf der holografischen Rekonstruktion einer ebenen Objektwelle durch eine spezifisch aberrierte Referenzwellenfront. Wir werden die quantitative Untersuchung des intermodalen Crosstalks eines modalen Wellenfrontsensors präsentieren, welcher zur genauen Messung von Defokus und Koma ausgelegt ist. Die Charakterisierung des intermodalen Crosstalks ist dabei notwendig, um ein möglichst effizientes und genaues Sensorverhalten zu erzielen.

Device Calibration Impacts Security of Quantum Key Distribution - Jain, Nitin; Wittmann, Christoffer; Lydersen, Lars; Wiechers, Carlos; Elser, Dominique Alexander; Marquardt, Christoph; Makarov, Vadim; Leuchs, Gerd (Physical Review Letters, 2011)
Characterizing the physical channel and calibrating the cryptosystem hardware are prerequisites for establishing a quantum channel for quantum key distribution (QKD). Moreover, an inappropriately implemented calibration routine can open a fatal security loophole. We propose and experimentally demonstrate a method to induce a large temporal detector efficiency mismatch in a commercial QKD system by deceiving a channel length calibration routine. We then devise an optimal and realistic strategy using faked states to break the security of the cryptosystem. A fix for this loophole is also suggested. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Die Optik - eine physikalische Disziplin im Aufwind bietet Chancen für Deutschland - Leuchs, Gerd; et al. (LaserOpto, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.optik.1optik.dieopt

Differential ray tracing for an improved simulation of incoherent illumination systems - Lindlein, Norbert; et al. (Frontiers in Optics, FiO 2008, 2008)
Analyzing intensity distributions is of great importance for today's illumination systems design. Contrary to Monte-Carlo techniques, differential ray tracing possesses great potential to improve simulation efficiency by reducing computational time while concurrently showing accurate results. © 2008 Optical Society of America.

Different types of coherence: Young-type interference versus Dicke superradiance - Bhatti, Daniel; Bojer, Manuel; von Zanthier, Joachim (Physical Review A, 2021)
Dicke superradiance, i.e., the enhanced spontaneous emission of coherent radiation, is often attributed to radiation emitted by synchronized dipoles coherently oscillating in phase. At the same time, Dicke derived superradiance assuming atoms in entangled Dicke states which do not display any dipole moment. To shed light on this apparent paradox, we study the intensity distribution arising from two identical two-level atoms prepared either in an entangled Dicke state or in a separable atomic state with a nonvanishing dipole moment. We find that the two configurations produce similar far-field intensity patterns, although they stem from fundamentally distinct types of coherence: while in the second case the atoms display coherence among the individual particles, leading to Young-type interference like that known from classical dipoles, atoms in Dicke states possess collective quantum coherence stemming from entanglement and quantum correlations of the state, leading to an interference pattern resulting from enhanced spontaneous emission. This demonstrates that the radiation generated by synchronized dipoles and Dicke superradiance - even if they do produce the same interference pattern - are fundamentally distinct phenomena and have to be interpreted in different ways.
CRIS-Team Scopus Importer:2021-11-26

Diffraction limited holographic lenses in dichromated gelatine - Lindlein, Norbert; et al. (Optical Engineering, 1996)
Holographic lenses in volume media suffer from the mismatch between the recording and the reconstruction wavelength. The lenses are recorded in the blue spectral range because of spectral sensitivity of the recording material. The lenses investigated here are reconstructed with red light. The aim of this work is the realization of diffraction-limited holographic lenses with a high diffraction efficiency in the presence of a wavelength mismatch. Therefore the lenses have to be recorded with at least one aspheric recording wavefront in order to fulfill the Bragg condition on the one hand and to correct the wave aberrations on the other. We propose an iterative optimization procedure which also eliminates the wave aberrations caused by the misalignments of the recording setup. This optimization procedure requires the accurate measurement of the wave aberrations. These aberrations are eliminated by an appropriate modification of the aspheric recording wavefront. In this paper the design principle, the recording setup, the interferometric measurement, and the iterative optimization procedure are given. This optimization procedure results in diffraction-limited holographic lenses. © 1996 Society of Photo-Optical Instrumentation Engineers.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.diffra
Keywords: Dichromated gelatine; Holographic lenses; Holographic optical elements; Thick phase gratings; Wave aberration; Wavelength mismatch

Diffractive complete lateral shearing interferometer with reduced coherence - Harder, Irina; Nercissian, Vanusch; Schwider, Johannes; Berger, Andreas; Mantel, Klaus Peter; Lindlein, Norbert (Proceedings of the EOS Topical Meeting on Diffractive Optics 2010, 2010)

Diffractive lateral shearing interferometer for phase shift mask measurement using an excimer laser source - Lindlein, Norbert; et al. (Eighth International Symposium on Laser Metrology, 2005)
The physical limits of optical lithography are mainly determined by the aperture of the mask projection system and the wavelength of the light. In addition to the wavelength shift to the deep UV the application of special techniques to improve the processing window are required. This has furthered the application of the phase shift mask as a lithography tool. The generation of the exact intensity distribution needed in the plane of the wafer strongly depends on the accuracy of the phase shift introduced by the phase shift mask. However, one difficult issue is the reliable measurement of the phase shift introduced by the phase mask at the working wavelength. This is of course mainly due to the lack of suitable and simple interferometric devices for the deep-UV-region - here 193 nm. We propose the use of a diffractive shearing interferometer as a way out. By combining two Ronchi-phase gratings in series it is possible to produce shear and phase shifts for the evaluation of the fringe patterns simply by axial and lateral shifts of the phase gratings relative to each other. Since the excimer laser emits spatially partial coherent light only, the coherence issue is one of the physical problems dealt with. The state of the art of our experiments will be presented.

Diffractive simultaneous bidirectional shearing interferometry using tailored spatially coherent light - Nercissian, Vanusch; Harder, Irina; Mantel, Klaus Peter; Berger, Andreas; Leuchs, Gerd; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2011)

Diffractive simultaneous lateral shearing interferometry - Lindlein, Norbert; et al. (Optical Measurement Systems for Industrial Inspection VII, 2011)
A lateral shearing interferometer usually provides the slope data of a wave front under test along one direction. For the complete reconstruction of the wavefront, two slope datasets along different directions are required. Based on diffractive gratings, a simultaneous measurement of bothdata sets can be carried out. Two possible realizations are presented using a polarization signature and a partially coherent light source. © 2011 SPIE.
Keywords: Diffraction gratings; Interferometry; Spatial coherence

Diffractive Systems: Aberration Correction with Diffractive Elements - Lindlein, Norbert (Encyclopedia of Modern Optics, 2004)
UnivIS-Import:2015-04-20:Pub.2004.nat.dphy.optik.1optik.diffra

Diffraktive optische Elemente zur Lichtmanipulation - Schwider, Johannes; Dresel, Thomas; Beyerlein, Mathias; Harder, Irina; Lindlein, Norbert; Collischon, Martin; Leuchs, Gerd (2001)
UnivIS-Import:2015-04-14:Pub.2001.nat.dphy.optik.1optik.diffra

Diffraktives 2D-Shearing-Interferometer mit partieller rÃa4umlicher KohÃa4renz - Nercissian, Vanusch; Mantel, Klaus; Harder, Irina; Berger, Andreas; Schwider, Johannes; Lindlein, Norbert (DGaO-Proceedings, 2010)

Digitizing 3D objects for Reverse Engineering and Virtual Reality - Häusler, Gerd; et al. (Principles of 3D Image Analysis andSynthesis, 2000)
UnivIS-Import:2015-04-20:Pub.2000.nat.dphy.optik.1optik.digiti

Direct experimental test of non-separability and other quantum techniques using continuous variables of light - Korolkova, Natalia; Silberhorn, Christine; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (European Physical Journal D, 2002)
We present schemes for the generation and evaluation of continuous variable entanglement of bright optical beams and give a brief overview of a variety of optical techniques and quantum communication applications on this basis. A new entanglement-based quantum interferometry scheme with bright beams is suggested. The performance of the presented schemes is independent of the relative interference phase which is advantageous for quantum communication applications. © EDP Sciences, Springer-Verlag, Società Italiana di Fisica 2002.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.direct

Direct integration of the S-matrix applied to rigorous diffraction - Iff, Wolfgang; Lindlein, Norbert; Tishchenko, A. V. (Journal of Optics, 2014)

Directional Dicke Subradiance with Nonclassical and Classical Light Sources - Bhatti, Daniel; Schneider, Raimund; Oppel, Steffen; von Zanthier, Joachim (Physical Review Letters, 2018)
We investigate Dicke subradiance of N >= 2 distant quantum sources in free space, i.e., the spatial emission patterns of spontaneously radiating noninteracting multilevel atoms or multiphoton sources, prepared in totally antisymmetric states. We find that the radiated intensity is marked by a full suppression of spontaneous emission in particular directions. In resemblance to the analogous, yet inverted, superradiant emission profiles of N distant two-level atoms prepared in symmetric Dicke states, we call the corresponding emission patterns directional Dicke subradiance. We further derive that higher-order intensity correlations of the light emitted by statistically independent thermal light sources display the same directional Dicke subradiant behavior and show that it stems from the same interference phenomenon as in the case of quantum sources. We finally present measurements of directional Dicke subradiance for N = 2,...,5 distant thermal light sources corroborating the theoretical finding

Direct measurement of the coupled spatiotemporal coherence of parametric down-conversion under negative group-velocity dispersion - Cutipa Giménez, Paula; Spasibko, Kirill Yu; Chekhova, Maria (Optics Letters, 2020)
We present a direct measurement of the spatiotemporal coherence of parametric down-conversion in the range of negative group-velocity dispersion. In this case, the frequency-angular spectra are ring-shaped, and temporal coherence is coupled to spatial coherence. Correspondingly, the lack of coherence due to spatial displacement can be compensated for with the introduction of time delay. We show a simple technique, based on a modified Mach-Zehnder interferometer, which allows us to measure time coherence and near-field space coherence simultaneously, with complete control over both variables. This technique is also suitable for the measurement of second-order coherence, where the main applications are related to two-photon spectroscopy.
CRIS-Team Scopus Importer:2020-07-24

Direct measurement of the geometric spin hall effect of light - Korger, Jan; Aiello, Andrea; Chille, Vanessa; Wittmann, Christoffer; Banzer, Peter; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Frontiers in Optics, FIO 2012, 2012)
We experimentally demonstrate a recently predicted novel beam shift phenomenon, the geometric spin Hall effect of light. This effect is fundamentally different from ordinary beam shifts due to its purely geometric nature. © OSA 201

Discontinuous space variant sub-wavelength structures for generating radially polarized light in visible region - Ghadyani, Zahra; Rothau, Sergej; Lindlein, Norbert; Leuchs, Gerd; Lohse, Olga; Harder, Irina (Journal of the European Optical Society: Rapid Publications, 2011)

Discover better optical sensors - By exploring and exploiting nature's limits - Häusler, Gerd (Optics InfoBase Conference Papers, 2019)
Nature's limits are precious: they often reveal uncertainty products connecting coherence, resolution, precision, channel capacity… So we can bargain with nature for "optimal" 3D sensors with novel features or just better precision, resolution, speed.
CRIS-Team Scopus Importer:2021-04-20

Discrimination of optical coherent states using a photon number resolving detector - Wittmann, Christoffer; Andersen, Ulrik Lund; Leuchs, Gerd (Journal of Modern Optics, 2010)
The discrimination of non-orthogonal quantum states with reduced or without errors is a fundamental task in quantum measurement theory. In this work, we investigate a quantum measurement strategy capable of discriminating two coherent states probabilistically with significantly smaller error probabilities than can be obtained using non-probabilistic state discrimination. We find that appropriate postselection of the measurement data of a photon number resolving detector can be used to discriminate two coherent states with small error probability. We compare our new receiver to an optimal intermediate measurement between minimum error discrimination and unambiguous state discrimination.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.optik.1optik.discri
Keywords: Quantum information; Quantum receivers; Quantum state discrimination

Distillation of Squeezing from Non-Gaussian Quantum States - Heersink, Joel; Marquardt, Christoph; Dong, Ruifang; Filip, Radim; Lorenz, Stefan; Leuchs, Gerd; Andersen, Ulrik Lund (Physical Review Letters, 2006)
We show that single copy distillation of squeezing from continuous variable non-Gaussian states is possible using linear optics and conditional homodyne detection. A specific non-Gaussian noise source, corresponding to a random linear displacement, is investigated experimentally. Conditioning the signal on a tap measurement, we observe probabilistic recovery of squeezing. © 2006 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.distil

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2020)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of -1.648 +/- 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source's suitability for scalable hybrid quantum network applications with pulsed quantum light. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2020-11-13

Diversity Detection of Speckles for Double-Wavelength Interferometry on Rough Surfaces - Leuchs, Gerd; et al. (Applied Optics, 2002)
When the topography of a rough surface is measured with a double-wavelength interferometer, the phase error of the signal corresponding to the synthetic wavelength increases in the vicinity of dark speckles. To overcome this problem we perform an amplitude-dependent averaging of the synthetic phase over independent speckles (diversity detection). We either use spatially neighboring speckles or in the case of depolarizing surfaces, we use speckles of the same spatial mode, but with orthogonal polarizations. For the latter case the lateral resolution stays unaffected. The reduction of the speckle noise is demonstrated experimentally for a laterally scanning double-wavelength interferometer with superheterodyne detection of the synthetic phase. © 2002 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.divers

DPSK Signal Regeneration Using a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Stephan, Christian; Cvecek, Kristian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Conf. Proc. OFC, Paper OThB2, March, 2007)
Power characteristics and phase functions of a NALM are investigated in simulations and experimentally, showing a phase-preserving nonlinear characteristics suitable for amplitude regeneration of phase-encoded signals. A negative power penalty of -1.5 dB was obtained. ©2006 Optical Society of America.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.dpsksi

Drei-Stellungstest für Asphären: Steigerung der Genauigkeit - Geist, Eduard; Mantel, Klaus Peter; Harder, Irina; Lindlein, Norbert (DGAO-Proceedings, 2010)
Keywords: Jahrestagung der DGaO

Dual-wave-front computer-generated holograms for quasi-absolute testing of aspherics. - Beyerlein, Mathias; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2002)
Testing of aspherics by means of computer-generated holograms (CGHs) is well known. To perform a quasi-absolute test of rotationally symmetric aspheric surfaces, two wave fronts must be encoded in the CGH. Both the null lens and a spherical lens have to be stored. This enables successive measurements of the aspheric and of a cat's-eye position without changing the object arm of the interferometer. Two possibilities for encoding both wave fronts have been investigated. A first-order approximation for estimating the influence of disturbing diffraction orders is given.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.dualwa

Dynamic array spot shaping for laser micro machining - Lindlein, Norbert; et al. (Laser Beam Shaping X, 2009)
Laser manufacturing of microstructures using a single focus is a well known technology. Multi-spot optics are applied for process parallelizing if the demand on throughput in mass production rises or large areas of material have to be processed. Diffractive optical elements (DOEs) are used for parallel laser processing of a repetitive structure. These elements split the beam into a periodic spot pattern, where each spot shows the same shape and energy. This allows simultaneous manufacturing of several equal shaped structures at the same time. For patterning a surface this is state of the art and the appropriate technique to reduce processing time while maintaining a high lateral resolution as well as a good relative positioning of the structure due to the DOE. We investigate the usage of microlens arrays as multifunctional elements for forming an arbitrary shaped laser beam into a spot-, a ring-spot- or a line-array pattern. It can be shown that the intensity distribution of each spot is equal to the intensity distribution of all other spots in the whole pattern. The shape of the spots is defined by the angular distribution of the incident beam. We demonstrate that besides other optical properties the output beam profile strongly depends on the Fresnel-Number and is influenced by diffraction and interference effects. We present important design rules which consider geometrical and physical optics. The properties of the spot arrays, like spot diameter, Rayleigh length and beam divergence in dependency of beam and system properties are investigated. Finally we will show some laser micro structuring and micro drilling results in different materials. © 2009 SPIE.
Keywords: Flys Eye Condenser; Laser Beam Homogenizer; Material Processing; Micro Optics; Spot Array Generator

Dynamic Brillouin cooling for continuous optomechanical systems - Zhu, Chang Long; Stiller, Birgit (Materials for Quantum Technology, 2023)
Up until now, ground state cooling using optomechanical interaction is realized in the regime where optical dissipation is higher than mechanical dissipation. Here, we demonstrate that optomechanical ground state cooling in a continuous optomechanical system is possible by using backward Brillouin scattering while mechanical dissipation exceeds optical dissipation which is the common case in optical waveguides. The cooling is achieved in an anti-Stokes backward Brillouin process by modulating the intensity of the optomechanical coupling via a pulsed pump to suppress heating processes in the strong coupling regime. With such dynamic modulation, a significant cooling factor can be achieved, which can be several orders of magnitude lower than for the steady-state case. This modulation scheme can also be applied to Brillouin cooling generated by forward intermodal Brillouin scattering.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Brillouin scattering; mechanical cooling; optomechanics; quantum optics

Dynamic Brillouin cooling for continuous optomechanical systems - Zhu, Changlong; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Cooling a mechanical oscillator to its quantum ground state by overcoming the effects of thermal environment has always attracted great interests [1-3]. Preparing a single mode mechanical oscillator to its ground state has been realized in cavity optomechanics by using sideband cooling. Beyond the cooling of single mode mechanical mode, lots of novel phonon cooling methods for multimode have been proposed recently for extended optomechanical platforms with many degrees of freedom. The intriguing limit of these cases is quantum ground state cooling in continuous optomechanical systems. Brillouin-based technologies provide cooling for groups of phonons in continuous optomechanical systems [4,5]. However, the large mechanical loss, which exceeds optical loss, limits the optomechanical continuum cooling. For general backward Brillouin scattering with higher frequency and thus lower Q-factor, it was thought that it is impractical for ground-state cooling in continuous optomechanical systems.
CRIS-Team Scopus Importer:2024-12-16

Dynamic range expansion of a Shack-Hartmann sensor by use of a modified unwrapping algorithm - Lindlein, Norbert; et al. (Optics Letters, 1998)
An algorithm for expanding the dynamic range of Shack-Hartmann sensors is proposed. The distribution of the spot dislocations is treated with a modified unwrapping algorithm that is widely used in interferometry. The algorithm unwraps the spot dislocations and assigns the spots to their original subapertures, leading to a huge expansion of the dynamic range. For the proposed algorithm there remains a limitation on the maximum wave-front curvature instead of on the maximum wave-front slope. Examples are given that show spot fields that were wrapped four times; the measured wave front had a peak-to-valley value of 116λ. © 1998 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.dynami

Dynamics of Development of Laser-Induced Structures on the Surface of a Titanium Alloy - Fomicheva, Iana; Druzhinin, Petr; Amler, Hans; Schuesslbauer, Wolfgang; Christiansen, Silke; Leuchs, Gerd (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
We investigated the dynamics of LSFL (Low Spatial Frequency LIPSS) evolution on the titanium alloy surface. To create them, 12 W picosecond 1.064 μm laser with a pulse repetition rate from 50 kHz to 500 kHz was used. For different laser repetition rate (500, 150, 100 and 50 kHz), the ranges of LSFL periods and peak Fluence of pulse (Fp) for which the maximum period is reached were determined. We also determined the laser parameters at which the resulting LSFL have good quality and uniformity, regardless of the initial surface roughness.
CRIS-Team Scopus Importer:2023-06-02
Keywords: HSFL; LIPSS; LSFL; surface patterning; Ti6Al4V; titanium alloy

Effective Negative Nonlinearity of a Nonlinear Amplifying Loop Mirror for Compensating Nonlinearity-Incuced Signal Distortions - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Communication, 2008. ECOC 2008. 34th European Conference on 21-25, 2008)
UnivIS-Import:2017-12-18:Pub.2008.tech.IE.LEH.effect

Effect of Amplitude Noise on Multi-Level Phase Regeneration - Lenz, M.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (Lasers and Electro-Optics Europe (CLEO EUROPE/EQEC), 2011 Conference on and 12th European Quantum Electronics Conference, 2011)
lhft_intern.bib::Lenz2011

Effect of dimensionality on the spectra of hybrid plasmonic-photonic crystals - Romanova, Alexandra; Korovin, A. V.; Romanov, Sergey (Physics of the Solid State, 2013)
Based on colloidal crystals of various dimensionality, hybrid metal-dielectric plasmonic-photonic heterocrystals have been prepared. It has been shown that the spectra of optical transmission of heterocrystals are mostly controlled by the sum of contributions of composing plasmonic and photonic crystals. At the same time, there are a number of phenomena caused by the mutual effect of heterostructure components, which lead to a deviation of observed optical properties from the linear superposition of responses of these crystals. In particular, it has been found that the anomalous transmission controlled by the plasmonic crystal decreases with increasing the dimensionality of the photonic crystal attached to it. At the same time, light reflection on a metallized surface changes light diffraction in photonic crystals and leads to Fabry-Perot oscillation amplification. It has been assumed that an intermediate layer is formed, in which Bloch modes of the photonic crystal and surface plasmon-polaritons of the plasmonic crystal are hybridized.
EAM Import::2019-03-14

Efficient coupling to an optical resonator by exploiting time-reversal symmetry - Bader, Marianne; Heugel, Simon Tobias; Chekhov, Alexander; Sondermann, Markus; Leuchs, Gerd (New Journal of Physics, 2013)
The interaction of a cavity with an external field is symmetric under time reversal. Thus, coupling to a resonator is most efficient when the incident light is the time reversed version of a free cavity decay, i.e. when it has a rising exponential shape matching the cavity lifetime. For light entering the cavity from only one side, the maximally achievable coupling efficiency is limited by the choice of the cavity mirrors' reflectivities. Such an empty-cavity experiment serves also as a model system for single-photon single-atom absorption dynamics. We present experiments coupling exponentially rising pulses to a cavity system which allows for high coupling efficiencies. The influence of the time constant of the rising exponential is investigated as well as the effect of a finite pulse duration. We demonstrate coupling 94% of the incident TEM mode into the resonator. © IOP Publishing and Deutsche Physikalische Gesellschaft.

Efficient generation of temporally shaped photons using nonlocal spectral filtering - Averchenko, Valentin; Sych, Denis; Marquardt, Christoph; Leuchs, Gerd (Physical Review A, 2020)
We study the generation of single-photon pulses with the tailored temporal shape via nonlocal spectral filtering. A shaped photon is heralded from a time-energy entangled photon pair upon spectral filtering and time-resolved detection of its entangled counterpart. We show that the temporal shape of the heralded photon is defined by the time-inverted impulse response of the spectral filter and does not depend on the heralding instant. Thus one can avoid postselection of particular heralding instants and achieve a substantially higher heralding rate of shaped photons as compared to the generation of photons via nonlocal temporal modulation. Furthermore, the method can be used to generate shaped photons with a coherence time in the ns-mu s range and is particularly suitable to produce photons with the exponentially rising temporal shape required for efficient interfacing to a single quantum emitter in free space.
CRIS-Team WoS Importer:2020-01-24

Efficient microwave to optical photon conversion: An electro-optical realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G. L. (Optica, 2016)
Linking classical microwave electrical circuits to the optical telecommunication band is at the core of modern communication. Future quantum information networks will require coherent microwave-to-optical conversion to link electronic quantum processors and memories via low-loss optical telecommunication networks. Efficient conversion can be achieved with electro-optical modulators operating at the single microwave photon level. In the standard electro-optic modulation scheme, this is impossible because both up- and down-converted sidebands are necessarily present. Here, we demonstrate true single-sideband up- or down-conversion in a triply resonant whispering gallery mode resonator by explicitly addressing modes with asymmetric free spectral range. Compared to previous experiments, we show a 3 orders of magnitude improvement of the electro-optical conversion efficiency, reaching 0.1% photon number conversion for a 10 GHz microwave tone at 0.42 mW of optical pump power. The presented scheme is fully compatible with existing superconducting 3D circuit quantum electrodynamics technology and can be used for nonclassical state conversion and communication. Our conversion bandwidth is larger than 1 MHz and is not fundamentally limited.
CRIS-Team Scopus Importer:2021-06-29

Efficient optical up-conversion by coherent sum-frequency generation for highly sensitive terahertz detection - Sedlmeir, Florian; Schwefel, Harald; Strekalov, Dmitry V.; Bauerschmidt, Sebastian; Preu, Sascha; Malzer, Stefan; Döhler, Gottfried; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Detection of weak THz signals is very challenging due to the extremely low energy of one THz photon (temperature equivalent of 48K). Frequency up-conversion to the near infra-red (NIR) and subsequent detection of the up-converted photon with sensitive, low-noise detectors is one way to achieve this task, albeit suffering form extremely poor conversion rates. Whispering gallery mode resonators (WGMRs), however, support well confined modes with high quality factors (Q) and extremely high field intensities inside the resonator, thus allowing efficient non-linear conversion rates. © 2011 IEEE.

Efficient polarization squeezing in optical fibers - Leuchs, Gerd; et al. (Optics Letters, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.effici

Efficient saturation of an ion in free space - Fischer, Martin; Bader, Marianne; Maiwald, Robert; Golla, Andrea; Sondermann, Markus; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2014)
We report on the demonstration of a light-matter interface coupling light to a single (Formula presented.) ion in free space. The interface is realized through a parabolic mirror partially surrounding the ion. It transforms a Laguerre–Gaussian beam into a linear dipole wave converging at the mirror’s focus. By measuring the non-linear response of the atomic transition, we deduce the power required for reaching an upper-level population of (Formula presented.) to be (Formula presented.) at half linewidth detuning from the atomic resonance. Performing this measurement while scanning the ion through the focus provides a map of the focal intensity distribution. From the measured power, we infer a coupling efficiency of (Formula presented.) on the linear dipole transition when illuminating from half solid angle, being among the best coupling efficiencies reported for a single atom in free space.

Efficient single sideband microwave to optical conversion using a LiNbO3 WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dimitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We present a coherent microwave to telecom signal converter based on the electro-optical effect using a crystalline WGM-resonator coupled to a 3D microwave cavity, achieving high photon conversion efficiency of 0.1% with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Effiziente Berechnung der Impulsantwort zeitabhängiger Signale in gedruckten Polymer Optischen Wellenleitern (POWs) - Backhaus, Carsten; Loosen, Florian; Lindlein, Norbert (Proceeding, 118. DGaO-Jahrestagung, 2017)
Gedruckte Polymer optische Wellenleiter (POWs) sind hochgradig multimodig, sodass eine Raytracing Simulation mit guter Näherung verwendet werden darf. Neben der Erweiterung des Simulationsmodells von Wellenleitern bezüglich der Dämpfung des Signals [1] wurde eine Erweiterung bezüglich der Signaldispersion eingeführt. Für diese wurde ein effizientes Verfahren entwickelt, welches für die Anwendung auf POWs optimiert ist, indem die speziellen physikalischen Eigenschaften dieser ausgenutzt werden. Erste Ergebnisse aus den Simulationen werden hier präsentiert. Die Effizienz resultiert aus der Annahme, dass die Signallaufzeit t eines Strahls als Verhältnis der Weglänge und der Lichtgeschwindigkeit c/n im Medium berechnet werden kann. Abhängig von der Mode des Strahls, wird er im Strahlenmodell unterschiedliche Weglängen zurücklegen. Indem man alle Strahlen vom Sender zum Detektor nach ihrer Signallaufzeit ordnet und in kleine Laufzeitintervalle Δt einteilt, kann man die Strahlleistung aller Strahlen innerhalb eines Laufzeitintervalls aufsummieren, und erhält die Impulsantwort des Systems direkt durch eine Raytracing Simulation. [1] F. Loosen et al. DGaO Proceedings C5 (2016)

Eine neue Methode zur Abformung sensibler Objekte - Häusler, Gerd; et al. (Restauro, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.einene

Electrical circuit model of arrays of resonant elements - Lomanets, Vadym; Zhuromskyy, Oleksandr; Onishchukov, G.; Peschel, Ulf (Physical Review B, 2012)
We present an effective electrical circuit model that can be used for a quasianalytic analysis of electromagnetic oscillations in arrays of coupled elements, resonant in the microwave domain. The model accounts for electric and magnetic interactions between charges and currents excited in individual resonators. Respective coupling coefficients can be calculated from the field and current distributions in a subsystem of just one or two elements, provided by a finite-difference electromagnetic solver. The model was used to investigate current distributions and dispersion relations of wave propagation on chains of coupled split-ring resonators. The change of the dispersion characteristics from forward to backward propagating wave type observed experimentally is readily reproduced by the model.
EAM Import::2019-03-14

Electronic noise-free measurements of squeezed light - Leuchs, Gerd; et al. (Optics Letters, 2008)
We study the implementation of a correlation measurement technique for the characterization of squeezed light. We show that the sign of the covariance coefficient revealed from the time-resolved correlation data allow us to distinguish among squeezed, coherent, and thermal states. In contrast to the traditional method of characterizing squeezed light, involving measurement of the variation of the difference photocurrent, the correlation measurement method allows one to eliminate the contribution of the electronic noise, which becomes a crucial issue in experiments with dim sources of squeezed light. © 2008 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.electr

Electro-optic frequency comb generation in lithium niobate whispering gallery mode resonators - Rueda, Alfredo; Sedlmeir, Florian; Leuchs, Gerd; Kuamri, Madhuri; Schwefel, Harald G.L. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Optical frequency combs (OFCs) are light sources whose spectra consists of equally spaced frequency lines in the optical domain [1]. They have great potential for improving high-capacity data transfer, all-optical atomic clocks, spectroscopy, and high-precision measurements [2].
CRIS-Team Scopus Importer:2019-11-15

Emission of circularly polarized light by a linear dipole - Neugebauer, Martin; Banzer, Peter; Nechayev, Sergey (Science Advances, 2019)
Controlling the polarization state and the propagation direction of photons is a fundamental prerequisite for many nanophotonic devices and a precursor for future on-chip communication, where the emission properties of individual emitters are particularly relevant. Here, we report on the emission of partially circularly polarized photons by a linear dipole. The underlying effect is linked to the near-field part of the angular spectrum of the dipole, and it occurs in any type of linear dipole emitter, ranging from atoms and quantum dots to molecules and dipole-like antennas. We experimentally observe it by near-field to far-field transformation at a planar dielectric interface and numerically demonstrate the utility of this phenomenon by coupling the circularly polarized light to the individual paths of crossing waveguides.
CRIS-Team Scopus Importer:2019-07-09

Emission of semiconductor nanocrystals in photonic crystal environment - Romanov, Sergey; Peschel, Ulf (Nanocrystals: Synthesis, Properties and Applications, 2010)
EAM Import::2019-03-14

Empirical Strategy forDetection and Removal of Misalignment Aberrations inInterferometry - Lindlein, Norbert; et al. (Optik, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.empiri

Encapsulation of silver nanowire networks by atomic layer deposition for indium-free transparent electrodes - Göbelt, Manuela; Keding, Ralf; Schmitt, Sebastian W.; Hoffmann, Bjoern; Jaeckle, Sara; Latzel, Michael; Radmilovic, Vuk V.; Radmilovic, Velimir R.; Spiecker, Erdmann; Christiansen, Silke; Hoffmann, Björn (Nano Energy, 2015)
We report on the development of a novel nano-composite transparent electrode material to be used in various energy applications e.g. as contacts for solar cells, composed of a wet-chemically synthesized silver nanowire (AgNW) network encapsulated in a transparent conductive oxide (TCO) which was deposited with nano-scale precision by atomic layer deposition (ALD). The AgNWs form a random network on a substrate of choice when being drop casted. ALD encapsulation of AgNWs guarantees a conformal and thickness controlled coating of the wires e.g. by the selected aluminum doped zinc oxide (AZO). Annealing of the AgNWs prior to ALD coating, yield a local sintering of AgNWs at their points of intersection, which improves the conductivity of the composite electrodes by reducing their sheet resistance. To demonstrate the performance of these AgNW/AZO composite transparent electrodes, they were used as a top electrode on wafer-based silicon (Si) - solar cells. A novel combination of scanning electron microscopy and image processing is used to determine the degree of percolation of the AgNWs on large areas of the nano-composite AgNW/AZO electrodes. Our results show that the solar cell with percolated AgNW/AZO electrode show the highest short circuit current density (28 mA/cm(2)) and a series resistance in the same order of magnitude compared to reference solar cells with a thermally evaporated silver grid electrode. The electrode example we chose reveals that the developed AgNW/AZO electrode is a technologically relevant and cheap alternative to conventional solar cell screen printed grid electrodes, which contain similar to 95% more Ag per device area, with a high potential to be further systematically optimized by the presented image processing method. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Atomic layer deposition; Silver nano wires; Transparent electrode; Encapsulation; Aluminum doped zinc oxide (AZO); Solar cell

Engineering of spontaneous emission in free space via conditional measurements - Bojer, Manuel; Götzendörfer, Lukas; Bachelard, Romain; von Zanthier, Joachim (Physical Review Research, 2022)
We study the collective spontaneous emission of three identical two-level atoms initially prepared in the excited states by measuring Glauber's third-order photon correlation function. Assuming two atoms at subwavelength distance from each other such that they are subject to the dipole-dipole interaction while the third one is located several wavelengths away, we observe super- and subradiant decay alike, depending on the direction of observation. Unlike the case where no remote atom is introduced or no conditional measurements are performed, the spontaneous emission behavior of the conditioned three-atom system is strongly modified, i.e., differing from the single-atom and the canonical two-atom configuration. The conditional measurements associated with the three-photon correlation function in combination with the dipole-dipole interaction between the adjacent atoms lead to quantum interference among the different decay channels allowing one to engineer the spontaneous emission in space and time.
CRIS-Team Scopus Importer:2022-10-21

Enhanced free space beam capture by improved optical tapers - Bartley, Tim; Heim, Bettina; Elser, Dominique Alexander; Sych, Denis; Sabuncu, Metin; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (2010)
In our continuous variable quantum key distribution (QKD) scheme, the homodyne detection set-up requires balancing the intensity of an incident beam between two photodiodes. Realistic lens systems are insufficient to provide a spatially stable focus in the presence of large spatial beam-jitter caused by atmospheric transmission. We therefore present an improved geometry for optical tapers which offer up to four times the angular tolerance of a lens. The effective area of a photodiode can thus be increased, without decreasing its bandwidth. This makes them suitable for use in our free space QKD experiment and in free space optical communication in general. © Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering 201
Keywords: Atmospheric optics; Beam-jitter; Free space communication; Optical taper; Quantum key distribution; Random media

Enhanced spin-orbit coupling in an epsilon-near-zero material - Eismann, Jörg; Ackermann, Lisa; Kantor, Brian; Nechayev, Sergey; Alam, M. Zahirul; Fickler, Robert; Boyd, Robert W.; Banzer, Peter (Optica, 2022)
Light can carry both spin and orbital angular momentum. While it is known that a nonparaxial circularly polarized beam couples the spin angular momentum to orbital angular momentum, this phenomenon does not hold upon col-limation of the field. With the rising interest in epsilon-near-zero photonics, integral ingredients to this field are the beam-shaping capabilities of such a regime. In this work, it is experimentally shown that a permanent conversion of spin-to-orbital angular momentum arises naturally from an incident circularly polarized field on an isotropic inter-face due to the asymmetry in the Fresnel coefficients. More significantly, the conversion efficiency can be substantially enhanced in the presence of an epsilon-near-zero film due to the unique Fresnel properties exhibited in such a regime. It is further shown that the conversion efficiency scales with the nonparaxiality of the incident field. Our study showcases the intriguing phenomena resulting from the combination of concepts as old as Fresnel coefficients and modern mate-rials such as epsilon-near-zero films. (C) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement
CRIS-Team WoS Importer:2022-10-21

Entangled photons from subwavelength nonlinear films - Santiago-Cruz, Tomas; Sultanov, Vitaliy; Zhang, Haizhong; Krivitsky, Leonid A.; Chekhova, Maria (Optics Letters, 2021)
Miniaturized entangled photon sources, in particular based on subwavelength metasurfaces, are highly demanded for the development of integrated quantum photonics. Here, as a first step towards the development of quantum optical metasurfaces (QOMs), we demonstrate generation of entangled photons via spontaneous parametric down-conversion (SPDC) from subwavelength films. We achieve photon pair generation with a high coincidence-to-accidental ratio in lithium niobate and gallium phosphide nanofilms. By implementing the fiber spectroscopy of SPDC in nanofilms, we measure a spectrum with a bandwidth of 500 nm, limited only by the overall detection efficiency. The spectrum reveals vacuum field enhancement due to a Fabry-Perot resonance inside the nonlinear films. It also suggests a strategy for observing SPDC from QOM. Our experiments lay the groundwork for future development of flat SPDC sources, including QOM. (C) 2021 Optical Society of America
CRIS-Team WoS Importer:2021-03-19

Entanglement of polarization and orbital angular momentum - Bhatti, Daniel; von Zanthier, Joachim; Agarwal, G. S. (Physical Review A, 2015)
We investigate two-photon entangled states using two important degrees of freedom of the electromagnetic field, namely orbital angular momentum (OAM) and spin angular momentum. For photons propagating in the same direction we apply the idea of entanglement duality and develop schemes to do entanglement sorting based on either OAM or polarization. In each case the entanglement is tested using appropriate witnesses. We finally present generalizations of these ideas to three-and four-photon entangled state

Entanglement Stabilization in a Superconducting Quantum Processor using Parity Detection and Real-Time Feedback - Eichler, Christopher (Workshop on Machine Learning for Quantum Technology, 2019)

Entangling different degrees of freedom by quadrature squeezing cylindrically polarized modes - Gabriel, C.; Aiello, Andrea; Zhong, W.; Euser, T. G.; Joly, N. Y.; Banzer, Peter; Foertsch, M.; Elser, Dominique; Andersen, U. L.; Marquardt, Christoph; Russell, P. St. J.; Leuchs, Gerd (Physical Review Letters, 2011)
Quantum systems such as, for example, photons, atoms, or Bose-Einstein condensates, prepared in complex states where entanglement between distinct degrees of freedom is present, may display several intriguing features. In this Letter we introduce the concept of such complex quantum states for intense beams of light by exploiting the properties of cylindrically polarized modes. We show that already in a classical picture the spatial and polarization field variables of these modes cannot be factorized. Theoretically it is proven that by quadrature squeezing cylindrically polarized modes one generates entanglement between these two different degrees of freedom. Experimentally we demonstrate amplitude squeezing of an azimuthally polarized mode by exploiting the nonlinear Kerr effect in a specially tailored photonic crystal fiber. These results display that such novel continuous-variable entangled systems can, in principle, be realized.© 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Entangling Fiber Solitons - Quantum Noise Engineering for Interferometry and Communication - Leuchs, Gerd; et al. (Optics and Photonics News, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.entang

Entangling the Whole by Beam Splitting a Part - Croal, Callum; Peuntinger, Christian; Chille, Vanessa; Marquardt, Christoph; Leuchs, Gerd; Korolkova, Natalia; Mista, Ladislav (Physical Review Letters, 2015)
A beam splitter is a basic linear optical element appearing in many optics experiments and is frequently used as a continuous-variable entangler transforming a pair of input modes from a separable Gaussian state into an entangled state. However, a beam splitter is a passive operation that can create entanglement from Gaussian states only under certain conditions. One such condition is that the input light is suitably squeezed. We demonstrate, experimentally, that a beam splitter can create entanglement even from modes which do not possess such a squeezing provided that they are correlated to, but not entangled with, a third mode. Specifically, we show that a beam splitter can create three-mode entanglement by acting on two modes of a three-mode fully separable Gaussian state without entangling the two modes themselves. This beam splitter property is a key mechanism behind the performance of the protocol for entanglement distribution by separable states. Moreover, the property also finds application in collaborative quantum dense coding in which decoding of transmitted information is assisted by interference with a mode of the collaborating party.
CRIS-Team Scopus Importer:2022-06-05

Environment-assisted quantum-information correction for continuous variables - Leuchs, Gerd; Andersen, Ulrik Lund; et al. (Physical Review A, 2010)
Quantum-information protocols are inevitably affected by decoherence which is associated with the leakage of quantum information into an environment. In this article we address the possibility of recovering the quantum information from an environmental measurement. We investigate continuous-variable quantum information, and we propose a simple environmental measurement that under certain circumstances fully restores the quantum information of the signal state although the state is not reconstructed with unit fidelity. We implement the protocol for which information is encoded into conjugate quadratures of coherent states of light and the noise added under the decoherence process is of Gaussian nature. The correction protocol is tested using both a deterministic as well as a probabilistic strategy. The potential use of the protocol in a continuous-variable quantum-key distribution scheme as a means to combat excess noise is also investigated. © 2010 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.optik.1optik.enviro

Erratum: Lattice-plasmon-induced asymmetric transmission in two-dimensional chiral arrays (APL Photonics (2022) 7 (016105) DOI: 10.1063/5.0074849) - Apurv Chaitanya, N.; Butt, M. A. T.; Reshef, O.; Boyd, Robert W.; Banzer, Peter; De Leon, Israel (APL Photonics, 2022)
The original article1 contains an error in Eq. (1). The correct equation is. (Formula Presented) The original article’s analysis, findings, and conclusions remain the same.
CRIS-Team Scopus Importer:2022-10-14

Estimating the coincidence rate between the optical and radio array of IceCube-Gen2 - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube-Gen2 Neutrino Observatory is proposed to extend the all-flavour energy range of IceCube beyond PeV energies. It will comprise two key components: I) An enlarged 8 km3 in-ice optical Cherenkov array to measure the continuation of the IceCube astrophysical neutrino flux and improve IceCube’s point source sensitivity above ∼ 100 TeV; and II) A very large in-ice radio array with a surface area of about 500 km2. Radio waves propagate through ice with a kilometer-long attenuation length, hence a sparse radio array allows us to instrument a huge volume of ice to achieve a sufficient sensitivity to detect neutrinos with energies above tens of PeV. The different signal topologies for neutrino-induced events measured by the optical and in-ice radio detector - the radio detector is mostly sensitive to the cascades produced in the neutrino interaction, while the optical detector can detect long-ranging muon and tau leptons with high accuracy - yield highly complementary information. When detected in coincidence, these signals will allow us to reconstruct the neutrino energy and arrival direction with high fidelity. Furthermore, if events are detected in coincidence with a sufficient rate, they resemble the unique opportunity to study systematic uncertainties and to cross-calibrate both detector components. We present the expected rate of coincidence events for 10 years of operation. Furthermore, we analyzed possible detector optimizations to increase the coincidence rate.
CRIS-Team Scopus Importer:2025-02-04

Etched microlenses for Optical Systems - Lindlein, Norbert; et al. (EOS Topical Meetings Digest Series, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.etched

Evaluation algorithms for multistep measurement of spatially varying linear polarization and phase - Berger, Andreas; Nercissian, Vanusch; Mantel, Klaus Peter; Harder, Irina (Optics Letters, 2012)

Evaluation of 4H-SiC MOSFET transfer characteristics using machine-learning techniques - Lehmeyer, Johannes; Citak, Timon; Weber, Heiko B.; Krieger, Michael (Electronics Letters, 2023)

Excitation of gap plasmonic wavguides by nano antennas - Schmauß, Bernhard; Weng, J.; Banzer, P.; Ploss, D.; Kriesch, A.; Peschel, Ulf (Conference on Lasers and Electro-Optics CLEO, Paper QMF1, San Jose, May, 2010)
We experimentally demonstrate the excitation of plasmonic gap waveguides by nano antennas. The excitation is shown to be both spatially and spectrally dependent which can potentially be used for the selective excitation of plasmonic nanostructure
lhft_intern.bib::Schmauss10

Excitation of plasmonic gap waveguides by nanoantennas - Romanov, Sergey; et al. (Optics Express, 2009)
We model and optimize the excitation of a plasmonic gap waveguide by a dipole antenna. The coupling efficiency strongly depends on antenna and waveguide properties where impedanec matching plays a critical role. The optimization of antenna lengths and gap widths shows that concepts of circuit networks can likewise be applied to optical frequencies. Using classical optimization schemes known from electrical engineering we manage to increase the coupling efficiency by a factor of 129 compared with the situation without antennas. © 2009 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.excita

Executing Algorithms for Optimization and Quantum Phase Recognition on a Superconducting Quantum Processor - Eichler, Christopher (Seminar hosted by Michael Hartmann, 2021)
Keywords: wwwqudev

Exotic looped trajectories of photons in three-slit interference - Magaña-Loaiza, Omar S; De Leon, Israel; Mirhosseini, Mohammad; Fickler, Robert; Safari, Akbar; Mick, Uwe; McIntryre, Brian; Banzer, Peter; Rodenburg, Brandon; Leuchs, Gerd; Boyd, Robert W. (Nature Communications, 2016)
The validity of the superposition principle and of Born's rule are well-accepted tenants of quantum mechanics. Surprisingly, it has been predicted that the intensity pattern formed in a three-slit experiment is seemingly in contradiction with the most conventional form of the superposition principle when exotic looped trajectories are taken into account. However, the probability of observing such paths is typically very small, thus rendering them extremely difficult to measure. Here we confirm the validity of Born's rule and present the first experimental observation of exotic trajectories as additional paths for the light by directly measuring their contribution to the formation of optical interference fringes. We accomplish this by enhancing the electromagnetic near-fields in the vicinity of the slits through the excitation of surface plasmons. This process increases the probability of occurrence of these exotic trajectories, demonstrating that they are related to the near-field component of the photon's wavefunction.

Expansion of the dynamic range of a Shack-Hartmann sensor by using astigmatic microlenses - Lindlein, Norbert; Pfund, Johannes; Schwider, Johannes (Optical Engineering, 2000)
The dynamic range of a Shack-Hartmann sensor is normally limited by the fact that the foci can leave their subapertures and so a definite attachment of the foci to their subapertures is difficult. One method for solving this problem is to give the focal spots a kind of label to identify them even if they leave their subaperture. We describe how the dynamic range of a Shack-Hartmann sensor can be expanded by using lenses with well-defined astigmatism. We also derive a relation between the spot displacements and the partial derivatives of the wavefront for large wavefront slopes.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.expans

Experimental Comparison of All-Optical Phase-Preserving Amplitude Regeneration Techniques - Endres, D.; Stephan, C.; Sponsel, K.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (12th International Conf. on Digital Object Identifier (ICTON), Munich, June, 2010)
lhft_intern.bib::Endres10

Experimental continuous-variable cloning of partial quantum information - Leuchs, Gerd; et al. (Physical Review A, 2008)
The fidelity of a quantum transformation is strongly linked with the prior partial information of the state to be transformed. We illustrate this interesting point by proposing and demonstrating the superior cloning of coherent states with prior partial information. More specifically, we propose two simple transformations that under the Gaussian assumption optimally clone symmetric Gaussian distributions of coherent states as well as coherent states with known phases. Furthermore, we implement for the first time near-optimal state-dependent cloning schemes relying on simple linear optics and feedforward. © 2008 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.experi_3

Experimental cross-polarization detection of coupling far-field light to highly confined plasmonic gap modes via nanoantennas - Wen, J.; Banzer, Peter; Kriesch, Arian; Ploss, Daniel; Schmauß, Bernhard; Peschel, Ulf (Applied Physics Letters, 2011)
We experimentally demonstrate the coupling of far-field light to highly confined plasmonic gap modes via connected nanoantennas. The excitation of plasmonic gap modes is shown to depend on the polarization, position, and wavelength of the incident beam. Far-field measurements performed in crossed polarization allow for the detection of extremely weak signals re-emitted from gap waveguides and can increase the signal-to-noise ratio dramatically.
lhft_intern.bib::Wen11

Experimental cryptography using continuous polarization states - Leuchs, Gerd; et al. (Quantum Communications and Cryptograph, 2006)
UnivIS-Import:2015-04-20:Pub.2006.nat.dphy.optik.1optik.experi_8

Experimental Demonstration of Coherent State Estimation with Minimal Disturbance - Leuchs, Gerd; et al. (Physical Review Letters, 2006)
We investigate the optimal trade-off between information gained about an unknown coherent state and the state disturbance caused by the measurement process. We propose several optical schemes that can enable this task, and we implement one of them, a scheme that relies on only linear optics and homodyne detection. Experimentally we reach near optimal performance, limited only by detection inefficiencies. In addition, we show that such a scheme can be used to enhance the transmission fidelity of a class of noisy channels. © 2006 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.experi

Experimental demonstration of continuous variable cloning with phase-conjugate inputs - Leuchs, Gerd; et al. (Physical Review Letters, 2007)
We report the first experimental demonstration of continuous variable cloning of phase-conjugate coherent states as proposed by Cerf and Iblisdir. In contrast to this proposal, the cloning transformation is accomplished using only linear optical components, homodyne detection, and feedforward. As a result of combining phase conjugation with a joint measurement strategy, superior cloning is demonstrated with cloning fidelities reaching 89%. © 2007 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.experi_7

Experimental Demonstration of Continuous Variable Entanglement Distillation - Dong, Ruifang; Lassen, Mikael Ostergaard; Marquardt, Christoph; Filip, Radim; Andersen, Ulrik Lund; Leuchs, Gerd (Quantum Electronics and Laser Science Conference 2008, 2008)
We experimentally demonstrate distillation of continuous variable entanglement through an attenuating quantum channel. Through a simple protocol based entirely on linear optics and homodyne detection we probabilistically filter out a highly entangled state from a less non-entangled mixed state.<br

Experimental Demonstration of Continuous Variable Quantum Erasing - Leuchs, Gerd; et al. (Physical Review Letters, 2004)
The concept of continuous variable quantum erasing was analyzed by using light beams. The quantum nondemolition (QND) coupling was accomplished by using a beam splitter coupled to squeezed light. It was observed that the phase quadrature information of the single state could be recovered by erasing the amplitude quadrature information. It was also observed that the measured values of open diamonds increased when the degree of input squeezing was reduced.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.experi

Experimental demonstration of linear and spinning Janus dipoles for polarisation- and wavelength-selective near-field coupling - Picardi, Michela F.; Neugebauer, Martin; Eismann, Joerg S.; Leuchs, Gerd; Banzer, Peter; Rodriguez-Fortuno, Francisco J.; Zayats, Anatoly V. (Light: Science & Applications, 2019)
The electromagnetic field scattered by nano-objects contains a broad range of wavevectors and can be efficiently coupled to waveguided modes. The dominant contribution to scattering from subwavelength dielectric and plasmonic nanoparticles is determined by electric and magnetic dipolar responses. Here, we experimentally demonstrate spectral and phase selective excitation of Janus dipoles, sources with electric and magnetic dipoles oscillating out of phase, in order to control near-field interference and directional coupling to waveguides. We show that by controlling the polarisation state of the dipolar excitations and the excitation wavelength to adjust their relative contributions, directionality and coupling strength can be fully tuned. Furthermore, we introduce a novel spinning Janus dipole featuring cylindrical symmetry in the near and far field, which results in either omnidirectional coupling or noncoupling. Controlling the propagation of guided light waves via fast and robust near-field interference between polarisation components of a source is required in many applications in nanophotonics and quantum optics.
CRIS-Team Scopus Importer:2019-06-21

Experimental demonstration of macroscopic quantum coherence in Gaussian states - Marquardt, Christoph; Andersen, Ulrik L.; Leuchs, Gerd; Takeno, Yuishi; Yukawa, Mitsuyoshi; Yonezawa, Hidehiro; Furusawa, Akira (Physical Review A, 2007)
We witness experimentally the presence of macroscopic coherence in Gaussian quantum states using a recently proposed criterion. The macroscopic coherence stems from interference between macroscopically distinct states in phase space, and we prove experimentally that a coherent state contains these features with a distance in phase space of 0.51±0.02 shot noise units. This is surprising because coherent states are generally considered being at the border between classical and quantum states, not yet displaying any nonclassical effect. For squeezed and entangled states the effect may be larger but depends critically on the state purity. © 2007 The American Physical Societ
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.experi_8

Experimental demonstration of the geometric spin hall effect of light in highly focused vector beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Lindlein, Norbert; Aiello, Andrea; Marquardt, Christoph; Korger, Jan; Leuchs, Gerd (Quantum Electronics and Laser Science Conference, QELS 2012, 2012)
We demonstrate the geometric spin Hall effect of light by focusing a specially polarization tailored beam of light, resulting in the generation of purely transverse angular momentum in the focal plane. © 2012 OS

Experimental Distillation of Squeezed States - Heersink, Joel; Marquardt, Christoph; Filip, Radim; Dong, Ruifang; Chekhova, Maria V.; Lorenz, S.; Leuchs, Gerd; Andersen, Ulrik Lund (QThL3 Quantum Electronics and Laser Science Conference (CLEO:FS), 2006)
We report on the first experimental distillation of an intense squeezed state from a non-Gaussian mixture of polarization squeezed states. Conditioning the signal on a tap measurement, we observe probabilistic recovery of the squeezing.<br

Experimental entanglement distillation of mesoscopic quantum states - Dong, Ruifang; Lassen, Mikael; Heersink, Joel; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd; Andersen, L. Ulrik (Nature Physics, 2008)
The distribution of entangled states between distant parties in an optical network is crucial for the successful implementation of various quantum communication protocols such as quantum cryptography, teleportation and dense coding. However, owing to the unavoidable loss in any real optical channel, the distribution of loss-intolerant entangled states is inevitably afflicted by decoherence, which causes a degradation of the transmitted entanglement. To combat the decoherence, entanglement distillation, a process of extracting a small set of highly entangled states from a large set of less entangled states, can be used. Here we report on the distillation of deterministically prepared light pulses entangled in continuous variables that have undergone non-Gaussian noise. The entangled light pulses are sent through a lossy channel, where the transmission is varying in time similarly to light propagation in the atmosphere. By using linear optical components and global classical communication, the entanglement is probabilisticallyincreased. © 2008 Macmillan Publishers Limited. All rights reserve
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.experi

Experimental evidence for Raman-induced limits to efficient squeezing in optical fibers - Leuchs, Gerd; et al. (Optics Letters, 2008)
We report new experiments on polarization squeezing using ultrashort photonic pulses in a single pass of a birefringent fiber. We measure what is to our knowledge a record squeezing of -6.8±0.3 dB in optical fibers, which when corrected for linear losses is -10.4±0.8 dB. The measured polarization squeezing as a function of optical pulse energy, which spans a wide range from 3.5-178.8 pJ, shows a very good agreement with the quantum simulations, and for the first time we see the proof experimentally that Raman effects limit and reduce squeezing at high pulse energy. © 2008 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.experi_9

Experimental measurement of the Berry curvature from anomalous transport - Wimmer, Martin; Price, Hannah M.; Carusotto, Iacopo; Peschel, Ulf (Nature Physics, 2017)
The geometric properties of energy bands underlie fascinating phenomena in many systems, including solid-state, ultracold gases and photonics. The local geometric characteristics such as the Berry curvature can be related to global topological invariants such as those classifying the quantum Hall states or topological insulators. Regardless of the band topology, however, any non-zero Berry curvature can have important consequences, such as in the semi-classical evolution of a coherent wavepacket. Here, we experimentally demonstrate that the wavepacket dynamics can be used to directly map out the Berry curvature. To this end, we use optical pulses in two coupled fibre loops to study the discrete time evolution of a wavepacket in a one-dimensional geometric 'charge' pump, where the Berry curvature leads to an anomalous displacement of the wavepacket. This is both the first direct observation of Berry curvature effects in an optical system, and a proof-of-principle demonstration that wavepacket dynamics can serve as a high-resolution tool for mapping out geometric properties.
CRIS-Team Scopus Importer:2023-04-20

Experimental Polarization Squeezing and Continuous Variable Entanglement via the Optical Kerr Effect - Leuchs, Gerd; et al. (Quantum Information with continuous variables of atoms and light, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dphy.optik.1optik.experi_9

Experimental Quantum Cloning with Continuous Variables - Leuchs, Gerd; Andersen, Ulrik Lund; Lütkenhaus, Norbert; et al. (Quantum Information with continuous variables of atoms and light, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dphy.optik.1optik.experi

Experimental quantum purification of coherent states - Leuchs, Gerd; et al. (Physical Review A, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.experi

Experimental reconstruction of spatial Schmidt modes for a wide-field SU(1,1) interferometer - Frascella, Gaetano; Zakharov, Roman V.; Tikhonova, Olga V.; Chekhova, Maria (Laser Physics, 2019)
We study the spatial mode content at the output of a wide-field SU(1,1) interferometer, i.e. a nonlinear interferometer comprising two coherently-pumped spatially-multimode optical parametric amplifiers placed in sequence with a focusing element in between. This device is expected to provide a phase sensitivity below the shot-noise limit for multiple modes over a broad angular range. To reconstruct the spatial modes and their weights, we implement a simple method based on the acquisition of only intensity distributions. The eigenmode decomposition of the field is obtained through the measurement of the covariance of intensities at different spatial points. We investigate both the radial and azimuthal (orbital angular momentum) modes and show that their total number is large enough to enable applications of the interferometer in spatially-resolved phase measurements.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Orbital angular momentum; Parametric down-conversion; Schmidt modes; SU(1; 1) interferometer

Experimental results for expanding the dynamic range of a Shack-Hartmann sensor using astigmatic microlenses - Lindlein, Norbert; et al. (Optical Engineering, 2002)
A conventional Shack-Hartmann wavefront sensor cannot be used for the measurement of wavefronts with steep slopes if the spots leave their respective subapertures. In an earlier paper [N. Lindlein, J. Pfund, and J. Schwider, "Expansion of the dynamic range of a Shack-Hartmann sensor by using astigmatic microlenses," Opt. Eng. 39(8), 2220-2225 (2000)], we described a method to expand the dynamic range of a Shack-Hartmann wavefront sensor by marking the spots using astigmatic microlenses. We present experimental results for this method and describe how this special sensor can be interpreted as a combination of several Shack-Hartmann sensors with enlarged subapertures.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.experi
Keywords: Dynamic range expansion; Microlenses; Shack-Hartmann sensor; Wavefront sensor

Experimental results of the simultaneous measurement of spatially varying phase and polarization. - Rothau, Sergej; Kellermann, Christine; Lindlein, Norbert (116. Annual Meeting of the DGaO, 2015)

Experimental results of the simultaneous measurement of spatially varying phase and polarization - Rothau, Sergej; Kellermann, Christine; Lindlein, Norbert (2015)

Experimental Tomographic State Reconstruction of Itinerant Microwave Photons - Eichler, Christopher; et al. (QSIT lunch seminar, 2010)
A wide range of experiments studying microwave photons localized in superconducting cavities have made important contributions to our understanding of the quantum properties of radiation. Propagating microwave photons, however, have so far been studied much less intensely. Here we present measurements in which we reconstruct the Wigner function of itinerant single photon Fock states and their superposition with the vacuum using linear amplifiers and quadrature amplitude detectors. We have developed efficient methods to separate the detected single photon signal from the noise added by the amplifier by analyzing the moments of the measured amplitude distribution up to 4th order. This work is expected to enable studies of propagating microwaves in the context of linear quantum optics. Combining single photon sources with beamsplitter and squeezing devices, efficient photon state measurements could allow for future linear optics quantum computation with microwaves photons.
Keywords: wwwqudev

Experimental verification of high spectral entanglement for pulsed waveguided spontaneous parametric down-conversion - Leuchs, Gerd; et al. (Physical Review A, 2009)
We study the spectral properties of spontaneous parametric down-conversion (SPDC) in a periodically poled waveguided structure of potassium-titanyl- phosphate (KTP) crystal pumped by ultrashort pulses. Our theoretical analysis reveals a strongly entangled and asymmetric structure of the two-photon spectral amplitude for type-II SPDC. We confirm these predictions experimentally by measuring single-photon spectra, on one hand, and the dependence of Hong-Ou-Mandel interference visibility on the width of spectral filtering, on the other hand. © 2009 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.experi

Experiment towards continuous-variable entanglement swapping: Highly correlated four-partite quantum state - Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Heersink, Joel; Brownnutt, Michael; Silberhorn, Christine; Pan, Quing; van Loock, Peter; Korolkova, Natalia; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2003)
We present a protocol for performing entanglement swapping with intense pulsed beams. In a first step, the generation of amplitude correlations between two systems that have never interacted directly is demonstrated. This is verified in direct detection with electronic modulation of the detected photocurrents. The measured correlations are better than expected from a classical reconstruction scheme. In an entanglement swapping process, a four-partite entangled state is generated. We prove experimentally that the amplitudes of the four optical modes are quantum correlated 3 dB below shot noise, which is consistent with the presence of genuine four-party entanglement.<br

Exploration of mass splitting and muon/tau mixing parameters for an eV-scale sterile neutrino with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physics Letters B, 2024)
We present the first three-parameter fit to a 3+1 sterile neutrino model using 7.634 years of data from the IceCube Neutrino Observatory on νμ+ν‾μ charged-current interactions in the energy range 500–9976 GeV. Our analysis is sensitive to the mass-squared splitting between the heaviest and lightest mass state (Δm412), the mixing matrix element connecting muon flavor to the fourth mass state (|Uμ4|2), and the element connecting tau flavor to the fourth mass state (|Uτ4|2). Predicted propagation effects in matter enhance the signature through a resonance as atmospheric neutrinos from the Northern Hemisphere traverse the Earth to the IceCube detector at the South Pole. The remaining sterile neutrino matrix elements are left fixed, with |Ue4|2=0 and δ14=0, as they have a negligible effect, and δ24=π is set to give the most conservative limits. The result is consistent with the no-sterile neutrino hypothesis with a probability of 4.3%. Profiling the likelihood of each parameter yields the 90% confidence levels: 2.4eV2<Δm412<9.6eV2, 0.0081<|Uμ4|2<0.10, and |Uτ4|2<0.035, which narrows the allowed parameter-space for |Uτ4|2. However, the primary result of this analysis is the first map of the 3+1 parameter space exploring the interdependence of Δm412, |Uμ4|2, and |Uτ4|2.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Atmospheric neutrino IceCube TeV oscillation sterile

Exploring quantum microwave radiation emitted from superconducting electronic circuits - Eichler, Christopher (2013)
Superconducting electronic circuits have turned into one of the prime physical systems to investigate quantum optical and atomic physics phenomena in engineered solid state devices. While the on-demand generation and the processing of quantum states on a chip are now routinely achieved with high fidelity, it remains challenging to detect propagating microwave photons with equally high efficiency. This is mainly due to the absence of efficient photon counters in this frequency range. In my presentation, I explain how we employ low-noise linear amplifiers instead of photon counters for measuring microwave field correlations at the quantum level. For this purpose we have developed efficient data acquisition, processing and analysis techniques to separate the quantum signal of interest from the noise added by the amplifiers [1]. In our experiments we have successfully generated and characterized various types of interesting quantum fields, ranging from on-demand single photons [2], over squeezed radiation [3], to spatially entangled fields [4]. Recently, we have also developed our own parametric amplifiers to perform nearly quantum limited measurements of microwave radiation [3,6]. These enabled us to observe entanglement between a quantum two-level system and microwave photons propagating freely through a transmission line [5]. The possibility to accurately synthesize, guide and characterize non-classical microwave fields bears great potential to be used in radiation based quantum simulation and quantum network architectures and for probing other systems with yet unrivaled sensitivity. References: [1] C. Eichler et al., PRA 86, 032106–13 (2012), [2] C. Eichler et al., PRL. 106, 220503 (2011), [3] C. Eichler et al., PRL 107, 113601 (2011), [4] C. Lang et al. Nat. Phys., in print (2013), [5] C. Eichler et al., PRL. 109, 240501 (2012), [6] C. Eichler and Wallraff, A., arXiv:1305.6583
Keywords: wwwqudev

Exploring Quantum Microwave Radiation Using Linear Detectors - Eichler, Christopher (Workshop on Quantum Radar, 2014)
Keywords: wwwqudev

Exploring the phase structure of the multi-flavor Schwinger model with quantum computing - Funcke, Lena; Hartung, Tobias; Jansen, Karl; Kühn, Stefan; Pleinert, Marc-Oliver; Schuster, Stephan; von Zanthier, Joachim (Proceedings of Science, 2023)
We propose a variational quantum eigensolver suitable for exploring the phase structure of the multi-flavor Schwinger model in the presence of a chemical potential. The parametric ansatz circuit we design is capable of incorporating the symmetries of the model, present in certain parameter regimes, which allows for reducing the number of variational parameters substantially. Moreover, the ansatz circuit can be implementated on both measurement-based and circuit-based quantum hardware. We numerically demonstrate that our ansatz circuit is able to capture the phase structure of the model and allows for faithfully approximating the ground state. Our results show that our approach is suitable for current intermediate-scale quantum hardware and can be readily implemented on existing quantum devices.
CRIS-Team Scopus Importer:2024-12-16

Extraordinary low transmission effects for ultra-thin patterned metal films - Reibold, David; Shao, F.; Erdmann, Andreas; Peschel, Ulf (Optics Express, 2009)
Thin metal films show a residual transmission for light in the visible and UV spectral range. This transmission can be strongly reduced by an appropriate sub-wavelength patterning of the metal film. Our investigation is focused on metal films with a thickness much below 100nm, where the transmission response is dominated by the individual posts acting like antennas and cannot be attributed to the excitation of surface plasmons. The almost complete suppression of transmission for ultra-thin metal films depends mainly on the absorber width, but not on the pitch of the pattern. The effect is robust with respect to imperfections of the geometry or larger features imprinted into the sub-wavelength pattern. © 2008 Optical Society of America.
UnivIS-Import:2017-07-10:Pub.2009.tech.IE.LEB.extrao

Extraordinary transmission through a single coaxial aperture in a thin metal film - Banzer, Peter; Kindler, Jochen; Quabis, Susanne; Peschel, Ulf; Leuchs, Gerd (Optics Express, 2010)
We investigate experimentally the transmission properties of single sub-wavelength coaxial apertures in thin metal films (t = 110 nm). Enhanced transmission through a single sub-wavelength coaxial aperture illuminated with a strongly focused radially polarized light beam is reported. In our experiments we achieved up to four times enhanced transmission through a single coaxial aperture as compared to a (hollow) circular aperture with the same outer diameter.We attribute this enhancement of transmission to the excitation of a TEM-mode for illumination with radially polarized light inside the single coaxial aperture. A strong polarization contrast is observed between the transmission for radially and azimuthally polarized illumination. Furthermore, the observed transmission through a single coaxial aperture can be strongly reduced if surface plasmons are excited. The experimental results are in good agreement with finite difference time domain (FDTD) simulations.
EAM Import::2019-03-14

Extreme Concentration and Nanoscale Interaction of Light - Leuchs, Gerd; Andrianov, Alexey V.; Anashkina, Elena A.; Manshina, Alina A.; Banzer, Peter; Sondermann, Markus (ACS Photonics, 2022)
Concentrating light strongly calls for appropriate polarization patterns of the focused light beam and for up to a full 4πsolid angle geometry. Focusing on the extreme requires efficient coupling to nanostructures of one kind or another via cylindrical vector beams having such patterns, the details of which depend on the geometry and property of the respective nanostructure. Cylindrical vector beams can not only be used to study a nanostructure, but also vice versa. Closely related is the discussion of topics such as the ultimate diffraction limit, a resonant field enhancement near nanoscopic absorbers, as well as speculations about nonresonant field enhancement, which, if it exists, might be relevant to pair production in vacuum. These cases do require further rigorous simulations and more decisive experiments. While there is a wide diversity of scenarios, there are also conceptually very different models offering helpful intuitive pictures despite this diversity.
Created from Fastlane, Scopus look-up
Keywords: field enhancement; focusing; light-matter interactions; nonlinear optics; quantum optics

Extreme Events through Prevailing Backscattering and Their Suppression by a Focusing Nonlinearity - Schultheiß, Vincent; Wimmer, Martin; Malzer, Stefan; Peschel, Ulf (Physical Review X, 2018)
We investigate linear and nonlinear light propagation in weakly perturbed AlGaAs slab waveguides whose fabrication induced local defects give rise to random multiple scattering. The statistical evaluation of the intensity distribution at the rear facet reveals an abundance of high-amplitude events in the linear regime, contradicting the predictions of the central limit theorem by far. In this article we propose weak successive backscattering to be a generator of high-amplitude events, while a focusing nonlinearity of the Kerr type counterintuitively diminishes them, thus effectively randomizing the intensity distribution. We support our experimental findings with numerical simulations based on the stray matrix approach introduced by Edrei et al. [Phys. Rev. Lett. 62, 2120 (1989)]. This novel proposed mechanism for the formation of extreme events in the context of linear wave dynamics represents the first encounter of the phenomenon in the limit of weak scattering.
CRIS-Team WoS Importer:2019-02-20

Extreme thermodynamics in nanolitre volumes through stimulated Brillouin–Mandelstam scattering - Geilen, Andreas; Popp, Alexandra; Das, Debayan; Junaid, Saher; Poulton, Christopher G.; Chemnitz, Mario; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (Nature Physics, 2023)
Examining the physical properties of materials—particularly of toxic liquids—under a wide range of thermodynamic states is a challenging problem due to the extreme conditions the material has to experience. Such temperature and pressure regimes, which result in a change in the refractive index and sound velocity, can be accessed by optoacoustic interactions such as Brillouin–Mandelstam scattering. Here we demonstrate the Brillouin–Mandelstam measurements of nanolitre volumes of liquids in extreme thermodynamic regimes. This is enabled by a fully sealed liquid-core optical fibre containing carbon disulfide. Within this waveguide, which exhibits tight optoacoustic confinement and a high Brillouin gain, we are able to conduct spatially resolved measurements of the local Brillouin response, giving us access to a resolved image of the temperature and pressure values along the liquid channel. We measure the material properties of the liquid core at very large positive pressures (above 1,000 bar) and substantial negative pressures (below –300 bar), as well as explore the isobaric and isochoric regimes. The extensive thermodynamic control allows the tunability of the Brillouin frequency shift of more than 40% using only minute volumes of liquid.
CRIS-Team Scopus Importer:2023-10-06

Fading channel estimation for free-space continuous-variable secure quantum communication - Ruppert, Laszlo; Peuntinger, Christian; Heim, Bettina; Günthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique Alexander; Leuchs, Gerd; Filip, Radim; Marquardt, Christoph (New Journal of Physics, 2019)
We investigate estimation of fluctuating channels and its effect on security of continuous-variable quantum key distribution. We propose a novel estimation scheme which is based on the clusterization of the estimated transmittance data. We show that uncertainty about whether the transmittance is fixed or not results in a lower key rate. However, if the total number of measurements is large, one can obtain using our method a key rate similar to the non-fluctuating channel even for highly fluctuating channels. We also verify our theoretical assumptions using experimental data from an atmospheric quantum channel. Our method is therefore promising for secure quantum communication over strongly fluctuating turbulent atmospheric channels.
CRIS-Team WoS Importer:2020-03-06

Far field calculation of distorted Gaussian beams - Pflaum, Christoph; Rall, Phillip Lino; Lindlein, Norbert (Journal of the Optical Society of America A-Optics Image Science and Vision, 2022)
Far field calculations of beams, such as laser beams, are often applied in optical engineering. Current beam propagation methods fail in certain range parameters due to high storage requirements of the algorithms. This paper presents a new beam propagation method for far field calculations of distorted Gaussian beams in a homogeneous medium including optical elements, such as lenses. The method works even in the case of a large distance from the observation plane to the beam waist and can be applied to larger divergence angles. This new simulation technique factors out the phase of the Gaussian TEM00 beam and solves the resulting partial differential equation by suitable finite difference or finite element discretization methods.<br

Fast 3d - Camera for Industrial and Medical Applications - Häusler, Gerd; et al. (Proc. of ODIMAP II, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.fast3d

Feasibility of free space quantum key distribution with coherent polarization states - Heim, Bettina; Leuchs, Gerd; et al. (New Journal of Physics, 2009)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.feasib

Feasibility of Printed Optical Waveguides Over the Entire Process Chain by OPTAVER - Hoffmann, Gerd Albert; Wienke, Alexander; Kaierle, Stefan; Overmeyer, Ludger; Hamjah, Mohd Khairulamzari; Reitberger, Thomas; Zeitler, Jochen; Franke, Jörg; Lorenz, Lukas; Bock, Karlheinz; Backhaus, Carsten; Loosen, Florian; et al. (Springer International Publishing, 2022)
The integration of the knowledge of different engineering disciplines to build a three-dimensional optical short-range interconnect system is the core of this book. For this purpose, the physical and technological principles of optical technologies have to be considered. The focus here is on optical transmission technology. Attenuation, the propagation of optical signals, the construction of printed optical waveguides and their manufacturing processes play a special role. Likewise, product development methods of technical systems are a related field; since up to now, especially for 3D-Opto-MID, no adequate methodology exists. Analogies to mechatronic systems and their sub-processes do exist, but these have to be evaluated and expanded with regard to the new optomechatronic components.
CRIS-Team Scopus Importer:2024-12-16

Feasibility of quantum key distribution with macroscopically bright coherent light - Kovalenko, Olena; Spasibko, Kirill; Chekhova, Maria; Usenko, Vladyslav C.; Filip, Radim (Optics Express, 2019)
We address feasibility of continuous-variable quantum key distribution using bright multimode coherent states of light and homodyne detection. We experimentally verify the possibility to properly select signal modes by matching them with the local oscillator and this way to decrease the quadrature noise concerned with unmatched bright modes. We apply the results to theoretically predict the performance of continuous-variable quantum key distribution scheme using multimode coherent states in scenarios where modulation is applied either to all the modes or only to the matched ones, and confirm that the protocol is feasible at high overall brightness. Our results open the pathway towards full-scale implementation of quantum key distribution using bright light, thus bringing quantum communication closer to classical optics.
CRIS-Team Scopus Importer:2019-12-24

Feasibility of squeezing detection over satellite links - Muller, Christian R.; Seshadreesan, Kaushik P.; Leuchs, Gerd; Marquardt, Christoph (2017 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2017, 2018)
Quantum squeezing is the nonlinear quantum mechanical effect by which the Heisenberg uncertainty in one observable can be reduced below the shot noise level at the expense of increased uncertainty in its conjugate observable. We study the detection of optical quadrature squeezing via homodyne detection in satellite links. The propagation of the quantum states over large distances and through a varying gravitational potential offers the possibility to test the fundamental laws of physics at the interface of quantum mechanics and general relativity. We model the task as a binary hypothesis testing problem where the null hypothesis corresponds to the vacuum state and the alternative hypothesis corresponds to the squeezed state. Using the Chernoff bound, we derive the number of individual measurements required to limit the average error probabilities to a given value.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Continuous-variables; Homodyne detection; Optical satellite communication; Quadrature squeezing

Fiber-modes and fiber-anisotropy characterization using low-coherence interferometry - Ma, Y. Z.; Sych, Denis; Onishchukov, Georgy; Ramachandran, S.; Peschel, Ulf; Schmauß, Bernhard; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2009)
An optical low-coherence interferometry technique has been used to simultaneously resolve the mode profile and to measure the intermodal dispersion of guided modes of a few-mode fiber. Measurements are performed using short samples of fiber (about 50 cm). There is no need for a complex mode-conversion technique to reach a high interference visibility. Four LP mode groups of the few-mode fiber are resolved. Experimental results and numerical simulations show that the ellipticity of the fiber core leads to a distinct splitting of the degenerate high-order modes in group index. For the first time, to the best of our knowledge, it has been demonstrated that degenerate LP11 modes are much more sensitive to core shape variations than the fundamental modes and that intermodal dispersion of high-order degenerate modes can be used for characterizing the anisotropy of an optical waveguide.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.fiberm

Fiber optic based system for polarization sensitive spectroscopy of semiconductor quantum structures - Arora, Ashish; Karmakar, Biswajit; Sharma, Sayan; Schardt, Michael; Malzer, Stefan; Bansal, Bhavtosh; Döhler, Gottfried; Arora, Brij Mohan (Review of Scientific Instruments, 2010)
We describe an optical fiber based setup for performing polarization resolved magneto-optical spectroscopy measurements under low temperatures (∼4 K) and high magnetic fields (∼8 T). The measurements are performed in a windowless helium Dewar. Circularly polarized light is produced inside the Dewar by inserting the polarizing elements between the fiber end and the sample. Photoconductivity spectra of a GaAs/AlGaAs multiquantum-well sample have been measured over the photon energy range of 1.5-1.7 eV in left and right circularly polarized light under crossed magnetic and electric fields. It is shown that reversing the direction of magnetic field produces the same spectral changes as caused by changing the direction of circular polarization with the optical components. © 2010 American Institute of Physics.

Fiber Solitons—Quantum Interferometry and Entanglement - Leuchs, Gerd; Silberhorn, Christine; Glöckl, Oliver; Marquardt, Christoph; Korolkova, Natalia (Quantum Electronics and Laser Science Conference 2002, 2002)
The study of quantum properties of soliton pulses in fibers spans the full range from basic research to applications. New developments in high precision quantum interferometry and quantum communications will be reported as well as novel aspects of the range limit due to losses.<br

Fibre-optic photon-number squeezing in the normal group-velocity dispersion regime - Sizmann, Andreas; Fauster, Thomas; Leuchs, Gerd; et al. (Journal of Modern Optics, 1998)
The nonlinear optical Kerr effect, acting on optical pulses in fibres, creates spectral sidebands and noise correlations between these sidebands. The reduction of photon-number fluctuations of these pulses below the shot-noise limit by spectral filtering is well established in the anomalous dispersion regime which allows for soliton formation. Here it is demonstrated that a significant quantum-noise reduction with spectral filtering can also be reached for pulses in the normal dispersion regime. The filter function was optimized and the power dependence of the noise reduction was investigated. The best squeezing result is (1.2 ± 0.2) dB (corresponding to (2.6 ± 0.7) dB inferred for 100% detection efficiency).
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.fibreo

Flexible beam shaping system using fly's eye condenser - Lindlein, Norbert; Lano, Maik; Zimmermann, Maik; Bich, Andreas; Eisner, Martin; Harder, Irina; Voelkel, Reinhard; Weible, Ken (Applied Optics, 2010)
Normally, fly's eye condensers are used to homogenize light. However, in the case of fully coherent light, a fly's eye condenser, in connection with some simple optical elements, such as a diffractive axicon, a grating, and a telescope, can be used as a quite flexible beam shaping system, forming arrays of rings, parts of rings, or other structures with varying diameters. We present the principle, some simulation results, and some first experimental results. © 2010 Optical Society of America.

Fluorescence-based remote irradiation sensor in liquid-filled hollow-core photonic crystal fiber - Zeltner, Richard; Bykov, D. S.; Xie, S.; Euser, T. G.; Russell, Philip St. John (Applied Physics Letters, 2016)
We report an irradiation sensor based on a fluorescent ``flying particle'' that is optically trapped and propelled inside the core of a water-filled hollow-core photonic crystal fiber. When the moving particle passes through an irradiated region, its emitted fluorescence is captured by guided modes of the fiber core and so can be monitored using a filtered photodiode placed at the fiber end. The particle speed and position can be precisely monitored using in-fiber Doppler velocimetry, allowing the irradiation profile to be measured to a spatial resolution of 10 extgreekmm. The spectral response can be readily adjusted by appropriate choice of particle material. Using dye-doped polystyrene particles, we demonstrate detection of green (532 nm) and ultraviolet (340 nm) light.
EAM Import::2019-03-14

Focusing characteristics of a 4pi parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (arXiv, 2016)

Focusing characteristics of a 4π parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2017)

Focusing light to a tighter spot - Leuchs, Gerd; et al. (Optics Communications, 2000)
The smallest spot sizes are reached by focusing an annular shaped light beam with a high aperture lens. We show theoretically that the focal area is further reduced when using a novel radially polarized instead of a linearly polarized light annulus. In the vicinity of the focus there is a large longitudinally polarized field component which is still narrower and has no pronounced side lobes. A special photosensitive layer prepared to be sensitive only to this longitudinal field component may be used to reach an even smaller focal area, 0.1 λ2, which is determined by the contour of the intensity distribution at half the maximum value. The radially polarized doughnut mode may also be used to build improved near field sensors having a substantially increased brightness.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.focusi

Form assessment of hollow cylindrical specimens - Lindlein, Norbert; et al. (Applied Optics, 2002)
Grazing-incidence interferometry that makes use of diffractive axicons for the measurement of cylindrical mantle surfaces has already been reported. However, measurement of concave rod structures poses a severe problem because these structures are subject to spurious fringes caused by parasitic diffraction orders of the diffractive axicons. By breaking the symmetry of the interferometric setup it is possible to obtain unique interferograms of the inner mantle surfaces of hollow cylinders as cages for roller bearings or other workpieces produced on lathe machines that have a suitable surface finish. Special design issues for the computer-generated holograms and the interferometric setup are discussed, and test examples are given. © 2002 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2002.nat.dphy.optik.1optik.formas

Form birefringent quarter wave plate for polarization conversion - Ghadyani, Zahra; Rothau, Sergej; Russina, Olga; Harder, Irina; Lindlein, Norbert (37th International Conference on Micro and Nano Engineering, 2011)

Fortschritte bei der Automatisierung des Reverse Engineering - Häusler, Gerd; et al. (Optische Formerfassung, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.fortsc

Four-state discrimination scheme beyond the heterodyne limit - Müller, Christian R.; Usuga, Mario A.; Wittmann, Christoffer; Takeoka, Masahiro; Marquardt, Christoph; Andersen, Ulrik L.; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We propose and experimentally demonstrate a hybrid discrimination scheme for the quadrature phase shift keying protocol, which outperforms heterodyne detection for any signal power. The discrimination is composed of a quadrature measurement, feed forward and photon detection. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Fractional Talbot effect for periodic microlens arrays - Lindlein, Norbert; et al. (Optical Engineering, 1997)
It is well known that the foci of a periodic array of microlenses are reproduced and multiplied in the fractional Talbot planes. But the intensity between the multiplied foci varies in general in one period, especially if the light in the spacing between the lenses is not absorbed but transmitted. Additionally, in the case of microlenses with a high numerical aperture the parabolic approximation or Fresnel diffraction, which is normally used to explain the Talbot effect, is no longer valid. A theoretical explanation and numerical simulations are given together with experimental results. © 1997 Society of Photo-Optical Instrumentation Engineers.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.fracti
Keywords: Array illuminator; Fractional Talbot effect; Intensity of foci; Microlens arrays; Propagation of angular spectrum; Self-imaging

Free-space propagation of high-dimensional structured optical fields in an urban environment - Lavery, Martin P. J.; Peuntinger, Christian; Günthner, Kevin; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Science Advances, 2017)
Spatially structured optical fields have been used to enhance the functionality of a wide variety of systems that use light for sensing or information transfer. As higher-dimensional modes become a solution of choice in optical systems, it is important to develop channel models that suitably predict the effect of atmospheric turbulence on these modes. We investigate the propagation of a set of orthogonal spatial modes across a free-space channel between two buildings separated by 1.6 km. Given the circular geometry of a common optical lens, the orthogonal mode set we choose to implement is that described by the Laguerre-Gaussian (LG) field equations. Our study focuses on the preservation of phase purity, which is vital for spatial multiplexing and any system requiring full quantum-state tomography. We present experimental data for the modal degradation in a real urban environment and draw a comparison to recognized theoretical predictions of the link. Our findings indicate that adaptations to channel models are required to simulate the effects of atmospheric turbulence placed on high-dimensional structured modes that propagate over a long distance. Our study indicates that with mitigation of vortex splitting, potentially through precorrection techniques, one could overcome the challenges in a real point-to-point free-space channel in an urban environment.
CRIS-Team Scopus Importer:2022-06-05

Free space quantum communication using continuous polarization variables - Heim, Bettina; Peuntinger, Christian; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
We experimentally investigate atmospheric influences on quantum communication using continuous polarization variables. Signal and local oscillator are combined in one spatial mode, which leads to excellent interference at the homodyne detection. Phase fluctuations are thus auto-compensated. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Full-field mode sorter using two optimized phase transformations for high-dimensional quantum cryptography - Fickler, Robert; Bouchard, Frederic; Giese, Enno; Grillo, Vincenzo; Leuchs, Gerd; Karimi, Ebrahim (Journal of Optics, 2020)
High-dimensional encoding schemes have emerged as a novel way to perform quantum information tasks. For high dimensionality, temporal and transverse spatial modes of photons are the two paradigmatic degrees of freedom commonly used in such experiments. Nevertheless, general devices for multi-outcome measurements are still needed to take full advantage of the high-dimensional nature of encoding schemes. We propose a general full-field mode sorting scheme consisting of only up to two optimized phase elements based on evolutionary algorithms that allows for joint sorting of azimuthal and radial modes. We further study the performance of our scheme through simulations in the context of high-dimensional quantum cryptography, where sorting in different mutually unbiased bases and high-fidelity measurement schemes are crucial.
CRIS-Team WoS Importer:2020-01-31

Functional Plasmonic Nanocircuits with Low Insertion and Propagation Losses - Kriesch, Arian; Burgos, Stanley P.; Ploss, Daniel; Pfeifer, Hannes; Atwater, Harry A.; Peschel, Ulf (Nano Letters, 2013)
We experimentally demonstrate plasmonic nanocircuits operating as subdiffraction directional couplers optically excited with high efficiency from free-space using optical Yagi-Uda style antennas at extgreekl0 = 1550 nm. The optical Yagi-Uda style antennas are designed to feed channel plasmon waveguides with high efficiency (45% in coupling, 60% total emission), narrow angular directivity (<40°), and low insertion loss. SPP channel waveguides exhibit propagation lengths as large as 34 extgreekmm with adiabatically tuned confinement and are integrated with ultracompact (5 × 10 extgreekmm2), highly dispersive directional couplers, which enable 30 dB discrimination over extgreekDl = 200 nm with only 0.3 dB device loss.
EAM Import::2019-03-14

Fusion of computed tomography data and optical 3D images of the dentition for streak artefact correction in the simulation of orthognathic surgery - Nkenke, Emeka; Häusler, Gerd; Lell, Michael; et al. (Dentomaxillofacial Radiology, 2004)
Objective: To determine the limits of accuracy of fusion of optical three-dimensional (3D) imaging and computed tomography (CT) with and without metal artefacts in an experimental setting and to show the application of this hybrid system in 3D orthognathic surgery simulation. Methods: Ten plaster casts of dental arches were subjected to a CT scan and optical 3D surface imaging. Subsequently, the first molars in the plaster casts were supplied with metal restorations, bilaterally, and new CT scans and optical surface images were assessed. The registration of the surface data of the two imaging modalities of the study models without and with metal restorations was carried out. The mean distance between the two data sets was calculated. From a patient a CT scan of the skull as well as optical 3D images of plaster casts of the dental arches were acquired. Again the two imaging modalities were registered and virtual orthognathic surgery simulation was carried out. Results: The mean distance between the corresponding data points of CT and optical 3D surface images was 0.1262 ±0.0301 mm and 0.2671±0.0580 mm, respectively, for the plaster casts without and with metal restorations. The differences between these data were statistically significant (P< 0.0005). For the patient case a mean difference of 0.66±0.49 mm and 0.56±0.48 mm for mandible and maxilla, respectively, was calculated between CT and optical surface data. Conclusion: The accuracy of the fusion of 3D CT surface data and optical 3D imaging is significantly reduced by metal artefacts. However, it seems appropriate for virtual orthognathic surgery simulation, as post-operative orthodontics are performed frequently. © 2004 The British Institute of Radiology.
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.optik.1optik.fusion
Keywords: Computed tomography; Image fusion; Metal artefacts; Optical 3D imaging; Phase measuring triangulation

Gaussian beam output from a large-mode-area higher-order-mode fiber - Lindlein, Norbert; et al. (2007 European Conference on Lasers and Electro-Optics and the International Quantum Electronics Conference, CLEO, 2007)

GAWBS noise reduction in microstructured fibers - Elser, Dominique Alexander; Korn, Alexander; Lorenz, Stefan; Glöckl, Oliver; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (2005 European Quantum Electronics Conference, EQEC '05, 2005)
Guided Acoustic Wave Brillouin Scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. We experimentally demonstrate the reduction of GAWBS noise in microstructured fibers in comparison with standard fibers. © 2005 IEEE.
Created from Fastlane, Scopus look-up

Generalized Brillouin diagrams for evanescent waves in metamaterials with interelement coupling - Tatartschuk, Eugen; Radkovskaya, A.; Shamonina, E.; Solymar, L. (Physical Review B, 2010)
A graphical representation for two-dimensional periodic structures is introduced that provides the full information contained in the dispersion equation: not only for the pass band but for the neighboring stop bands as well. It is a seamless natural extension of Brillouin diagrams obtained by adding eight new zones which incorporate the properties of evanescent waves. The accuracy of the infinite lattice approximation is tested both by simulations and experiments using magnetoinductive waves. For waves propagating in one direction and evanescent in the other direction, the results of the three different methods are shown to be in good agreement. The versatility of the new representation and its applicability to the design of near-field manipulating metamaterials is discussed.
EAM Import::2019-03-13

Generalized theory of optical resonator and waveguide modes and their linear and Kerr nonlinear coupling - Silver, Jonathan M.; Del'Haye, Pascal (Physical Review A, 2022)
We derive a general theory of linear coupling and Kerr nonlinear coupling between modes of dielectric optical resonators from first principles. The treatment is not specific to a particular geometry or choice of mode basis, and can therefore be used as a foundation for describing any phenomenon resulting from any combination of linear coupling, scattering, and Kerr nonlinearity, such as bending and surface roughness losses, geometric backscattering, self- and cross-phase modulation, four-wave mixing, third-harmonic generation, and Kerr frequency comb generation. The theory is then applied to a translationally symmetric waveguide in order to calculate the evanescent coupling strength to the modes of a microresonator placed nearby, as well as the Kerr self- and cross-phase modulation terms between the modes of the resonator. This is then used to derive a dimensionless equation describing the symmetry-breaking dynamics of two counterpropagating modes of a loop resonator and prove that cross-phase modulation is exactly twice as strong as self-phase modulation only in the case that the two counterpropagating modes are otherwise identical.
CRIS-Team Scopus Importer:2022-03-18

Generation and applications of quantum engineered optical soliton pulses - Leuchs, Gerd; Andersen, Ulrik Lund; Glöckl, Oliver; Marquardt, Christoph; Heersink, Joel; Lorenz, Stefan (2005 European Quantum Electronics Conference, EQEC '05, 2005)
We describe various quantum protocols, all of which can be described by Bogoliubov transformations. Furthermore, a scheme by which correlated sidebands of a single spatial mode can be separated into two spatial modes is outlined. © 2005 IEEE.
Created from Fastlane, Scopus look-up

Generation and Direct Detection of Broadband Mesoscopic Polarization-Squeezed Vacuum - Leuchs, Gerd; et al. (Physical Review Letters, 2009)
Using a traveling-wave optical parametric amplifier with two orthogonally oriented type-I BBO crystals pumped by picosecond pulses, we generate vertically and horizontally polarized squeezed vacuum states within a broad frequency-angular range. Depending on the phase between these states, fluctuations in one or another Stokes parameter are suppressed below the shot-noise limit. Because of the large number of photon pairs produced, no local oscillator is required, and 3 dB squeezing is observed by means of direct detection. © 2009 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.genera

Generation and Reconstruction of Two Mode Squeezed States in the Microwave Domain - Eichler, Christopher; et al. (APS March Meeting, 2011)
Keywords: wwwqudev

Generation and subwavelength focusing of longitudinal magnetic fields in a metallized fiber tip - Ploss, Daniel; Kriesch, Arian; Pfeifer, Hannes; Banzer, Peter; Peschel, Ulf (Optics Express, 2014)
We demonstrate experimentally and numerically that in fiber tips as they are used in NSOMs azimuthally polarized electrical fields (|Eazi|2 / |Etot|2 ≈55% ± 5% for extgreekl0= 1550 nm), respectively subwavelength confined (FWHM ≈450 nm ≈ extgreekl0/3.5) magnetic fields, are generated for a certain tip aperture diameter (d = 1.4 extgreekmm). We attribute the generation of this field distribution in metal-coated fiber tips to symmetry breaking in the bend and subsequent plasmonic mode filtering in the truncated conical taper.
EAM Import::2019-03-13

Generation of a radially polarized beam of high quality - Quabis, Susanne; Dorn, Ralf; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.genera

Generation of a wave packet tailored to efficient free space excitation of a single atom - Golla, Andrea; Chalopin, Benoit; Bader, Marianne; Harder, Irina; Mantel, Klaus; Maiwald, Robert; Lindlein, Norbert; Sondermann, Markus; Leuchs, Gerd (European Physical Journal D, 2012)
We demonstrate the generation of an optical dipole wave suitable for the process of efficiently coupling single quanta of light and matter in free space. We employ a parabolic mirror for the conversion of a transverse beam mode to a focused dipole wave and show the required spatial and temporal shaping of the mode incident onto the mirror. The results include a proof of principle correction of the parabolic mirror's aberrations. For the application of exciting an atom with a single photon pulse, we demonstrate the creation of a suitable temporal pulse envelope. We infer coupling strengths of 89% and success probabilities of up to 87% for the application of exciting a single atom for the current experimental parameters. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2012.

Generation of continuous variable Einstein-Podolsky-Rosen entanglement via the Kerr nonlinearity in an optical fibre - Leuchs, Gerd; et al. (Physical Review Letters, 2001)
A report on generation of a continuous variable Einstein-Podolsky-Rosen (EPR) entanglement was presented using an optical fiber interferometer. Two independent squeezed beams were generated using Kerr nonlinearity. ERP entanglement was obtained between the output beams. Correlation of amplitude quadratures was measured below the quantum noise limit.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.genera

Generation of entangled matter qubits in two opposing parabolic mirrors - Trautmann, Nils; Bernad, Jozsef Zsolt; Sondermann, Markus; Alber, Gernot; Sanchez-Soto, Luis; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2014)
We propose a scheme for the remote preparation of entangled matter qubits in free space. For this purpose, a setup of two opposing parabolic mirrors is considered, each one with a single ion trapped at its focus. To get the required entanglement in this extreme multimode scenario, we take advantage of the spontaneous decay, which is usually considered as an apparent nuisance. Using semiclassical methods, we derive an efficient photon-path representation to deal with this problem. We also present a thorough examination of the experimental feasibility of the scheme. The vulnerabilities arising in realistic implementations reduce the success probability, but leave the fidelity of the generated state unaltered. Our proposal thus allows for the generation of high-fidelity entangled matter qubits with high rate.

Geometrical Optics - Lindlein, Norbert; Leuchs, Gerd (Handbook of Lasers and Optics, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dphy.optik.1optik.geomet

Geometric Spin Hall Effect of Light at polarizing interfaces - Korger, J.; Aiello, Andrea; Gabriel, C.; Banzer, Peter; Kolb, T.; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2011)
The geometric Spin Hall Effect of Light (geometric SHEL) amounts to a polarization-dependent positional shift when a light beam is observed from a reference frame tilted with respect to its direction of propagation. Motivated by this intriguing phenomenon, the energy density of the light beam is decomposed into its Cartesian components in the tilted reference frame. This illustrates the occurrence of the characteristic shift and the significance of the effective response function of the detector. We introduce the concept of a tilted polarizing interface and provide a scheme for its experimental implementation. A light beam passing through such an interface undergoes a shift resembling the original geometric SHEL in a tilted reference frame. This displacement is generated at the polarizer and its occurrence does not depend on the properties of the detection system.We give explicit results for this novel type of geometric SHEL and show that at grazing incidence this effect amounts to a displacement of multiple wavelengths, a shift larger than the one introduced by Goos-Hänchen and Imbert-Fedorov effects. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-05

Geometric spin Hall effect of light in tightly focused polarization-tailored light beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Orlovas, Sergejus; Lindlein, Norbert; Aiello, Andrea; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2014)

GHz kinematic sensing with classically entangled beams of light - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, M.; Giacobino, E.; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2021-06-29

Gold film-terminated 3-dimensional photonic crystals - Ding, B.; Pemble, M. E.; Korovin, A. V.; Peschel, Ulf; Romanov, Sergey (Applied Physics A-Materials Science & Processing, 2011)
Hybrid metal-dielectric photonic crystals assembled from an opal film coated by a gold film are designed in order to realize optical spectra that emanate from mixing Bloch modes in the opal and surface plasmon polaritons in corrugated gold films. The photonic crystal provides a spatial template for the gold film profile and modifies the electromagnetic vacuum in the vicinity to the gold layer. Reflectance spectroscopy was applied to deconvolute the plasmonic and photonic bandgap components in the optical response of hybrid crystals as opposite to their mixed appearance in the transmission spectra.
EAM Import::2019-03-13

Graph Neural Networks for low-energy event classification & reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves Jr, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Journal of Instrumentation, 2022)
IceCube, a cubic-kilometer array of optical sensors built to detect atmospheric and astrophysical neutrinos between 1 GeV and 1 PeV, is deployed 1.45 km to 2.45 km below the surface of the ice sheet at the South Pole. The classification and reconstruction of events from the in-ice detectors play a central role in the analysis of data from IceCube. Reconstructing and classifying events is a challenge due to the irregular detector geometry, inhomogeneous scattering and absorption of light in the ice and, below 100 GeV, the relatively low number of signal photons produced per event. To address this challenge, it is possible to represent IceCube events as point cloud graphs and use a Graph Neural Network (GNN) as the classification and reconstruction method. The GNN is capable of distinguishing neutrino events from cosmic-ray backgrounds, classifying different neutrino event types, and reconstructing the deposited energy, direction and interaction vertex. Based on simulation, we provide a comparison in the 1 GeV-100 GeV energy range to the current state-of-the-art maximum likelihood techniques used in current IceCube analyses, including the effects of known systematic uncertainties. For neutrino event classification, the GNN increases the signal efficiency by 18% at a fixed background rate, compared to current IceCube methods. Alternatively, the GNN offers a reduction of the background (i.e. false positive) rate by over a factor 8 (to below half a percent) at a fixed signal efficiency. For the reconstruction of energy, direction, and interaction vertex, the resolution improves by an average of 13%-20% compared to current maximum likelihood techniques in the energy range of 1 GeV-30 GeV. The GNN, when run on a GPU, is capable of processing IceCube events at a rate nearly double of the median IceCube trigger rate of 2.7 kHz, which opens the possibility of using low energy neutrinos in online searches for transient events.
CRIS-Team WoS Importer:2023-02-17

Gravitational radiation from birefringent matter dynamics - Alex, Nils (Physical Review D, 2020)
We present the second-order gravitational dynamics for a spacetime inhabited by matter fields which feature vacuum birefringence. The derivation follows a perturbative variant of the covariant constructive gravity program, ensuring diffeomorphism invariance of gravity and causal compatibility of matter theory and gravity. A subsequent spatiotemporal split of this theory reveals the presence of unphysical artifacts, which are cured by imposing constraints on the gravitational constants, reducing their number from ten to seven. Within this sector, we derive the gravitational radiation emitted by a binary system in circular motion. The system emits massless waves, which correspond to the radiation predicted by Einstein gravity, but also massive waves, which are generated only above a certain angular frequency threshold and are unknown to Einstein gravity. A gravitational-wave detector modeled as a sphere of freely falling test masses shows quantitatively and qualitatively new behavior under the influence of this radiation. The result is a prediction of gravitational self-coupling from first principles, demonstrating the predictive power of covariant constructive gravity for modified gravity research, especially in the era of gravitational-wave astronomy.
CRIS-Team WoS Importer:2020-11-27

Grazing incidence interferometry for rough convex aspherics - Schwider, Johannes; Kellermann, Christine; Lindlein, Norbert; Rothau, Sergej; Mantel, Klaus (arXiv, 2016)

Grazing incidence interferometry for testing rough aspherics: experimental results and data analysis - Rothau, Sergey; Mantel, K.; Lindlein, Norbert (OPTICS AND PHOTONICS FOR ADVANCED DIMENSIONAL METROLOGY, 2021)
CRIS-Team WoS Importer:2021-07-30

Grazing incidence test for cylindrical microlenses with high numerical aperture - Lindlein, Norbert; et al. (Journal of Optics A-Pure and Applied Optics, 2002)
Cylinder symmetry of test objects allows grazing incidence tests. Here we propose the use of two diffractive optical elements (DOEs) instead of a single DOE in perpendicular incidence. The splitting of the optical function of the DOEs allows low spatial frequencies in the diffractive elements. In fact, the diffractive structures are curves parallel to the meridian of the cylinder lens. Here an interferometric test is described where identical DOEs serve as beamsplitter and combiner. The undiffracted wavefront serves as reference. Phase shifting evaluations are possible by axial translations of one of the DOEs. The effective wavelength can be chosen within wide limits. Actually, we used a pitch of 5 μm, which is identical to the effective wavelength of the test. A surface deviation of 2.5 μm corresponds to a fringe distance. The interferometric test enables rms values of better than 20 nm for any aspheric geometry of the meridian curve, even with lenses having numerical apertures up to 0.9.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.grazin
Keywords: Computer-generated holograms; Interferometers; Phase shifting interferometry

Growth of GaN micro- and nanorods on graphene-covered sapphire: Enabling conductivity to semiconductor nanostructures on insulating substrates - Heilmann, Martin; Sarau, George; Göbelt, Manuela; Latzel, Michael; Sadhujan, Sumesh; Tessarek, Christian; Christiansen, Silke (Crystal Growth and Design, 2015)
The self-catalyzed growth of vertically aligned and hexagonally shaped GaN micro- and nanorods on graphene transferred onto sapphire is achieved through metal-organic vapor phase epitaxy. However, a great influence of the underlying substrate is evident, since vertically aligned structures with a regular shape could not be grown on graphene transferred to SiO2. The optical properties of the regular GaN nanorods were investigated by spatially and spectrally resolved cathodoluminescence showing defect related emission only near the interface between the sapphire substrate and nanorods but not from their upper part. Micro-raman spectroscopy confirms that the single-layer graphene remains virtually unchanged in terms of the Raman signal, even after undergoing high temperatures (∼1200 °C) during nanorod growth. Furthermore, Raman mapping demonstrates that GaN structures predominantly grow on defective parts of graphene, giving new insight into the nucleation and growth mechanism of semiconductors on graphene. To validate the conductivity of graphene, when being attached to the sapphire substrate and after the nanorod growth, current-voltage investigations were carried out on single, as-grown, GaN nanorods with a nanoprober in a scanning electron microscope. These measurements demonstrate the viability of graphene as a conductive electrode, for example, as a back contact for GaN nanorods grown on insulating sapphire.

Guided acoustic wave Brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Wittmann, Christoffer; Andersen, Ulrik Lund; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Journal of Physics: Conference Series, 2007)
In silica glass fibers, thermally excited acoustic phonons scatter light into the beam propagating in the forward direction. At acoustic frequencies up to several hundreds of megahertz, the wave vectors of the phonons interacting with the light propagate essentially transversally to the fiber axis. This effect is known as Guided Acoustic Wave Brillouin Scattering (GAWBS) and leads to phase and polarization noise in the guided light. For fiber-based quantum optics experiments, this excess noise is a major limitation. In Photonic Crystal Fibers (PCFs), light is guided by a microstructure simultaneously acting as a 2D transversal phononic crystal which modifies the acoustic noise spectrum. We demonstrate a GAWBS-noise reduction in commercially available PCFs. This gives rise to the prospect of fiber-based quantum optic devices exhibiting less excess noise, thus resulting in higher quantum state purity. Further improvement can be achieved by tailoring the photonic microstructure such that a reduction of phonon noise by design is achieved. © 2007 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up

Helstrom measurement: A nondestructive implementation - Han, Rui; Leuchs, Gerd; Bergou, Janos A. (Physical Review A, 2020)
We discuss an implementation of the minimum error state discrimination measurement, originally introduced by Helstrom [Quantum Detection and Estimation Theory (Academic Press, New York, 1976)]. In this implementation, instead of performing the optimal projective measurement directly on the system, it is first entangled to an ancillary system and the measurement is performed on the ancilla. We show that, by an appropriate choice of the entanglement transformation, the Helstrom bound can be attained. The advantage of this approach is twofold. First, it provides an implementation when the optimal projective measurement cannot be directly performed. For example, in the case of continuous variable states (binary and N phase-shifted coherent signals), the available detection methods, photon counting and homodyning, are insufficient to perform the required cat-state projection. In the case of symmetric states, the square-root measurement is optimal, but it is not easy to perform directly for more than two states. Our approach provides a feasible alternative in both cases. Second, the measurement is nondestructive from the point of view of the original system and one has a certain amount of freedom in designing the post-measurement state, which can then be processed further.
CRIS-Team WoS Importer:2020-03-24

Hertel exophtalmometry versus computed tomography and optical 3D imaging for the determination of the globe position in zygomatic fractures - Häusler, Gerd; Nkenke, Emeka; Neukam, Friedrich Wilhelm; et al. (International Journal of Oral and Maxillofacial Surgery, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.hertel

Hierarchical quantum master equation approach to charge transport in molecular junctions with time-dependent molecule-lead coupling strengths - Erpenbeck, André; Götzendörfer, Lukas; Schinabeck, Christian; Thoss, Michael (European Physical Journal - Special Topics, 2019)
Time-dependent currents in molecular junctions can be caused by structural fluctuations or interaction with external fields. In this paper, we demonstrate how the hierarchical quantum master equation approach can be used to study time-dependent transport in a molecular junction. This reduced density matrix methodology provides a numerically exact solution to the transport problem including time-dependent energy levels, molecule-lead coupling strengths and transitions between electronic states of the molecular bridge. Based on a representative model, the influence of a time-dependent molecule-lead coupling on the electronic current is analyzed in some detail.
CRIS-Team WoS Importer:2019-04-12

High-dimensional intracity quantum cryptography with structured photons - Sit, Alicia; Bouchard, Frederic; Fickler, Robert; Gagnon-Bischoff, Jeremie; Larocque, Hugo; Heshami, Khabat; Elser, Dominique; Peuntinger, Christian; Günthner, Kevin; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd; et al. (Optica, 2017)
Quantum key distribution (QKD) promises information-theoretically secure communication and is already on the verge of commercialization. The next step will be to implement high-dimensional protocols in order to improve noise resistance and increase the data rate. Hitherto, no experimental verification of high-dimensional QKD in the single-photon regime has been conducted outside of the laboratory. Here, we report the realization of such a single-photon QKD system in a turbulent free-space link of 0.3 km over the city of Ottawa, taking advantage of both the spin and orbital angular momentum photonic degrees of freedom. This combination of optical angular momenta allows us to create a 4-dimensional quantum state; wherein, using a high-dimensional BB84 protocol, a quantum bit error rate of 11% was attained with a corresponding secret key rate of 0.65 bits per sifted photon. In comparison, an error rate of 5% with a secret key rate of 0.43 bits per sifted photon is achieved for the case of 2-dimensional structured photons. We thus demonstrate that, even through moderate turbulence without active wavefront correction, high-dimensional photon states are advantageous for securely transmitting more information. This opens the way for intracity high-dimensional quantum communications under realistic conditions.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Free-space optical communication; Optical vortices; Quantum cryptography

Highly improved range sensing - by reduction of spatial coherence - Häusler, Gerd; et al. (Optik, 2001)
Optical range sensors based on triangulation are widely used for the shape measurement of optically rough objects. The origin of the achievable measuring uncertainty of the distance is speckle noise. Speckle noise is unavoidable in spatially coherent systems. We demonstrate two experiments which prove that without spatial coherence, the measuring uncertainty can be dramatically reduced, and we present an on-line 3D-sensor for laser-material processing, exploiting this knowledge.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.highly
Keywords: Coherent noise; Distance measurement; Laser material processing; Optical metrology; Triangulation

High numerical aperture imaging with different polarization patterns - Lindlein, Norbert; Quabis, Susanne; Peschel, Ulf; Leuchs, Gerd (Optics Express, 2007)
The modulation transfer function (MTF) is calculated for imaging with linearly, circularly and radially polarized light as well as for different numerical apertures and aperture shapes. Special detectors are only sensitive to one component of the electric energy density, e.g. the longitudinal component. For certain parameters this has advantages concerning the resolution when comparing to polarization insensitive detectors. It is also shown that in the latter case zeros of the MTF may appear which are purely due to polarization effects and which depend on the aperture angle. Finally some ideas are presented how to use these results for improving the resolution in lithography. © 2007 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.highnu

Holographic Measurement of Surface Topography - Limits and New Options - Häusler, Gerd; Willomitzer, Florian (DGsO-Proceedings 2023, 2023)
There is a plethora of options for optical 3D-metrology. Inspired by the progress of digital holography, we discuss two questions: Can we implement all classical (non-holographic) sensors via digital holography? And even more interesting: Can digital holography enable options beyond classical sensors?
Keywords: holography; metrology; topography; 3-D

Holographic microlens arrays - Lindlein, Norbert; et al. (EOS Topical Meetings Digest Series, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.optik.1optik.hologr

Homogenization and beam shaping with micro lens arrays - Harder, Irina; Lano, Maik; Lindlein, Norbert; Schwider, Johannes (Proceedings of SPIE, 2004)
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.optik.1optik.homoge

Homogenization and beam shaping with microlens arrays - Lindlein, Norbert; et al. (Photon Management, 2004)
Mostly, the typical light distribution of a light source, as a LED or an excimer laser, is not suitable for the application. The excimer laser beam for example shows a distinct elliptical Gaussian profile. As another example the layout of the light emitting chip and the reflector of a LED form an extremely inhomogeneous luminescent area. To achieve a better adapted beam profile a homogenizing setup with beam shaping qualities can be used. In this talk two setups for homogenization with the help of refractive micro lens arrays are shown and compared. The main attention is turned on the influence of the numerical aperture of the micro lenses, the limitations due to the spatial coherence degree and the difficulties of the alignment of the systems. In addition, a diffractive solution of homogenization for spatial partially coherence is presented.
Keywords: Beam shaping; Excimer; Homogenization; LED; Microlens array; Spatial coherence

How much 3D-Information can weacquire? Optical Range Sensors at the Physical Limit, and where to apply them - Häusler, Gerd (Proceedings of Third International Conference on 3-DDigital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.howmuc

How much should we pay for optical 3d-sensors? - a respectable scientific question - Häusler, Gerd (Proceedings of ICO 04, Tokyo, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.howmuc

Huygens' dipole for polarization-controlled nanoscale light routing - Nechayev, Sergey; Eismann, Jörg; Neugebauer, Martin; Wozniak, Pawel; Bag, Ankan; Leuchs, Gerd; Banzer, Peter (Physical Review A, 2019)
Structured illumination allows for satisfying the first Kerker condition of in-phase perpendicular electric and magnetic dipole moments in any isotropic scatterer that supports electric and magnetic dipole resonances. The induced Huygens' dipole may be utilized for unidirectional coupling to waveguide modes that propagate transverse to the excitation beam. We study two configurations of a Huygens' dipole, longitudinal electric and transverse magnetic dipole moments or vice versa. We experimentally show that only the radially polarized emission of the first and azimuthally polarized emission of the second configuration are directional in the far field. This polarization selectivity implies that directional excitation of either transverse magnetic (TM) or transverse electric (TE) waveguide modes is possible. Applying this concept to a single dielectric nanoantenna excited with structured light, we are able to experimentally achieve scattering directivities of around 23 and 18 dB in TM and TE modes, respectively. This strong directivity paves the way for tunable polarization-controlled nanoscale light routing and applications in optical metrology, localization microscopy, and on-chip optical devices.
CRIS-Team WoS Importer:2019-04-30

Hybrid Colloidal Plasmonic-Photonic Crystals - Romanov, Sergei G.; Korovin, Alexander V.; Regensburger, Alois; Peschel, Ulf (Advanced Materials, 2011)
We review the recently emerged class of hybrid metal-dielectric colloidal photonic crystals. The hybrid approach is understood as the combination of a dielectric photonic crystal with a continuous metal film. It allows to achieve a strong modification of the optical properties of photonic crystals by involving the light scattering at electronic excitations in the metal component into moulding of the light flow in series to the diffraction resonances occurring in the body of the photonic crystal. We consider different realizations of hybrid plasmonic-photonic crystals based on two- and three-dimensional colloidal photonic crystals in association with flat and corrugated metal films. In agreement with model calculations, different resonance phenomena determine the optical response of hybrid crystals leading to a broadly tuneable functionality of these crystals.
EAM Import::2019-03-13

Hybrid Orthorhombic Carbon Flakes Intercalated with Bimetallic Au-Ag Nanoclusters: Influence of Synthesis Parameters on Optical Properties - Butt, Muhammad Abdullah; Mamonova, Daria; Petrov, Yuri; Proklova, Alexandra; Kritchenkov, Ilya; Manshina, Alina; Banzer, Peter; Leuchs, Gerd (Nanomaterials, 2020)
Until recently, planar carbonaceous structures such as graphene did not show any birefringence under normal incidence. In contrast, a recently reported novel orthorhombic carbonaceous structure with metal nanoparticle inclusions does show intrinsic birefringence, outperforming other natural orthorhombic crystalline materials. These flake-like structures self-assemble during a laser-induced growth process. In this article, we explore the potential of this novel material and the design freedom during production. We study in particular the dependence of the optical and geometrical properties of these hybrid carbon-metal flakes on the fabrication parameters. The influence of the laser irradiation time, concentration of the supramolecular complex in the solution, and an external electric field applied during the growth process are investigated. In all cases, the self-assembled metamaterial exhibits a strong linear birefringence in the visible spectral range, while the wavelength-dependent attenuation was found to hinge on the concentration of the supramolecular complex in the solution. By varying the fabrication parameters one can steer the shape and size of the flakes. This study provides a route towards fabrication of novel hybrid carbon-metal flakes with tailored optical and geometrical properties.
CRIS-Team WoS Importer:2020-08-14

Idealized Einstein-Podolsky-Rosen states from non-phase-matched parametric down-conversion - Okoth, Cameron; Kovlakov, E.; Boensel, F.; Cavanna, A.; Straupe, S.; Kulik, S. P.; Chekhova, Maria (Physical Review A, 2020)
The most common source of entangled photons is spontaneous parametric down-conversion (SPDC). The degree of energy and momentum entanglement in SPDC is determined by the nonlinear interaction volume. By reducing the length of a highly nonlinear material, we relax the longitudinal phase-matching condition and reach record levels of transverse momentum entanglement. The degree of entanglement is estimated using both correlation measurements and stimulated emission tomography in wave-vector space. The high entanglement of the state in wave-vector space can be used to massively increase the quantum information capacity of photons, but more interestingly the equivalent state measured in position space is correlated over distances far less than the photon wavelength. This property promises to improve the resolution of many quantum imaging techniques beyond the current state of the art.
CRIS-Team WoS Importer:2020-02-04

Identifying modes of large whispering-gallery mode resonators from the spectrum and emission pattern - Schunk, Gerhard; Fuerst, Josef U.; Foertsch, Michael; Strekalov, Dmitry V.; Vogl, Ulrich; Sedlmeir, Florian; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (Optics Express, 2014)
Identifying the mode numbers in whispering-gallery mode resonators (WGMRs) is important for tailoring them to experimental needs. Here we report on a novel experimental mode analysis technique based on the combination of frequency analysis and far-field imaging for high mode numbers of large WGMRs. The radial mode numbers q and the angular mode numbers p = l-m are identified and labeled via far-field imaging. The polar mode numbers l are determined unambiguously by fitting the frequency differences between individual whispering gallery modes (WGMs). This allows for the accurate determination of the geometry and the refractive index at different temperatures of the WGMR. For future applications in classical and quantum optics, this mode analysis enables one to control the narrow-band phase-matching conditions in nonlinear processes such as second-harmonic generation or parametric down-conversion.
CRIS-Team Scopus Importer:2022-06-05

Imaging individual barium atoms in solid xenon for barium tagging in nEXO - Chambers, C.; Walton, T.; Fairbank, D.; Craycraft, A.; Yahne, D. R.; Todd, J.; Iverson, A.; Fairbank, W.; Alamre, A.; Albert, J. B.; Anton, Gisela; Arnquist, I. J.; et al. (Nature, 2019)
Double-β-decay involves the simultaneous conversion of two neutrons into two protons, and the emission of two electrons and two neutrinos; the neutrinoless process, although not yet observed, is thought to involve the emission of the two electrons but no neutrinos. The search for neutrinoless-double-β-decay probes fundamental properties of neutrinos, including whether or not the neutrino and antineutrino are distinct particles. Double-β-decay detectors are large and expensive, so it is essential to achieve the highest possible sensitivity with each study, and removing spurious contributions (‘background’) from detected signals is crucial. In the nEXO neutrinoless-double-β-decay experiment, the identification, or ‘tagging’, of the 136 Ba daughter atom resulting from the double-β decay of 136 Xe provides a technique for discriminating background. The tagging scheme studied here uses a cryogenic probe to trap the barium atom in a solid xenon matrix, where the barium atom is tagged through fluorescence imaging. Here we demonstrate the imaging and counting of individual barium atoms in solid xenon by scanning a focused laser across a solid xenon matrix deposited on a sapphire window. When the laser irradiates an individual atom, the fluorescence persists for about 30 seconds before dropping abruptly to the background level—a clear confirmation of one-atom imaging. Following evaporation of a barium deposit, the residual barium fluorescence is 0.16 per cent or less. Our technique achieves the imaging of single atoms in a solid noble element, establishing the basic principle of barium tagging for nEXO.
CRIS-Team Scopus Importer:2019-05-17

Imaging Quality Improvement by a Diffusively Scattering Screen - Leuchs, Gerd (Optik, 1996)
The quality of an image can be enhanced by using a stationary diffusively scattering screen placed in an intermediate image plane. Image impairment caused by small optical materials defects or dust particles is reduced. The effect is demonstrated using a microfilm reader.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.imagin

Imaging: Speckle and Coherence - Häusler, Gerd (Encyclopedia of Modern Optics, 2004)
UnivIS-Import:2015-04-20:Pub.2004.nat.dphy.optik.1optik.imagin

Implementation of a Scattering Method for Rough Surfaces in a Raytracing Software linked with a CAD (Computer-Aided Design) Toolbox - Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (Frontiers in Optics 2016, OSA Technical Digest (online) (Optical Society of America, 2016), paper FW3H.2, 2016)
The design and simulation of printed polymer optical waveguides is a new approach in the field of raytracing techniques, to link the CAD routines with the simulation process of the waveguides via raytracing methods.
Keywords: Polymer waveguides (130.5460); Propagating methods (220.2560); Scattering; rough surfaces (290.5880)

Important Parameters of Printed Polymer Optical Waveguides (POWs) in Simulation and Fabrication - Reitberger, Thomas; Franke, Jörg; Loosen, Florian; Lindlein, Norbert (Proc. SPIE 10098, Physics and Simulation of Optoelectronic Devices XXV, 100981B (February 22, 2017), 2017)
In this paper, polymer optical waveguides (POWs), fabricated by using flexographic printing for printing conditioning lines onto polymethylmethacrylate (PMMA) foil substrate material and Aerosol Jet Printing for producing the core and cladding of the waveguide, are characterized by using Monte Carlo raytracing for the scattering process. This method offers the opportunity to simulate the propagation of light, which are traced through the produced POWs. In the first step, the surface roughness of all optical materials, which are involved in the fabrication process of the POWs, are measured. The roughness measurement of substrate, core and cladding material is necessary to interlink the surface roughness (Monte Carlo scattering model) with a non-sequential raytracing method. Not only the surface of each material is investigated, but also the roughness measurement of the interlayer between the printed core and cladding material is examined. To build up the complete manufacturing technology virtually, also the process parameters of the printing need to be investigated. The results of the tracing must be a value of the attenuation of a simulated printed POW to give the designer a feedback about the optical quality of the waveguide before the printing process. This project is part of the DFG (the German Research Foundation) founded research group OPTAVER where the goal is to build up the whole manufacturing process, from the CAD, over the simulation, to the fabrication process and coupling of such printed POWs. © (2017) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
Keywords: Fabrication; Polymers; Simulations; Waveguides; Printing; Cladding; Scattering; Surface roughness; Manufacturing; Optical materials

Improved modeling of in-ice particle showers for IceCube event reconstruction - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
The IceCube Neutrino Observatory relies on an array of photomultiplier tubes to detect Cherenkov light produced by charged particles in the South Pole ice. IceCube data analyses depend on an in-depth characterization of the glacial ice, and on novel approaches in event reconstruction that utilize fast approximations of photoelectron yields. Here, a more accurate model is derived for event reconstruction that better captures our current knowledge of ice optical properties. When evaluated on a Monte Carlo simulation set, the median angular resolution for in-ice particle showers improves by over a factor of three compared to a reconstruction based on a simplified model of the ice. The most substantial improvement is obtained when including effects of birefringence due to the polycrystalline structure of the ice. When evaluated on data classified as particle showers in the high-energy starting events sample, a significantly improved description of the events is observed.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Cherenkov detectors; Neutrino detectors; programs; Simulation methods

Improved white-light interferometry on rough surfaces by statistically independent speckle patterns - Häusler, Gerd; Hybl, Ondrej; Wiesner, Bernhard (Applied Optics, 2012)
White-light interferometry (WLI) on rough surfaces is based on interference from individual speckles. The measurement uncertainty of WLI is limited by a random shift of these individual interference patterns. The statistical error in each measurement point depends on the brightness of the corresponding speckle: a dark speckle yields a larger error than a bright speckle. In this paper, a novel method is presented to reduce the measurement uncertainty significantly: by sequentially switching the direction of the illumination, the camera sees several independent speckle patterns in sequence. From each pattern, the brightest speckles are selected to eventually calculate an accurate height map. This height map displays no outliers, and the measured surface roughness is close to the stylus measurements.

Improvement of NOLM-based phase-preserving amplitude limiters by fiber optimizations - Stephan, C.; Sponsel, K.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (Lasers and Electro-Optics (CLEO) and Quantum Electronics and Laser Science Conference (Qels), May, 2010)
lhft_intern.bib::Stephan10a

Incoherent averaging of phase singularities in speckle-shearing interferometry - Mantel, Klaus Peter; Nercissian, Vanusch; Lindlein, Norbert (Optics Letters, 2014)

Indefinite-Mean Pareto Photon Distribution from Amplified Quantum Noise - Manceau, Mathieu; Spasibko, Kirill Yu; Leuchs, Gerd; Filip, Radim; Chekhova, Maria (Physical Review Letters, 2019)
Extreme events appear in many physics phenomena, whenever the probability distribution has a "heavy tail" differing very much from the equilibrium one. Most unusual are the cases of power-law (Pareto) probability distributions. Among their many manifestations in physics, from "rogue waves" in the ocean to Lévy flights in random walks, Pareto dependences can follow very different power laws. For some outstanding cases, the power exponents are less than 2, leading to indefinite values not only for higher moments but also for the mean. Here we present the first evidence of indefinite-mean Pareto distribution of photon numbers at the output of nonlinear effects pumped by parametrically amplified vacuum noise, known as bright squeezed vacuum (BSV). We observe a Pareto distribution with power exponent 1.31 when BSV is used as a pump for supercontinuum generation, and other heavy-tailed distributions (however, with definite moments) when it pumps optical harmonics generation. Unlike in other fields, we can flexibly control the Pareto exponent by changing the experimental parameters. This extremely fluctuating light is interesting for ghost imaging and for quantum thermodynamics as a resource to produce more efficiently nonequilibrium states by single-photon subtraction, the latter of which we demonstrate experimentally.
CRIS-Team Scopus Importer:2019-10-08

Indistinguishable MHz-narrow heralded photon pairs from a whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph (APL Photonics, 2025)
The Hong-Ou-Mandel interference plays a vital role in many quantum optical applications where indistinguishability of two photons is important. Such photon pairs are commonly generated as the signal and idler in the polarization-degenerate spontaneous parametric downconversion (SPDC). To scale this approach to a larger number of photons, we demonstrate how two independent signal photons radiated into different spatial modes can be rendered conditionally indistinguishable by a heralding measurement performed on their respective idlers. We use the SPDC in a whispering gallery resonator, which is already proven to be versatile sources of quantum states. Its extreme conversion efficiency allowed us to perform our measurements with only 50 nW of in-coupled pump power in each propagation direction. The Hong-Ou-Mandel interference of two counterpropagating signal photons manifested itself in the fourfold coincidence rate, where the detection of two idler photons heralds a pair of signal photons with a desired temporal overlap. We achieved the Hong-Ou-Mandel dip contrast of 74% ± 5%. Importantly, the optical bandwidth of all involved photons is of the order of a MHz and is continuously tunable. This, on the one hand, makes it possible to achieve the necessary temporal measurement resolution with standard electronics and, on the other hand, creates a quantum state source compatible with other candidates for qubit implementation, such as optical transitions in solid-state or vaporous systems. We also discuss the possibility of generating photon pairs with similar temporal modes from two different whispering gallery resonators.
CRIS-Team Scopus Importer:2025-05-30

Inducing a detector efficiency mismatch to hack a commercial quantum key distribution system - Jain, N.; Lydersen, L.; Wittmann, C.; Wiechers, C.; Elser, D.; Marquardt, Christoph; Makarov, V.; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Quantum key distribution (QKD) is poised to be the first widespread implementation of quantum communication. In principle, it offers unconditional security: an eavesdropper introduces errors and thus cannot remain concealed from the legitimate parties. However, in practical implementations the actual security depends on a host of technological and protocol-operational components. Eve could exploit imperfections in Alice's or Bob's equipment (such as source or detectors) remotely, or vulnerabilities in the actual implementation of the abstract QKD protocol. Several such attacks have been proposed [1,2], and various proof-of-principle demonstrations on commercial QKD devices have been performed in recent years [3-5]. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-06-05

Influence of group-velocity dispersion on multilevel phase-preserving amplitude regeneration in a nonlinear amplifying loop mirror - Röthlingshöfer, Tobias; Toth, Daniel; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2012)
Numerical simulations have shown a significant influence of group-velocity dispersion (GVD) of the highly nonlinear fiber on the transfer characteristics of a nonlinear amplifying loop mirror (NALM). The effect is especially strong for the anomalous dispersion regime where an interaction of GVD and self-phase modulation (SPM) leads to formation of high-order solitons. The irregularities of the resulting NALM transfer functions can be used for phase-preserving amplitude regeneration of several, irregular-spaced amplitude states for multi-level modulation formats. The regeneration performance was estimated for a 16QAM signal with three amplitude states where a reduction of amplitude noise without significant signal phase distortions has been observe
lhft_intern.bib::Roethlingshoefer2012ca

Influence of Group Velocity Dispersion on phase-preserving Amplitude Regeneration by a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Lasers and Electro-Optics, 2008 and Conference on Quantum Electronics and Laser Science, pages 1-2, 4 - 8 May, 2008)
The influence of dispersion of the highly nonlinear fiber in the loop of a nonlinear amplifying loop mirror on its performance as a 2R regenerator for phase-encoded optical signals has been studied. © 2008 Optical Society of Americ
UnivIS-Import:2017-12-18:Pub.2008.tech.IE.LEH.influe

Influence of Heat Accumulation in the Laser Treatment Area on the Dynamics of LIPSS Formation for Pure Titanium and Titanium Alloy - Druzhinin, Petr; Fomicheva, Iana; Amler, Hans; Leuchs, Gerd; Christiansen, Silke H. (CLEO: Applications and Technology, CLEO: A and T 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
The dependences of LSFL period and the types of large LIPSS for pure titanium and titanium alloy on the amount of heat accumulation in the treatment area by a picosecond laser are presented.
CRIS-Team Scopus Importer:2024-10-04

Influence of Initial Surface Roughness on LIPSS Formation and Its Consecutive Impact on Cell/Bacteria Attachment for TiAl6V4 Surfaces - Sotelo, Lamborghini; Fontanot, Tommaso; Vig, Sanjana; Herre, Patrick; Yousefi, Peyman; Fernandes, Maria Helena; Sarau, George; Leuchs, Gerd; Christiansen, Silke (Advanced Materials Technologies, 2023)
The influence of the initial surface roughness of TiAl6V4 samples on the orientation and periodicity of the resulting laser-induced periodic surface structures (LIPSS), as well as the surface wettability and chemistry is reported here. Before LIPSS fabrication, initial sample surface roughness is adjusted by variations of finial polishing steps with polishing grain sizes of 18.3, 8.4, 5, and 0.5 µm. A 3 × 3 irradiation matrix was defined and lasered on all samples by changing the laser power and distance between consecutive laser scans. The resulting structures were characterized by scanning electron microscopy (SEM), atomic force microscopy, Raman spectroscopy, and contact angle measurements. As a further step, three representative generated structures were chosen to explore their bone implant viability by resazurin assays, alkaline phosphatase activity, and direct SEM imaging of the induced cells (MG63) and bacteria (Escherichia coli and Staphylococcus aureus). Results show that initial surface roughness has big influence on the wettability of the resulting surface, as well as inducing small variations on the orientation of the generated LIPSS. Structures generated with a higher integrated fluence have also shown to enhance cell differentiation while reducing bacterial activity, making them a great candidate for improved bone implant compatibility and durability.
CRIS-Team Scopus Importer:2023-04-20
Keywords: biocompatibility; laser functionalization; laser-induced periodic surface structures; TiAl6V4

Influence of Rayleigh Backscattering on the Performance of NOLM-Based Phase-Preserving Amplitude Limiters - Stephan, C.; Sponsel, K.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (OSA Optics and Photonics Congress, Advanced Photonics, BGPP Topical Meeting, Karlsruhe, 21.-24. Juni, 2010)
lhft_intern.bib::Stephan10

Influence of Rayleigh Backscattering on the Performance of NOLM-Based Phase-Preserving Amplitude Limiters - Stephan, C.; Sponsel, K.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (Conference on OFC / NFOEC, March, San Diego, 2010)
lhft_intern.bib::Stephan10b

Influence on the optical performance of droplets and enclosures in printed polymer optical waveguides - Backhaus, Carsten; Förner, Johannes; Wienke, Alexander; Hoffmann, Gerd-Albert; Eiche, Yannic; Lorenz, Lukas; Kaierle, Stefan; Overmeyer, Ludger; Franke, Jörg; Bock, Karlheinz; Lindlein, Norbert (Physics and Simulation of Optoelectronic Devices XXIX, 2021)
Printing polymer optical waveguides by means of combined printing processes has proven to be a challenging but effective way of producing waveguides with a loss less than 0.3dB/cm. In order to evaluate the optical performance of the produced waveguides, optical simulations have been carried out. In this work we show the influence on the optical performance by simulating droplets and enclosures in multimode waveguides with a proprietary raytracing algorithm. Critical waveguide parameters such as width and height variation will be evaluated. Finally, experimentally achieved optical performance is presented and compared with the simulation resul
Keywords: Raytracing; Polymer Optical Waveguides; Aerosol Jet Printing; Optical Simulation; Waveguide Quality Analysis; Signal Attenuation; Waveguides; 3D Printing

Information theoretical optimization for optical range sensors, - Häusler, Gerd; et al. (Applied Optics, 2003)
Most of the known optical range sensors require a large amount of two-dimensional raw data from which the three-dimensional (3D) data are decoded and so are associated with considerable cost. The cost arises from expensive hardware as well as from the time necessary to acquire the images. We will address the question of how one can acquire maximum shape information with a minimum amount of image raw data, in terms of information theory. It is shown that one can greatly reduce the amount of raw data needed by proper optical redundancy reduction. Through these considerations, a 3D sensor is introduced, which needs only a single color (red-green-blue) raw image and still delivers data with only approximately 2-μm longitudinal measurement uncertainty. © 003 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.inform

Innovative optical components and their impact on future transmission systems - Schmauß, Bernhard; Striegler, Arne; Meißner, Markus (Invited talk, APOC, Wuhan, China, November, 2003)
Optical transmission systems made impressive progress in the field of system capacity, reach and flexibility. Beside all improvements achieved so far, signal distortion on the one hand side and noise accumulation on the other hand side are the limitations of optical transmission system performance. In terms of signal distortion besides advanced link design strategies optical regenerators are of high interest for signal conditioning along a fiber link. Our paper reviews signal regeneration techniques focusing on fiber nonlinearity based setups both in interferometric and non interferometric architecture. We analyze the impact of regenerator design parameters as fiber nonlinear parameters, regenerator input power and characteristics of filters on signal improvement and demonstrate e.g. the increase of system reach. In order to address the upcoming techniques of advanced modulation formats we introduce a fiber based regenerator scheme that shows attractive potential especially for phase modulated signals. Combining these new optical formats with regenerative methods is attractive for high performance systems. For the differential phase shift keying (DPSK) modulation format we investigate the potential of a cross phase modulation based type of regenerator in more detail. The availability of suitable regenerator components, especially highly nonlinear fibers is one of the challenges. Especially the new fiber types known as photonic crystal fibers can act as bases for new structures and thus will open the door for ultra high performance optical transmission systems.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.innova
Keywords: Modulation Format; Optical Transmission; Regeneration

Inorganic photovoltaics - Planar and nanostructured devices - Ramanujam, Jeyakumar; Verma, Amit; Gonzalez-Diaz, B.; Guerrero-Lemus, Ricardo; Del Canizo, Carlos; Garcia-Tabares, Elisa; Rey-Stolle, Ignacio; Granek, Filip; Korte, Lars; Tucci, Mario; Rath, Jatin; Singh, Udai P.; et al. (Progress in Materials Science, 2016)
Since its invention in the 1950s, semiconductor solar cell technology has evolved in great leaps and bounds. Solar power is now being considered as a serious leading contender for replacing fossil fuel based power generation. This article reviews the evolution and current state, and potential areas of near future research focus, of leading inorganic materials based solar cells, including bulk crystalline, amorphous thin-films, and nanomaterials based solar cells. Bulk crystalline silicon solar cells continue to dominate the solar power market, and continued efforts at device fabrication improvements, and device topology advancements are discussed. III-V compound semiconductor materials on c-Si for solar power generation are also reviewed. Developments in thin-film based solar cells are reviewed, with a focus on amorphous silicon, copper zinc tin sulfide, cadmium telluride, as well as nanostructured cadmium telluride. Recent developments in the use of nano-materials for solar power generation, including silicon and gallium arsenide nanowires, are also reviewed.

Inorganic photovoltaics – Planar and nanostructured devices - Ramanujam, Jeyakumar; Verma, Amit; Gonzalez-Diaz, B.; Guerrero-Lemus, Ricardo; Del Canizo, Carlos; Garcia-Tabares, Elisa; Rey-Stolle, Ignacio; Granek, Filip; Korte, Lars; Tucci, Mario; Rath, Jatin; Singh, Udai P.; et al. (Progress in Materials Science, 2016)
<ul class="issue-navigation" style="margin: 0px 0px 16px; padding-right: 0px; padding-left: 0px; box-sizing: border-box; list-style: none; background: rgb(245, 245, 245); overflow: hidden; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> <div class="Abstracts" style="margin: 0px; padding: 0px; box-sizing: border-box; line-height: 24px; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> Since its invention in the 1950s, semiconductor solar cell technology has evolved in great leaps and bounds. Solar power is now being considered as a serious leading contender for replacing fossil fuel based power generation. This article reviews the evolution and current state, and potential areas of near future research focus, of leading inorganic materials based solar cells, including bulk crystalline, amorphous thin-films, and nanomaterials based solar cells. Bulk crystalline silicon solar cells continue to dominate the solar power market, and continued efforts at device fabrication improvements, and device topology advancements are discussed. III–V compound semiconductor materials on c-Si for solar power generation are also reviewed. Developments in thin-film based solar cells are reviewed, with a focus on amorphous silicon, copper zinc tin sulfide, cadmium telluride, as well as nanostructured cadmium telluride. Recent developments in the use of nano-materials for solar power generation, including silicon and gallium arsenide nanowires, are also reviewed.

In Process 3D-Sensing for Laser Material Processing - Häusler, Gerd; et al. (Proc. of Third International Conference on 3D Digital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.forsch.gradui.gradui_6.inproc

In-Situ surface characterization of nano- and microparticles by optical Second Harmonic Generation - Schürer, Benedikt; Wunderlich, Sarina; Peschel, Ulf; Peukert, Wolfgang (Nanotechnology 2010: Advanced Materials, CNTs, Particles, Films and Composites, 2010)
Nonlinear optical spectroscopic techniques, namely Second Harmonic Generation (SHG) spectroscopy and Sum Frequency Generation (SFG), are highly interface sensitive and can be used to obtain information exclusively from the surface of particles. Second Harmonic Generation (SHG) has proven to be a versatile technique that can be used to probe different kinds of surface properties of dispersed particle systems in in-situ. Prominent examples are the direct study of molecular adsorption at the surface of particles and the determination of surface potentials of nano- and microparticles. However, in most of these studies well-defined spherical and monodisperse particles with low number densities were used. Here we demonstrate the application of the SHG technique for the study of more complex and technically relevant particle systems. We discuss the influence of particle concentration and particle size distribution. Moreover, we apply a novel nonlinear Mie Model that is capable to simulate the SH scattering from the surface of spherical particles and we show that the model can be used to extract information about molecules at the particle liquid interfac
Keywords: Nonlinear Mie model; Nanoparticles; Second Harmonic Generation; Optics; Surface characterization

Instantaneous speckle reduction? Yes, but there is no free lunch! - Häusler, Gerd; Dötzer, Florian; Mantel, Klaus (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We are motivated by the question if scanning laser projection with low speckle noise is possible. Scanning laser projection requires "instantaneous" speckle reduction, within a few nanoseconds-meaning that no moving diffusors can be used. We will argue that instantaneous speckle reduction is possible by conversion of spatial coherence to spatial incoherence-but nature demands for a compensation. The cost can be estimated via the information theoretical concept "channel capacity", which incorporates the etendue as well as the signal-to-noise ratio. We will show that an optical system with low spatial coherence (=low speckle noise) must provide significantly more degrees of freedom than a coherent imaging system. The consequence for the technical optical system is serious: Significant speckle reduction can only be achieved by an excessively large projection aperture. This is not just a sophistic consideration, it seriously restricts the design of scanning laser projectors.
Created from Fastlane, Scopus look-up
Keywords: Channel capacity; Etendue; Laser projection; Speckle noise; Speckle noise reduction

Integrated Photonics for Quantum Communication on a Cubesat - Pudelko, Jonas; Bayraktar, Ömer; Khan, Imran; Boxleitner, Winfried; Petscharnig, Stefan; Pacher, Christoph; Leuchs, Gerd; Marquardt, Christoph (2023 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC), 2023)
The limited range of quantum key distribution (QKD) in fiber based systems led to several projects aiming for the development of a satellite based QKD infrastructure, like the conduction of quantum limited measurements from a geostationary satellite [1] or the MICIUS mission, which impressively demonstrated QKD on a global scale [2]. However, due to the high costs of satellite launches the profitability of commercial systems would benefit dramatically from further reduction in size, weight and power. Photonic integration [3] addresses these points by allowing the integration of all optical components of a QKD system on a photonic integrated circuit (PIC). In this work, we are going to demonstrate building blocks for quantum communication from space based on photonic integration technology by building a payload for the CubeSat mission QUBE [4] consisting of an integrated sender for weak coherent states as well as an integrated Quantum Random Number Generator (QRNG).<br

Interacting waves on chains of split-ring resonators in the presence of retardation - Lomanets, Vadym; Zhuromskyy, Oleksandr; Onishchukov, Georgy; Sydoruk, Oleksiy; Tatartschuk, Eugen; Shamonina, E.; Leuchs, Gerd; Peschel, Ulf (Applied Physics Letters, 2010)
Wave propagation is studied experimentally in a one-dimensional periodic chain of magnetically coupled split-ring resonators with a spacing of about one tenth of the resonant wavelength. Retardation leads to a strong interaction between magnetoinductive and free-space waves. Two kinds of guided modes are observed: a slow backward wave which propagates far outside the light cone, and a fast forward wave close to the light cone. The two merge in a region of zero group velocity. The results are relevant for all one- and two-dimensional periodic systems interacting with waves of the surrounding space.
EAM Import::2019-03-13

Interaction of highly focused vector beams with a metal knife-edge - Marchenko, P.; Orlov, S.; Huber, C.; Banzer, Peter; Quabis, Susanne; Peschel, Ulf; Leuchs, Gerd (Optics Express, 2011)
We investigate the interaction of highly focused linearly polarized optical beams with a metal knife-edge both theoretically and experimentally. A high numerical aperture objective focusses beams of various wavelengths onto samples of different sub-wavelength thicknesses made of several opaque and pure materials. The standard evaluation of the experimental data shows material and sample dependent spatial shifts of the reconstructed intensity distribution, where the orientation of the electric field with respect to the edge plays an important role. A deeper understanding of the interaction between the knife-edge and the incoming highly focused beam is gained in our theoretical model by considering eigenmodes of the metal-insulator-metal structure. We achieve good qualitative agreement of our numerical simulations with the experimental findings.
EAM Import::2019-03-13

Interaction of light carrying orbital angular momentum with a chiral dipolar scatterer - Wozniak, Pawel; De Leon, Israel; Hoeflich, Katja; Leuchs, Gerd; Banzer, Peter (Optica, 2019)
The capability to distinguish the handedness of circularly polarized light is a well-known intrinsic property of a chiral nanostructure. It is a long-standing controversial debate, however, whether a chiral object can also sense the vorticity, or the orbital angular momentum (OAM), of a light field. Since OAM is a spatial property, it seems rather counter-intuitive that a point-like chiral object could be able to distinguish the sense of the wave-front of light carrying OAM. Here, we show that a dipolar chiral nanostructure is indeed capable of distinguishing the sign of the phase vortex of the incoming light beam. To this end, we take advantage of the conversion of the sign of OAM, carried by a linearly polarized Laguerre-Gaussian beam, into the sign of optical chirality upon tight focusing. Our study provides for a deeper insight into the discussion of chiral light-matter interactions and the respective role of OAM. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-09-13

Interaction of light with hematite hierarchical structures: Experiments and simulations - Distaso, Monica; Zhuromskyy, Oleksandr; Seemann, Benjamin; Pflug, Lukas; Mackovic, Mirza; Encina, Ezequiel Roberto; Klupp Taylor, Robin; Müller, Rolf; Leugering, Günter; Spiecker, Erdmann; Peschel, Ulf; Peukert, Wolfgang (Journal of Quantitative Spectroscopy & Radiative Transfer, 2017)
Mesocrystalline particles have been recognized as a class of multifunctional materials with potential applications in different fields. However, the internal organization of nanocomposite mesocrystals and its influence on the final properties have not yet been investigated. In this paper, a novel strategy based on electrodynamic simulations is developed to shed light on how the internal structure of mesocrystals influences their optical properties. In a first instance, a unified design protocol is reported for the fabrication of hematite/PVP particles with different morphologies such as pseudo-cubes, rods-like and apple-like structures and controlled particle size distributions. The optical properties of hematite/PVP mesocrystals are effectively simulated by taking their aggregate and nanocomposite structure into consideration. The superposition T-Matrix approach accounts for the aggregate nature of mesocrystalline particles and validate the effective medium approximation used in the framework of the Mie theory and electromagnetic simulation such as Finite Element Method. The approach described in our paper provides the framework to understand and predict the optical properties of mesocrystals and more general, of hierarchical nanostructured particles.
Keywords: Effective medium approximation; FEM; Maxwell-Garnett theory; Mesocrystals; Scattering; T-Matrix

Interfacing transitions of different alkali atoms and telecom bands using one narrowband photon pair source - Schunk, Gerhard; Vogl, Ulrich; Strekalov, Dmitry V.; Förtsch, Michael; Sedlmeir, Florian; Schwefel, Harald; Göbelt, Manuela; Christiansen, Silke; Leuchs, Gerd; Marquardt, Christoph (Optica, 2015)
Quantum information technology strongly relies on the coupling of optical photons with narrowband quantum systems, such as quantum dots, color centers, and atomic systems. This coupling requires matching the optical wavelength and bandwidth to the desired system, which presents a considerable problem for most available sources of quantum light. Here we demonstrate the coupling of alkali dipole transitions with a tunable source of photon pairs. Our source is based on spontaneous parametric downconversion in a triply resonant whispering gallery mode resonator. For this, we have developed novel wavelength-tuning mechanisms that allow a coarse tuning to either the cesium or rubidium wavelength, with subsequent continuous fine-tuning to the desired transition. As a demonstration of the functionality of the source, we performed a heralded single-photon measurement of the atomic decay. We present a major advance in controlling the spontaneous downconversion process, which makes our bright source of heralded single photons now compatible with a plethora of narrowband resonant system
Keywords: Atomic; Quantum communications; Quantum optics; Spectroscopy

Interference of two intense entanglement sources: entanglement swapping and multi-partite entanglement - Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Heersink, Joel; Pan, Quing; van Loock, Peter; Korolkova, Natalia; Leuchs, Gerd (2003 European Quantum Electronics Conference. EQEC 2003, 2003)
Progress of entanglement swapping experiment is reported. Four highly correlated modes are created by the interference of two entangled systems. As calculations show, there are strong hints that the state is indeed multi-partite entangled.<br
Keywords: Quantum entanglement; Physics; Hilbert space; Telecommunication standards; Cryptography; Teleportation

Interferometrical measurement of cylindrical lenses with the help of computer generated holograms - Lindlein, Norbert; et al. (Proceedings of SPIE, 2001)
Two different methods for the measurement of cylindrical lenses will be presented in this paper. The first method uses the principle of grazing incidence interferometry. A computer generated diffractive optical element (DOE) generates the wave fronts which impinge under grazing incidence onto the surfaces to be tested. The light is reflected at the surfaces and diffracted at a second DOE identical to the first one. The 0-th diffraction order of both DOEs is used as reference wave. The deviations of up to three surfaces (front-side, backside and one of the border sides) of a cylindrical lens from their ideal shape can be measured simultaneously. Additionally, the orientation of these three surfaces with respect to each other are determined. The second method measures the aberrations of a cylindrical lens in transmitted light by using an interferometer of the Mach-Zehnder type. The cylindrical wave of the lens under test is compensated by a DOE which generates a plane wave if the incident wave is an ideal cylindrical wave. So, the wave aberrations of the cylindrical lens can be measured. The set-up is designed for cylindrical lenses with a high numerical aperture of up to 0.8. The principles of both methods and first experimental results will be presented.
UnivIS-Import:2015-04-14:Pub.2001.nat.dphy.optik.1optik.interf
Keywords: Computer generated holograms; Grazing incidence interferometry; Interferometry; Mach-Zehnder interferometer; Testing of aspherics; Testing of cylindrical lenses

Interferometric grazing incidence test of rough steep convex aspherics: full 3D reconstruction of the object - Rothau, Sergey; Schamburek, Tobias; Mantel, K.; Lindlein, Norbert (Applied Optics, 2022)
A grazing incidence interferometric measurement procedure is applied to test rough convex steep rotationally symmetric aspherics. The measurement of rough surfaces is possible; i.e., without the need to polish the surfaces, due to the large effective wavelength (λeff = 10 µm) of the test. One measurement step using diffractive beam splitters and phase-shifting techniques delivers the surface information along one meridian. The full surface description can be stitched together from several phase results combined with appropriate object rotations. This publication includes, besides the short recapitulation of the measurement principle and experimental setup, a presentation of the simulated and measured data of an aspherical object under test. The data analysis of each meridian is focused on the elimination of the misalignment aberrations caused by specimen displacements. Finally, the stitching of multiple meridian regions to a 3D surface map of the specimen is shown.
CRIS-Team Scopus Importer:2022-06-03

Interferometric grazing incidence test of rough steep convex spherical and aspherical surfaces: First simulations and experimental proof of principle - Rothau, Sergey; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2019)
In the past, grazing incidence interferometry has been applied for rough plane, cylindrical, acylindrical, and general rod-like surfaces using diffractive beam splitters. Here, we demonstrate that also rough convex steep rotational symmetric spherical or aspherical surfaces can be measured along one meridian in a single step using diffractive beam splitters and phase-shifting techniques. The extension to the whole surface can be attained by successive meridional measurements of the surface under test by azimuthal adjustments. The principle of the method is given and for a spherical ball lens as an extremely curved surface simulated, and experimental data are presented. The features of the interferogram are discussed, and the experimental evaluation of a single meridian including the unwrapped phase data is shown.
CRIS-Team Scopus Importer:2019-11-29

Interferometric grazing incidence test of rough steep convex spherics: Experimental data analysis - Rothau, Sergey; Mantel, K.; Lindlein, Norbert (Applied Optics, 2021)
Grazing incidence interferometry has been applied to plane, cylindrical, acylindrical, and general rod-like surfaces using diffractive beam splitters. Here, in a first step towards measuring aspherics, we demonstrate that also rough convex steep rotationally symmetric spherics can be measured along one meridian in a single step using diffractive beam splitters and phase shifting techniques. The measurement of rough surfaces is possible, i.e., without the need to polish the surfaces, due to the large effective wavelength (λeff ≈ 10 µm) of the test. We include, besides the short recapitulation of the measurement principle and experimental setup, a presentation of the measured data of one small meridian region for the special case of spherical objects under test. The subsequent data analysis combined with suitable simulations focuses on elimination of the misalignment aberrations from the results caused by specimen displacements in the setup.
CRIS-Team Scopus Importer:2021-01-08

Interferometric measurement of holographic lenslets - Lindlein, Norbert; et al. (Journal of Modern Optics, 1993)
A holographic optical element can either be characterized by the wave aberrations or by the point spread function or alternatively by the modulation transfer function. Here we propose the measurement of the wave aberrations with the help of a Twyman-Green interferometer adapted to the requirements for testing holographic optical elements. The evaluation of the interferograms is done with the phase-shifting technique. The resulting wave aberrations are expressed by Zemike coefficients. In addition to this evaluation, the point spread function and the modulation transfer function are calculated from the wave aberrations. The set-up, the evaluation method and also exemplary results of a tested holographic optical element are presented. © 1993 Taylor & Francis Ltd.

Interferometric measurement of micro-lenses including cylindrical lenses - Lindlein, Norbert; Lamprecht, Jürgen; Schwider, Johannes (Microoptics, 2004)
UnivIS-Import:2015-04-20:Pub.2004.nat.dphy.optik.1optik.interf

Interferometric null test of a deep parabolic reflector generating a Hertzian dipole field - Leuchs, Gerd; Mantel, Klaus; Berger, Andreas; Konermann, Hildegard; Sondermann, Markus; Peschel, Ulf; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2008)
We report on interferometric characterization of a deep parabolic mirror with a depth of more than five times its focal length. The interferometer is of Fizeau type; its core consists of the mirror itself, a spherical null element, and a reference flat. Because of the extreme solid angle produced by the paraboloid, the alignment of the setup appears to be very critical and needs auxiliary systems for control. Aberrations caused by misalignments are removed via fitting of suitable functionals provided by means of ray tracing simulations. It turns out that the usual misalignment approximations fail under these extreme conditions.© 2008 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2008.nat.dphy.optik.1optik.interf

Interferometric null test of a parabolic reflector generating a Hertzian dipole field - Lindlein, Norbert; et al. (Interferometry XIV: Techniques and Analysis, 2008)
Interferometric surface tests of stigmatic aspherics can be carried out in a null test configuration. Null tests require reference null elements either plane or spherical surfaces or both. A parabolic reflector transforms a plane into a spherical wave which converges to the focus of the paraboloid. Therefore, a spherical ball lens or a steel ball can be placed into the focus enabling a double-pass geometry for the null test. Here a Fizeau interferometer geometry has been selected in order to guarantee invariance against polarization distortions under the assumption that radially polarized laser light is used for the interferometer. Radial polarized light is necessary to mimic a Hertzian dipole field. Due to the extreme solid angle produced by the paraboloid the alignment of the setup is very critical and needs auxiliary systems for the control. Aberrations caused by misalignments are removed via fitting of suitable functional provided through ray-trace simulations. It turned out that the usual vector approximations fail under these extreme circumstances. Test results are given for a paraboloid with 2mm focal length transforming a plane wave into a near dipole wave comprising a solid angle of about 3,4π.

Interferometric quasi-absolute tests for aspherics using a radial shear position - Mantel, Klaus Peter; Geist, Eduard; Harder, Irina; Lindlein, Norbert; Leuchs, Gerd (Optics Letters, 2009)
Increasing accuracy requirements in aspheric metrology make the development of absolute testing procedures for aspheric surfaces important. One strategy is transferring the standard practice three-position test for spheres to aspherics. The three-position test, however, involves a cat's eye position and therefore has certain drawbacks. We propose an absolute testing method for rotationally symmetric aspherics where the cat's eye position is replaced with a radially sheared position. Together with rotational movements of the specimen, the surface deviations can be obtained in an absolute manner. To demonstrate the validity of the procedure, we present a measurement result for a sphere and compare it with a result obtained by the standard three-position test. © 2009 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.interf

Interferometric testsfor micro-optics - Lindlein, Norbert; Schwider, Johannes (1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.interf_5

Interferometrie in streifender Inzidenz an Asphären - Rothau, Sergej; Schamburek, Tobias; Lindlein, Norbert (122, 2021)

Interferometrie in streifender Inzidenz: Simulationen und Messergebnisse - Rothau, Sergej; Schwider, Johannes; Mantel, Klaus; Lindlein, Norbert (120. Annual Meeting of the DGaO, 2019)

Interferometrischer 3D-Sensor zur berührungslosen Vermessung technischer Oberflächen - Leuchs, Gerd; et al. (VDI-Berichte, 2000)
We demonstrate interferometric 3D-measurements of technical objects with rough surfaces. Objects with heights of a few millimetres up to several centimetres are measured from a distance of about one meter. With an integration time of 60ms a distance resolution of a few 10μm is achieved.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.interf_89

Interferometry Simultaneous Measurement of the Surfaces of Cylindrical Lenses by Grazing Incidence Interferometry - Mantel, Klaus Peter; Lindlein, Norbert; Schwider, Johannes (VDI-Berichte, 2002)
Fabrication errors of cylindrical lenses may be divided into two categories: surface deviations and errors in the position and orientation of the surfaces relative to each other. A simultaneous measurement of both error sources is possible by means of grazing incidence interferometry. Thereby, the surface deviations and the misalignment errors of each surface relative to the diffractive null elements can be acquired for up to three surfaces at the same time. The misalignment errors provide information about the relative position of the surfaces and allow the detection of various error types like wedge errors and centering errors.
UnivIS-Import:2015-04-14:Pub.2002.nat.dphy.optik.1optik.interf_4

Intracavity Squeezing Can Enhance Quantum-Limited Optomechanical Position Detection through Deamplification - Peano, Vittorio; Schwefel, Harald; Marquardt, Christoph; Marquardt, Florian (Physical Review Letters, 2015)
It has been predicted and experimentally demonstrated that by injecting squeezed light into an optomechanical device, it is possible to enhance the precision of a position measurement. Here, we present a fundamentally different approach where the squeezing is created directly inside the cavity by a nonlinear medium. Counterintuitively, the enhancement of the signal-to-noise ratio works by deamplifying precisely the quadrature that is sensitive to the mechanical motion without losing quantum information. This enhancement works for systems with a weak optomechanical coupling and/or strong mechanical damping. This can allow for larger mechanical bandwidth of quantum-limited detectors based on optomechanical devices. Our approach can be straightforwardly extended to quantum nondemolition qubit detection.
CRIS-Team Scopus Importer:2022-06-05

Investigating plasmonic gap modes coupled to nanoantennas - Wen, J.; Kriesch, Arian; Ploss, Daniel; Banzer, Peter; Schmauß, Bernhard; Peschel, Ulf (Lasers and Electro-Optics Europe (CLEO EUROPE/EQEC), 2011 Conference on and 12th European Quantum Electronics Conference, 2011)
lhft_intern.bib::Wen2011

Investigating the Optical Properties of a Laser Induced 3D Self-Assembled Carbon–Metal Hybrid Structure - Butt, Muhammad Abdullah; Lesina, Antonino Calà; Neugebauer, Martin; Bauer, Thomas; Ramunno, Lora; Vaccari, Alessandro; Berini, Pierre; Petrov, Yuriy; Danilov, Denis; Manshina, Alina; Banzer, Peter; Leuchs, Gerd (Small, 2019)
Carbon-based and carbon–metal hybrid materials hold great potential for applications in optics and electronics. Here, a novel material made of carbon and gold–silver nanoparticles is discussed, fabricated using a laser-induced self-assembly process. This self-assembled metamaterial manifests itself in the form of cuboids with lateral dimensions on the order of several micrometers and a height of tens to hundreds of nanometers. The carbon atoms are arranged following an orthorhombic unit cell, with alloy nanoparticles intercalated in the crystalline carbon matrix. The optical properties of this metamaterial are analyzed experimentally using a microscopic Müller matrix measurement approach and reveal a high linear birefringence across the visible spectral range. Theoretical modeling based on local-field theory applied to the carbon matrix links the birefringence to the orthorhombic unit cell, while finite-difference time-domain simulations of the metamaterial relates the observed optical response to the distribution of the alloy nanoparticles and the optical density of the carbon matrix.
CRIS-Team Scopus Importer:2019-05-02
Keywords: computational modeling; laser-induced deposition; metal alloy nanoparticles; microscopic Müller matrix measurement technique; orthorhombic carbon

Investigating the Surface of Nanoparticles by Second Harmonic Generation - Wunderlich, Sarina; Peschel, Ulf; Schürer, Benedikt; Peukert, Wolfgang (Conference on Lasers and Electro-Optics (CLEO)/Quantum Electronics and Laser Science Conference (QELS), 2010)
We investigate Second Harmonic Generation at the surface of nanoparticles both by modeling and experiment. We present an ab initio simulation method, which allows deducing surface properties as well as the nature of adsorbed molecules. (C) 2010 Optical Society of America

Investigation of noise sources down to the shot-noise limit in Yb-doped fiber amplifers for TMI investigations - Popp, Alexandra; Bock, Victor; Sedlmeir, Florian; Muller, Christian R.; Haarlammert, Nicoletta; Schreiber, Thomas; Marquardt, Christoph; Tunnermann, Andreas; Leuchs, Gerd (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Ytterbium-doped fiber laser amplifiers are known for their high single-pass gain and average powers up to the kilowatt range, while maintaining single-mode output. An upper limitation for the achievable output power is given by transverse mode instabilities (TMI). Due to the interference with higher order modes that create a thermally induced long period grating, chaotic power transfer happens above a certain threshold, which degrades the beam quality. It has been shown that this effect can be influenced by manipulating the grating strength itself. It has also been shown that a certain phase relation of the grating to the guided modes is necessary to efficiently transfer power or hinder the effect by phase disturbance [1]. A natural phase disturbance is given by noise, which is introduced by the pump or seed source in a fiber amplifer. In this contribution, we experimentally investigate the amount of intensity noise in a fiber-pre-amplifer, which is typically used in kW experiments and relate it to the fundamental shot noise limit (SNL). In the experiments, we used a single-frequency external cavity diode laser as a low noise source and amplify it by 30 dB from 10 mW to an output power of 10 W. This is a typical pre-amplifier configuration, before such sources can be amplified to the kW level. The fiber amplifier is a double-clad fiber with a 10/125 μm geometry, pumped by a wavelength stabilized pump diode at 976 nm via a monolithic pump coupler. In order to prevent stimulated Brillouin scattering, the seed laser is phase modulated by a combination of a sinusoid and white noise and thus broadened to 50 GHz linewidth. The noise measurements are done by balanced self-homodyne detection including optimized photodiode readout circuits spanning different frequency ranges. The recorded spectra are given in Fig. 1. The SNL was verified through an attenuation measurement for the subtracted detector signals. Finally, the measured excess noise values are fitted by their corresponding second-order polynomial power dependency and extrapolated to the full power of the amplifier. The seed source, phase modulator and fiber amplifier have been characterized in this setup separately to investigate their contributions. For the fiber amplifier, both co- and counter-pumping configuration, are analysed. Due to detector limitations, all given spectra are measured at an optical power in the mW regime corresponding to approx. 30 dB of attenuation in the amplifiers.
CRIS-Team Scopus Importer:2019-11-15

Investigation of phase singularities in the vicinity of small structures using a Linnik interference microscope - Leuchs, Gerd; et al. (Technisches Messen, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.invest

Ist 'Technisches Sehen' gleich 'Kamera + Computer'? - Häusler, Gerd; Leuchs, Gerd (Uni-Kurier-Magazin, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.isttec

Iterative correction of holographic lenses - Lindlein, Norbert; et al. (Proceedings of SPIE, 1994)
Holographic optical lens elements (HOEs) are volume grating in thick material such as dichromated gelatine (DCG) which suffer from the wavelength mismatch between the recording process and the practical application e.g., at laser diode wavelengths. Wavelength mismatch between recording and reconstruction is caused by the fact that the best recording materials are sensitive only in the blue region of the spectrum. The advantage of volume gratings (thickness 13 μm) is the large angle of deflection of the first diffraction order with a high diffraction efficiency. An optimized recording geometry using only spherical wave fronts allows on the one hand for the elimination of one of the third order aberrations (predominantly: astigmatism) or on the other hand for the fulfillment of the Bragg condition. To optimize the properties of holographic optical lens elements with one aspheric recording wave a kind of iterative procedure for the manufacturing is proposed. Each iteration consists of three different steps.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.optik.1optik.iterat

Joint Surface Reconstruction and 4D Deformation Estimation from Sparse Data and Prior Knowledge for Marker-Less Respiratory Motion Tracking - Berkels, Benjamin; Bauer, Sebastian; Ettl, Svenja; Arold, Oliver; Hornegger, Joachim; Rumpf, Martin (Medical Physics, 2013)

Kalibrierung einer 3D Video Kamera - Häusler, Gerd; et al. (3.Optische Formerfassung, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.kalibr

Kalibrierung von optischen 3D-Sensoren - Häusler, Gerd; et al. (Optik, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.kalibr_2

Kalibrierverfahren von Sphären bei partieller Kohärenz - Lindlein, Norbert; Mantel, Klaus; Geist, Eduard; Hussendörfer, Benjamin (DGaO-Proceedings 2010 - http://www.dgao-proceedings.de - ISSN: 1614-8436, 2010)

Kelvin's chirality of optical beams - Nechayev, Sergey; Eismann, Jörg; Alaee, Rasoul; Karimi, Ebrahim; Boyd, Robert W.; Banzer, Peter (Physical Review A, 2021)
Geometrical chirality is a property of objects that describes a three-dimensional mirror-symmetry violation and therefore it requires a nonvanishing spatial extent. In contrary, optical chirality describes only the local handedness of electromagnetic fields and neglects the spatial geometrical structure of optical beams. In this Letter we put forward the physical significance of geometrical chirality of spatial structure of optical beams, which we term Kelvin's chirality. Furthermore, we report on an experiment revealing the coupling of Kelvin's chirality to optical chirality upon transmission of a focused beam through a planar medium. Our work emphasizes the importance of Kelvin's chirality in all light-matter interaction experiments involving structured light beams with spatially inhomogeneous phase and polarization distributions.
CRIS-Team Scopus Importer:2021-04-02

Kerr-effect induced correlations of optical fiber solitons and the impact of phase control - Leuchs, Gerd; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Heersink, Joel; Korolkova, Natalia (Frontiers in Optics 2003, 2003)
Experiments are reported in which the quantum properties of intense optical pulses at 1.5 micrometer are controlled via their non-linear interaction with the optical fiber. Intense light pulses may exhibit non-classical features such as entanglement with application in quantum communication. The role of phase control will be discussed.<br

Kerr Enhancement of Optomechanics in Microresonators - Ghalanos, George N.; Silver, Jonathan M.; Zhang, Shuangyou; Del Bino, Leonardo; Bi, Toby; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
When on-chip microresonators were first fabricated in 2005, it became apparent that these cavities exhibit op-tomechanical properties, evident by the parametric oscillation instability that was observed [1], [2]. This behaviour, resulting from radiation pressure, was then exploited for experiments involving cavity cooling [3], and coherent amplification in the form of a phonon laser [4].
CRIS-Team Scopus Importer:2021-10-29

Kerr-Nonlinearity-Induced Mode-Splitting in Optical Microresonators - Ghalanos, George N.; Silver, Jonathan M.; Del Bino, Leonardo; Moroney, Niall; Zhang, Shuangyou; Woodley, Michael T. M.; Svela, Andreas O.; Del'Haye, Pascal (Physical Review Letters, 2020)
The Kerr effect in optical microresonators plays an important role for integrated photonic devices and enables third harmonic generation, four-wave mixing, and the generation of microresonator-based frequency combs. Here we experimentally demonstrate that the Kerr nonlinearity can split ultra-high-Q microresonator resonances for two continuous-wave lasers. The resonance splitting is induced by self- and cross-phase modulation and counterintuitively enables two lasers at different wavelengths to be simultaneously resonant in the same microresonator mode. We develop a pump-probe spectroscopy scheme that allows us to measure power dependent resonance splittings of up to 35 cavity linewidths (corresponding to 52 MHz) at 10 mW of pump power. The required power to split the resonance by one cavity linewidth is only 286 mu W. In addition, we demonstrate threefold resonance splitting when taking into account four-wave mixing and two counterpropagating probe lasers. These Kerr splittings are of interest for applications that require two resonances at optically controlled offsets, e.g., for optomechanical coupling to phonon modes, optical memories, and precisely adjustable spectral filters.
CRIS-Team WoS Importer:2020-06-19

Kohärenzradar - ein 3D-Sensor im Genauigkeitsbereich von 1 µ - Häusler, Gerd; et al. (Technisches Messen, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.kohren

Künstliche nanostrukturierte Polarisationselemente - Rothau, Sergej; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Large-Area 3D Plasmonic Crescents with Tunable Chirality - Görlitzer, Eric; Mohammadi, Reza; Nechayev, Sergey; Banzer, Peter; Vogel, Nicolas (Advanced Optical Materials, 2019)
Chiral plasmonic nanostructures hold promise for enhanced chiral sensing and circular dichroism spectroscopy of chiral molecules. It is therefore of interest to fabricate chiral plasmonic nanostructures with tailored chiroptical properties over large areas with reasonable effort. Here, a colloidal lithography approach is used to produce macroscopic arrays of sub-micrometer 3D chiral plasmonic crescent structures over areas >1 cm 2 . The chirality originates from symmetry breaking by the introduction of a step within the crescent structure. This step is produced by an intermediate layer of silicon dioxide onto which the metal crescent structure is deposited. It is experimentally demonstrated that the chiroptical properties in such structures can be tailored by changing the position of the step within the crescent. These experiments are complemented by finite element simulations and the application of a multipole expansion to elucidate the physical origin of the circular dichroism of the crescent structures.
CRIS-Team Scopus Importer:2019-06-04
Keywords: chirality; colloidal lithography; multipole decomposition; plasmonics; split-ring resonator

Large field-of-view scanning white-light interferometers - Häusler, Gerd; et al. (18th Annual Meeting of American Society for Precision Engineering, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.largef

Laser-Induced Synthesis of Electrocatalytically Active Ag, Pt, and AgPt/Polyaniline Nanocomposites for Hydrogen Evolution Reactions - Vasileva, Anna A. A.; Mamonova, Daria V. V.; Petrov, Yuri V. V.; Kolesnikov, Ilya E. E.; Leuchs, Gerd; Manshina, Alina A. A. (Nanomaterials, 2023)
We present an efficient and easily implemented approach for creating stable electrocatalytically active nanocomposites based on polyaniline (PANI) with metal NPs. The approach combines in situ synthesis of polyaniline followed by laser-induced deposition (LID) of Ag, Pt, and AgPt NPs. The observed peculiarity of LID of PANI is the role of the substrate during the formation of multi-metallic nanoparticles (MNP). This allows us to solve the problem of losing catalytically active particles from the electrode's surface in electrochemical use. The synthesized PANI/Ag, PANI/Pt, and PANI/AgPt composites were studied with different techniques, such as SEM, EDX, Raman spectroscopy, and XPS. These suggested a mechanism for the formation of MNP on PANI. The MNP-PANI interaction was demonstrated, and the functionality of the nanocomposites was studied through the electrocatalysis of the hydrogen evolution reaction. The PANI/AgPt nanocomposites demonstrated both the best activity and the most stable metal component in this process. The suggested approach can be considered as universal, since it can be extended to the creation of electrocatalytically active nanocomposites with various mono- and multi-metallic NPs.
CRIS-Team WoS Importer:2023-01-27

Laser triangulation: Fundamental uncertainty in distance measurement - Häusler, Gerd; et al. (Applied Optics, 1994)
This paper presents a theoretical discussion of the fundamental uncertainty of distance measurements by caused by speckle during laser triangulation. Other contributing factors are the observation aperture and the angle of triangulation. For short-range macroscopic applications this uncertainty is in the range of couple micrometers to more than 10 μm, and is independent of the size of the spot size projected, provided this spot is larger than the observed speckle. Low temporal illumination reduces the uncertainty by more than twice for rough surfaces, although N-fold loss of lateral resolution results from an N-fold improvement in the distance uncertainty.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.optik.1optik.lasert

Lateral Shearing Interferometer for Phase Shift Mask Measurement at 193 nm - Lindlein, Norbert; et al. (Proceedings of SPIE, 2002)
The physical limits of optical lithography are mainly determined by the aperture of the mask projection system and the wavelength of the light. In addition to the wavelength shift to the deep UV the application of special techniques to improve the processing window are required. This has furthered the application of the phase shift mask as a lithography tool. The generation of the exact intensity distribution needed in the plane of the wafer strongly depends on the accuracy of the phase shift introduced by the phase shift mask. However, one difficult issue is the reliable measurement of the phase shift introduced by the phase mask at the working wavelength. This is of course mainly due to the lack of suitable and simple interferometric devices for the deep-UV-region - here 193 nm. We propose the use of a diffractive shearing interferometer as a way out. By combining two Ronchi-phase gratings it is possible to produce shear and phase shifts for the evaluation of the fringe patterns simply by axial and lateral shifts of the phase gratings relative to each other. Since the excimer laser emits spatially partial coherent light only the coherence issue is one of the physical problems dealt with in our experiments. The state of the art of our experiments so far reached will be presented.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.latera
Keywords: 193 nm lithography; Complex degree of coherence; Phase measurement; Phase shift mask; Shearing interferometer

Lateral Shearing Interferometry with Simultaneous Detection of both Gradient Fields on a Common Detector Grid - Lindlein, Norbert; et al. (6th International Workshop on Advanced Optical Metrology, Fringe 2009, 2009)

Lateral spin transport in paraxial beams of light - Neugebauer, Martin; Grosche, Simon; Rothau, Sergej; Leuchs, Gerd; Banzer, Peter (Optics Letters, 2016)
We investigate the lateral transport of (longitudinal) spin angular momentum in a special polarization tailored light beam composed of a superposition of a y-polarized zero-order and an x-polarized first-order Hermite-Gaussian mode. This phenomenon is linked to the relative Gouy phase shift between the individual modes upon propagation, but can also be interpreted as a geometric phase effect. Experimentally, we demonstrate the implementation of such a mode and measure the spin density upon propagation.

Lattice-plasmon-induced asymmetric transmission in two-dimensional chiral arrays - Apurv Chaitanya, N.; Butt, Muhammad; Reshef, O.; Boyd, Robert W.; Banzer, Peter; De Leon, Israel (APL Photonics, 2022)
Asymmetric transmission - direction-selective electromagnetic transmission between two ports - is a phenomenon exhibited by two-dimensional chiral systems. The possibility of exploiting this phenomenon in chiral metasurfaces opens exciting possibilities for applications such as optical isolation and routing without external magnetic fields. This work investigates optical asymmetric transmission in chiral plasmonic metasurfaces supporting lattice plasmon modes and unveils its physical origins. We show numerically and experimentally that asymmetric transmission is caused by an unbalanced excitation of such lattice modes by circularly polarized light of opposite handedness. The excitation efficiencies of the lattice modes, and hence, the strength of the asymmetric transmission, are controlled by engineering the in-plane scattering of the individual plasmonic nanoparticles such that the maximum scattering imbalance occurs along one of the in-plane diffraction orders of the metasurface. Furthermore, we show that only the nonzero diffraction orders contribute to this effect. By highlighting the role of the localized plasmon modes supported by the nanoparticle and their radiative coupling to the lattice structure, our study provides a guideline for designing metasurfaces with asymmetric transmission enabled by lattice plasmons.
CRIS-Team Scopus Importer:2022-02-04

Lectures on Quantum Information - Leuchs, Gerd; et al. (Wiley-VCH Verlag GmbH & Co KGaA, 2006)
UnivIS-Import:2015-04-02:Pub.2006.nat.dphy.optik.1optik.lectur

Lectures on Quantum Information - Leuchs, Gerd; et al. (Wiley-VCH Verlag GmbH & Co KGaA, 2006)
UnivIS-Import:2015-05-08:Pub.2006.nat.dphy.optik.1optik.contin_6

Light in curved two-dimensional space - Schultheiß, Vincent; Schultheiß, Vincent; Batz, Sascha; Peschel, Ulf (Advances in Physics: X, 2020)
The extrinsic and intrinsic curvature of a two-dimensional wave-guide influences wave propagation therein. While this can already be apprehended from a geometric point of view in terms of geodesics generalizing straight lines as the shortest distance between any two points, in wave optics interference phenomena strongly govern the field evolution, too. Radii of curvature in the order of the wavelength of light modify the local effective refractive index by altering the mode profile. Macroscopic radii only influence light propagation for non-vanishing intrinsic (or Gaussian) curvature. A positive Gaussian curvature leads to refocusing and thus an imaging behavior, whereas negative Gaussian curvature forces the field profile to diverge exponentially. These effects can be explained by an effective transverse potential acting on the electromagnetic field distribution's envelope. This can also be extended to nonlinear beam propagation. In this review paper we give a thorough introduction to differential geometry in two-dimensional manifolds and its incorporation with Maxwell's equations. We report on first fundamental experiments in this newly emerging field, which may lead to applications in integrated optical circuits. The dose conceptual analogy to phenomena in four-dimensional spacetime with constant curvature as well as toy-models of the Schwarzschild metric and a wormhole topology are also discussed.
CRIS-Team WoS Importer:2020-07-17

Light-matter interaction in free space - Leuchs, Gerd; Sondermann, Markus (Journal of Modern Optics, 2013)
We review recent experimental advances in the field of efficient coupling of single atoms and light in free space. Furthermore, a comparison of efficient free space coupling and strong coupling in cavity quantum electrodynamics (QED) is given. Free space coupling does not allow for observing oscillatory exchange between the light field and the atom which is the characteristic feature of strong coupling in cavity QED. Like cavity QED, free space QED does, however, offer full switching of the light field, a 180° phase shift conditional on the presence of a single atom as well as 100% absorption probability of a single photon by a single atom. Furthermore, free space cavity QED comprises the interaction with a continuum of modes. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: atom-photon coupling; free space QED; strong focussing

Light propagation in a GRIN microlens with gain or loss and comparison with lossless case - Lindlein, Norbert; et al. (Micro-Optics, VCSELs, and Photonic Interconnects II: Fabrication, Packaging, and Integration, 2006)
The correspondence between the linear integral transform and the ray-transfer matrix of a diffraction-free first-order optical system is used to describe the ray trajectory and to study the point spread function (PSF) in an active GRIN microlens characterized by a complex refractive index. The results show that the active microlens is regarded as a lossless microlens with a Gaussian mask induced by the complex refractive index. Comparison between light propagation effects in passive and active GRIN microlens is outlined.
Keywords: Active material; GRIN optics; PSF; Ray-tracing

Limits of Optical Range Sensors and How to Exploit Them - Häusler, Gerd; et al. (Trends in Optics and Phototonics, 1999)
UnivIS-Import:2015-04-20:Pub.1999.nat.dphy.optik.1optik.limits

Linear and nonlinear experiments in PT-Symmetric photonic mesh lattices - Wimmer, Martin; Christodoulides, Demetrios; Peschel, Ulf (Parity-time Symmetry and Its Applications, 2018)
Photonic mesh lattices provide a versatile experimental platform for studying light propagation in a discrete environment. By using standard telecommunication equipment it is possible to influence the evolution of light by actively modulating its amplitude and phase. Fiber components thus offer a ready to use solution for creating a PT -symmetric optical network. Here, we analyze two classes of PT -symmetric networks: Those with local PT symmetry fulfilling the conditions of PT symmetry in each time step but not globally and those with global PT symmetry providing completely real eigenvalues. We investigate light propagation in these dissipative media in the linear and nonlinear regime and discuss nonlinear localization as well as the formation of soliton. Furthermore, Bloch oscillations are induced by an external phase modulation and are found to restore pseudo-Hermitian propagation.
CRIS-Team Scopus Importer:2023-04-20

Localization and registration of 3D-objects in space - where are the limits? - Häusler, Gerd; et al. (Applied Optics, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.locali

Localizing Eavesdroppers Inside a Quantum Channel Using Stimulated Brillouin Scattering - Popp, Alexandra; Stiller, Birgit; Marquardt, Christoph (2023 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC), 2023)
While modern communication systems pose a high standard of security using state-of-the-art encryption techniques based on computational hardness problems, quantum key distribution (QKD) offers a unique advantage using the laws of quantum mechanics. A secret key is shared between two parties, using quantum states of light over a quantum channel. Due to the quantum nature of the states, any interception or other way of eavesdropping will manifest in the distortion of the quantum state resulting in a change of accessible parameters. Whenever such a change of parameters is noticed, the shared key is marked unsecure and hashed down largely or, in the worst case, discarded.<br
Keywords: Quantum computing; Quantum channels; Europe; Quantum state; Distortion; Quantum key distribution; Encryption

Local sampling of the SU(1,1) Wigner function - Fabre, Nicolas; Klimov, Andrei B.; Leuchs, Gerd; Sánchez-Soto, Luis L. (AVS Quantum Science, 2023)
Despite its indisputable merits, the Wigner phase-space formulation has not been widely explored for systems with SU(1,1) symmetry, as a simple operational definition of the Wigner function has proved elusive in this case. We capitalize on unique properties of the parity operator, to derive in a consistent way a bona fide SU(1,1) Wigner function that faithfully parallels the structure of its continuous-variable counterpart. We propose an optical scheme, involving a squeezer and photon-number-resolving detectors, that allows for direct point-by-point sampling of that Wigner function. This provides an adequate framework to represent SU(1,1) states satisfactorily.
CRIS-Team Scopus Importer:2023-03-03

Local wave fronts at diffractive elements - Lindlein, Norbert; et al. (Journal of the Optical Society of America A: Optics and Image Science, and Vision, 1993)
Equations for calculating the principal curvatures and principal directions of local wave fronts in an optical system that consists of diffractive curved or plane surfaces between isotropic and homogeneous media are presented. The equations for refractive and reflecting surfaces are obtained as special cases of the equations for diffractive surfaces. This method is a kind of generalized ray tracing and permits an easy determination of the position of the local focus or the position and direction of the local focal lines in the case of local astigmatism; it must be emphasized that elements and systems with spherical aberration or coma also have local astigmatism. © 1993 Optical Society of America.

Long distance free-space propagation of light carrying orbital angular momentum - Lavery, Martin P.J.; Peuntinger, Christian; Günthner, Kevin; Bauer, Thomas; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2016)
We present analysis of the technical challenges facing deployment of longdistance free-space links employing orbital angular momentum multiplexing. Our analysis indicates atmospheric mitigation techniques, and modal purity are important consideration for system design.
CRIS-Team Scopus Importer:2022-06-05

Lossless propagation of magnetic dipole excitations on chains of dielectric particles with high refractive index - Zhuromskyy, Oleksandr; Peschel, Ulf (Physical Review B, 2014)
Lossless propagation of longitudinal magnetic dipole waves along chains of high-index subwavelength particles is predicted for a narrow frequency range around the magnetic Mie resonance of the individual particles. Mathematical analogies between dipole and magnetoinductive waves are used to reduce back-reflections thus improving the power transfer efficiency of respective particle waveguides. The proposed technique can be used to optimize the propagation of even more complex particle-based configurations.
EAM Import::2019-03-12

Lower bounds for the time-bandwidth product of a single-photon pulse - Averchenko, V.; Reiß, D. A.; Sych, D.; Leuchs, Gerd (Physica Scripta, 2020)
Two complementary properties, such as frequency and duration of a pulse, cannot be precisely measured simultaneously. The lower bound on the time-bandwidth product, known also as uncertainty relation, plays a very important role in quantum theory. In this work, we consider single-photon pulses with arbitrary temporal and spectral profiles, and derive a lower bound for the single-photon time-bandwidth product. We investigate how this bound depends on the modal purity, the single-mode fidelity, and the effective number of modes. Our results can be used to solve the inverse problem, namely, to estimate characteristics of the single-photon pulse based on the time-bandwidth product obtained from temporal and spectral measurements of the pulse.
CRIS-Team Scopus Importer:2020-03-06

Low-threshold optical parametric oscillations in a whispering gallery mode resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique Alexander; Aiello, Andrea; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2010)
In whispering gallery mode (WGM) resonator light is guided by continuous total internal reflection along a curved surface. Fabricating such resonators from an optically nonlinear material one takes advantage of their exceptionally high quality factors and small mode volumes to achieve extremely efficient optical frequency conversion. Our analysis of the phase-matching conditions for optical parametric down-conversion (PDC) in a spherical WGM resonator shows their direct relation to the sum rules for photons' angular momenta and predicts a very low parametric oscillation threshold. We realized such an optical parametric oscillator (OPO) based on naturally phase-matched PDC in lithium niobate. We demonstrated a single-mode, strongly nondegenerate OPO with a threshold of 6.7μW and linewidth under 10 MHz. This work demonstrates the remarkable capabilities of WGM-based OPOs. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Making Diffraction Limited Refractive Microlenses of Spherical and Elliptical Form - Lindlein, Norbert; et al. (EOS Topical Meetings Digest Series, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.making

Management of spontaneous enophthalmos due to silent sinus syndrome: a case report - Nkenke, Emeka; Alexiou, Christoph; Iro, Heinrich; Amann, Kerstin Ute; Kirchner, Thomas; Häusler, Gerd; Neukam, Friedrich Wilhelm; Holbach, Benedict (International Journal of Oral and Maxillofacial Surgery, 2005)
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.manage

Manufacturing of Polymer Optical Waveguides for 3D-Opto-MID: Review of the OPTAVER Process - Hamjah, Mohd Khairulamzari; Zeitler, Jochen; Eiche, Yannic; Lorenz, Lukas; Backhaus, Carsten; Hoffmann, Gerd Albert; Wienke, Alexander; Kaierle, Stefan; Overmeyer, Ludger; Lindlein, Norbert; Bock, Karlheinz; Franke, Jörg (2021 14th International Congress: Molded Interconnect Devices, MID 2021 - Proceedings, 2021)
In order to meet the increasing demand for data transmission over short distances of up to 100 m, the Optical Assembly and Connection Technology for ComponentIntegrated Bus Systems (OPTAVER) research group, funded by the German Research Foundation (DFG), developed a process for the additive manufacturing of three-dimensional optical waveguides. The research group focuses on design and modeling, simulation, and manufacturing polymer optical waveguides to produce 3D-Opto-Mechatronic-Integrated Devices (3D-Opto-MID). Inside 3D-Opto-MID, an optical coupler is presented based on an asymmetrical coupling principle. This paper reviews the entire process chain and the corresponding research results of the OPTAVER process.
CRIS-Team Scopus Importer:2021-03-26
Keywords: 3D-Opto-MID; aerosol jet printing; asymmetrical optical bus coupling; flexographic printing; functionalization; printed multimode waveguides; Raytracing; wave propagation method

Many-Body Quantum Dynamics of Polarization Squeezing in Optical Fibers - Leuchs, Gerd; et al. (Physical Review Letters, 2006)
We report new experiments that test quantum dynamical predictions of polarization squeezing for ultrashort photonic pulses in a birefringent fiber, including all relevant dissipative effects. This exponentially complex many-body problem is solved by means of a stochastic phase-space method. The squeezing is calculated and compared to experimental data, resulting in excellent quantitative agreement. From the simulations, we identify the physical limits to quantum noise reduction in optical fibers. The research represents a significant experimental test of first-principles time-domain quantum dynamics in a one-dimensional interacting Bose gas coupled to dissipative reservoirs. © 2006 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.manybo

M-ary phase shift keying receiver beating the standard quantum limit for any signal power - Müller, Christian R.; Leven, Andreas; Bülow, Henning; Schmalen, Laurent; Leuchs, Gerd; Marquardt, Christoph (European Conference on Optical Communication, ECOC, 2014)
We analyze a novel quantum receiver for M-ary phase-shift keyed signals that outperforms the standard quantum limit for any signal power. We provide a detailed analysis of its robustness against realistic imperfections and discuss the achievable mutual information.
CRIS-Team Scopus Importer:2022-06-05

Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Neukam, Johannes; Bielke, Thorsten; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Journal of Physics : Conference Series, 2011)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as better characterization of the process by quantitatively evaluating the important parameter - the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.masstr_3

Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Defect and Diffusion Forum, 2012)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as a better characterization of the process by quantitative evaluation of the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity in to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized. © (2012) Trans Tech Publications.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.masstr
Keywords: Diffusion coefficient; Microgravity; Shearing-interferometer; Supercritical carbon dioxide

Maximizing the electric field strength in the foci of high numerical aperture optics - Sondermann, Markus; Lindlein, Norbert; Leuchs, Gerd (arXiv, 2008)

Measurement devices with and for micro-optics at the university of Erlangen - Lindlein, Norbert; et al. (Proceedings of SPIE, 1998)
Several devices for the measurement of micro-optical elements will be presented. These are a Mach-Zehnder interference microscope for the measurement of the wave aberrations of microlenses in transmission using a HeNe laser (633nm wavelength) and a shearing interferometer for the measurement of microlenses in transmission in the near infrared (1319nm). This shearing interferometer uses two Ronchi gratings to provide a lateral shear and is therefore very compact and stable. We also describe a Twyman-Green interference microscope for the measurement of (nearly) spherical surfaces in reflection using partially coherent illumination. Microlenses can be also used to build measurement devices for micro- and macro-optics. We will present a Shack-Hartmann wavefront sensor with microlenses for the measurement of quite arbitrary wavefronts and a confocal set-up which uses an array of microlenses and stops to provide a confocal measurement without a lateral scanning of the object. This confocal setup can be used to measure the surface profile of micro-optical structures like gratings or microlenses.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.measur
Keywords: Confocal microscope; Mach-Zehnder interferometer; Measurement devices for micro-optical elements; Microlenses; Shack-Hartmann wavefront sensor; Shearing interferometer; Twyman-Green interferometer

Measurement of atmospheric neutrino mixing with improved IceCube DeepCore calibration and data processing - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2023)
We describe a new data sample of IceCube DeepCore and report on the latest measurement of atmospheric neutrino oscillations obtained with data recorded between 2011-2019. The sample includes significant improvements in data calibration, detector simulation, and data processing, and the analysis benefits from a sophisticated treatment of systematic uncertainties, with significantly greater level of detail since our last study. By measuring the relative fluxes of neutrino flavors as a function of their reconstructed energies and arrival directions we constrain the atmospheric neutrino mixing parameters to be sin2θ23=0.51±0.05 and Δm322=2.41±0.07×10-3 eV2, assuming a normal mass ordering. The errors include both statistical and systematic uncertainties. The resulting 40% reduction in the error of both parameters with respect to our previous result makes this the most precise measurement of oscillation parameters using atmospheric neutrinos. Our results are also compatible and complementary to those obtained using neutrino beams from accelerators, which are obtained at lower neutrino energies and are subject to different sources of uncertainties.
CRIS-Team Scopus Importer:2023-08-25

Measuring Microwave Frequency Radiation at the Quantum Noise Limit - Eichler, Christopher (Conference on Mesoscopic Transport and Quantum Coherence 2017, 2017)
Electromagnetic radiation at microwave frequencies couples to a variety of systems ranging from electrical over mechanical to spin degrees of freedom. Engineered solid state devices facilitate thea controlled isolation of such modes on the single particle level and their strong interaction with individual microwave frequency photons. The sensitive detection and characterization of such photons is thus of central importance, which has propelled the development of quantum limited parametric amplifiers and more recently also photo detectors. In my talk I will discuss advances in the low noise amplification of microwave frequency radiation [1] and present their application in various experimental settings, including the sensitive detection of electron spin resonance [2], the fast and high fidelity readout of superconducting qubits [3], and the implementation of quantum variational algorithms [4]. [1] Eichler et al., Phys. Rev. Lett. 113, 110502 (2014); [2] Eichler et al., Phys. Rev. Lett. 118, 037701 (2017); [3] Walter et al., Phys. Rev. Applied 7, 054020 (2017); [4] Eichler et al., Phys. Rev. X 5, 041044 (2015).
Keywords: wwwqudev

Measuring microwave photon correlations with quantum limited amplifiers - Eichler, Christopher (invited talk by Yasunobu Nakamura, 2014)

Measuring the Kerr-nonlinearity of Ag in plasmonic nano-circuits - Kriesch, Arian; Pfeifer, Hannes; Burgos, Stanley P.; Ploss, Daniel; Banzer, Peter; Atwater, Harry A.; Peschel, Ulf (Nonlinear Optics 2013, 2013)
We observe nonlinear switching of ultrashort (600fs) laser pulses in subwavelength plasmonic nanocircuits. This allows us to experimentally determine the third-order nonlinear coefficient of silver.
EAM Import::2019-03-12

Measuring the modulus of the spatial coherence function using an error tolerant phase shifting algorithm - Rothau, Sergej; Schwider, Johannes; Harder, Irina (117. Annual Meeting of the DGaO, 2016)

Measuring the temperature and heating rate of a single ion by imaging - Srivathsan, Bharath; Fischer, Martin; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (New Journal of Physics, 2019)

Mehr Sicherheit durch Quantenschlüssel - Leuchs, Gerd; et al. (Zeitschrift für Physik, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.mehrsi

Mehrwellenlängen-Interferometrie zur absoluten Abstandsmessung und 3D-Bildgebung - Leuchs, Gerd; et al. (Technisches Messen, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.mehrwe

Messen ohne Auszuspannen - Langer Lasertaster für Schleifmaschinen - Leuchs, Gerd; et al. (Kontrolle : Qualitätssicherung in der Produktion, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.messen

Methods and stability tests associated with the sterile neutrino search using improved high-energy νμ event reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We provide supporting details for the search for a 3+1 sterile neutrino using data collected over 10.7 years at the IceCube Neutrino Observatory. The analysis uses atmospheric muon-flavored neutrinos from 0.5 to 100 TeV that traverse Earth to reach the IceCube detector and finds a best-fit point at sin2(2θ24)=0.16 and Δm412=3.5 eV2 with a goodness-of-fit p value of 12% and consistency with the null hypothesis of no oscillations to sterile neutrinos with a p value of 3.1%. Several improvements were made over past analyses, which are reviewed in this article, including upgrades to the reconstruction and the study of sources of systematic uncertainty. We provide details of the fit quality and discuss stability tests that split the data for separate samples, comparing results. We find that the fits are consistent between split datasets.
CRIS-Team Scopus Importer:2024-11-29

Metrical calibration of a Phase measuring triangulation sensors - Häusler, Gerd; et al. (Proceedings of the Vision Modeling and Visualization Conference 2001, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.metric

Micro-cylinder-lens testing using computer-generated holograms - Mantel, Klaus Peter; Lamprecht, Jürgen; Lindlein, Norbert; Schreiner, Roland; Schwider, Johannes; Ferstl, Manfred (Fringe 2001, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.microc

Microdeflectometry - a novel tool to acquire three-dimensional microtopography with nanometer height resolution - Häusler, Gerd; Richter, Claus; Leitz, Karl-Heinz; Knauer, Markus C. (Optics Letters, 2008)
We introduce "microdeflectometry," a novel technique for measuring the microtopography of specular surfaces. The primary data are the local slope of the surface under test. Measuring the slope instead of the height implies high information efficiency and extreme sensitivity to local shape irregularities. The lateral resolution can be better than 1 μm, whereas the resulting height resolution is in the range of 1 nm. Microdeflectometry can be supplemented by methods to expand the depth of field, with the potential to provide quantitative 3D imaging with scanning-electron-microscope-like features. © 2008 Optical Society of America.
LFT Import::2019-07-29 (1515)

Microlens laser beam homogenizer - From theory to application - Zimmermann, Maik; Lindlein, Norbert; Völkl, Ralf; Weible, Ken (Laser Beam Shaping VIII, 2007)
Many applications in laser manufacturing like semiconductor lithography, micro-machining, micro-structuring or material-analysis require a homogeneous intensity distribution of the laser beam over its complete profile. Refractive and diffractive beam homogenizer solutions have been developed for this challenge, but their applicability strongly depends on the physics of the individual laser beam. This paper investigates the influence of laser beam properties like spatial coherence for microlens beam homogenizers. Diffraction at the small lens apertures and interference effects of periodic arrays are explained by using diffraction theory. Different microlens beam homogenizer configurations are presented. Design considerations that might be helpful for the layout of a specific microlens beam homogenizer system are discussed. It is shown that, among other factors, the Fresnel number is the most important quantity to characterize the influence of diffraction effects on microlens laser beam homogenizers. The influence of the spatial partial coherence will be explained for the example of a Fly's eye condenser. For cw laser sources, the influence of a rotating diffuser plate on grating interference and speckles effects is investigated. Finally, the theory will be compared to some practical examples in planar laser measurement techniques, in combustion diagnostics and micromachining with Excimer laser
LFT Import::2019-08-05 (1478)
Keywords: Coherence; Diffraction; Diffuser; Flat-top; Homogenizer; Laser; Microlens; Shaping

Microresonator Soliton Frequency Combs Enabled by Quintic Dispersion - Bi, Toby; Zhang, Shuangyou; Hill, Lewis; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Recent advances in fabrication and precision measurement techniques for dispersion engineering have enabled soliton frequency combs to operate in the near-zero GVD regime in microresonators [1,2]. These particular frequency combs are phase-matched through higher-order dispersion, usually via third-order dispersion. With low variation in the resonator mode spacing and the emission of dispersive waves, near-zero GVD frequency combs are able to cover a broad frequency range. In this work, we present near-zero GVD solitons experimentally generated in a microresonator using a continuous-wave (CW) source where the dominant higher-order dispersion term is fifth-order (5th-OD). We also numerically verify the existence of 5th-OD enabled solitons. This constitutes the first observation of near-zero GVD solitons pumped by a CW laser and the first observation of generated solitons dominated by fifth-order dispersion (FiOD) [3].
CRIS-Team Scopus Importer:2024-12-16

Microscale Generation of Entangled Photons without Momentum Conservation - Okoth, Cameron; Cavanna, Andrea; Santiago-Cruz, T.; Chekhova, Maria (Physical Review Letters, 2019)
We report, for the first time, the observation of spontaneous parametric down-conversion (SPDC) free of phase matching (momentum conservation). We alleviate the need to conserve momentum by exploiting the position-momentum uncertainty relation and using a planar geometry source, a 6 μm thick layer of lithium niobate. Nonphase-matched SPDC opens up a new platform on which to investigate fundamental quantum effects but it also has practical applications. The ultrasmall thickness leads to a frequency spectrum an order of magnitude broader than that of phase-matched SPDC. The strong two-photon correlations are still preserved due to energy conservation. This results in ultrashort temporal correlation widths and huge frequency entanglement. The studies we make here can be considered as the initial steps into the emerging field of nonlinear quantum optics on the microscale and nanoscale.
CRIS-Team Scopus Importer:2020-02-21

Microsphere kinematics from the polarization of tightly focused nonseparable light - Berg-Johansen, Stefan; Neugebauer, Martin; Aiello, Andrea; Leuchs, Gerd; Banzer, Peter; Marquardt, Christoph (Optics Express, 2021)
Recently, it was shown that vector beams can be utilized for fast kinematic sensing via measurements of their global polarization state [Optica 2, 864 (2015)]. The method relies on correlations between the spatial and polarization degrees of freedom of the illuminating field which result from its nonseparable mode structure. Here, we extend the method to the nonparaxial regime. We study experimentally and theoretically the far-field polarization state generated by the scattering of a dielectric microsphere in a tightly focused vector beam as a function of the particle position. Using polarization measurements only, we demonstrate position sensing of a Mie particle in three dimensions. Our work extends the concept of back focal plane interferometry and highlights the potential of polarization analysis in optical tweezers employing structured light.
CRIS-Team Scopus Importer:2021-04-30

Microwave Quantum Optics with Superconducting Circuits: From Quantum Variational Algorithms to Sensitive Electron Spin Resonance (ESR) Measurements - Eichler, Christopher (Resonator QED Conference, 2017)
The high level of control achievable over quantized degrees of freedom has turned superconducting circuits into one of the prime physical architectures for quantum computing and simulation. Along with the continuing progress towards building a universal quantum computer, the availability of small-scale quantum devices has raised interest in hybrid quantum-classical algorithms, in which the power of quantum computation is combined with classical optimization [1]. In my talk, I will present an experimental realization of this idea based on the controlled generation of matrix product states (MPS) – a class of states which has proven extremely powerful as a variational ansatz for numerical simulations. The correlation properties of these states are used to experimentally find the ground state of an interacting Bose gas confined in one dimension [2]. Our findings reveal interesting connections between the physics of cavity QED, solid state theory, and quantum information science. Extensions of the presented approach may be envisaged to also explore dynamical phenomena and discrete lattice models, offering interesting interdisciplinary perspectives. Technologically crucial for our experiments have been the development of quantum limited amplifiers [3] and the ability to measure photon statistics in the microwave frequency range [4]. Apart from being essential in our quest to build a practical quantum simulation platform, these technologies turn out very useful for exploring other systems such as spins and electrons in semiconductors [5,6]. [1] S. Barret et al., PRL 110, 090501 (2013), J.R. McClean et al., NJP 18, 023023, (2016) [2] C. Eichler et al., Phys. Rev. X 5, 041044 (2015) [3] C. Eichler et al. Phys. Rev. Lett. 106, 220503 (2011), C. Eichler et al. PRA 86, 032106 (2012) [4] C. Eichler et al., PRL 113, 110502 (2014), C. Eichler et al., PRL 107, 113601 (2011) [5] Y. Liu, et al., Science 347, 258 (2015), J. Stehlik et al., Phys. Rev. Applied 4, 014018 (2015) [6] Eichler et al., Phys. Rev. Lett. 118, 037701 (2017)
Keywords: wwwqudev

Mimicking chiral light-matter interaction - Nechayev, Sergey; Banzer, Peter (Physical Review B, 2019)
We demonstrate that achiral electric-dipole scatterers can mimic an interaction of light with chiral matter by generating far-field circular polarization upon scattering, even though the optical chirality of the incident field as well as that of the scattered light is zero. On the one hand, the presented effect originates from the fact that electric-dipole scatterers respond selectively only to the incident electric field, which eventually results in depolarization of the transmitted beam and in generation of far-field circular polarization. On the other hand, although the incident beam does not possess any optical chirality, it lacks reflection symmetry and therefore it is geometrically chiral. To experimentally demonstrate this effect, we utilize a cylindrical vector beam with spiral polarization and a spherical gold nanoparticle positioned on the optical axis-the axis of rotational symmetry of the system. Our experiment and a simple theoretical model address the fundamentals of duality symmetry in optics and chiral light-matter interactions, accentuating their richness and ubiquity yet in highly symmetric configurations.
CRIS-Team WoS Importer:2019-06-25

Misalignment effects of the Shack-Hartmann sensor - Lindlein, Norbert; et al. (Applied Optics, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.misali

Misalignment effects of the shack–hartmann sensor - Lindlein, Norbert; et al. (Applied Optics, 1998)
The Shack–Hartmann sensor uses a microlens array and a CCD camera for wave–front measurements. To obtain wave–front measurements with high accuracy, an accurate relative alignment of both is essential. The different states of misalignment of the Shack–Hartmann sensor are divided into groups and are treated theoretically and experimentally. Their effect on the accuracy of wave–front measurements is evaluated. In addition, a practical method for proper alignment of the Shack–Hartmann sensor is proposed. © 1998 Optical Society of America.

Modeling and correction of fringe patterns in Doppler asymmetric spatial heterodyne interferometry - Wei, Daikang; Gong, Qiucheng; Chen, Qiuyu; Zhu, Yajun; Kaufmann, Martin; Olschewski, Friedhelm; Knieling, Peter; Dötzer, Florian; Mantel, Klaus; Xu, Jiyao; Koppmann, Ralf; Riese, Martin (Applied Optics, 2022)
Doppler asymmetric spatial heterodyne (DASH) interferometry is a novel concept for observing atmospheric winds. This paper discusses a numerical model for the simulation of fringe patterns and a methodology to correct fringe images for extracting Doppler information from ground-based DASH measurements. Based on the propagation of optical waves, the fringe pattern was modeled considering different angular deviations and optical aberrations. A dislocation between two gratings can introduce an additional spatial modulation associated with the diffraction order, which was seen in laboratory measurements. A phase correction is proposed to remove phase differences between different row interferograms, which is the premise for calculating the average interferogram to improve the signal-to-noise ratio. Laboratory tests, simulation results, and Doppler velocity measurements indicate that a matrix determined in the laboratory can be applied to correct interferograms obtained from ground-based DASH measurements.
CRIS-Team Scopus Importer:2024-12-16

Modeling, Simulation and Manufacturing of Polymer Optical Waveguides by Using the OPTAVER Process - Reitberger, Thomas; Zeitler, Jochen; Backhaus, Carsten; Hoffmann, Gerd-Albert; Wienke, Alexander; Lorenz, Lukas; Bock, Karlheinz; Wolter, Klaus-Jürgen; Suttmann, Oliver; Overmeyer, Ludger; Lindlein, Norbert; Franke, Jörg (Applied Industrial Optics: Spectroscopy, Imaging and Metrology 2019, 2019)
This paper shows the modeling, simulation and production of polymer optical waveguides using the OPTAVER process. The additive manufactured multimode waveguides with their typical cross-section of a circle shape are of low cost and high-performance.<br

Modeling the dielectric function of degenerately doped ZnO: Al thin films grown by ALD using physical parameters - Latzel, Michael; Göbelt, Manuela; Brönstrup, Gerald; Venzago, Cornel; Schmitt, W.; Sarau, George; Christiansen, Silke (Optical Materials Express, 2015)
Transparent conductive thin films are a key building block of modern optoelectronic devices. A promising alternative to expensive indium containing oxides is aluminum doped zinc oxide (AZO). By correlating spectroscopic ellipsometry and photoluminescence, we analyzed the contributions of different optical transitions in AZO grown by atomic layer deposition to a model dielectric function (MDF) over a wide range of photon energies. The derived MDF reflects the effects of the actual band structure and therefore describes the optical properties very accurately. The presented MDF is solely based on physically meaningful parameters in contrast to empirical models like e.g. the widely used Sellmeier equation, but nevertheless real and imaginary parts are expressed as closed-form expressions. We analyzed the influence of the position of the Fermi energy and the Fermi-edge singularity to the different parts of the MDF. This information is relevant for design and simulation of optoelectronic devices and can be determined by analyzing the results from spectroscopic ellipsometry.

Mode structure and photon number correlations in squeezed quantum pulses - Leuchs, Gerd; et al. (Physical Review A, 2002)
Knowing the answer to the question of what is the complete quantum description of a pulse would be very helpful in quantum information processing: one could fully utilize the squeezing and entanglement properties of the sources. After forming a soliton pulse in a fiber, one can determine its multimode quantum state in the most comprehensive way. Hence, one can then optimize the medium properties to achieve maximum squeezing, or the maximum purity of an entangled state.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.modest

Modifications of the coherence radar for in vivo profilometry in dermatology - Häusler, Gerd; et al. (SPIE j, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.modifi

Möglichkeiten und Grenzen optischer 3D-Sensoren in der industriellen Praxis - Häusler, Gerd (Optische Messtechnik an diffus reflektierenden Medien, 1997)
UnivIS-Import:2015-04-20:Pub.1997.nat.dphy.optik.1optik.mglich

Molecular Mie model for second harmonic generation and sum frequency generation - Wunderlich, Sarina; Schürer, Benedikt; Sauerbeck, Christian; Peukert, Wolfgang; Peschel, Ulf (Physical Review B, 2011)
A theoretical model to simulate second harmonic and sum frequency generation from stratified spherical particles of arbitrary material is presented and compared with the widely used Rayleigh-Gans-Debye approximation and to experimental results from polystyrene particles with adsorbed malachite green molecules. In this model, the nonlinear polarization is caused by individual dipoles placed in the vicinity of the sphere and is simulated on a molecular basis. This offers greater flexibility to model more sophisticated systems.

More Than 34 dB Backscattering Suppression in Microresonators - Svela, Andreas O.; Silver, Jonathan M.; Del Bino, Leonardo; Zhang, Shuangyou; Woodley, Michael T.M.; Vanner, Michael R.; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Optical modes in whispering-gallery-mode (WGM) resonators generally come in pairs of degenerate modes with opposite propagation directions: a clockwise and a counter-clockwise mode. However, sub-wavelength-size imperfections on the surface and in the bulk material of the resonators, usually cause some amount of Rayleigh scattering between the modes [1]. For sufficiently high levels of backscattering, the coupling between the modes can be observed as a resolvable splitting in the frequency domain [2]. Coupling of the modes is unfavourable for some WGM resonator applications, for example gyroscopes [3] , dual frequency combs [4] , and applications relying on symmetry breaking of counter-propagating light [5] , [6].
CRIS-Team Scopus Importer:2021-10-29

Multi-flavour neutrino searches from the Milky Way Galaxy - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
High-energy neutrinos are expected to be produced in the Milky Way by cosmic ray interactions at sites of acceleration or during their propagation. Neutrinos provide distinctive information on hadronic interactions and can be pointed back to production origins, unraveling unique properties of the Galaxy. We present an analysis on the search for the diffuse neutrino flux along the Galactic Plane by using data collected at the largest operating neutrino telescope in the world - the IceCube Neutrino Observatory. More than 10 years of data since the completion of the detector are used in this analysis. We utilize three event selections including through-going tracks, showers and starting-tracks to reach full-sky coverage and to be sensitive to all three neutrino flavours.
CRIS-Team Scopus Importer:2025-02-04

Multilevel amplitude and phase regeneration in a nonlinear amplifying loop mirror with a phase-sensitive amplifier - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2012)
A novel regenerator scheme for all-optical multilevel simultaneous amplitude and phase noise suppression is proposed. For a star-8QAM signal, consisting of two amplitude and four phase states, EVM reduction is 4 dB and 2.5 dB for the high- and low-power states, respectively. The limiting effects of the regenerator performance have been considered.
lhft_intern.bib::Roethlingshoefer2012cb

Multilevel Phase-Preserving Amplitude Regeneration Using a Single Nonlinear Amplifying Loop Mirror - Hierold, Martin; Roethlingshoefer, Tobias; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2011)
lhft_intern.bib::Hierold2011

Multimode Quantum Correlations - Leuchs, Gerd; et al. (Coherence and Statistics of Photons and Atoms, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dphy.optik.1optik.multim

Multi-pass Shack-Hartmann planeness test: monitoring thermal stress - Schwider, Johannes; Leuchs, Gerd (Optics Express, 2010)

Multiphoton effects with bright squeezed vacuum - Kopylov, D. A.; Spasibko, K. Yu; Cutipa, P.; Murzina, T. V.; Chekhova, Maria (Optics InfoBase Conference Papers, 2020)
Light generated through strongly pumped parametric down-conversion has extremely strong photon-number fluctuations and is therefore highly efficient for multiphoton effects. In addition, its spectral and spatial properties can be tailored to allow two-dimensional multiphoton spectroscopy.
CRIS-Team Scopus Importer:2020-11-13

Multiple-Wavelength Interferometry for Absolute Distance Measurement and Three-Dimentional Imaging - Leuchs, Gerd; et al. (Technisches Messen, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.multip

Multipolar hierarchy of efficient quantum polarization measures - De La Hoz, Pablo; Klimov, A. B.; Bjork, G.; Kim, Y. -H.; Mueller, C.; Marquardt, Christoph; Leuchs, Gerd; Sanchez-Soto, L. L.; Marquardt, Christoph (Physical Review A - Atomic, Molecular, and Optical Physics, 2013)
We advocate a simple multipole expansion of the polarization density matrix. The resulting multipoles appear as successive moments of the Stokes variables and can be obtained from feasible measurements. In terms of these multipoles we construct a whole hierarchy of measures that accurately assess higher-order polarization fluctuations. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Multi-stage spontaneous symmetry breaking of light in Kerr ring resonators - Hill, Lewis; Oppo, Gian Luca; Del'Haye, Pascal (Communications Physics, 2023)
Symmetry breaking of light states is of interest for the understanding of nonlinear optics, photonic circuits, telecom applications and optical pulse generation. Here we demonstrate multi-stage symmetry breaking of the resonances of ring resonators with Kerr nonlinearity. This multi-stage symmetry breaking naturally occurs in a resonator with bidirectionally propagating light with orthogonal polarization components. The derived model used to theoretically describe the system shows that the four circulating field components can display full symmetry, full asymmetry, and multiple versions of partial symmetry, and are later shown to result in complex oscillatory dynamics - such as four-field self-switching, and unusual pulsing with extended delays between subsequent peaks. To highlight a few examples, our work has application in the development of photonic devices like isolators and circulators, logic gates, and random numbers generators, and could also be used for optical-sensors, e.g. by further enhancing the Sagnac effect.
CRIS-Team Scopus Importer:2024-12-16

Multi-twist polarization ribbon topologies in highly-confined optical fields - Bauer, Thomas; Banzer, Peter; Bouchard, Frederic; Orlov, Sergej; Marrucci, Lorenzo; Santamato, Enrico; Boyd, Robert W.; Karimi, Ebrahim; Leuchs, Gerd (New Journal of Physics, 2019)
Electromagnetic plane waves, solutions to Maxwell's equations, are said to be 'transverse' in vacuum. Namely, the waves' oscillatory electric and magnetic fields are confined within a plane transverse to the waves' propagation direction. Under tight-focusing conditions however, the field can exhibit longitudinal electric or magnetic components, transverse spin angular momentum, or non-trivial topologies such as Mobius strips. Here, we show that when a suitably spatially structured beam is tightly focused, a three-dimensional polarization topology in the form of a ribbon with two full twists appears in the focal volume. We study experimentally the stability and dynamics of the observed polarization ribbon by exploring its topological structure for various radii upon focusing and for different propagation planes.
CRIS-Team WoS Importer:2019-05-24

Mutually unbiased bases and generalized Bell states - Leuchs, Gerd; et al. (Physical Review A, 2009)
We employ a straightforward relation between mutually unbiased and Bell bases to extend the latter in terms of a direct construction for the former. We analyze in detail the properties of these generalized Bell states, showing that they constitute an appropriate tool for testing entanglement in bipartite multiqudit systems. © 2009 The American Physical Society.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.mutual

Nanobore PCF maintaining cylindrically polarized modes - Euser, T. G.; Joly, N. Y.; Gabriel, C.; Marquardt, Christoph; Zang, L. Y.; Banzer, P.; Brenn, A.; Elser, D.; Förtsch, M.; Rammler, S.; Scharrer, M.; Leuchs, Gerd; et al. (Optics InfoBase Conference Papers, 2010)
A nanoscale hole placed centrally in the core of a PCF breaks the degeneracy between radially and azimuthally polarized modes, causing a large splitting in phase velocity, group velocity and dispersion. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Nanoscale Conducting Oxide PlasMOStor - Lee, Ho W.; Papadakis, Georgia; Burgos, Stanley P.; Chander, Krishnan; Kriesch, Arian; Pala, Ragip; Peschel, Ulf; Atwater, Harry A. (Nano Letters, 2014)
We experimentally demonstrate an ultracompact PlasMOStor, a plasmon slot waveguide field-effect modulator based on a transparent conducting oxide active region. By electrically modulating the conducting oxide material deposited into the gaps of highly confined plasmonic slot waveguides, we demonstrate field-effect dynamics giving rise to modulation with high dynamic range (2.71 dB/ extgreekmm) and low waveguide loss (∼0.45 dB/ extgreekmm). The large modulation strength is due to the large change in complex dielectric function when the signal wavelength approaches the surface plasmon resonance in the voltage-tuned conducting oxide accumulation layer. The results provide insight about the design of ultracompact, nanoscale modulators for future integrated nanophotonic circuits.
EAM Import::2019-03-12

Nanoscale Vectorial Electric and Magnetic Field Measurement - Eismann, Jörg S.; Banzer, Peter (ACS Photonics, 2024)
In technology, old or new, from basic imaging through a camera lens to advanced applications such as fluorescence microscopy and optical lithography, there are countless examples that would be inconceivable without the utilization of focused light. As technology evolves, the demands on spatially confined light fields grow but so do the challenges of accurately characterizing these complex fields. This study introduces a technique to measure the full vectorial nature of light, reaching sub/wavelength spatial resolution while capturing the 3D amplitude and phase for both electric and magnetic fields. This is achieved based on a polarization-resolved far-field analysis of light scattered by a single spherical nanoparticle acting as a local probe. For experimental verification, the method is applied to tightly focused light fields under various input scenarios. Offering high resolution, precision, and flexibility, this technique shows great promise for both fundamental research and applications in technologies relying on highly localized light fields.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electromagnetic field metrology; nanoscale; scattering; tight focusing; vectorial fields

Naturally phase-matched second-harmonic generation in a whispering-gallery-mode resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique Alexander; Lassen, M.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2010)
We demonstrate for the first time natural phase matching for optical frequency doubling in a high-Q whispering-gallery-mode resonator made of lithium niobate. A conversion efficiency of 9% is achieved at 30μW in-coupled continuous wave pump power. The observed saturation pump power of 3.2 mW is almost 2 orders of magnitude lower than the state-of-the-art value. This suggests an application of our frequency doubler as a source of nonclassical light requiring only a low-power pump, which easily can be quantum noise limited. Our theoretical analysis of the three-wave mixing in a whispering-gallery-mode resonator provides the relative conversion efficiencies for frequency doubling in various modes. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Naturally phase matched second harmonic generation in a whispering gallery mode resonator - Fürst, Josef; Strekalov, Dmitry; Elser, Dominique Alexander; Lassen, Mikael; Andersen, Ulrik L.; Marquardt, Christoph; Leuchs, Gerd (Lasers and Electro-Optics/Quantum Electronics and Laser Science Conference: 2010 Laser Science to Photonic Applications, CLEO/QELS 2010, 2010)
We observed conversion efficiencies of 9% at 30 μW pump power in LiNbO3, as well as self-limiting effects at high powers. The continuous-wave pump at a wavelength of 1064nm and the second-harmonic feature Q > 107. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Near-Field Analysis of Bright and Dark Modes on Plasmonic Metasurfaces Showing Extraordinary Suppressed Transmission - Dobmann, Sabine; Kriesch, Arian; Ploss, Daniel; Peschel, Ulf (Advanced Optical Materials, 2014)
Plasmonic metasurfaces are investigated that consist of a sub-wavelength line pattern in an ultrathin ( 10 nm) silver film, designed for extraordinary suppressed transmission (EOST) in the visible spectral range. Measurements with a near-field scanning optical microscope (NSOM) demonstrate that farfield irradiation resonantly excites antenna-like (bright) modes that are localized on the metal ridges. The re-radiation of these modes into the far-field interferes destructively with the transmitted wave, thus suppressing transmission almost completely. In contrast, a second type of mode, bound (dark) surface plasmon polaritons (SPPs) launched from an NSOM tip, propagates well across the metasurface, preferentially perpendicular to the grating lines.
EAM Import::2019-03-12

Near-infrared single-photon spectroscopy of a whispering gallery mode resonator using energy-resolving transition edge sensors - Foertsch, Michael; Gerrits, Thomas; Stevens, Martin J.; Strekalov, Dmitry; Schunk, Gerhard; Fuerst, Josef U.; Vogl, Ulrich; Sedlmeir, Florian; Schwefel, Harald G. L.; Leuchs, Gerd; Nam, Sae Woo; Marquardt, Christoph (Journal of Optics, 2015)
We demonstrate a method to perform spectroscopy of near-infrared single photons without the need of dispersive elements. This method is based on a photon energy resolving transition edge sensor and is applied for the characterization of widely wavelength tunable narrow-band single photons emitted from a crystalline whispering gallery mode resonator. We measure the emission wavelength of the generated signal and idler photons with an uncertainty of up to 2 nm.
CRIS-Team Scopus Importer:2022-06-05
Keywords: boronitrene; graphene; nonlinear optics; sum-frequency generation

Neue Ergebnisse in der optischen Datengewinnung und der Weiterverarbeitung - Häusler, Gerd; et al. (Optische 3D-Formerfassung, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.neueer

New concept of a polymer optical ray splitter simulated by Raytracing with a new Bisection-Algorithm - Backhaus, Carsten; Dötzer, Florian; Hoffmann, Gerd-Albert; Lorenz, Lukas; Overmeyer, Ludger; Bock, Karlheinz; Lindlein, Norbert (Frontiers in Optics + Laser Science APS/DLS, 2019)
Recent fabrication methods print polymer optical waveguides (POWs) on three-dimensional carriers. The special geometry of the POWs enables the realisation of an optical ray splitter which is simulated by raytracing using a new bisection-algorithm.
Keywords: Laser light; Optical design; Polymer waveguides; Printed circuit boards; Ray tracing; Stray light

New insights into colloidal gold flakes: structural investigation, micro-ellipsometry and thinning procedure towards ultrathin monocrystalline layers - Hoffmann, B.; Bashouti, M. Y.; Feichtner, Thorsten; Mackovic, Mirza; Dieker, Christel; Salaheldin, A. M.; Richter, P.; Gordan, O. D.; Zahn, D. R. T.; Spiecker, Erdmann; Christiansen, S.; Hoffmann, Björn (Nanoscale, 2016)
High-quality fabrication of plasmonic devices often relies on wet-chemically grown ultraflat, presumably single-crystalline gold flakes due to their superior materials properties. However, important details about their intrinsic structure and their optical properties are not well understood yet. In this study, we present a synthesis routine for large flakes with diameters of up to 70 mu m and an in-depth investigation of their structural and optical properties. The flakes are precisely analyzed by transmission electron microscopy, electron backscatter diffraction and micro-ellipsometry. We found new evidence for the existence of twins extending parallel to the Au flake 111 surfaces which have been found to not interfere with the presented nanopatterning. Micro-Ellipsometry was carried out to determine the complex dielectric function and to compare it to previous measurements of bulk single crystalline gold. Finally, we used focused ion beam milling to prepare smooth crystalline layers and high-quality nanostructures with desired thickness down to 10 nm to demonstrate the outstanding properties of the flakes. Our findings support the plasmonics and nano optics community with a better understanding of this material which is ideally suited for superior plasmonic nanostructures.

New Modifications of the Coherence Radar - Häusler, Gerd; et al. (Proc. of the 3rd Int. Workshop on Automatic Processing of Fringe Patterns, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.newmod

New Range Sensors at the Physical Limit of Measuring Uncertainty - Häusler, Gerd; et al. (Proc. of the EOS Topical Meeting on Optoelectronics Distance Measurements and Applications, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.newran

Noise-free QND-measurement using optical solitons - Leuchs, Gerd; et al. (Physical Review A, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.noisef

Noise-powered probabilistic concentration of phase information - Usuga, Mario A.; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Leuchs, Gerd; Andersen, Ulrik L. (Nature Physics, 2010)
Phase-insensitive optical amplification of an unknown quantum state is known to be a fundamentally noisy operation that inevitably adds noise to the amplified state. However, this fundamental noise penalty in amplification can be circumvented by resorting to a probabilistic scheme as recently proposed and demonstrated in refs 6, 7, 8. These amplifiers are based on highly non-classical resources in a complex interferometer. Here we demonstrate a probabilistic quantum amplifier beating the fundamental quantum limit using a thermal-noise source and a photon-number-subtraction scheme. The experiment shows, surprisingly, that the addition of incoherent noise leads to a noiselessly amplified output state with a phase uncertainty below the uncertainty of the state before amplification. This amplifier might become a valuable quantum tool in future quantum metrological schemes and quantum communication protocols. © 2010 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

NOLM based DPSK Signal Regeneration - Striegler, Arne; Meißner, Markus; Cvecek, Kristian; Sponsel, Klaus; Leuchs, Gerd; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2005)
We present a nonlinear optical loop mirror (NOLM)-based 2R-regenerator setup, which is capable of regenerating signals modulated in phase-sensitive modulation formats. In a conventional NOLM, fluctuations of the signal amplitude are converted into phase fluctuations. Therefore, it is not suitable for regeneration of signals, modulated in formats such as differential phase-shift keying (DPSK) or duobinary. In this letter, we present a modified NOLM setup for 2R-regeneration taking return-to-zero DPSK as an example. © 2005 IEEE.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.nolmba
Keywords: All-optical regeneration; Differential phase-shift keying (DPSK); Nonlinear optical loop mirror (NOLM)

Non-classical light generated in a whispering gallery mode parametric oscillator - Förtsch, Michael; Schunk, G.; Fürst, J. U.; Strekalov, D. V.; Aiello, A.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
We present the generation of quantum correlated twin beams in a whispering gallery mode resonator made from lithium niobate and the first direct observation of amplitude squeezing for the single parametric beams. © 2011 AOS.
CRIS-Team Scopus Importer:2022-06-05

Noninvasive manipulation of the optical response of opal photonic crystals - Romanov, Sergei G.; Regensburger, Alois; Korovin, Alexander V.; Romanova, Alexandra; Peschel, Ulf (Physical Review B, 2013)
The efficient manipulation with optical spectra of colloidal photonic crystals was achieved using the metal mirror positioned either immediately or at a distance from the crystal surface. If the mirror is close to the surface, the changes are mostly quantitative and relate to the improved light confinement. If the spacer provides a 2 extgreekp phase shift for round trip of the light at the wavelength of the diffraction resonance of the opal lattice, the defect band is formed in the photonic stop-band leading to 20–40 times increase of the transmission. The upper limit of the quality factor of the defect band was estimated by extrapolating the development of the defect transmission band as a function of the photonic crystal thickness. The specific features related to the photonic crystal dimensionality were revealed in the defect band spectra. The obtained results support the idea of achieving the control on the optical functionality of photonic crystals by recycling the transmitted light in the crystal volume.
EAM Import::2019-03-08

Nonlinear enhanced microresonator gyroscope - Silver, Jonathan M.; Del Bino, Leonardo; Woodley, Michael T. M.; Ghalanos, George N.; Svela, Andreas O.; Moroney, Niall; Zhang, Shuangyou; Grattan, Kenneth T.; Del'Haye, Pascal (Optica, 2021)
Optical gyroscopes based on the Sagnac effect have been the mainstay of inertial navigation in aerospace and shipping for decades. These gyroscopes are typically realized either as ring-laser gyroscopes (RLGs) or fiber-optic gyroscopes (FOGs). With the recent rapid progress in the field of ultrahigh-quality optical whispering-gallery mode and ring microresonators, attention has been focused on the development of microresonator-based Sagnac gyroscopes as a more compact alternative to RLGs and FOGs. One avenue that has been explored is the use of exceptional points in non-Hermitian systems to enhance the responsivity to rotation. We use a similar phenomenon, namely, the critical point of a spontaneous symmetry-breaking transition between counterpropagating light, to demonstrate a microresonator gyroscope with a responsivity enhanced by a factor of around 10(4). We present a proof-of-principle rotation measurement as well as a characterization of the system's dynamical response, which shows the universal critical behaviors of responsivity enhancement and critical slowing down, both of which are beneficial in an optical gyroscope. We believe that this concept could be used to realize simple and cheap chip-based gyroscopes with sensitivities approaching those of today's RLGs and FOGs. (C) 2021 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2021-10-08

Nonlinear optics in crystalline: Whispering gallery resonators - Marquardt, Christoph; Strekalov, Dmitry V.; Fürst, Josef; Förtsch, Michael; Leuchs, Gerd (Optics and Photonics News, 2013)
CRIS-Team Scopus Importer:2022-06-05

Nonlinear optics with full three-dimensional illumination - Penjweini, Rojiar; Weber, Markus; Sondermann, Markus; Boyd, Robert W.; Leuchs, Gerd (Optica, 2019)

Nonlinear Phase Noise Compensation Using a Modified Nonlinear Optical Loop Mirror - Sponsel, K.; Stephan, C.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (OSA Optics and Photonics Congress, Advanced Photonics, BGPP Topical Meeting, Karlsruhe, 21.-24. Juni, 2010)
lhft_intern.bib::Sponsel10

Nonlinear Phase Noise Reduction in a DPSK Transmission System Using Cascaded Nonlinear Amplifying Loop Mirrors - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2009)
The performance of a nonlinear amplifying loop mirror as a phase-preserving amplitude 2R regenerator in a differential phase-shift-keying transmission system with nonlinear phase noise as dominant limiting effect has been investigated in a recirculating fiber-loop setup. The experimental results show that cascaded regenerators can efficiently prevent the accumulation of nonlinear phase noise in such systems. It was possible to significantly increase the transmission quality; alternatively, a considerable increase of fiber launch power could be achieved for the same bitor ratio. As a limiting effect, the amplified Rayleigh backscattering in the highly nonlinear fiber is identified when the regenerator is passed multiple times. © 2009 IEEE.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.nonlin
Keywords: 2r regeneration; Differential phase-shift keying (DPSK); Nonlinear amplifying loop mirror (NALM); Nonlinear phase noise

Nonlinear Phase-Shift Compensation by a Nonlinear Amplifying Loop Mirror - Schmauß, Bernhard; Sponsel, Klaus; Stephan, C.; Onishchukov, Georgy; Leuchs, Gerd (Conference on Lasers and Electro-Optics CLEO, Paper JThE59, San Jose, May, 2010)
The nonlinear amplifying loop mirror as a nonlinear phase-shift compensator for multilevel phase-encoded optical signals is considered. Simulations of a 20 Gb/s DQPSK transmission system showed a significant BER improvement for post-compensation.
lhft_intern.bib::Schmauss10a

Nonlinear power dependence of the spectral properties of an optical parametric oscillator below threshold in the quantum regime - Shafiee, Golnoush; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schunk, Gerhard; Vogl, Ulrich; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (New Journal of Physics, 2020)
Photon pairs and heralded single photons, obtained from cavity-assisted parametric down conversion (PDC), play an important role in quantum communications and technology. This motivated a thorough study of the spectral and temporal properties of parametric light, both above the optical parametric oscillator (OPO) threshold, where the semiclassical approach is justified, and deeply below it, where the linear cavity approximation is applicable. The pursuit of a higher two-photon emission rate leads into an interesting intermediate regime, between above OPO threshold and very low pump power, where the OPO still operates considerably below the threshold but the nonlinear cavity phenomena cannot be neglected anymore. Here, we investigate this intermediate regime and show that the spectral and temporal properties of the photon pairs, as well as their emission rate, may significantly differ from the widely accepted linear model. The observed phenomena include frequency pulling and broadening in the temporal correlation for the down-converted optical fields. These factors need to be taken into account when devising practical applications of the high-rate cavity-assisted spontaneous PDC sources.
CRIS-Team WoS Importer:2020-08-21

Nonlinear Quantum Optics in a Millimeter Size Whispering Gallery Mode Resonator - Leuchs, Gerd; Marquardt, Christoph; Schwefel, Harald (Nonlinear Optics, NLO 2015, 2015)
Whispering gallery resonators made from nonlinear crystals offer high quality factors combined with small mode volumes leading to an enhanced effective X(2) nonlinearity. These properties facilitate studying quantum optical effects in the nonlinear regime with interacting fields differing in frequency by up to four orders of magnitude. Furthermore, the small size results in a large mode spacing allowing for heralded single photon generation in a single mode
CRIS-Team Scopus Importer:2022-06-05

Nonlinear single sideband microwave to optical conversion using an electro-optic WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2016)
Nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band is achieved within a crystalline whispering gallery mode resonator, reaching 0.1% photon number conversion efficiency with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Non-null testing of aspherical surfaces by using a Shack-Hartmann sensor - Lindlein, Norbert; Pfund, Johannes; Schwider, Johannes (OSA Technical Digest, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dphy.optik.1optik.nonnul

Nonnull testing of rotationally symmetric aspheres: a systematic error assessment - Lindlein, Norbert; et al. (Applied Optics, 2001)
An optical setup for the testing of rotationally symmetric aspheres without a null optic is proposed. The optical setup is able to transfer the strongly curved wave fronts that stem from the reflection of a spherical testing wave front at a rotationally symmetric asphere. By simulation it is proved that the algorithms of the Shack-Hartmann sensor that is used can cope with the steep wave-front slopes (∼110λ/mm) in the detection plane. The systematic errors of the testing configuration are analyzed and separated. For all types of error, functionals are derived whose significance is proved by simulation. The maximum residual errors in the simulations are fewer than λ/500 (peak to valley). © 2001 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.nonnul

Nonparaxial polarizers - Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Optics Letters, 2009)
We develop a theoretical description for polarizers that goes beyond the paraxial approximation. By combining existing theories for fields with nonplanar wavefronts, we are able to derive a simple power series expansion expressing the electric field of a light beam after a polarizer as a linear function of the field and its spatial derivatives evaluated before the polarizer. The first few terms of such expansion are explicitly given, and their physical meaning is discussed. © 2009 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Non-phase matched spontaneous parametric down conversion in ultra-thin lithium niobate - Okoth, Cameron; Santiago, Tomás; Cavanna, Andrea; Chekhova, Maria (Optics InfoBase Conference Papers, 2019)
We report the generation of entangled photon pairs via type-0 spontaneous parametric down conversion in ultra-thin lithium niobate in which momentum between the.
CRIS-Team Scopus Importer:2019-07-09

Nonreciprocal vortex isolator via topology-selective stimulated Brillouin scattering - Zeng, Xinglin; Russell, Philip St. J.; Wolff, Christian; Frosz, Michael H.; Wong, Gordon Kwan Leung; Stiller, Birgit (Science Advances, 2022)
Optical nonreciprocity, which breaks the symmetry between forward and backward propagating optical waves, has become vital in photonic systems and enables many key applications. So far, all the existing nonreciprocal systems are implemented for linearly or randomly polarized fundamental modes. Optical vortex modes, with wavefronts that spiral around the central axis of propagation, have been extensively studied over the past decades and offer an additional degree of freedom useful in many applications. Here, we report a light-driven nonreciprocal isolation system for optical vortex modes based on topology-selective stimulated Brillouin scattering (SBS) in chiral photonic crystal fiber. The device can be reconfigured as an amplifier or an isolator by adjusting the frequency of the control signal. The experimental results show vortex isolation of 22 decibels (dB), which is at the state of the art in fundamental mode isolators using SBS. This device may find applications in optical communications, fiber lasers, quantum information processing, and optical tweezers.
CRIS-Team Scopus Importer:2022-11-04

Nonunity gain minimal-disturbance measurement - Leuchs, Gerd; et al. (Physical Review A, 2007)
We propose and experimentally demonstrate an optimal nonunity gain Gaussian scheme for partial measurement of an unknown coherent state that causes minimal disturbance of the state. The information gain and the state disturbance are quantified by the noise added to the measurement outcomes and to the output state, respectively. We derive the optimal trade-off relation between the two noises and we show that the tradeoff is saturated by nonunity gain teleportation. Optimal partial measurement is demonstrated experimentally using a linear optics scheme with feedforward. © 2007 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.nonuni

Non-unity gain quantum nondemolition measurements based on measurement and re-preparation - Leuchs, Gerd; et al. (Optics Letters, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.nonuni

Novel diagnostic and therapeutic techniques reveal changed metabolic profiles in recurrent focal segmental glomerulosclerosis - Müller-Deile, Janina; Sarau, George; Kotb, Ahmed M.; Jaremenko, Christian; Rolle-Kampczyk, Ulrike E.; Daniel, Christoph; Kalkhof, Stefan; Christiansen, Silke H.; Schiffer, Mario (Scientific Reports, 2021)
Idiopathic forms of Focal Segmental Glomerulosclerosis (FSGS) are caused by circulating permeability factors, which can lead to early recurrence of FSGS and kidney failure after kidney transplantation. In the past three decades, many research endeavors were undertaken to identify these unknown factors. Even though some potential candidates have been recently discussed in the literature, “the” actual factor remains elusive. Therefore, there is an increased demand in FSGS research for the use of novel technologies that allow us to study FSGS from a yet unexplored angle. Here, we report the successful treatment of recurrent FSGS in a patient after living-related kidney transplantation by removal of circulating factors with CytoSorb apheresis. Interestingly, the classical published circulating factors were all in normal range in this patient but early disease recurrence in the transplant kidney and immediate response to CytoSorb apheresis were still suggestive for pathogenic circulating factors. To proof the functional effects of the patient’s serum on podocytes and the glomerular filtration barrier we used a podocyte cell culture model and a proteinuria model in zebrafish to detect pathogenic effects on the podocytes actin cytoskeleton inducing a functional phenotype and podocyte effacement. We then performed Raman spectroscopy in the < 50 kDa serum fraction, on cultured podocytes treated with the FSGS serum and in kidney biopsies of the same patient at the time of transplantation and at the time of disease recurrence. The analysis revealed changes in podocyte metabolome induced by the FSGS serum as well as in focal glomerular and parietal epithelial cell regions in the FSGS biopsy. Several altered Raman spectra were identified in the fractionated serum and metabolome analysis by mass spectrometry detected lipid profiles in the FSGS serum, which were supported by disturbances in the Raman spectra. Our novel innovative analysis reveals changed lipid metabolome profiles associated with idiopathic FSGS that might reflect a new subtype of the disease.
CRIS-Team Scopus Importer:2021-03-19

Novel sources for polarisation squeezing and polarisation entanglement using photonic crystal fibres - Milanovic, Josip; Lassen, Mikael; Förtsch, Michael; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference, 2009)
CRIS-Team Scopus Importer:2022-06-05

Null-Test-Measurement of Cylindrical Microlenses in Transmitted Light - Lindlein, Norbert; et al. (VDI-Berichte, 2002)
A fiber optic Mach-Zehnder-interferometer is described, which allows the test of cylindrical microlenses with a high numerical aperture in transmitted light. The interferometer is working in the near infrared and uses diffractive optical elements as null lenses providing a reference cylindrical wave. The setup, the null-optic, the light source and a method to eliminate misalignment aberrations are described in detail and a typical measurement sequence is presented.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.nullte

Null test measurement of high-numerical aperture cylindrical micro lenses in transmitted light - Lindlein, Norbert; et al. (Optical Manufacturing and Testing V, 2003)
An interferometrical measurement method is presented for determining the quality of cylindrical micro lenses with a numerical aperture of up to 0.8 in transmitted light. In order to maximize the achievable accuracy, a null test configuration was chosen. The reference cylindrical waves are shaped by computer generated diffractive optical elements (DOEs), which are made by optical or e-beam lithography. The resulting wave front is analyzed by a fiber optic phase-shifting Mach-Zehnder-interferometer or a Shack-Hartmann wave front sensor. Besides the general setup, which is working in the near infrared (NIR), special aspects will be presented concerning the elimination of misalignment aberrations, the complete filtering of parasitic diffraction orders and the generation of an anamorphic optical transformation for increasing the lateral resolution perpendicular to the cylindrical axis. By means of experimental results the possibilities and accuracy of this technique are discussed.
Keywords: Cylindrical micro lens; Diffractive optics; Null test; Phase shifting interferometry

Observation of Entanglement between a superconducting Qubit and an Itinerant Microwave Field - Eichler, Christopher (2012)
The generation of entanglement between stationary qubits and propagating photons both enables the study of non-local effects in quantum mechanics and provides a resource for communication between different nodes in a quantum network. Qubit - photon entanglement has so far only been implemented at optical frequencies with single atoms or electron spins. Recent progress in the development of superconducting qubits and in the characterization of propagating microwave fields has also enabled exciting new quantum optics experiments using microwaves. Here, we present experiments in which we prepare and reconstruct the state of non-classical microwave fields by combining novel photon field characterization methods with efficient measurement techniques. We also demonstrate the generation of entangled states between a superconducting qubit and a photon field. Extracting all relevant correlations between the two systems we are able to reconstruct the full density matrix and to verify the entanglement of Bell type states and more complex ones.
Keywords: wwwqudev

Observation of high-energy neutrinos from the Galactic plane - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
IceCube has discovered a flux of astrophysical neutrinos and presented evidence for the first neutrino sources, a flaring blazar known as TXS 0506+056 and the active galaxy NGC 1068. However, the sources responsible for the majority of the astrophysical neutrino flux remain elusive. In addition to hypothetical sources within our Galaxy, high energy neutrinos are produced when cosmic rays interact at their acceleration sites and during propagation through the interstellar medium. The Galactic plane has therefore long been hypothesized as a neutrino source. In this contribution, new results are presented for searches of neutrino sources utilizing a dataset that builds upon recent advances in deep-learning-based reconstruction methods for neutrino-induced cascades. This work presents the first observation of high-energy neutrinos from the Milky Way Galaxy, rejecting the background-only hypothesis at 4.5 σ. The neutrino signal is consistent with diffuse emission from the Galactic plane, potentially in combination with emission by a population of sources.
CRIS-Team Scopus Importer:2025-02-04

Observation of light propagation in volume scatterers with 10 11-fold slow motion - Häusler, Gerd; et al. (Optics Letters, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.observ

Observation of multimode quantum correlations in fiber optical solitons - Leuchs, Gerd; et al. (Physical Review Letters, 1998)
Quantum correlations of photon numbers in different spectral components of ultrashort optical solitons have been observed experimentally. These correlations are crucial for the understanding and characterization of the internal quantum structure of soliton pulses and contribute significantly to soliton squeezing by spectral filtering. The accessible information on the nonclassical state of the correlated spectral components is discussed with the example of two modes. The method may be generalized to obtain a complete quantum description of a multimode field.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.observ

Observation of Seven Astrophysical Tau Neutrino Candidates with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review Letters, 2024)
We report on a measurement of astrophysical tau neutrinos with 9.7 yr of IceCube data. Using convolutional neural networks trained on images derived from simulated events, seven candidate ντ events were found with visible energies ranging from roughly 20 TeV to 1 PeV and a median expected parent ντ energy of about 200 TeV. Considering backgrounds from astrophysical and atmospheric neutrinos, and muons from π±/K± decays in atmospheric air showers, we obtain a total estimated background of about 0.5 events, dominated by non-ντ astrophysical neutrinos. Thus, we rule out the absence of astrophysical ντ at the 5σ level. The measured astrophysical ντ flux is consistent with expectations based on previously published IceCube astrophysical neutrino flux measurements and neutrino oscillations.
CRIS-Team Scopus Importer:2024-04-26

Observation of the Geometric Spin Hall Effect of Light - Korger, Jan; Aiello, Andrea; Chille, Vanessa; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2014)

Observation of Time Reversed Light Propagation by an Exchange of Eigenstates - Wimmer, Martin; Peschel, Ulf (Scientific Reports, 2018)
As time flow dictates all evolution, its effective reversal is a topic of active research in a broad range of disciplines, including acoustics, hydrodynamics and optics. This multifarious set of environments is reflected by a great diversity of approaches to observe various echoes of wave functions. Here, we experimentally demonstrate time reversal of a pulse sequence propagating through a photonic mesh lattice realized by two coupled loops of telecommunication fibres. Our system features a symmetric band structure, which allows for almost perfect reversal of its evolution by exchanging the population between two opposing bands. The protocol applied is based on a non-adiabatic and instantaneous exchange of eigenstates resulting in highly efficient time reversal of a pulse chain.
CRIS-Team Scopus Importer:2023-04-20

On-Demand Coupling of Electrically Generated Excitons with Surface Plasmons via Voltage-Controlled Emission Zone Position - Zakharko, Yuriy; Held, Martin; Sadafi, Fabrizio-Zagros; Gannott, Florentina; Mandavi, Ali; Peschel, Ulf; Klupp Taylor, Robin; Zaumseil, Jana (ACS Photonics, 2016)
The ability to confine and manipulate light below the diffraction limit is a major goal of future multifunctional optoelectronic/plasmonic systems. Here, we demonstrate the design and realization of a tunable and localized electrical source of excitons coupled to surface plasmons based on a polymer light emitting field-effect transistor (LEFET). Gold nanorods that are integrated into the channel support localized surface plasmons and serve as nanoantennas for enhanced electroluminescence. By precise spatial control of the near-infrared emission zone in the LEFET via the applied voltages the near-field coupling between electrically generated excitons and the nanorods can be turned on or off as visualized by a change of electroluminescence intensity. Numerical calculations and spectroscopic measurements corroborate significant local electroluminescence enhancement due to the high local density of photonic states in the vicinity of the gold nanorods. Importantly, the integration of plasmonic nanostructures hardly influences the electrical performance of the LEFETs, thus, highlighting their mutual compatibility in novel active plasmonic devices.
Keywords: surface plasmon polariton; organic semiconductor; field-effect transistor; electroluminescence; Purcell effect; active plasmonics

On the analogy between a single atom and an optical resonator - Heugel, Simon Tobias; Villar, Alessandro; Sondermann, Markus; Peschel, Ulf; Leuchs, Gerd (Laser Physics, 2010)
A single atom in free space can have a strong influence on a light beam and a single photon can have a strong effect on a single atom in free space. Regarding this interaction, two conceptually different questions can be asked: can a single atom fully absorb a single photon and can a single atom fully reflect a light beam. The conditions for achieving the full effect in either case are different. Here we discuss related questions in the context of an optical resonator. When shaping a laser pulse properly it will be fully absorbed by an optical resonator, i.e., no light will be reflected and all the pulse energy will accumulate inside the resonator before it starts leaking out. We show in detail that in this case the temporal pulse shape has to match the time-reversed pulse obtained by the cavity's free decay. On the other hand a resonator, made of highly reflecting mirrors which normally reflect a large portion of any incident light, may fully transmit the light, as long as the light is narrow band and resonant with the cavity. The analogy is the single atom-normally letting most of the light pass-which under special conditions may fully reflect the incident light beam. Using this analogy we are able to study the effects of practical experimental limitations in the atom-photon coupling, such as finite pulses, bandwidths, and solid angle coverage, and to use the optical resonator as a test bed for the implementation of the quantum experiment. © 2010 Pleiades Publishing, Ltd.

On the experimental investigation of the electric and magnetic response of a single nano-structure - Banzer, Peter; Peschel, Ulf; Quabis, Susanne; Leuchs, Gerd (Optics Express, 2010)
We demonstrate an experimental method to separately test the optical response of a single sub-wavelength nano-structure to tailored electric and magnetic field distributions in the optical domain. For this purpose a highly focused y-polarized TEM10-mode is used which exhibits spatially separated longitudinal magnetic and transverse electric field patterns. By displacing a single sub-wavelength nano-structure, namely a single split-ring resonator (SRR), in the focal plane, different coupling scenarios can be achieved. It is shown experimentally that the single split-ring resonator tested here responds dominantly as an electric dipole. A much smaller but yet statistically significant magnetic dipole contribution is also measured by investigating the interaction of a single SRR with a magnetic field component perpendicular to the SRR plane (which is equivalent to the curl of the electric field) as well as by analyzing the intensity and polarization distribution of the scattered light with high spatial resolution. The developed experimental setup as well as the measurement techniques presented in this paper are a versatile tool to investigate the optical properties of single sub-wavelength nano-structures.
EAM Import::2019-03-08

Optical 3D Sensors - Häusler, Gerd (Principles of 3D Image Analysis and Synthesis, 2000)
UnivIS-Import:2015-04-20:Pub.2000.nat.dphy.optik.1optik.optica_0

Optical amplification at the quantum limit - Andersen, Ulrik Lund; Leuchs, Gerd (Journal of Modern Optics, 2007)
In this paper we evaluate experimentally measured signal-to-noise ratio performance of different types of optical amplifiers [V. Josse, M. Sabuncu, N. Cerf, et al., Phys. Rev. Lett. 96 163602 (2006); Z.Y. Ou, S.F. Pereira and H.J. Kimble, Phys. Rev. Lett. 70 3239 (1993)]. We pay particular attention to the low gain regime where the quantum limit of the amplifier varies with gain. Independent of the amplifier type the noise performance is remarkably close to the quantum limit. Low gain optical amplifiers are of interest for quantum communication.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.optica

Optical Beam Propagation and Ray Tracing Simulation of Interruption-Free Asymmetric Multimode Bus Couplers - Lorenz, Lukas; Nieweglowski, Krzysztof; Wolter, Klaus-Jürgen; Loosen, Florian; Lindlein, Norbert; Bock, Karlheinz (Journal of Microelectronics and Electronic Packaging, 2017)
In this article, we present a coupling concept for an interruption-free asymmetric bidirectional optical bus coupler for board and module level. With this approach, it is possible to connect several electro-optical devices to a single waveguide. A core-to-core connection principle is used, where the cores get into physical contact at their side faces. The coupling ratio can be tuned by adjusting the overlap area of the two cores with different contact pressures. Because of a bending in one of the waveguides, it is possible to achieve a specific asymmetric coupler design, where the coupling ratio depends on the coupling direction (bent waveguide to rigid one or vice versa). To derive design rules for prototyping, a simulation is performed using two different independent approaches for cross-checking. With a ray tracing simulation, coupling ratios and energy distribution within the bent core are analyzed. In addition, a simulation with the beam propagation method is used to take wave optical effects into account as well as to establish a holistic view on the coupling concept.
Keywords: Optical bus coupler; asymmetric coupling; planar multimode waveguide; beam propagation method; nonsequential ray tracing

Optical Coherence Profilometry (OCP) of human skin in vivo - Häusler, Gerd; et al. (SPIE j, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.multic

Optical Coherence Tomography by 'spectral radar': dynamic range estimation and in vivo measurements of skin - Häusler, Gerd; et al. (Proceedings of SPIE, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.optica

Optical Coherence Tomography by "Spectral Radar": Improvement of Signal-to-Noise Ratio - Häusler, Gerd; et al. (Proceedings of SPIE, 2000)
`Spectral radar' combines a white light interferometer with a spectrometer. It is an optical sensor for the acquisition of skin morphology based on OCT techniques. The scattering amplitude along one vertical axis from the surface into the bulk can be measured within one exposure. We will discuss some essentials of signal formation and a new method of signal evaluation that significantly reduces artifacts from some source imperfections. We will further demonstrate new measurements.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.optica_4

Optical coherence tomography with a nonlinear interferometer in the high parametric gain regime - MacHado, Gerard J.; Frascella, Gaetano; Torres, Juan P.; Chekhova, Maria (Applied Physics Letters, 2020)
We demonstrate optical coherence tomography based on an SU(1,1) nonlinear interferometer with high-gain parametric downconversion. For imaging and sensing applications, this scheme promises to outperform previous experiments working at low parametric gain, since higher photon fluxes provide lower integration times for obtaining high-quality images. In this way, one can avoid using single-photon detectors or CCD cameras with very high sensitivities, and standard spectrometers can be used instead. Other advantages are higher sensitivity to small loss and amplification before detection so that the detected light power considerably exceeds the probing one.
CRIS-Team Scopus Importer:2020-09-25

Optical coherence tomography with the Spectral Radar. Fast optical analysis in volume scatterers by short coherence interferometry - Häusler, Gerd; et al. (SPIE j, 1996)
We present a sensor for acquisition of cross-sectional images of volume scatterers, we call it 'spectral radar'. Medical and technical applications are possible. The sensor is a modified Michelson interferometer, with a broad bandwidth light source. The scattering amplitude a(z) along one vertical axis from the surface into the bulk can be measured within one exposure. No reference arm scanning is necessary. Measurement results of stationary and non stationary scattering phantoms, human skin and of a fish eye in vitro are show
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.optica_3

Optical diametric drive acceleration through action–reaction symmetry breaking - Wimmer, Martin; Regensburger, Alois; Bersch, Christoph; Miri, Mohammad-Ali; Batz, Sascha; Onishchukov, Georgy; Christodoulides, Demetrios N.; Peschel, Ulf (Nature Physics, 2013)
Newton's third law of motion is one of the pillars of classical physics. This fundamental principle states that the forces two bodies exert on each other are equal and opposite. Had the resulting accelerations been oriented in the same direction, this would have instead led to a counterintuitive phenomenon, that of diametric drive. In such a hypothetical arrangement, two interacting particles constantly accelerate each other in the same direction through a violation of the action–reaction symmetry. Although in classical mechanics any realization of this process requires one of the two particles to have a negative mass and hence is strictly forbidden, it could nevertheless be feasible in periodic structures where the effective mass can also attain a negative sign. Here we report the first experimental observation of such diametric drive acceleration for pulses propagating in a nonlinear optical mesh lattice. The demonstrated reversal of action–reaction symmetry could enable altogether new possibilities for frequency conversion and pulse-steering applications.
EAM Import::2019-03-08

Optical Gap solitons and Truncated Nonlinear Bloch Waves in Temporal Lattices - Bersch, Christoph; Onishchukov, Georgy; Peschel, Ulf (Physical Review Letters, 2012)
We experimentally demonstrate the formation and stable propagation of various types of discrete temporal solitons in an optical fiber system. Pulses interacting with a time-periodic potential and defocusing nonlinearity are shown to form gap solitons and nonlinear truncated Bloch waves. Multi-pulse solitons with defects, as well as novel structures composed of a strong soliton riding on a weaker truncated nonlinear Bloch wave are shown to propagate over up to eleven coupling lengths. The nonlinear dynamics of all pulse structures is monitored over the full propagation distance which provides detailed insight into the soliton dynamics.
EAM Import::2019-03-08

Optical harmonic generation from bright squeezed vacuum - Spasibko, Kirill; Kopylov, Denis A.; Krutyanskiy, Victor L.; Murzina, Tatiana V.; Leuchs, Gerd; Chekhova, Maria (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2023-03-27

Optical Landau state mapping with in-plane electric fields - Karmakar, Biswajit; Schardt, Michael; Malzer, Stefan; Arora, Brij Mohan; Döhler, Gottfried (Physica Status Solidi (C) Current Topics in Solid State Physics, 2007)
We report on a theoretical and experimental investigation of magneto-absorption in quantum wells (QWs) in the presence of a uniform in-plane electric field. From a simple theoretical model a linear real-space shift of the electron Landau level wave functions relative to the hole counterparts is expected under increasing in-plane electric field. As a result, quadratic Stark shifts, fading of the zero-field allowed transitions, and increasing oscillator strength for the originally forbidden transitions are predicted. These predictions are confirmed by experiments on GaAs/AlGaAs-QWs and found to be in reasonably good agreement with simulations based on a simple model. © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.

Optical measurement methods for refractive microlenses and microlens arrays - Lindlein, Norbert; et al. (Proceedings of SPIE, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.optica

Optical Memory Based on Conterpropagating Light in Microresonators - Bino, Leonardo Del; Moroney, Niall; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
A consequence of the Kerr effect in ring microresonators is that light can not always circulate simultaneously in both directions. Instead, under the appropriate conditions of input power and detuning, light can couple into the resonator only in one direction while the other continues on the coupling waveguide [1] - [3]. The two resulting light states, clockwise (CW) and counterclockwise (CCW), can be interpreted as the digital states 1 and 0 as shown in Fig. 1 (c). Microresonators have been theorized to be a suitable solution for on-chip logical processing and switching [4]. Here we present an all-optical bistable device based on the difference of the Kerr effect for co-propagating and counterpropagating light. The device does not require any electrical power, and relies only on a single laser input for its operation. The optical state is set by the dominant input power direction. The system exhibits hysteresis ( Fig. 1 (d) ) hence the optical state is maintained until an significant input in the opposite direction is received. The hysteresis provides resilience to fluctuations in the inputs up to half of the total input power.
CRIS-Team Scopus Importer:2021-10-29

Optical properties of a tilted polarizer and geometric spin hall effect of light - Korger, Jan; Aiello, Andrea; Gabriel, Christian; Banzer, Peter; Kolb, Tobias; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Optical Range Sensing with spatially modulated Coherence - Häusler, Gerd; et al. (Proc. of the Int. Symp. on Laser Applications in Precision Measurements, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.optica

Optical signal Regeneration at Different Modulation Formats - Schmauß, Bernhard; Striegler, Arne; Meißner, Markus (Proceedings of SPIE, 2004)
Optical transmission systems made impressive progress in the field of system capacity, reach and flexibility. Beside all improvements achieved so far, signal distortion on the one hand side and noise accumulation on the other hand side are the limitations of optical transmission systems. In terms of signal distortion besides advanced link design strategies optical regenerators are of high interest for signal conditioning along a fiber link. Furthermore the upcoming techniques of advanced modulation formats build a basis for further improvement of transmission quality that ends up with even higher reach, higher robustness against transmission impairments, lower signal to noise requirements etc. In this talk the current status of research in the field of optical signal regenerators suitable for signal regeneration for different modulation formats will be reviewed and presented, where we restrict our analysis to 2R regenerators. The focus will be put on regenerators taking advantage of non linear optical effects in order to improve signal quality. The main challenge is the treatment of phase modulated signals within regenerators. Especially the differential phase shift keying (DPSK) modulation format or the duobinary modulation format are attractive candidates for such kind of regenerators for further improvement of DPSK based transmission systems. The paper will go through several regenerative concepts like non linear optical loop mirror (NOLM) based and cross phase modulation based regenerators in order to figure out their potential for advanced modulation format based systems.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.optica
Keywords: Modulation Format; Optical Transmission; Regeneration

Optical simulations of printed Polymer Optical Waveguides (POWs): search for their optical limitations caused by fabrication and application geometry - Backhaus, Carsten; Vögl, Christian; Zeitler, Jochen; Reitberger, Thomas; Lindlein, Norbert; Franke, Jörg (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, 2019)
Keywords: Polymer waveguides; Polymethyl methacrylate; Refractive index; Roughness; Surfaces; Systems design

Optical Testing of Refractive Microlenses - Lindlein, Norbert; et al. (Technisches Messen, 2002)
Microlens testing requires in many cases the measurement of surface deviations and the measurement of the wave aberrations of the lens. The lens function is for the multitude of microlenses brought about through curved surfaces of dielectric substrates. Only GRIN lenses rely on the three-dimensional distribution of the refractive index. For the measurement of the surface deviations the Twyman-Green interferometer and for cylinder lenses the grazing incidence test using diffractive beam splitters are best suited. Wave aberrations should be measured in single pass geometry because of systematic errors in case of big aberrations due to double pass arrangements. Therefore, the Mach-Zehnder on the one hand and the shearing interferometer on the other can be recommended for microlens tests. At the time being also wave front sensor as the Shack-Hartmann test are becoming a suitable alternative to the shearing methods because of its simplicity and sufficient sensitivity. A special field is the test of whole lens arrays. This concerns the paraxial as well as the aberration data. Low aperture lens arrays might be illuminated with plane waves indicating the uniformity of the lens data if a whole field is evaluated simultaneously.
Keywords: Aberrations measurement; Diffractive beam splitters; Interferometry; Microlenses; Wave front sensors

Optical Tomography: 3D-Metrology in Scattering Media - Häusler, Gerd; et al. (3D-Image Analysis and Synthesis, 1996)
UnivIS-Import:2015-04-20:Pub.1996.nat.dphy.optik.1optik.optica_1

Optical Transient Suppression using Stimulated Raman Attenuation - Holtmannspötter, Michael; Stephan, C.; Onishchukov, Georgy; Leuchs, Gerd; Schmauß, Bernhard (ECOC, September, 2008)
Dynamic optical attenuation based on the Raman Effect is investigated experimentally. The suppression of optical power transients as they arise from dynamic processes of EDFAs is shown. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.optica_3

Optical trapping of nanoparticles by full solid-angle focusing - Salakhutdinov, Vsevolod; Sondermann, Markus; Carbone, Luigi; Giacobino, Elisabeth; Bramati, Alberto; Leuchs, Gerd (Optica, 2016)
Optical dipole traps are used for trapping and localizing particles in various scientific fields,including classical optics,quantum optics,and biophysics. Here,we propose and implement a dipole trap for nanoparticles that is based on focusing from the full solid angle with a deep parabolic mirror. The key aspect is the generation of a linear-dipole mode,which is predicted to provide a tight trapping potential. We demonstrate the trapping of rod-shaped nanoparticles and validate the trapping frequencies to be of the order of the expected ones. The described realization of an optical trap is applicable for various other kinds of solid-state targets. The obtained results demonstrate the feasibility of optical dipole traps that simultaneously provide high trap stiffness and allow for efficient interaction of light and matter in free space.
Keywords: (260.5430) Polarization; (270.0270) Quantum optics; (350.4855) Optical tweezers or optical manipulation

Optics in Curved Space - Schultheiß, Vincent; Batz, Sascha; Szameit, Alexander; Dreisow, Felix; Nolte, Stefan; Tuennermann, Andreas; Longhi, Stefano; Peschel, Ulf (Physical Review Letters, 2010)
We experimentally study the impact of intrinsic and extrinsic curvature of space on the evolution of light. We show that the topology of a surface matters for radii of curvature comparable with the wavelength, whereas for macroscopically curved surfaces only intrinsic curvature is relevant. On a surface with constant positive Gaussian curvature we observe periodic refocusing, self-imaging, and diffractionless propagation. In contrast, light spreads exponentially on surfaces with constant negative Gaussian curvature. For the first time we realized two beam interference in negatively curved space.
EAM Import::2019-03-08

Optikprüfung von refraktiven Mikrolinsen - Leuchs, Gerd; Lindlein, Norbert; et al. (Technisches Messen, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.optikp

Optimally cloned binary coherent states - Müller, Christian; Leuchs, Gerd; Marquardt, Christoph; Andersen, U. L. (Physical Review A, 2017)
Binary coherent state alphabets can be represented in a two-dimensional Hilbert space. We capitalize this formal connection between the otherwise distinct domains of qubits and continuous variable states to map binary phase-shift keyed coherent states onto the Bloch sphere and to derive their quantum-optimal clones. We analyze the Wigner function and the cumulants of the clones, and we conclude that optimal cloning of binary coherent states requires a nonlinearity above second order. We propose several practical and near-optimal cloning schemes and compare their cloning fidelity to the optimal cloner.
CRIS-Team Scopus Importer:2022-06-05

Optimal spatial mode distributions for the coupling of a single photon to an atomic dipole transition in free space - Lindlein, Norbert; et al. (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference, 2009)

Optimierte Segmentierung der Papille in HRT-Retinaaufnahmen - Arold, Oliver; Bock, Rüdiger; Meier, Jörg; Michelson, Georg; Hornegger, Joachim (Bildverarbeitung für die Medizin 2008 - Algorithmen, Systeme, Anwendungen, 2008)

Optimised exposure strategies for artifial waveplates - Harder, Irina; Lohse, Olga; Rothau, Sergej; Piaszenski, Guido (39th International Conference on Micro and Nano Engineering, 2013)

Optimization of a nonlinear amplifying loop mirror for amplitude regeneration in phase-shift-keyed transmission - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2007)
We present the numerical optimization of the transmission characteristics of a nonlinear amplifying loop mirror for amplitude regeneration of phase-encoded optical transmission formats. Adjusting the splitting factor, the amplifier gain and the phase bias, minimal phase distortions can be achieved while strong amplitude fluctuations are regenerated. The limiting effects of noise from the built-in amplifier and of amplified Rayleigh backscattering are also discussed. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.optimi
Keywords: 2R-regeneration; All-optical regeneration; Differential phase-shift keying; Nonlinear amplifying loop mirror

Optimization of Dispersion-Imbalanced Loop Mirror for Phase-Preserving Amplitude Regeneration - Röthlingshöfer, Tobias; Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE/LEOS Winter Topicals Meeting Series, 2009)
The adaptation and optimization of a dispersionimbalance loop mirror for phase-preserving amplitude 2R regeneration is shown by numerical simulations. Its performance has been evaluated for DPSK transmission. A 4.8dB Q-factor improvement has been demonstrated.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.optimi

Optimization of titanium and titanium alloy surface properties by ultra-short laser processing for improved antibacterial characteristics - Aceti, D. M.; Daskalova, A.; Angelova, L.; Filipov, E.; Sotelo, Lamborghini; Andreeva, A.; Trifonov, A.; Buchvarov, I. (Journal of Physics: Conference Series, 2022)
The aim of the current study is to improve in a one step process the properties of Ti and Ti alloy surfaces by enhancing their bioactivity in order to provide better conditions for microbial rejection. We propose to alter the biomaterial characteristics by a method alternative to the chemical ones, namely, non-contact processing of the surface by ultra-short laser pulses. The laser-induced modification results in a surface with different topographic features and an increased presence of oxides. We performed hierarchical laser patterning of the surface inducing the formation of areas covered by nanostructures, or laser-induced periodic surface structures (LIPSS), alternating with areas covered by micropillars in their turn surmounted by LIPSS. The increased roughness achieved due to the presence of micropillars, together with a marked presence of oxides, has been proven by several studies to enhance the biocompatibility of the material by improving the surface wettability and, furthermore, promoting the cells adhesion and osseointegration, while reducing the adhesion of pathogens. The laser processed surface, consisting of a pattern of parallel lines, showed improved and anisotropic wettability. The water contact angle value decreased by â1/410° in a direction orthogonal to the lines of the pattern, and by â1/440° in a parallel direction.
CRIS-Team Scopus Importer:2022-05-20

Optimization of white light interferometry at rough surfaces by error analysis - Häusler, Gerd; et al. (Optik, 2004)
White light interferometry can be used to measure the shape of rough surfaces. At rough surfaces, the measuring uncertainty in principle cannot be better than the surface roughness, which is commonly in the range of 1 micron. Hence, the requirements for the hard- and software components of the instrument are not as high as for interferometry in the nanometer regime. An analysis of the dominant error sources allows the design of an "optimal" sensor with a measuring uncertainty as small as physically possible, with components as good as necessary and as simple as possible.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.optimi
Keywords: Measuring uncertainty; White light interferometry

Optimizing the generation of polarization squeezed light in nonlinear optical fibers driven by femtosecond pulses - Andrianov, A. V.; Kalinin, Nikolay; Sorokin, A. A.; Anashkina, E. A.; Sánchez-Soto, L. L.; Corney, J. F.; Leuchs, Gerd (Optics Express, 2023)
Bright squeezed light can be generated in optical fibers utilizing the Kerr effect for ultrashort laser pulses. However, pulse propagation in a fiber is subject to nonconservative effects that deteriorate the squeezing. Here, we analyze two-mode polarization squeezing, which is SU(2)-invariant, robust against technical perturbations, and can be generated in a polarization-maintaining fiber. We perform a rigorous numerical optimization of the process and the pulse parameters using our advanced model of quantum pulse evolution in the fiber that includes various nonconservative effects and real fiber data. Numerical results are consistent with experimental results.
CRIS-Team Scopus Importer:2023-01-06

Optimum splitting ratio for amplifier noise reduction by an asymmetric nonlinear optical loop mirror - Meißner, Markus; Rösch, Matthias; Korolkova, Natalia; Sizmann, Andreas; Schmauß, Bernhard; Leuchs, Gerd (Optical Communication, 2002)
UnivIS-Import:2015-04-16:Pub.2002.nat.dphy.optik.1optik.optimu

Optimum splitting ratio for amplifier noise reduction by an asymmetric nonlinear optical loop mirror - Meißner, Markus; Rösch, Matthias; Schmauß, Bernhard; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2005)
We theoretically and experimentally analyze the influence of the splitting ratio and the input power on the noise reduction capability of an asymmetric nonlinear optical loop mirror (NOLM) for different input noise levels. An easy method to calculate the optimum parameters for noise reduction is also presented. The best noise reduction is found at NOLM input powers at which the nonlinear transfer function has a slope close to zero. Additionally, the splitting ratio of the NOLM has to be adapted to its input noise level to suppress amplitude fluctuations effectively. Since the noise reduction by the NOLM is due to the Kerr nonlinearity, which has a timescale below a few femtoseconds, the noise reduction is applicable to short pulses in the picosecond and femtosecond range. This makes the NOLM applicable as an optical regenerator in an optical data transmission system at high bit rates, such as 160 GBit/s. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.optimu

Optimum splitting ratio for amplifier noise reduction vy an asymmetric nonlinear optical loop mirror - Schmauß, Bernhard; Meißner, Markus; Rösch, Matthias; Leuchs, Gerd (Applied Physics B, Febr., 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.optimu

Optische 3D-Messtechnik in der Mund-, Kiefer-, Gesichtschirurgie - Häusler, Gerd; Nkenke, Emeka; et al. (Informatik 2005 - Informatik live! (35. Jahrestagung der Ges. für Informatik e.V.), 2005)
UnivIS-Import:2015-04-20:Pub.2005.nat.dphy.optik.1optik.optisc

Optische 3D-Sensoren helfen dem Restaurator - Häusler, Gerd; et al. (Das moderne Museum - Die Vorträge der MUTEC 99, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.optisc

Optische 3D-Sensoren mit großem Meßbereich und hoher Genauigkeit - Häusler, Gerd; et al. (Info Phys Tech, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.optik.1optik.optisc_7

Optische 3D-Sensoren und deren industrielle Anwendung - Häusler, Gerd; et al. (Technisches Messen, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.ptisch

Optische Messtechnik an diffus reflektierenden Medien - Häusler, Gerd; et al. (Expert-Verlag, 1997)
UnivIS-Import:2015-05-08:Pub.1997.nat.dphy.optik.1optik.mglich

Optischer Sensor wacht über Lasermaterialbearbeitung - Häusler, Gerd; et al. (F and M; Feinwerktechnik, Mikrotechnik, Messtechnik, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.optik.1optik.optisc

Optoelectronic interconnects with holographic optical elements - Lindlein, Norbert; et al. (3rd International Conference on Holographic Systems, Components and Applications, 1991)
Highly efficient holographic optical elements (HOEs) in dichromated gelatin (DGG) have been demonstrated. Several systems and components will be presented: (1) interconnections based on a light guiding glass plate with holographic coupling elements, (2) permutation elements for optoelectronic switching systems, (3) holographic beamsplitters and (4) holographic microlens arrays.

Orbital angular momentum modes of high-gain parametric down-conversion - Beltran, Lina; Frascella, Gaetano; Perez, Angela M.; Fickler, Robert; Sharapova, Polina R.; Manceau, Mathieu; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Journal of Optics, 2017)
Light beams with orbital angular momentum (OAM) are convenient carriers of quantum information. They can also be used for imparting rotational motion to particles and providing high resolution in imaging. Due to the conservation of OAM in parametric down-conversion (PDC), signal and idler photons generated at low gain have perfectly anti-correlated OAM values. It is interesting to study the OAM properties of high-gain PDC, where the same OAM modes can be populated with large, but correlated, numbers of photons. Here we investigate the OAM spectrum of high-gain PDC and show that the OAM mode content can be controlled by varying the pump power and the configuration of the source. In our experiment, we use a source consisting of two nonlinear crystals separated by an air gap. We discuss the OAM properties of PDC radiation emitted by this source and suggest possible modifications.
CRIS-Team Scopus Importer:2023-03-27
Keywords: bright squeezed vacuum; coherent modes; orbital angular momentum; parametric down-conversion; Schmidt modes

Orbital-to-spin angular momentum conversion employing local helicity - Nechayev, Sergey; Eismann, Jörg; Leuchs, Gerd; Banzer, Peter (Physical Review B, 2019)
Spin-orbit interactions in optics traditionally describe an influence of the polarization degree of freedom of light on its spatial properties. The most prominent example is the generation of a spin-dependent optical vortex upon focusing or scattering of a circularly polarized plane wave by a nanoparticle, converting spin to orbital angular momentum of light. Here we present a mechanism of conversion of orbital-to-spin angular momentum of light upon scattering of a linearly polarized vortex beam by a spherical silicon nanoparticle. We show that focused linearly polarized Laguerre-Gaussian beams of first order (l = +1) exhibit an -dependent spatial distribution of helicity density in the focal volume. By using a dipolar scatterer the helicity density can be manipulated locally, while influencing globally the spin and orbital angular momentum of the beam. Specifically, the scattered light can be purely circularly polarized with the handedness depending on the orbital angular momentum of the incident beam. We corroborate our findings with theoretical calculations and an experimental demonstration. Our work sheds light on the global and local properties of helicity conservation laws in electromagnetism.
CRIS-Team WoS Importer:2019-03-15

Overcoming detection losses in a supersensitive interferometer with coherent and squeezed vacuum inputs - Frascella, Gaetano; Agne, Sascha; Khalili, Farid Ya; Chekhova, Maria (Optics InfoBase Conference Papers, 2020)
We report phase sensitivity overcoming the shot-noise limit by 3 dB for a squeezing-assisted interferometer with 50% detection losses. The performance is tolerant to losses up to 87% because of an optical parametric amplifier at the output.
CRIS-Team Scopus Importer:2020-11-13

Overcoming inefficient detection in sub-shot-noise absorption measurement and imaging - Knyazev, Eugene; Khalili, Farid Ya; Chekhova, Maria (Optics Express, 2019)
Photon-number squeezing and correlations enable measurement of absorption with an accuracy exceeding that of the shot-noise limit. However, sub-shot noise imaging and sensing based on these methods require high detection efficiency, which can he a serious obstacle it measurements are carried out in "difficult" spectral ranges. We show that this problem can he overcome through the phase-sensitive amplification before detection. Here we propose an experimental scheme of sub-shot-noise imaging with tolerance to detection losses. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-03-29

Painting by numbers: Nanoparticle-based colorants in the post-empirical age - Klupp Taylor, Robin; Seifrt, Frantiek; Zhuromskyy, Oleksandr; Peschel, Ulf; Leugering, Günter; Peukert, Wolfgang (Advanced Materials, 2011)
The visual appearance of the artificial world is largely governed by films or composites containing particles with at least one dimension smaller than a micron. Over the past century and a half, the optical properties of such materials have been scrutinized and a broad range of colorant products, based mostly on empirical microstructural improvements, developed. With the advent of advanced synthetic approaches capable of tailoring particle shape, size and composition on the nanoscale, the question of what is the optimum particle for a certain optical property can no longer be answered solely by experimentation. Instead, new and improved computational approaches are required to invert the structure-function relationship. This progress report reviews the development in our understanding of this relationship and indicates recent examples of how theoretical design is taking an ever increasingly important role in the search for enhanced or multifunctional colorants. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: colloids; core/shell nanoparticles; designed nanostructures; functional coatings; structure-property relationships

Parallel optoelectronic interconnections with high packing density through a light-guiding plate using grating couplers and field lenses - Lindlein, Norbert; et al. (Optics Communications, 1993)
Optoelectronic interconnections between boards at 1-100 cm distances are proposed, which are based on a typically some 5- 10 mm thick light-guiding plate for confinement and transport of the optical signals with low loss, on the order of 0.1 dB/cm. The plate is equipped with grating couplers fabricated as volume phase holograms in dichromated gelatin with insertion loss as low as 0.5 dB/coupler. The apertures of the optoelectronic transmitters are imaged onto the apertures of the receivers by aspheric field lenses or mirrors mounted on the plate. Such optical systems render packing densities as high as 1000 channel/cm possible that are required for the application of densely packed integrated arrays of semiconductor lasers and detectors. Grating dispersion, axial astigmatism, geometrical distortion and coma are eliminated in the proposed optical setup. Results from ray tracing and an experiment are presented. © 1993.

Parallel two-step phase-shifting point-diffraction interferometry for microscopy based on a pair of cube beamsplitters - Peng, Gao; Yao, Baoli; Min, Junwei; Harder, Irina; Nercissian, Vanusch; Mantel, Klaus; Guo, Rongli; Zheng, Juanjuan; Ye, Tong (Optics Express, 2011)

Parity Measurement in Action: Detecting Errors in the Surface Code and Heralding itinerant Cat States using Superconducting Circuits - Eichler, Christopher (MPI for the Science of Light:, 2020)
Parity Measurements in Action: Detecting Errors in the Surface Code and Heralding Itinerant Cat States using Superconducting Circuits. Parity measurements distinguish between quantum states with an even and an odd number of excitations without revealing any additional information about the state. Nondestructive parity detection allows one to project onto highly entangled states and therefore plays a central role in quantum error correction. In my talk, I discuss two complementary implementations of parity detection both realized in superconducting circuits. First, we measure the parity of the photon number of propagating radiation fields and thereby herald itinerant Schrödinger cat states [1]. Second, we perform ancilla-based parity detection in multi-qubit systems to implement the smallest viable instance of the surface code capable of detecting any single error [2]. Both experiments crucially rely on recent progress in performing high-fidelity, fast, and qubit-selective readout [3], and highlight the great potential of superconducting circuits for quantum information science. [1] J. - C. Besse, S. Gasparinetti, M. C. Collodo, T. Walter, A. Remm, J. Krause, C. Eichler, and A. Wallraff, arXiv:1912.09896 (2019); J. - C. Besse, S. Gasparinetti, M. C. Collodo, T. Walter, P. Kurpiers, M. Pechal, C. Eichler, and A. Wallraff, Phys. Rev. X 8, 021003 (2018) [2] C. Kraglund Andersen, A. Remm, S. Lazar, S. Krinner, N. Lacroix, G. J. Norris, M. Gabureac, C. Eichler, and A. Wallraff, arXiv:1912.09410 (2019); C. Kraglund Andersen*, A. Remm*, S. Lazar, S. Krinner, J. Heinsoo, J-C. Besse, M. Gabureac, A. Wallraff, and C. Eichler, NPJ Quantum Information 5, 69 (2019) [3] J. Heinsoo, C. Kraglund Andersen, A. Remm, S. Krinner, T. Walter, Y. Salathe, S. Gasparinetti, J-C. Besse, A. Potocnik, A. Wallraff, and C. Eichler, Phys. Rev. Applied 10, 034040 (2018); T. Walter, P. Kurpiers, S. Gasparinetti, P. Magnard, A. Potoćnik, Y. Salathe, M. Pechal, M. Mondal, M. Oppliger, C. Eichler, and A. Wallraff, Phys. Rev. Applied 7, 054020 (2017)
Keywords: wwwqudev

Parity Measurements in Action: Detecting Errors in the Surface Code and Heralding itinerant Cat States using Superconducting Circuits - Eichler, Christopher (MPI for Quantum Optics (MPQ), 2020)
Parity Measurements in Action: Detecting Errors in the Surface Code and Heralding Itinerant Cat States using Superconducting Circuits. Parity measurements distinguish between quantum states with an even and an odd number of excitations without revealing any additional information about the state. Nondestructive parity detection allows one to project onto highly entangled states and therefore plays a central role in quantum error correction. In my talk, I discuss two complementary implementations of parity detection both realized in superconducting circuits. First, we measure the parity of the photon number of propagating radiation fields and thereby herald itinerant Schrödinger cat states [1]. Second, we perform ancilla-based parity detection in multi-qubit systems to implement the smallest viable instance of the surface code capable of detecting any single error [2]. Both experiments crucially rely on recent progress in performing high-fidelity, fast, and qubit-selective readout [3], and highlight the great potential of superconducting circuits for quantum information science. [1] J. - C. Besse, S. Gasparinetti, M. C. Collodo, T. Walter, A. Remm, J. Krause, C. Eichler, and A. Wallraff, arXiv:1912.09896 (2019); J. - C. Besse, S. Gasparinetti, M. C. Collodo, T. Walter, P. Kurpiers, M. Pechal, C. Eichler, and A. Wallraff, Phys. Rev. X 8, 021003 (2018) [2] C. Kraglund Andersen, A. Remm, S. Lazar, S. Krinner, N. Lacroix, G. J. Norris, M. Gabureac, C. Eichler, and A. Wallraff, arXiv:1912.09410 (2019); C. Kraglund Andersen*, A. Remm*, S. Lazar, S. Krinner, J. Heinsoo, J-C. Besse, M. Gabureac, A. Wallraff, and C. Eichler, NPJ Quantum Information 5, 69 (2019) [3] J. Heinsoo, C. Kraglund Andersen, A. Remm, S. Krinner, T. Walter, Y. Salathe, S. Gasparinetti, J-C. Besse, A. Potocnik, A. Wallraff, and C. Eichler, Phys. Rev. Applied 10, 034040 (2018); T. Walter, P. Kurpiers, S. Gasparinetti, P. Magnard, A. Potoćnik, Y. Salathe, M. Pechal, M. Mondal, M. Oppliger, C. Eichler, and A. Wallraff, Phys. Rev. Applied 7, 054020 (2017)
Keywords: wwwqudev

Parity-time synthetic photonic lattices - Regensburger, Alois; Bersch, Christoph; Miri, Mohammad-Ali; Onishchukov, Georgy; Christodoulides, Demetrios N.; Peschel, Ulf (Nature, 2012)
The development of new artificial structures and materials is today one of the major research challenges in optics. In most studies so far, the design of such structures has been based on the judicious manipulation of their refractive index properties. Recently, the prospect of simultaneously using gain and loss was suggested as a new way of achieving optical behaviour that is at present unattainable with standard arrangements. What facilitated these quests is the recently developed notion of `parity–time symmetry' in optical systems, which allows a controlled interplay between gain and loss. Here we report the experimental observation of light transport in large-scale temporal lattices that are parity–time symmetric. In addition, we demonstrate that periodic structures respecting this symmetry can act as unidirectional invisible media when operated near their exceptional points. Our experimental results represent a step in the application of concepts from parity–time symmetry to a new generation of multifunctional optical devices and networks.
EAM Import::2019-03-08

Parsing polarization squeezing into Fock layers - Müller, Christian; Madsen, Lars S.; Klimov, Andrei B.; Sanchez-Soto, Luis L.; Leuchs, Gerd; Marquardt, Christoph; Andersen, Ulrik L. (Physical Review A, 2016)
We investigate polarization squeezing in squeezed coherent states with varying coherent amplitudes. In contrast to the traditional characterization based on the full Stokes parameters, we experimentally determine the Stokes vector of each excitation subspace separately. Only for states with a fixed photon number do the methods coincide; when the photon number is indefinite, we parse the state in Fock layers, finding that substantially higher squeezing can be observed in some of the single layers. By capitalizing on the properties of the Husimi Q function, we map this notion onto the Poincaré space, providing a full account of the measured squeezing.
CRIS-Team Scopus Importer:2022-06-05

Perfect excitation of a matter qubit by a single photon in free space - Leuchs, Gerd; et al. (EPL - Europhysics Letters, 2009)
We propose a scheme for perfect excitation of a single two-level atom by a single photon in free space. The photon state has to match the time reversed photon state originating from spontaneous decay of a two-level system. Here, we discuss its experimental preparation. The state is characterized by a particular asymmetric exponentially shaped temporal profile. Any deviations from this ideal state limit the maximum absorption. Although perfect excitation requires an infinite amount of time, we demonstrate that there is a class of initial one-photon quantum states which can achieve almost perfect absorption even for a finite interaction time. Our results pave the way for realizing perfect coupling between flying and stationary qubits in free space thus opening a possibility for building scalable quantum networks. © EPLA, 2009.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.perfec

Perfect imaging of hypersurfaces via transformation optics - Mantel, Klaus; Peschel, Ulf; Bachstein, Dustin (Optics Letters, 2011)

Perfect Imaging of Planes and Surfaces via Transformation Optics - Bachstein, Dustin; Mantel, Klaus; Peschel, Ulf (Proc. 5th EOS Topical Meeting on Advanced Imaging Techniques, ISBN 978-3-00-030503-0, 2010)

Performance analysis of simultaneous multilevel amplitude and phase regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (39th European Conference and Exhibition on Optical Communication (ECOC), 2013)
A star-8QAM regeneration was investigated in numerical simulations for two schemes: a combined NALM with a PSA in the loop and a cascade of PSA and NALM. Significant improvements in error vector magnitude and bit error rate are achieved for both schemes in a transmission system limited by amplified spontaneous emission and nonlinear phase noise.
lhft_intern.bib::Roethlingshoefer2013a

Perturbation theory of nearly spherical dielectric optical resonators - Gohsrich, Julius; Shah, Tirth; Aiello, Andrea (Physical Review A, 2021)
Dielectric spheres of various sizes may sustain electromagnetic whispering-gallery modes resonating at optical frequencies with very narrow linewidths. Arbitrary small deviations from the spherical shape typically shift and broaden such resonances. Our goal is to determine these shifted and broadened resonances. A boundary-condition perturbation theory for the acoustic vibrations of nearly circular membranes was developed by Rayleigh more than a century ago. We extend this theory to describe the electromagnetic excitations of nearly spherical dielectric cavities. This approach permits us to avoid dealing with decaying quasinormal modes. We explicitly find the frequencies and the linewidths of the optical resonances for arbitrarily deformed nearly spherical dielectric cavities, as power series expansions by a small parameter, up to and including second-order terms. We thoroughly discuss the physical conditions for the applicability of perturbation theory.
CRIS-Team WoS Importer:2021-09-03

Phase and polarization measurement of a spatially varying linear polarization distribution - Rothau, Sergej; Nercissian, Vanusch; Berger, Andreas; Harder, Irina; Mantel, Klaus Peter; Lindlein, Norbert (7th International Workshop on Advanced Optical Imaging and Metrology, Fringe 2013, 2013)
The first measurements show very good results and are consistent with the theory. The next step is the study of measurement results made with further combinations of φi and ωi and the investigation of their robustness against stochastic errors or the influence of elliptical polarization. © Springer-Verlag Berlin Heidelberg 2014.

Phase measurement of a spatially varying polarization distribution - Nercissian, Vanusch; Geier, Florian; Berger, Andreas; Rothau, Sergej; Ghadyani, Zahra; Harder, Irina; Mantel, Klaus Peter; Lindlein, Norbert (DGaO Proceedings, 2012)

Phase Measuring Deflectometry: a new approuch to measure specular free-form surfaces - Häusler, Gerd; et al. (Proceedings of SPIE, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.phasem

Phase noise suppression in Microstructured Fibers - Korn, Alexander; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (International Quantum Electronics Conference 2004, 2004)
We investigated thermal phase-noise in a microstructured fiber. We demonstrate that the microstructure of the fiber establishes a low order acoustic resonator thus suppressing all guided acoustic wave Brillouin scattering modes up to 300 MHz.<br

Phase-Preserving 2R-Regeneration of an 80-Gb/s RZ-DQPSK, Signal by Using a Nonlinear Amplifying Loop Mirror - Cvecek, Kristian; Sponsel, Klaus; Stephan, Christian; Ludwig, R.; Schubert, Christina; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (ECOC September, 2007)
The performance of a nonlinear amplifying loop mirror as a 2R regenerator for an 80-Gb/s RZ-DQPSK has been investigated. A significant eye-opening improvement and a negative power penalty of 2.6 dB have been obtained.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.phasep

Phase-Preserving 2R-Regeneration of a WDM RZ-DPSK Signal Using a Nonlinear Amplifying Loop Mirror - Cvecek, Kristian; Sponsel, Klaus; Stephan, C.; Onishchukov, Georgy; Ludwig, R.; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (Optical Communication / National Fiber Optic Engineers Conference OFC/NFOEC 24.-28.02., 2008)
A modified NALM setup for phase-preserving amplitude regeneration of WDM-DPSK signals is proposed. Demultiplexing-multiplexing within the NALM fiber loop is used to avoid WDM channel crosstalk, A negative power penalty of 1.2 dB was obtained. © 2007 Optical Society of America.
UnivIS-Import:2017-11-07:Pub.2008.tech.IE.LEH.phasep

Phase preserving 2R-Regeneration using a nonlinear optical loop mirror - Cvecek, Kristian; Striegler, Arne; Meißner, Markus; Sponsel, Klaus; Schmauß, Bernhard; Leuchs, Gerd (Cleo/Europe EQEC Conference, Munich, Germany, June, 2005)
In our experiment a NOLM regenerator is adapted for reducing amplitude jitter of a DPSK signal without destroying the phase information.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.phasep

Phase-preserving amplitude noise suppression using an attenuation-imbalanced NOLM - Parsons, E.; Stephan, K.; Sponsel, K.; Roethlingshoefer, T; Kueppers, F.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (Proc. SPIE, 7621, 762109, Jan., 2010)
lhft_intern.bib::Parsons10

Phase-preserving amplitude regeneration for a WDM RZ-DPSK signal using a nonlinear amplifying loop mirror - Onishchukov, Georgy; Cvecek, Kristian; Sponsel, Klaus; Stephan, Christian; Ludwig, R.; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2008)
We propose a modified nonlinear amplifying loop mirror (NALM) for phase-preserving 2R regeneration of wavelength division multiplexed (WDM) return-to-zero differential phase-shift-keyed signals. As proof of principle the regeneration capability of this NALM setup has been investigated experimentally for two 10 Gbit/s wavelength channels. A significant eye-opening improvement and a negative power penalty of 1.2 dB have been observed in both channels. © 2008 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.phasep

Phase-Preserving Amplitude Regeneration in DPSK Transmission Systems Using a Nonlinear Amplifying Loop Mirror - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Journal of Quantum Electronics, 2009)
A phase-preserving 2R regenerator based on a nonlinear amplifying loop mirror was implemented in a RZ-DPSK transmission system. Its performance has been investigated in numerical simulations and experimentally. The results show that amplitude regeneration using a NALM can efficiently prevent accumulation of nonlinear phase noise in a 10 Gb/s DPSK transmission system. In the experiments, significant improvements of eye opening and of BER as well as a 3 dB increase in fiber launch power have been demonstrated. Simulations at 10 Gb/s and 100 Gb/s indicated that the enhancement of the transmission quality is smaller at 100 Gb/s. The reason is that at 100 Gb/s nonlinear intra-channel effects rather than pure nonlinear phase noise are the main limiting factor and the NALM can only reduce the accumulation of amplitude noise in that case. © 2009 IEEE.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.phasep
Keywords: 2R regeneration; Differential phase-shift keying; Nonlinear amplifying loop mirror; Nonlinear phase noise

Phase-preserving amplitude regeneration of a two-amplitude-level modulation format - Röthlingshöfer, Tobias; Richter, Thomas; Schubert, Colja; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Conference on Lasers and Electro-Optics Pacific Rim, 2013)
It has been experimentally shown that a modified nonlinear loop mirror can be used for all-optical star8-QAM processing. An amplitude noise reduction of 2.2 dB could be demonstrated for the high-power state
lhft_intern.bib::Roethlingshoefer2013b

Phase-Preserving Amplitude Regeneration Using Dispersion-Imbalanced Loop Mirror - Röthlingshöfer, Tobias; Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Fiber Communication 2009, 2009)
Scheme and parameters of dispersion-imbalance loop mirror (DILM) have been optimized for phase-preserving amplitude 2R regeneration. DILM performance for DPSK transmission has been evaluated in numerical simulations. A 4.8 dB Q-factor improvement has been demonstrated. © 2009 OSA.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.phasep
Keywords: (060.4370) Nonlinear optics; fibers; (060.5060) Phase modulation

Phase-Preserving Multilevel Amplitude Regeneration Using a Modified Nonlinear Amplifying Loop Mirror - Hierold, M.; Roethlingshoefer, T.; Sponsel, K.; Onishchukov, G.; Schmauß, Bernhard; Leuchs, Gerd (12th International Conf. on Digital Object Identifier (ICTON), Munich, June, 2010)
lhft_intern.bib::Hierold10

Phase-Preserving Signal Regeneration by a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Cleo Juni, 2007)
This work presents the numerical investigations on the physical limitations and optimization of the nonlinear amplifying loop mirror (NALM) as a regenerator of phase-shift-keyed signals. The NALM consists of a bidirectional amplifier and a highly nonlinear fiber (HNLF), combined to a loop by a fiber coupler. The transfer functions for the NALM versus dispersion for an amplifier gain for anomalous and normal dispersion were studied. It should be mentioned that beside the nonlinear chirp, the NALM also causes spectral broadening and pulse shape distortions. Amplified spontaneous emission from the NALM amplifier is comparably lower and therefore negligible as a source of optical signal-to-noise ratio (OSNR) penalty.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.phasep_0

Phase regeneration of a star-8QAM signal in a phase-sensitive amplifier with conjugated pumps - Stiller, Birgit; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
We demonstrate numerically phase regeneration of a star-8QAM signal with two amplitude and four phase states in a phase-sensitive amplifier. In a dual-stage setup, two phase-conjugated idlers are generated in a first stage consisting of two fiber-optic parametric phase-insensitive amplifiers operated in highly nonlinear gain regime. These are used as pumps in the second, phase-sensitive amplification stage which enables efficient phase regeneration via a degenerate four-wave-mixing process. The latter can be operated in two different operation modes: without format conversion or with phase-shifted amplitude levels. In both regimes, we observe high phase-regeneration efficiency for all amplitude levels: the initial phase noise with 0.2 rad standard deviation is reduced by a factor of 5.
lhft_intern.bib::Stiller2014

Phase retrieval from carrier frequency interferograms: reduction of the impact of space-variant disturbances - Schwider, Johannes; Nercissian, Vanusch; Mantel, Klaus Peter (Journal of the European Optical Society: Rapid Publications, 2015)

Phase-shift extraction for generalized phase-shifting interferometry - Peng, Gao; Yao, Baoli; Lindlein, Norbert; Mantel, Klaus Peter; Harder, Irina; Geist, Eduard (Optics Letters, 2009)
A simple algorithm for blind extraction of phase shifts is proposed for generalized phase-shifting interferometry from only three interferograms. Based on the statistical property of the object wave, the algorithm calculates approximately the involved phase shifts as initial values. The extraction is further improved by an iterative method, considering the fact that the closer the phase shifts approach their real values, the more uniform the reconstructed reference wave will become. The feasibility of this algorithm is demonstrated by both simulation and experiment. © 2009 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.phases

Phase-shifting point-diffraction interferometry with common-path and in-line configuration for microscopy - Peng, Gao; Harder, Irina; Nercissian, Vanusch; Mantel, Klaus; Yao, Baoli (Optics Letters, 2010)

Phase-shifting Zernike phase contrast microscopy for quantitative phase measurement - Peng, Gao; Yao, Baoli; Harder, Irina; Lindlein, Norbert; Torcall-Milla, Francisco Jose (Optics Letters, 2011)

Phase singularity reduction in speckle interferometry by tailoring the spatial coherence of light - Mantel, K.; Barakat, Ismail; Nercissian, Vanusch; Harder, I.; Rothau, S. (Applied Optics, 2021)
Reducing the number of phase singularities in speckle interferometry by physical means increases the quality of the phase deconvolution and enhances the separability of fringe systems, especially for highly dynamic fringe systems. The reduction is achieved by tailoring the spatial coherence of the light source at the entrance of the interferometer. The reduction mechanism is non-intuitive and rests on a change of size and of position of the speckle patterns as a result of the spatially shaped coherence. After demonstrating the amount of reduction that may be achieved, the reduction mechanism is explained theoretically and via simulations, and it is vindicated in an experiment using a Michelson-Mach-Zehnder interferometer hybrid.
CRIS-Team Scopus Importer:2021-08-20

Photonic Activation Function Using Sound Waves - Slinkov, Grigorii; Becker, Steven; Englund, Dirk; Stiller, Birgit (2023 International Conference on Photonics in Switching and Computing, PSC 2023, 2023)
We experimentally demonstrate an in-fiber optoacoustic nonlinear activation function based on stimulated Brillouin scattering. The activation function can be tuned all-optically and shows an input-output behaviour of a LeakyReLU, Sigmoid, and quadratic function. Our scheme is coherent and frequency selective, which is suitable for operation in multi-frequency neural networks. In addition, the optoacoustic activation function can amplify its input signal, allowing to compensate on-the-fly for optical losses during propagation.
CRIS-Team Scopus Importer:2023-12-15
Keywords: neuromorphic computing; nonlinear optics; Optical neural networks; stimulated Brillouin scattering

Photon-number noise of spectrally filtered optical solitons - Leuchs, Gerd; et al. (New trend in optical soliton transmission systems, 1998)
UnivIS-Import:2015-04-20:Pub.1998.nat.dphy.optik.1optik.photon

Photon-number squeezed solitons from an asymmetric fiber-optic Sagnac interferometer - Leuchs, Gerd; et al. (Physical Review Letters, 1998)
Direct photon-number squeezing is demonstrated, for the first time to our knowledge, in a nonlinear fiber-optic interferometer. Launching 126-fs solitons into a highly asymmetric Sagnac loop, the maximum photocurrent noise reduction was 3.9 ± 0.2 dB below shot noise, corresponding to 6.0 ± 0.9 dB, when corrected for linear losses. The loop is a model system for squeezing generated by the interference of two pulses after nonlinear propagation through a fiber.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.photon_6

Photon Number Squeezing of Spectrally Filtered Sub-Picosecond Optical Solitons - Leuchs, Gerd; et al. (EPL - Europhysics Letters, 1997)
Photon number squeezing of spectrally filtered optical solitons has been observed in the sub-picosecond regime, where the Raman effect changes the internal quantum structure of each pulse. 160 fs pulses were propagated down a 10 m optical fibre of anomalous group velocity dispersion. At energies below the soliton energy subsequent spectral filtering with an optical band-pass squeezed the directly detected photocurrent fluctuations to 3.2 ± 0.1 dB (52%) below the shot-noise limit. This implies 4.5 dB (65%) of soliton photon number squeezing, if detection losses are taken into account. Using a spectral edge filter the spectral components of the pulses are shown to contribute asymmetrically to the squeezing due to stimulated Raman scattering.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.photon

Photon Pairs from Resonant Metasurfaces - Santiago-Cruz, Tomás; Fedotova, Anna; Sultanov, Vitaliy; Weissflog, Maximilian A.; Arslan, Dennis; Younesi, Mohammadreza; Pertsch, Thomas; Staude, Isabelle; Setzpfandt, Frank; Chekhova, Maria (Nano Letters, 2021)
All-dielectric optical metasurfaces are a workhorse in nano-optics, because of both their ability to manipulate light in different degrees of freedom and their excellent performance at light frequency conversion. Here, we demonstrate first-time generation of photon pairs via spontaneous parametric-down conversion in lithium niobate quantum optical metasurfaces with electric and magnetic Mie-like resonances at various wavelengths. By engineering the quantum optical metasurface, we tailor the photon-pair spectrum in a controlled way. Within a narrow bandwidth around the resonance, the rate of pair production is enhanced up to 2 orders of magnitude, compared to an unpatterned film of the same thickness and material. These results enable flat-optics sources of entangled photons - a new promising platform for quantum optics experiments.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Mie-type resonances; nonlinear metasurfaces; photon-pair generation; quantum optics; spontaneous parametric down-conversion

Photon Propagation in a Discrete Fiber Network: An Interplay of Coherence and Losses - Regensburger, Alois; Bersch, Christoph; Hinrichs, Benjamin; Onishchukov, Georgy; Schreiber, Andreas; Silberhorn, Christine; Peschel, Ulf (Physical Review Letters, 2011)
We study light propagation in a photonic system that shows stepwise evolution in a discretized environment. It resembles a discrete-time version of photonic waveguide arrays or quantum walks. By introducing controlled photon losses to our experimental setup, we observe unexpected effects like subexponential energy decay and formation of complex fractal patterns. This demonstrates that the interplay of linear losses, discreteness and energy gradients leads to genuinely new coherent phenomena in classical and quantum optical experiments. Moreover, the influence of decoherence is investigated.
EAM Import::2019-03-12

Photon-Qubit Entanglement and Hong-Ou-Mandel Interference at Microwave Frequencies - Eichler, Christopher (Workshop on Frontier between atomic and solid state physics, 2013)
Keywords: wwwqudev

Physikalische Grenzen der Formerfassung mit Licht - Häusler, Gerd; Leuchs, Gerd (Physikalische Blätter, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.physik

Picosecond acoustic dynamics in stimulated Brillouin scattering - Piotrowski, Johannes; Schmidt, Mikolaj K.; Stiller, Birgit; Poulton, Christopher G.; Steel, Michael J. (Optics Letters, 2021)
Recent experiments demonstrating storage of optical pulses in acoustic phonons via stimulated Brillouin scattering raise questions about the spectral and temporal capacities of such protocols and the limitations of the theoretical frameworks routinely used to describe them. We consider the dynamics of photon-phonon scattering induced by optical pulses with temporal widths comparable to the period of acoustic oscillations. We revisit the widely adopted classical formalism of coupled modes and demonstrate its breakdown. We use a simple extension to the formulation and find potentially measurable consequences in the dynamics of Brillouin experiments involving ultrashort pulses.
CRIS-Team Scopus Importer:2021-06-25

Plasmonic carbon nanohybrids from laser-induced deposition: controlled synthesis and SERS properties - Povolotckaia, Anastasia; Pankin, Dmitrii; Petrov, Yuriy; Vasileva, Anna; Kolesnikov, Ilya; Sarau, George; Christiansen, Silke; Leuchs, Gerd; Manshina, Alina (Journal of Materials Science, 2019)
A novel single-step, laser-induced and solution-based process is presented for synthesizing complex hybrid metal/carbon nanostructures. The process relies on simply illuminating the interface between a substrate and a liquid solution of the supramolecular complex [Au13Ag12(C2Ph)(20)(PPh2(C6H4)(3)PPh2)(3)][PF6](5) (hereinafter abbreviated as SMC) with an unfocussed He-Cd laser having a wavelength of 325nm and an intensity of I=0.5W/cm(2). The process results in hybrid nanostructures of well-controlled morphology: nanoparticles (NP) and 2D flakes, which may also grow jointly to form 3D morphologically complex multipetal flower-like' structures. At the atomic scale, the obtained metamaterials are complex in composition and structure, i.e., they contain bimetallic Au-Ag nanoclusters of diameter 3-5nm incorporated inside a carbonaceous matrix. This matrix can be amorphous or crystalline, and the details of the compositional outcome can be controlled and steered by the laser deposition parameters. Au-Ag nanoclusters show plasmonic behavior including the enhancement of electromagnetic fields of visible light. This leads to the enhancement of Raman scattering by the Au-Ag nanoparticle ensemble within the carbonaceous matrix. This enables a 3D architecture for stimulating surface-enhanced Raman scattering (SERS).
CRIS-Team WoS Importer:2019-04-04

Plasmonic excitations in metallic nanoparticles: Resonances, dispersion characteristics and near-field patterns - Tatartschuk, Eugen; Shamonina, Ekaterina; Solymar, Laszlo (Optics Express, 2009)
Metamaterials acquire their functionality from the structuring of the small building blocks, ``artificial atoms''. Our paper provides a study of the resonant behaviour for a variety of metallic nanoparticles in the region of hundreds of THz. Resonant modes for nanorods of rectangular cross section are investigated numerically for different types of excitation and the set of resonant frequencies (fundamental and higher order) are determined for rods of various length. From that the dispersion relationship for surface plasmon-polaritons propagating along the rod is deduced. We analyse resonant-mode near-field distribution of the electric field, including the field lines, to emphasise the underlying physics. Resonant frequencies are also found and field distributions analysed when the rods are combined to form particles of L, U and O shapes. The similarities and differences between those particles, both in the values and in the number of resonances, are discussed. The results of this study may aid the design of nanostructured metamaterials with required properties in the IR and optical domain.
EAM Import::2019-03-12

Polarisations- und phasenschiebende Interferometrie für die simultane Vermessung der Phasenfront und der Doppelbrechung eines Objekts - Rothau, Sergej; Mantel, Klaus; Lindlein, Norbert (118. Jahrestagung der DGaO, 2017)

Polarization and phase shifting interferometry - Rothau, Sergej; Mantel, Klaus; Lindlein, Norbert (Proc. SPIE 10329, 2017)
This publication presents a novel interferometric method for the simultaneous measurement of the phase andstate of polarization of a light wave with arbitrary, in particular locally varying elliptical polarization. The mea-surement strategy is based on variations of the reference wave concerning phase and polarization and processingthe interference patterns so obtained. With this method, that is very similar to the classical phase shiftinginterferometry, a complete analysis of spatially variant states of polarization and their phase fronts can be donein one measurement cycle. Furthermore, a direct analysis of specimens under test regarding birefringence andthe impact on the phase of the incoming light can be realized. The theoretical description of the investigatedmethods and their experimental implementation are presente

Polarization and phase-shifting interferometry for arbitrary, locally varying polarization states - Rothau, Sergej; Kellermann, Christine; Mayer, Simon; Mantel, Klaus Peter; Lindlein, Norbert (Applied Optics, 2017)
This publication presents what we believe is a novel interferometric method for the simultaneous measurement of the phase and state of polarization of a light wave with arbitrary polarization; in particular, it can be varying elliptical. The measurement strategy is based on variations of the reference wave, concerning phase and polarization and processing the interference patterns so obtained. With this method, which is very similar to classical phase-shifting interferometry, the general analysis of spatially variant states of polarization and their phase fronts can be done in one measurement cycle. Furthermore, the analysis of different optical elements regarding the impact on the polarization and phase of the incoming light can be realized. After the theoretical description of the method and the mathematical discussion of different algorithms, the realized measurement setup is presented. Afterward, the accuracy of the method is discussed.

Polarization and phase shifting interferometry for the simultaneous measurement of phase and polarization. - Rothau, Sergej; Lindlein, Norbert (2016)

Polarization and phase shifting interferometry for the simultaneous measurement of the phase and polarization - Rothau, Sergej; Lindlein, Norbert (117. Annual Meeting of the DGaO, 2016)

Polarization correlations in quantum optics - Sánchez-Soto, L. L.; Klimov, A. B.; Björk, G.; Söderholm, J.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
The standard degree of polarization involves exclusively first-order moments of the Stokes variables. This may be sufficient for most classical problems, but for quantum fields higher-order correlations are crucial. We claim that a complete polarization characterization must involve a whole hierarchy of polarization degrees constructed order by order, as it happens in coherence theory. We present here a second-order degree and determine it experimentally. ©2011 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Polarization-dependent effects on phase singularities in the vicinity of sub-lambda structures - Leuchs, Gerd; et al. (SPIE j, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.polari_0

Polarization-entangled photons from a whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Leuchs, Gerd; Marquardt, Christoph (npj Quantum Information, 2024)
Crystalline whispering gallery mode resonators (WGMRs) have been shown to facilitate versatile sources of quantum states that can efficiently interact with atomic systems. These features make WGMRs an efficient platform for quantum information processing. Here, we experimentally show that it is possible to generate polarization entanglement from WGMRs by using an interferometric scheme. Our scheme gives us the flexibility to control the phase of the generated entangled state by changing the relative phase of the interferometer. The S value of Clauser–Horne–Shimony–Holt’s inequality in the system is 2.45 ± 0.07, which violates the inequality by more than six standard deviations.<br
Keywords: Nonlinear optics; Quantum optics

Polarization entanglement from a crystalline whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Leuchs, Gerd; Marquardt, Christoph (CLEO 2024, 2024)
Polarization entanglement has not yet been shown in crystalline whispering gallery resonators. Here, we generate polarization entanglement by using an interferometric scheme. The S value of the Clauser-Horne-Shimony-Holt’s inequality in the system is 2.54 ± 0.06, in clear violation of the local realism.<br

Polarization features of optically pumped CdS nanowire lasers - Roeder, Robert; Ploss, Daniel; Kriesch, Arian; Buschlinger, Robert; Geburt, Sebastian; Peschel, Ulf; Ronning, Carsten (Journal of Physics D-Applied Physics, 2014)
High quality CdS nanowires suspended in air were optically pumped both below and above the lasing threshold. The polarization of the pump laser was varied while emission out of the end facet of the nanowire was monitored in a `head-on' measurement geometry. Highest pump-efficiency and most efficient absorption of the pump radiation are demonstrated for an incident electric field being polarized parallel to the nanowire axis. This polarization dependence, which was observed both above the lasing threshold and in the regime of amplified spontaneous emission, is caused by an enhanced absorption for parallel polarized optical pumping. Measured Stokes parameters of the nanowire emission reveal that due to the onset of lasing the degree of polarization rapidly increases from approximately 15 to 85%. Both Stokes parameters and degree of polarization of the nanowire lasing emission are independent of the excitation polarization. The transversal lasing mode is therefore not notably affected by the polarization of the pumping beam, although the supply with optical gain is significantly enhanced for an excitation polarization parallel to the nanowire axis.
EAM Import::2019-03-08

Polarization noise induced by photon-phonon interaction in hollow-core photonic crystal fibres - Zhong, W.; Heim, B.; Elser, D.; Marquardt, Christoph; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Guided acoustic wave Brillouin scattering (GAWBS), a weak forward scattering that stems from the interaction of light with thermally excited transverse phonons, has been studied in both standard fibres [1] and photonic crystal fibres [2, 3]. The acoustic phonon vibrations modulate the stress distribution in the silica fibre core, thus modulating the refractive index and inducing polarization and phase noise in the light field. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-06-05

Polarization optimized 4-π geometries for microscopy - Lindlein, Norbert; et al. (Frontiers in Optics, FiO 2007, 2007)
A smaller focal spot can be obtained by choosing a tailored polarization, e.g. radial polarization in the case rotationally symmetric high numerical aperture focusing. The same polarization mode maximizes the coupling to an atom when using the correct 4π geometry for transforming the incident light field. © 2007 Optical Society of America.

Polarization optimized focusing of light and coupling to sub-wavelength antennae - Leuchs, Gerd; et al. (Nanophotonics, 2004)
UnivIS-Import:2015-04-20:Pub.2004.nat.dphy.optik.1optik.polari

Polarization-Selective Out-Coupling of Whispering-Gallery Modes - Sedlmeir, Florian; Foreman, Matthew R.; Vogl, Ulrich; Zeltner, Richard; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Leuchs, Gerd; Schwefel, Harald G. L. (Physical Review Applied, 2017)
Whispering-gallery mode (WGM) resonators are an important platform for linear, nonlinear, and quantum optical experiments. In such experiments, independent control of in-coupling and out-coupling rates to different modes can lead to higher conversion efficiencies and greater flexibility in the generation of nonclassical states based on parametric down-conversion. In this work, we introduce a scheme that enables selective out-coupling of WGMs belonging to a specific polarization family, while the orthogonally polarized modes remain largely unperturbed. Our technique utilizes material birefringence in both the resonator and the coupler such that a negative (positive) birefringence allows for polarization-selective coupling to TE (TM) WGMs. We formulate a refined coupling condition suitable for describing the case where the refractive indices of the resonator and the coupler are almost the same, from which we derive a criterion for polarization-selective coupling. Finally, we experimentally demonstrate our proposed method using a lithium niobate disk resonator coupled to a lithium niobate prism, where we show a 22-dB suppression of coupling to TM modes relative to TE modes.
CRIS-Team Scopus Importer:2022-06-05

Polarization Squeezing and Continuous Variable Polarization Entanglement - Leuchs, Gerd; et al. (Physical Review A, 2002)
Polarization squeezing and continuous-variable polarization entanglement of light was studied. To study this concept, the properties of Stokes parameters and Poincare sphere were studied. For a range of simple polarization states, the general features of the Stokes operators were illustrated by evaluating their means and variances. It was shown that the Stokes parameters can be measured by the use of linear optical elements and direct detection schemes that are sensitive to the quantum correlations in the two polarization components of the light.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.polari

Polarization squeezing of intense pulses with a fiber Sagnac interferometer - Leuchs, Gerd; et al. (Physical Review A, 2003)
Quantum information and communication are important fields for the future. Due to the ease of detection of the Stokes operators, polarization squeezing will play an important role in the development of these fields, not least as a basis for polarization entanglement. This paper investigated polarization squeezing of intense pulses, using amplitude squeezed pulses generated by the Kerr nonlinearity of a glass fiber.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.polari

Polarization squeezing with photonic crystal fibers - Milanovic, Josip; Heersink, Joel; Marquardt, Christoph; Huck, A.; Andersen, Ulrik Lund; Leuchs, Gerd (Laser Physics, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.polari

Polychromatic Maximum Likelihood Reconstruction for Talbot-Lau X-ray Tomography - Schiffers, Florian; Käppler, Sebastian; Pelzer, Georg; Wolf, Andreas; Maier, Andreas; Anton, Gisela; Riess, Christian (International Conference on Fully Three-Dimensional Image Reconstruction in Radiology and Nuclear Medicine (Fully3D), 2017)

Practical limitations of Talbot imaging with microlens arrays - Lindlein, Norbert; et al. (Journal of Optics A: Pure and Applied Optics, 1997)
The Talbot effect which also appears for the foci of microlens arrays can, in principle, be used for array illuminators. In particular, the multiplication of the foci in the fractional Talbot planes seems to be promising. Certainly, in practice there are three effects which limit the application of the fractional Talbot effect for microlens arrays. Theoretical, numerical and experimental results are given to demonstrate these limitations. © 1997 IOP Publishing Ltd.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.practi

Practical limits of an optimized quantum receiver - Marquardt, Christoph; Müller, Christian R.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2014)
We present a quantum receiver for the discrimination of quadrature phase-shift keyed signals that approaches the Helstrom bound for any signal power and discuss the influence of practical limitations. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Practical notes on designing and analysing thick holographic optical elements - Lindlein, Norbert; Schwider, Johannes (Journal of Optics A: Pure and Applied Optics, 1992)
Equations for tracing rays through (aspheric) holographic optical elements (HOE) are reviewed, and, in addition, the diffraction efficiency of a thick HOE is taken into account. Expressions for calculating the phase functions of aspheric recording wave fronts of a thick HOE in the presence of a wavelength shift are given. A simple least squares fitting algorithm is used to compute analytic expressions of these phase functions. Finally, a method to calculate a focus of rays is described.

Practical Quantum Optics - Leuchs, Gerd (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
This short course aims at giving an introduction to quantum optics using phenomenological approaches and visualizing the field from the viewpoint of a practitioner. There are altogether five parts: (1) pointing out a close link between Maxwell's equations and the properties of the quantum vacuum with its virtual particle anti-particle pairs [1,2]; (2) introduction to field quantization from an experimental perspective using the intuition of a classical optical scientist; (3) answering the question “What does it mean if optics is quantum? What distinguishes quantum from classical? [3,5] (4) description of quantum optical experiments with discrete and with continuous variables with special emphasis on Wigner functions in phase space and the special role of the quantum measurement process [4]; (5) In this fifth part we address the question: “Is hard core quantum optics solely concerned with the study of fundamental physics questions or is it also useful for practical applications? From laser interferometric gravitational wave detection to quantum distribution of cryptographic keys and quantum information processing [6-8].
CRIS-Team Scopus Importer:2024-12-16

Precision in Length - Leuchs, Gerd (Laser Physics at the Limits, 2002)
UnivIS-Import:2015-04-20:Pub.2002.nat.dphy.optik.1optik.precis

Predicting plastron thermodynamic stability for underwater superhydrophobicity - Tesler, Alexander; Nurmi, Heikki A.; Kolle, Stefan; Prado, Lucia; Karunakaran, Bhuvaneshwari; Mazare, Anca Valentina; Erceg, Ina; de brito soares, Íris; Sarau, George; Christiansen, Silke; Stafslien, Shane; Alvarenga, Jack; et al. (Communications Materials, 2024)
Non-wettable surfaces, especially those capable of passively trapping air in rough protrusions, can provide surface resilience to the detrimental effects of wetting-related phenomena. However, the development of such superhydrophobic surfaces with a long-lasting entrapped air layer, called plastron, is hampered by the lack of evaluation criteria and methods that can unambiguously distinguish between stable and metastable Cassie-Baxter wetting regimes. The information to evaluate the stability of the wetting regime is missing from the commonly used contact angle goniometry. Therefore, it is necessary to determine which surface features can be used as a signature to identify thermodynamically stable plastron. Here, we describe a methodology for evaluating the thermodynamic underwater stability of the Cassie-Baxter wetting regime of superhydrophobic surfaces by measuring the surface roughness, solid-liquid area fraction, and Young’s contact angle. The method allowed the prediction of passive plastron stability for over one year of continuous submersion, the impeding of mussel and barnacle adhesion, and inhibition of metal corrosion in seawater. Such submersion-stable superhydrophobicity, in which water is repelled by a stable passive air layer trapped between the solid substrate and the surrounding liquid for extended periods at ambient conditions, opens new avenues for science and technologies that require continuous contact of solids with aqueous media. (Figure presented.).
CRIS-Team Scopus Importer:2024-07-12

Previous Record Record 8 of 11 Next Record Record from Web of Science® On the calibration of diffractive nulls for transmission tests of aspheric components - Schwider, Johannes; Lindlein, Norbert; Mantel, Klaus Peter; Harder, Irina (Optics Communications, 2007)
UnivIS-Import:2015-04-14:Pub.2007.nat.dphy.optik.1optik.previo

Probabilistic amplification and cloning of phase-covariant coherent states - Müller, C. R.; Wittmann, C.; Marek, P.; Filip, R.; Usuga, M. A.; Marquardt, Christoph; Andersen, U. L.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Probing colloidal interfaces by angle-resolved second harmonic light scattering - Schürer, Benedikt; Wunderlich, Sarina; Sauerbeck, Christian; Peschel, Ulf; Peukert, Wolfgang (Physical Review B, 2010)
We report angle-resolved second harmonic light scattering from bare colloidal particles in water. A nonlinear Mie model is used to quantitatively analyze the nonresonant second harmonic (SH) scattering profiles and to determine the elements of the local second-order surface susceptibility. The SH signal is attributed to oriented and electrically polarized water molecules at the charged particle interface. The results show how angle-resolved SH light scattering can be applied to probe not only resonant excited dye molecules but also nonresonant molecules such as water at the interface of colloidal particles.

Probing guided modes in a monolayer colloidal crystal on a flat metal film - Romanov, Sergei G.; Vogel, Nicolas; Bley, Karina; Landfester, Katharina; Weiss, Clemens K.; Orlov, Sergej; Korovin, Alexander V.; Chuiko, Gennady P.; Regensburger, Alois; Romanova, Alexandra; Kriesch, Arian; Peschel, Ulf (Physical Review B, 2012)
Two-dimensional slab hybrid metal-dielectric photonic crystals, which are prepared by assembling polymer colloidal spheres into closely packed monolayers of hexagonal symmetry on a gold-coated glass substrate, show an improved confinement of light compared with a colloidal monolayer on a glass substrate. We demonstrated that the optical response of such hybrid crystals consists of diffractively coupled waveguiding modes, Fabry–Perot resonances, and Mie resonances. Correspondingly, two major mechanisms, namely, band transport and hopping of localized excitations, participate in the in-plane light transport in such hybrid crystals.

Probing the Connection between IceCube Neutrinos and MOJAVE AGN - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Astrophysical Journal, 2024)
Active galactic nuclei (AGN) are prime candidate sources of the high-energy, astrophysical neutrinos detected by IceCube. This is demonstrated by the real-time multimessenger detection of the blazar TXS 0506+056 and the recent evidence of neutrino emission from NGC 1068 from a separate time-averaged study. However, the production mechanism of the astrophysical neutrinos in AGN is not well established, which can be resolved via correlation studies with photon observations. For neutrinos produced due to photohadronic interactions in AGN, in addition to a correlation of neutrinos with high-energy photons, there would also be a correlation of neutrinos with photons emitted at radio wavelengths. In this work, we perform an in-depth stacking study of the correlation between 15 GHz radio observations of AGN reported in the MOJAVE XV catalog, and 10 yr of neutrino data from IceCube. We also use a time-dependent approach, which improves the statistical power of the stacking analysis. No significant correlation was found for both analyses, and upper limits are reported. When compared to the IceCube diffuse flux, at 100 TeV and for a spectral index of 2.5, the upper limits derived are ∼3% and ∼9% for the time-averaged and time-dependent cases, respectively.
CRIS-Team Scopus Importer:2024-10-11

Probing the quantum properties of microwave radiation emitted from superconducting circuits. - Eichler, Christopher (Hannover, Institut für Theoretische Physik, 2013)
Keywords: wwwqudev

Processing Range Data for Reverse Engineering and Virtual Reality - Häusler, Gerd; et al. (Proceedings of Third International Conference on 3-DDigital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.proces

Production and control of refractive and diffractive microlenses - Lindlein, Norbert; et al. (Proceedings of the 4th International Conference on Holographic Systems, Components and Applications, 1993)
Here we will discuss two examples of microlenses where the generation process and the interferometric control are strongly interwoven. We developed an evaluation software under windows.

Progress toward third-order parametric down-conversion in optical fibers - Cavanna, Andrea; Hammer, Jonas; Okoth, Cameron; Ortiz-Ricardo, Erasto; Cruz-Ramirez, Hector; Garay-Palmett, Karina; U'Ren, Alfred B.; Frosz, Michael H.; Jiang, Xin; Joly, Nicolas; Chekhova, Maria (Physical Review A, 2020)
Optical fibers have been considered an optimal platform for third-order parametric down-conversion since they can potentially overcome the weak third-order nonlinearity by their long interaction length. Here we present, in the first part, a theoretical derivation for the conversion rate both in the case of spontaneous generation and in the presence of a seed beam. Then we review three types of optical fibers and we examine their properties in terms of conversion efficiency and practical feasibility.
CRIS-Team WoS Importer:2020-04-10

Proof-of-principle test of coherent-state continuous variable quantum key distribution through turbulent atmosphere - Derkach, Ivan; Peuntinger, Christian; Ruppert, Laszlo; Heim, Bettina; Gunthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd (SPIE Security + Defence, 2016)
Continuous-variable quantum key distribution is a practical application of quantum information theory that is aimed at generation of secret cryptographic key between two remote trusted parties and that uses multi-photon quantum states as carriers of key bits. Remote parties share the secret key via a quantum channel, that presumably is under control of of an eavesdropper, and which properties must be taken into account in the security analysis. Well-studied fiber-optical quantum channels commonly possess stable transmittance and low noise levels, while free-space channels represent a simpler, less demanding and more flexible alternative, but suffer from atmospheric effects such as turbulence that in particular causes a non-uniform transmittance distribution referred to as fading. Nonetheless free-space channels, providing an unobstructed line-of-sight, are more apt for short, mid-range and potentially long-range (using satellites) communication and will play an important role in the future development and implementation of QKD networks. It was previously theoretically shown that coherent-state CV QKD should be in principle possible to implement over a free-space fading channel, but strong transmittance fluctuations result in the significant modulation-dependent channel excess noise. In this regime the post-selection of highly transmitting sub-channels may be needed, which can even restore the security of the protocol in the strongly turbulent channels. We now report the first proof-of-principle experimental test of coherent state CV QKD protocol using different levels Gaussian modulation over a mid-range (1.6-kilometer long) free-space atmospheric quantum channel. The transmittance of the link was characterized using intensity measurements for the reference but channel estimation using the modulated coherent states was also studied. We consider security against Gaussian collective attacks, that were shown to be optimal against CV QKD protocols . We assumed a general entangling cloner collective attack (modeled using data obtained from the state measurement results on both trusted sides of the protocol), that allows to purify the noise added in the quantum channel . Our security analysis of coherent-state protocol also took into account the effect of imperfect channel estimation, limited post-processing efficiency and finite data ensemble size on the performance of the protocol. In this regime we observe the positive key rate even without the need of applying post-selection. We show the positive improvement of the key rate with increase of the modulation variance, still remaining low enough to tolerate the transmittance fluctuations. The obtained results show that coherent-state CV QKD protocol that uses real free-space atmospheric channel can withstand negative influence of transmittance fluctuations, limited post-processing efficiency, imperfect channel estimation and other finite-size effects, and be successfully implemented. Our result paves the way to the full-scale implementation of the CV QKD in real free-space channels at mid-range distances.<br

Propagation of broadband sub-picosecond soliton squeezing in a fiber - Leuchs, Gerd; et al. (Optics Express, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.propag

Propagation of Quantum Properties of Sub-Picosecond Solitons in a Fibre - Leuchs, Gerd; et al. (Optics Express, 1998)
We present new results on photon number squeezing of spectrally filtered solitons in fibers. The impact of frequency low-, high-, and bandpass filtering on noise reduction has been measured as a function of fiber length for 130-fs pulses close to the soliton energy. For short fibers our results agree qualitatively with theoretical predictions. For longer fibers, however, the measured squeezing increases to an unexpectedly large value. Spectral filtering of a strongly Raman-shifted, higher energy pulse squeezed the directly detected photocurrent fluctuations down to 3.8±0.2 dB (59%) below the shot noise level. The measured noise reductions are broadband from 5 to 90 MHz. © 1997 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.propag_4

Proposal for a hybrid clock system consisting of passive and active optical clocks and a fully stabilized microcomb - Yu, Deshui; Vollmer, Frank; Del'Haye, Pascal; Zhang, Shougang (Optics Express, 2023)
Optical atomic clocks produce highly stable frequency standards and frequency combs bridge clock frequencies with hundreds of terahertz difference. In this paper, we propose a hybrid clock scheme, where a light source pumps an active optical clock through a microresonator-based nonlinear third harmonic process, serves as a passive optical clock via indirectly locking its frequency to an atomic transition, and drives a chip-scale microcomb whose mode spacing is stabilized using the active optical clock. The operation of the whole hybrid system is investigated through simulation analysis. The numerical results show: (i) The short-term frequency stability of the passive optical clock follows an Allan deviation of σy(τ) = 9.3 × 10−14τ−1/2 with the averaging time τ, limited by the population fluctuations of interrogated atoms. (ii) The frequency stability of the active optical clock reaches σy(τ) = 6.2 × 10−15τ−1/2, which is close to the quantum noise limit. (iii) The mode spacing of the stabilized microcomb has a shot-noise-limited Allan deviation of σy(τ) = 1.9 × 10−11τ−1/2. Our hybrid scheme may be realized using recently developed technologies in (micro)photonics and atomic physics, paving the way towards on-chip optical frequency comparison, synthesis, and synchronization.
CRIS-Team Scopus Importer:2023-02-24

Prospect for detecting squeezed states of light created by a single atom in free space - Stobinska, Magdalena; Sondermann, Markus; Leuchs, Gerd (Optics Communications, 2010)
We discuss the possibilities of studying in detail the dynamics of spontaneous emission of a single photon by a single atom and measuring the transient degree of squeezing by means of full solid angle fluorescence detection. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.optik.1optik.prospe
Keywords: Resonance fluorescence; Single atom; Single photon; Squeezing

Prospects of Trapping Atoms with an Optical Dipole Trap in a Deep Parabolic Mirror for Light-Matter-Interaction Experiments - Sondermann, Markus; Fischer, Martin; Leuchs, Gerd (Advanced Quantum Technologies, 2020)
Keywords: light-matter interaction; optical trapping; parabolic mirror

Publisher Correction: Resonant electro-optic frequency comb (Nature, (2019), 568, 7752, (378-381), 10.1038/s41586-019-1110-x) - Rueda, Alfredo; Sedlmeir, Florian; Kumari, Madhuri; Leuchs, Gerd; Schwefel, Harald G.L. (Nature, 2019)
Change history: In the Methods section of this Letter, there were formatting errors to the equations of motion using the Heisenberg picture; see accompanying Amendment for further details. This has been corrected online.
CRIS-Team Scopus Importer:2019-05-28

Pump depletion in parametric down-conversion with low pump energies - Florez, Jefferson; Lundeen, Jeff S.; Chekhova, Maria (Optics Letters, 2020)
We report the efficient generation of high-gain parametric down-conversion, including pump depletion, with pump powers as low as 100 µW (energies 0.1 µJ/pulse) and conversion efficiencies up to 33%. In our simple configuration, the pump beam is tightly focused into a bulk periodically poled lithium niobate crystal placed in free space. We also observe a change in the photon number statistics for both the pump and down-converted beams as the pump power increases to reach the depleted pump regime. The experimental results are a clear signature of the interplay between the pump and the down-converted beams in highly efficient parametric down-conversion sources.
CRIS-Team Scopus Importer:2020-09-18

QPSK receiver outperforming the standard quantum limit for any signal power - Muller, Christian R.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2014)
We present a quantum receiver for the discrimination of quadrature phase-shiftkeyed signals that approaches the Helstrom bound for any signal power. The discrimination isperformed via adaptive displacements prior to a single photon detector. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Quadrature measurements of a bright squeezed state via sideband swapping - Leuchs, Gerd; et al. (Optics Letters, 2009)
The measurement of an arbitrary quadrature of a bright quantum state of light is a commonly requested action in many quantum information protocols, but it is experimentally challenging with previously proposed schemes. We suggest that the quadrature be measured at a specific sideband frequency of a bright quantum state by transferring the sideband modes under interrogation to a vacuum state and subsequently measuring the quadrature via homodyne detection. The scheme is implemented experimentally, and it is successfully tested with a bright squeezed state of light. © 2009 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.quadra

Quadrature phase shift keying coherent state discrimination via a hybrid receiver - Müller, Christian; Usuga, M. A.; Wittmann, Christoffer; Takeoka, M.; Marquardt, Christoph; Andersen, U. L.; Leuchs, Gerd (New Journal of Physics, 2012)
We propose and experimentally demonstrate a near-optimal discrimination scheme for the quadrature phase shift keying (QPSK) protocol. We show in theory that the performance of our hybrid scheme is superior to the standard scheme-heterodyne detection-for all signal amplitudes and underpin the predictions with our experimental results. Furthermore, our scheme provides hitherto the best performance in the domain of highly attenuated signals. The discrimination is composed of a quadrature measurement, a conditional displacement and a threshold detector. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

Quantencomputer heute und in Zukunft - Eichler, Christopher (2022)
Keywords: wwwquantum

Quantencomputer: Von Schrödingers Katze zu Hochleistungsrechnern der Zukunft. - Eichler, Christopher (2023)

Quantenrauschberuhigtes Licht - Leuchs, Gerd; et al. (Design & Elektronik, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.quante

Quantum Communication with continuous variables using multi-photonstates of light - Leuchs, Gerd; et al. (Proc. of the 15th European Meeting on Cybernetics and Systems Research, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dphy.optik.1optik.quantu

Quantum correlations in separable multi-mode states and in classically entangled light - Korolkova, N.; Leuchs, Gerd (Reports on Progress in Physics, 2019)
In this review we discuss intriguing properties of apparently classical optical fields, that go beyond purely classical context and allow us to speak about quantum characteristics of such fields and about their applications in quantum technologies. We briefly define the genuinely quantum concepts of entanglement and steering. We then move to the boarder line between classical and quantum world introducing quantum discord, a more general concept of quantum coherence, and finally a controversial notion of classical entanglement. To unveil the quantum aspects of often classically perceived systems, we focus more in detail on quantum discordant correlations between the light modes and on nonseparability properties of optical vector fields leading to entanglement between different degrees of freedom of a single beam. To illustrate the aptitude of different types of correlated systems to act as quantum or quantum-like resource, entanglement activation from discord, high-precision measurements with classical entanglement and quantum information tasks using intra-system correlations are discussed. The common themes behind the versatile quantum properties of seemingly classical light are coherence, polarization and inter and intra-mode quantum correlations.
CRIS-Team WoS Importer:2019-04-23

Quantum cryptography with bright entangled beams - Leuchs, Gerd; et al. (IQEC'2000 Conference Digest, 2000)
A scheme for the generation of bright entangled beams is discussed. The Einstein-Podolsky-Rosen (EPR) quantum correlations are produced by letting two amplitude-squeezed bright optical fields interfere on a 50:50 beamsplitter. This is illustrated in the phase space representation in a single-mode picture. The phase and amplitude uncertainty measurements exhibit strong correlations and anticorrelations which can be detected by recording the difference of the photocurrents.
UnivIS-Import:2015-04-16:Pub.2000.nat.dphy.optik.1optik.quantu_2

Quantum cryptography with twisted photons through an outdoor underwater channel - Bouchard, Frederic; Sit, Alicia; Hufnagel, Felix; Abbas, Aazad; Zhang, Yingwen; Heshami, Khabat; Fickler, Robert; Marquardt, Christoph; Leuchs, Gerd; Boyd, Robert W.; Karimi, Ebrahim (Optics Express, 2018)
Quantum communication has been successfully implemented in optical fibres and through free-space. Fibre systems, though capable of fast key and low error rates, are impractical in communicating with destinations without an established fibre link. Free-space quantum channels can overcome such limitations and reach long distances with the advent of satellite-to-ground links. However, turbulence, resulting from local fluctuations in refractive index, becomes a major challenge by adding errors and losses. Recently, an interest in investigating the possibility of underwater quantum channels has arisen. Here, we investigate the effect of turbulence on an underwater quantum channel using twisted photons in outdoor conditions. We study the effect of turbulence on transmitted error rates, and compare different quantum cryptographic protocols in an underwater quantum channel, showing the feasibility of high-dimensional encoding schemes. Our work may open the way for secure high-dimensional quantum communication between submersibles, and provides important input for potential submersibles-to-satellite quantum communication.
CRIS-Team Scopus Importer:2022-06-05

Quantum effects in optical fibers - Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2011)
The quantization of the light field is important for understanding some aspects of optical fiber systems: the quantum limit of amplifiers, the dynamics of solitons below shot noise and the appearance of non-classical light. © OSA/OFC/NFOEC 2011.
CRIS-Team Scopus Importer:2022-06-05

Quantum fiber solitons - generation, entanglement and detection - Leuchs, Gerd; Korolkova, Natalia; Glöckl, Oliver; Lorenz, Stefan; Heersink, Joel; Silberhorn, Christine; Marquardt, Christoph; Andersen, Ulrik L. (Quantum Information Processing: Schwerpunktprogramm 1078 der Deutschen Forschungsgemeinschaft, 2005)
UnivIS-Import:2015-04-20:Pub.2005.nat.dphy.optik.1optik.quantu_4
Keywords: Bright entangled beams; Entanglement of bright beams; Entanglement swapping; Non-separability; Polarization variables; Quantum correlations; Quantum fiber solitons; Quantum information processing; Sub-shot-noise phase quadrature measurements on intense beams

Quantum field theory and classical optics: Determining the fine structure constant - Leuchs, Gerd; Hawton, Margaret; Sanchez-Soto, Luis L. (Journal of Physics: Conference Series, 2017)
The properties of the vacuum are described by quantum physics including the response to external fields such as electromagnetic radiation. Of the two parameters that govern the details of the electromagnetic field dynamics in vacuum, one is fixed by the requirement of Lorentz invariance . The other one, and its relation to the quantum vacuum, is discussed in this contribution. Deriving ϵ 0 from the properties of the quantum vacuum implies the derivation of the fine structure constant.
CRIS-Team Scopus Importer:2023-04-20

Quantum filtering of optical coherent states - Leuchs, Gerd; et al. (Physical Review A, 2008)
We propose and experimentally demonstrate nondestructive and noiseless removal (filtering) of vacuum states from an arbitrary set of coherent states of continuous variable systems. Errors, i.e., vacuum states in the quantum information are diagnosed through a weak measurement, and on that basis, probabilistically filtered out. We consider three different filters based on on-off detection, phase stabilized, and phase randomized homodyne detection. We find that on-off detection, optimal in the ideal theoretical setting, is superior to the homodyne strategy also in a practical setting. © 2008 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.quantu

Quantum hacking of continuous-variable quantum key distribution systems: Realtime Trojan-horse attacks - Stiller, Birgit; Khan, Imran; Jain, Nitin; Jouguet, P.; Kunz-Jacques, S.; Diamanti, E.; Marquardt, Christoph; Leuchs, Gerd (Conference on Lasers and Electro-Optics Europe - Technical Digest, 2015)
We experimentally demonstrate successful Trojan-horse attacks on laboratory and commercial continuous-variable quantum key distribution systems with binary and Gaussian modulation. Furthermore, we analyze appropriate countermeasures regarding their spectral performance.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Optical pulses; Optical refraction; Optical variables control; Phase modulation; Protocols; Security

Quantum imaging with incoherently scattered light from a free-electron laser - Schneider, Raimund; Mehringer, Thomas; Mercurio, Giuseppe; Wenthaus, Lukas; Classen, Anton; Brenner, Gunter; Gorobtsov, Oleg; Benz, Adrian; Bhatti, Daniel; Bocklage, Lars; Fischer, Birgit; Lazarev, Sergey; et al. (Nature Physics, 2018)
The advent of accelerator-driven free-electron lasers (FEL) has opened new avenues for high-resolution structure determination via diffraction methods that go far beyond conventional X-ray crystallography methods(1-10). These techniques rely on coherent scattering processes that require the maintenance of first-order coherence of the radiation field throughout the imaging procedure. Here we show that higher-order degrees of coherence, displayed in the intensity correlations of incoherently scattered X-rays from an FEL, can be used to image two-dimensional objects with a spatial resolution close to or even below the Abbe limit. This constitutes a new approach towards structure determination based on incoherent processes(11,12), including fluorescence emission or wavefront distortions, generally considered detrimental for imaging applications. Our method is an extension of the landmark intensity correlation measurements of Hanbury Brown and Twiss(13) to higher than second order, paving the way towards determination of structure and dynamics of matter in regimes where coherent imaging methods have intrinsic limitations(14).

Quantum Information From Foundations to Quantum Technology Applications Preface to the New Edition - Bruss, Dagmar; Leuchs, Gerd (Quantum Information: From Foundations to Quantum Technology Applications, 2019)
CRIS-Team WoS Importer:2020-09-25

Quantum information processing and communication, Strategic report on current status, visions and goals for research in Europe - Leuchs, Gerd; et al. (European Physical Journal D, 2005)
We present an excerpt of the document "Quantum Information Processing and Communication: Strategic report on current status, visions and goals for research in Europe", which has been recently published in electronic form at the website of FET (the Future and Emerging Technologies Unit of the Directorate General Information Society of the European Commission, http://www.cordis.lu/ist/fet/qipc-sr.htm). This document has been elaborated, following a former suggestion by FET, by a committee of QIPC scientists to provide input towards the European Commission for the preparation of the Seventh Framework Program. Besides being a document addressed to policy makers and funding agencies (both at the European and national level), the document contains a detailed scientific assessment of the state-of-the-art, main research goals, challenges, strengths, weaknesses, visions and perspectives of all the most relevant QIPC sub-fields, that we report here. Dedicated to the memory of Prof. Th. Beth, one of the pioneers of QIPC, whose contributions have had a significant scientific impact on the development as well as on the visibility of a field that he enthusiastically helped to shape since its early days. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.quantu_2

Quantum Information Processing - Leuchs, Gerd; et al. (Wiley-VCH, 2003)
UnivIS-Import:2015-04-02:Pub.2003.nat.dphy.optik.1optik.quantu_6

Quantum Information Processing - Leuchs, Gerd; et al. (Wiley-VCH, 2003)
UnivIS-Import:2015-05-08:Pub.2003.nat.dphy.optik.1optik.quantu_7

Quantum Information Processing: Schwerpunktprogramm 1078 der Deutschen Forschungsgemeinschaft - Leuchs, Gerd; et al. (Wiley-VCH Verlag GmbH &Co KGaA, 2005)
UnivIS-Import:2015-04-02:Pub.2005.nat.dphy.optik.1optik.quantu

Quantum Information Processing: Schwerpunktprogramm 1078 der Deutschen Forschungsgemeinschaft - Leuchs, Gerd; et al. (Wiley-VCH Verlag GmbH & Co KGaA, 2005)
UnivIS-Import:2015-05-08:Pub.2005.nat.dphy.optik.1optik.quantu_0

Quantum Information Processing with Superconducting Circuits - Eichler, Christopher (GDR IQFA - 9th Colloquium, 2018)
Keywords: wwwqudev

Quantum Information with Continuous Variables of Atoms and Light - Leuchs, Gerd; et al. (Imperial College Press, 2007)
UnivIS-Import:2015-04-02:Pub.2007.nat.dphy.optik.1optik.quantu

Quantum interferometry - Leuchs, Gerd; et al. (Lectures on Quantum Information, 2006)
UnivIS-Import:2015-04-20:Pub.2006.nat.dphy.optik.1optik.quantu

Quantum interferometry with fiber solitons - a direct experimental test of non-separability - Leuchs, Gerd; et al. (Proceedings of the 8th Rochester Conference on Coherence and Quantum Optics, 2002)
UnivIS-Import:2015-04-16:Pub.2002.nat.dphy.optik.1optik.uantum

Quantum Interferometry with Gaussian States - Andersen, Ulrik L.; Gloeckl, Oliver; Gehring, Tobias; Leuchs, Gerd (Quantum Information: From Foundations to Quantum Technology Applications, 2019)
CRIS-Team WoS Importer:2020-09-25

Quantum interferometry with intense optical pulses - Leuchs, Gerd; et al. (Fortschritte Der Physik-Progress of Physics, 2003)
For intense optical pulses the optical Kerr interaction in matter such as an optical fiber is large enough to generate quantum states of light with significant non-classical properties. On this basis pairs of entangled light pulses have been generated. This entanglement can be used for novel schemes in high precision interferometry and for quantum communication protocols such as quantum dense coding.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.quantu

Quantum key distribution with bright entangled beams - Leuchs, Gerd; et al. (Physical Review Letters, 2002)
Continuous electron paramagnetic resonance (EPR)-like correlations of bright optical beams were used to suggest a quantum cryptographic scheme. The continuous information was discretized in a novel way by associating a respective measurement, amplitude, or phase, with a bit value 1 or 0 for binary key encoding. The binary bits were encoded by the choice to detect either of two conjugate variables accomplished independently and randomly by both communicating parties. The implementation of the scheme was experimentally simple, robust and well-suited for fiber-integrated or free-space transmission.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.quantu

Quantum Light from a Whispering-Gallery-Mode Disk Resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique; Aiello, Andrea; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2011)
Optical parametric down-conversion has proven to be a valuable source of nonclassical light. The process is inherently able to produce twin-beam correlations along with individual intensity squeezing of either parametric beam, when pumped far above threshold. Here, we present for the first time the direct observation of intensity squeezing of -1.2dB of each of the individual parametric beams in parametric down-conversion by use of a high quality whispering-gallery-mode disk resonator. In addition, we observed twin-beam quantum correlations of -2.7dB with this cavity. Such resonators feature strong optical confinement and offer tunable coupling to an external optical field. This work exemplifies the potential of crystalline whispering-gallery-mode resonators for the generation of quantum light. The simplicity of this device makes the application of quantum light in various fields highly feasible. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Quantum-like nonseparable structures in optical beams - Aiello, Andrea; Töppel, Falk; Marquardt, Christoph; Giacobino, Elisabeth; Leuchs, Gerd (New Journal of Physics, 2015)
When two or more degrees of freedom become coupled in a physical system, a number of observables of the latter cannot be represented by mathematical expressions separable with respect to the different degrees of freedom. In recent years it appeared clear that these expressions may display the same mathematical structures exhibited by multiparty entangled states in quantum mechanics. In this work, we investigate the occurrence of such structures in optical beams, a phenomenon that is often referred to as 'classical entanglement'. We present a unified theory for different kinds of light beams exhibiting classical entanglement and we indicate several possible extensions of the concept. Our results clarify and shed new light upon the physics underlying this intriguing aspect of classical optics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: classical entanglement; non-separability; optical beams

Quantum limited amplification and entanglement of microwave fields with coupled nonlinear cavities - Eichler, Christopher (2014)
Coupled nonlinear cavities provide a versatile testbed to study fundamental light-matter interactions and constitute a generic building block to realize photonic quantum simulators for strongly interacting systems. Their theoretical investigation and experimental realizations have therefore been driven forward in a variety of physical settings. In my talk I will present the implementation of a dissipative Bose-Hubbard dimer in superconducting circuits to achieve quantum limited amplification and to generate frequency entangled microwave photon pairs. Featuring a flexible control over the relevant system parameters, the presented lumped element circuit has also great potential to be used as an elementary cell in larger nonlinear cavity arrays. In contrast to previous implementations of microwave parametric amplifiers our device can be operated both as a bsingle mode squeezer and as a nondegenerate phase-preserving amplifier. In combination with its large achievable bandwidth, tunability and saturation power our device may find broad application in experiments aiming at quantum limited detection – particularly in superconducting circuits. Collaborators: Y. Salathe, J. Mlynek, S. Schmidt, Wallraff, A.
Keywords: wwwqudev

Quantum Limited Amplification, Vacuum Squeezing, and Frequency Conversion in Parametrically Driven Superconducting Circuits - Eichler, Christopher (Workshop on Parametric phenomena, 2017)
Keywords: wwwqudev

Quantum-limited measurements of intensity noise levels in Yb-doped fiber amplifiers - Popp, Alexandra; Distler, Victor; Jaksch, Kevin; Sedlmeir, Florian; Mueller, Christian R.; Haarlammert, Nicoletta; Schreiber, Thomas; Marquardt, Christoph; Tuennermann, Andreas; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2020)
We investigate the frequency-resolved intensity noise spectrum of an Yb-doped fiber amplifier down to the fundamental limit of quantum noise. We focus on the kHz and low MHz frequency regime with special interest in the region between 1 and 10 kHz. Intensity noise levels up to ≥ 60 dB above the shot noise limit are found, revealing great optimization potential. Additionally, two seed lasers with different noise characteristics were amplified, showing that the seed source has a significant impact and should be considered in the design of high power fiber amplifiers.
CRIS-Team Scopus Importer:2020-07-24

Quantum-limited measurements of optical signals from a geostationary satellite - Günthner, Kevin; Khan, Imran; Elser, Dominique Alexander; Stiller, Birgit; Bayraktar, Ömer; Mueller, Christian R.; Saucke, Karen; Troendle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optica, 2017)
The measurement of quantum signals that travel through long distances is fundamentally and technologically interesting. We present quantum-limited coherent measurements of optical signals that are sent from a satellite in geostationary Earth orbit to an optical ground station. We bound the excess noise that the quantum states could have acquired after having propagated 38,600 km through Earth’s gravitational potential, as well as its turbulent atmosphere. Our results indicate that quantum communication is feasible, in principle, in such a scenario, highlighting the possibility of a global quantum key distribution network for secure communication.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (010.1300) Atmospheric propagation; (060.1660) Coherent communications; (060.2605) Free-space optical communication; (270.5565) Quantum communications; (270.5568) Quantum cryptography

Quantum-limited measurements of optical signals from a satellite in geostationary earth orbit - Günthner, Kevin; Khan, Imran; Elser, Dominique; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Quantum-limited measurements of signals from geostationary earth orbit - Elser, Dominique; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (European Conference on Optical Communication, ECOC, 2016)
Quantum key distribution (QKD) has been implemented in metropolitan area networks around the world. Optical satellite communication is seen as suitable to provide the missing long-haul interconnections. We validate this approach by quantum measurements of optical signals from space.
CRIS-Team Scopus Importer:2021-06-29

Quantum Limits of Coherent Beam Combining - Leuchs, Gerd; Müller, Christian; Sedlmeir, Florian; Chatterjee, Sourav; Haarlammert, Nicoletta; Jauregui, Cesar; Schreiber, Thomas; Limpert, Jens; Tunnermann, Andreas; Marquardt, Christoph (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
Coherent beam combining refers to the process of generating a bright output beam by merging independent input beams with locked relative phases. We report the first quantum mechanical noise limit calculations for coherent beam combining and compare our results to quantum-limited amplification. We highlight a favourable noise scaling for both pure and noisy input states.
CRIS-Team Scopus Importer:2019-05-21

Quantum limits to center-of-mass measurements - Leuchs, Gerd; et al. (Physical Review A, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.quantu_8

Quantum measurements of signals from the Alphasat TDP1 laser communication terminal - Elser, D.; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, K.; Tröndle, D.; Heine, F.; Seel, S.; Greulich, P.; Zech, H.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Quantum optics [1] can be harnessed to implement cryptographic protocols that are verifiably immune against any conceivable attack [2]. Even quantum computers, that will break most current public keys [3, 4], cannot harm quantum encryption. Based on these intriguing quantum features, metropolitan quantum networks have been implemented around the world [5-15]. However, the long-haul link between metropolitan networks is currently missing [16]. Existing fiber infrastructure is not suitable for this purpose since classical telecom repeaters cannot relay quantum states [2]. Therefore, optical satellite-to-ground communication [17-22] lends itself to bridge intercontinental distances for quantum communication [23-40].
CRIS-Team Scopus Importer:2021-06-29

Quantum nature of Gaussian discord: Experimental evidence and role of system-environment correlations - Chille, Vanessa; Quinn, Niall; Peuntinger, Christian; Croal, Callum; Mista, Ladislav; Marquardt, Christoph; Leuchs, Gerd; Korolkova, Natalia (Physical Review A - Atomic, Molecular, and Optical Physics, 2015)
We provide experimental evidence of quantum features in bipartite states classified as entirely classical according to a conventional criterion based on the Glauber P function but possessing nonzero Gaussian quantum discord. Their quantum nature is experimentally revealed by acting locally on one part of the discordant state. We experimentally verify and investigate the effect of discord increase under the action of local loss and link it to the entanglement with the environment. Adding an environmental system purifying the state, we unveil the flow of quantum correlations within a global pure system using the Koashi-Winter inequality. For a discordant state generated by splitting a state in which the initial squeezing is destroyed by random displacements, we demonstrate the recovery of entanglement highlighting the role of system-environment correlations.
CRIS-Team Scopus Importer:2022-06-05

Quantumness beyond entanglement: The case of symmetric states - Goldberg, Aaron Z.; Grassl, Markus; Leuchs, Gerd; Sánchez-Soto, Luis L. (Physical Review A, 2022)
Nowadays, it is accepted that truly quantum correlations can exist even in the absence of entanglement. For the case of symmetric states, a physically trivial unitary transformation can alter a state from entangled to separable, and vice versa. We propose to certify the presence of quantumness via an average of a state's bipartite entanglement properties over all physically relevant modal decompositions. We investigate extremal states for such a measure: SU(2)-coherent states possess the least quantumness, whereas the opposite extreme is inhabited by states with maximally spread Majorana constellations.
CRIS-Team Scopus Importer:2022-03-18

Quantum Non-Demolition Measurements with Solitons - Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 1997)
The optical Kerr effect provides an ideal quantum non-demolition interaction. Experiments and proposals using this interaction are reviewed with special emphasis on optical soliton pulses propagating in fibres. The performance of a quantum non-demolition experiment using the optical Kerr effect may be reduced by self-phase modulation of the probe pulse. Proposals to overcome this limitation are discussed.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.quantu_1

Quantum physics in space - Belenchia, Alessio; Carlesso, Matteo; Bayraktar, Ömer; Dequal, Daniele; Derkach, Ivan; Gasbarri, Giulio; Herr, Waldemar; Li, Ying Lia; Rademacher, Markus; Sidhu, Jasminder; Oi, Daniel K.L.; Seidel, Stephan T.; et al. (Physics Reports-Review Section of Physics Letters, 2022)
Advances in quantum technologies are giving rise to a revolution in the way fundamental physics questions are explored at the empirical level. At the same time, they are the seeds for future disruptive technological applications of quantum physics. Remarkably, a space-based environment may open many new avenues for exploring and employing quantum physics and technologies. Recently, space missions employing quantum technologies for fundamental or applied studies have been proposed and implemented with stunning results. The combination of quantum physics and its space application is the focus of this review: we cover both the fundamental scientific questions that can be tackled with quantum technologies in space and the possible implementation of these technologies for a variety of academic and commercial purposes.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Quantum physics; Quantum technology; Space

Quantum random numbers based on the vacuum state - Gabriel, C.; Wittmann, C.; Sych, D.; Dong, R.; Mauerer, W.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Quantum reconstruction of an intense polarization squeezed optical state - Marquardt, Christoph; Heersink, Joel; Dong, Ruifang; Chekova, Maria; Klimov, Andrei B.; Sanchez-Soto, L. L.; Andersen, Ulrik L.; Leuchs, Gerd (Physical Review Letters, 2007)
We perform a reconstruction of the polarization sector of the density matrix of an intense polarization squeezed beam starting from a complete set of Stokes measurements. By using an appropriate quasidistribution, we map this onto the Poincaré space, providing a full quantum mechanical characterization of the measured polarization stat
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.quantu_3

Quantum Simulations with Microwave Radiation - Eichler, Christopher (67th Fujihara seminar, 2014)
Keywords: wwwqudev

Quantum Solitons in Fibers - Recent Experimental Progress and Perspectives - Leuchs, Gerd; et al. (Proc. of the Sixth International Conference on Sqeezed States and Uncertainty Relations, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.quantu_4

Quantum Solitons in Fibres - Internal Structure,Entanglement, and Cats - Leuchs, Gerd; et al. (Proc. of the International Conference on Squeezed States and Uncertainty Relations, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.quantu

Quantum Solitons in Optical Fibres: Basic Requisites for Experimental Quantum Communication - Leuchs, Gerd; et al. (Quantum Information Theory with Continuous Variables, 2003)
UnivIS-Import:2015-04-20:Pub.2003.nat.dphy.optik.1optik.quantu_3

Quantum State Reconstruction of an Intense Polarization Squeezed State - Marquardt, Christoph; Heersink, Joel; Chekhova, Maria V.; Klimov, A. B.; Sánchez-Soto, Luis L.; Andersen, Ulrik Lund; Leuchs, Gerd (Quantum Electronics and Laser Science Conference 2006, 2006)
The first quantum reconstruction of an intense Kerr squeezed state is reported. Taking into account the algebraic properties of the Stokes operators, the Wigner function describing a polarization squeezed state can also be fully reconstructed.<br

Quantum structure of fiber solitons and quantum communication - Leuchs, Gerd; et al. (Quantum Information Processing, 2003)
UnivIS-Import:2015-04-20:Pub.2003.nat.dphy.optik.1optik.quantu_7

Quantum uncertainty in the beam width of spatial optical modes - Chille, Vanessa; Banzer, Peter; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph; Treps, Nicolas; Fabre, Claude (Optics Express, 2015)
We theoretically investigate the quantum uncertainty in the beam width of transverse optical modes and, for this purpose, define a corresponding quantum operator. Single mode states are studied as well as multimode states with small quantum noise. General relations are derived, and specific examples of different modes and quantum states are examined. For the multimode case, we show that the quantum uncertainty in the beam width can be completely attributed to the amplitude quadrature uncertainty of one specific mode, which is uniquely determined by the field under investigation. This discovery provides us with a strategy for the reduction of the beam width noise by an appropriate choice of the quantum state.
CRIS-Team Scopus Importer:2022-06-05

Quantum witness of a damped qubit with generalized measurements - Bojer, Manuel; Friedenberger, Alexander; Lutz, Eric (Journal of Physics Communications, 2019)
We evaluate the quantum witness based on the no-signaling-in-time condition of a damped two-level system for nonselective generalized measurements of varying strength. We explicitly compute its dependence on the measurement strength for a generic example. We find a vanishing derivative for weak measurements and an infinite derivative in the limit of projective measurements. The quantum witness is hence mostly insensitive to the strength of the measurement in the weak measurement regime and displays a singular, extremely sensitive dependence for strong measurements. We finally relate this behavior to that of the measurement disturbance defined in terms of the fidelity between pre-measurement and post-measurement states.
CRIS-Team WoS Importer:2019-07-09

Quasi-absolute measurement of aspheres with a combined diffractive optical element as reference. - Lindlein, Norbert; et al. (Applied Optics, 2006)
We have already reported a method for the quasi-absolute test of rotationally symmetric aspheres by means of combined diffractive optical elements (combo-DOEs). The combo-DOEs carry the information for the ideal shape of an aspheric surface under test as well as a spherical wave for the measurement at the cat's eye position. An experimental demonstration of the procedure is given. Measurements with two different designs of combo-DOEs have been conducted, and their relative advantages and disadvantages are discussed.

Qubit-Photon Entanglement and Hong-Ou-Mandel Interference with Propagating Microwaves - Eichler, Christopher; et al. (APS March Meeting, 2013)
Keywords: wwwqudev

Range Sensing of the first, the second, and the third kind - Häusler, Gerd (Proc. of the EOS Topical Meetings Digest Series, 1994)
UnivIS-Import:2015-04-16:Pub.1994.nat.dphy.optik.1optik.ranges

Rauschunterdrückung und Pulsformung in faseroptischen Sagnac Interferometern (NOLM) - Wietfeld, André; Schmauß, Bernhard; Meißner, Markus; Leuchs, Gerd (ITG Workshop Modellierung photonischer Komponenten und Systeme, Stuttgart, November, 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.rausch_7

Rauschunterdrückung und Pulsformung mit einem Faser Sagnac Interferometer - Wietfeld, André; Meißner, Markus; Schmauß, Bernhard (Workshop der ITG Fachgruppe 5.3.1., 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.rausch

Rayleigh-Backscattering Impact on Performance of NOLM-Based Phase-Preserving Optical Limiters - Onishchukov, G.; Sponsel, K.; Stephan, C.; Roethlingshoefer, T.; Schmauß, Bernhard; Leuchs, Gerd (Photonics Society Summer Topical Meetings Series, IEEE, 2010)
lhft_intern.bib::Onishchukov10

Reaktionen des zwitterionischen Thiooxalsäure-2-amid-1-hydrazid-2-hydrazons - Dehne, Henry; Scheunemann, A.; Michalik, M.; Hartung, H.; Heinemann, Frank Wilhelm (Sulfur Letters, 1995)

Realization of two-qubit gates with tunable couplers in superconducting circuits - Eichler, Christopher; et al. (APS March Meeting, 2019)
Keywords: wwwqudev

Realizing a reinforcement learning agent for real-time quantum feedback - Eichler, Christopher (ENS Lyon, seminar hosted by Benjamin Huard, 2022)
Rapid advancements in building quantum information processing devices at scale call for radical paradigm shifts in the real-time control of quantum systems. Reinforcement learning offers a powerful approach to learn sophisticated control strategies in the absence of detailed models and promises to become a game changer in quantum technology as it did in many other disciplines ranging from board games, to robotics, to fundamental science. In my talk, I will show how we achieve real-time feedback control of a quantum system by using a reinforcement learning agent. We realize the agent as a novel low-latency neural-network on a field-programmable gate array interacting with a superconducting quantum system at MHz rates, which is more than 100 times faster than any other previous implementation of a reinforcement learning agent deployed in any physics experiment. Our work paves the way towards using reinforcement learning for real-time control of quantum computers, most notably for quantum error correction and fault-tolerant gate operations. Beyond that, the unprecedented speed of the agent marks an important engineering achievement , which can be deployed in a wide range of other applications, such as real-time the control of optical systems.
Keywords: wwwquantum

Realizing Quantum Convolutional Neural Networks on a Superconducting Quantum Processor - Eichler, Christopher (Seminar, Quantum Theory Group, 2022)
Keywords: wwwqudev

Realizing Quantum Convolutional Neural Networks on a Superconducting Quantum Processor - Eichler, Christopher (International Quantum Tensor Network, 2022)
Keywords: wwwqudev

Reconstructing two-dimensional spatial modes for classical and quantum light - Averchenko, Valentin A.; Frascella, Gaetano; Kalash, Mahmoud; Cavanna, Andrea; Chekhova, Maria (Physical Review A, 2020)
We propose a method for finding two-dimensional spatial modes of thermal field through a direct measurement of the field intensity and an offline analysis of its spatial fluctuations. Using this method, in a simple and efficient way we reconstruct the modes of a multimode fiber and the spatial Schmidt modes of squeezed vacuum generated via high-gain parametric down-conversion. The reconstructed shapes agree with the theoretical results.
CRIS-Team WoS Importer:2020-12-18

Reconstruction of smoothed polyhedral surfaces from multiple range images - Häusler, Gerd; et al. (3D Image Analysis and Synthesis '97, 1997)
UnivIS-Import:2015-04-20:Pub.1997.nat.dphy.optik.1optik.recons

Reduction of guided acoustic wave brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Andersen, Ulrik Lund; Korn, Alexander; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2006)
Guided acoustic wave Brillouin scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. This excess noise affects the performance of various experiments operating at the quantum noise limit. We experimentally demonstrate the reduction of GAWBS noise in a photonic crystal fiber in a broad frequency range by tailoring the acoustic modes using the photonic also as a phononic crystal. We compare the noise spectrum to the one of a standard fiber and observe a tenfold noise reduction in the frequency range up to 200 MHz. Based on our measurement results as well as on numerical simulations, we establish a model for the reduction of GAWBS noise in photonic crystal fibers. © 2006 The American Physical Society.
Created from Fastlane, Scopus look-up

Reduction of Nonlinear Phase Noise in DPSK Transmission Using a NALM - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE/LEOS Winter Topicals Meeting Series, 2009)
Performance of a NALM as phase-preserving amplitude 2R-regenerator in a DPSK transmission system has been investigated experimentally and numerically. A 3dB improvement of eye opening or alternatively a 3dB increase of fibre-launched power are demonstrated.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.reduct

Reduction of phase singularities in speckle-shearing interferometry by incoherent averaging of speckle patterns - Mantel, K.; Nercissian, Vanusch; Lindlein, Norbert (Optical Measurement Systems for Industrial Inspection IX, 2015)
Speckle interferometry is a well established technique for the optical characterization of rough objects, with the quantification of deformations as one particular application of interest. Owing to its common path property, a speckle-shearing interferometer is often the natural choice as a setup. Like other speckle techniques, however, speckle-shearing interferometry suffers from the existence of phase singularities present in the speckle patterns. Phase singularities introduce ambiguities into the phase unwrapping process and make this evaluation step highly sophisticated. In this work, we attempt to reduce the number of phase singularities by physical means, i. e. by applying an incoherent averaging of multiple, mutually independent speckle intensities. The effect of the incoherent averaging on the number of phase singularities has been investigated theoretically, by computer simulations, and experimentally. To obtain high contrast fringes in connection with a shearing setup, which would not be the case for a simple extended light source, a periodically structured light source with a period matched to the shear distance is applied. It turns out that the number of phase singularities may indeed be reduced, but only to a certain extent.
Keywords: incoherent averaging; phase singularities; Speckle-shearing interferometry

Reduction of the focal spot size by using polarization effects - Leuchs, Gerd; et al. (IQEC'2000 Conference Digest, 2000)
Polarization distribution of the focused beam reduced the focal area in an optical system with high numerical aperture (NA). Focal intensity distribution was measured using knife edge method setup. An incoming beam is focused by a microscope objective onto a specially designed p-i-n photodiode, where parts of the light sensitive area were covered with a sharp edged gold pad. By measuring the dependence of the photocurrent on the translation distance for different translation directions and orientations of the gold pad a reconstruction of the shape of the focus is possible by applying the Radon back-transformation.
UnivIS-Import:2015-04-16:Pub.2000.nat.dphy.optik.1optik.reduct_8

Reduction of the Rayleigh-Backscattering Impact in Nonlinear Loop Mirrors by Dispersion Management - Röthlingshöfer, Tobias; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (OSA Conference on Nonlinear Photonic, 2010)
UnivIS-Import:2016-06-01:Pub.2011.tech.IE.LEH.reduct

Reduktion der Residuenanzahl bei lateraler Speckle-Shearing-Interferometrie: Simulationen und Messergebnisse - Nercissian, Vanusch; Mantel, Klaus Peter; Harder, Irina; Lindlein, Norbert (115. Jahrestagung der DGaO, 2014)

Reduktion von Phasensingularitäten bei lateraler Shearing-Speckle-Interferometrie - Nercissian, Vanusch; Mantel, Klaus Peter; Seifert, Kristina Johanna; Berger, Andreas; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Refining Triangle Meshes by Non-Linear Subdivision - Häusler, Gerd; et al. (Proceedings of Third International Conference on 3-DDigital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.refini

Refraktive Strahlformungsoptik mittels direktschreibender Grautonlithographie - Leroch, Dominik; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Reliable simulation of optical bridge system by exchanging optical field data - Lindlein, Norbert; et al. (Photon Management III, 2008)
In succession of a benchmark study for the modeling of micro-optical components in the Network of Excellence on Micro-Optics (NEMO) we define a novel systematic approach for the evaluation of modeling results and the combination of different modeling approaches and modeling expertise. The method is applied for an optical bridge system, comprising both refractive and diffractive optical components. We work with different intermediate planes at which the field distributions obtained with different simulation tools are rigorously compared. Therefore all participating partners have programmed the necessary tools that allow the exchange of obtained field distributions. First evaluation results are discussed in detail.
Keywords: Diffractive element; Micro-lens; Modeling; Optical field data

Repeated Quantum Error Correction in a Surface Code Using Superconducting Circuits - Eichler, Christopher (Physics Frontiers with Quantum Science and Technology, 2022)
Keywords: wwwqudev

Repeated Quantum Error Correction in a Surface Code Using Superconducting Circuits - Eichler, Christopher (Walter-Meissner-Institut, 2022)
The ability to perform logical quantum operations fault-tolerantly by correcting unavoidable errors induced by control inaccuracies and decoherence, will be essential for building and operating large-scale quantum computers. In my talk, I present our recent demonstration of repeated quantum error correction using a surface code [1], which is known for it exceptionally high error threshold and its compatibility with planar qubit architectures featuring nearest-neighbor coupling. The code implemented in our experiments uses 17 physical qubits, nine of of which encode the logical information and eight of which perform repeatedmeasurements of error syndromes. By decoding the syndrome data in post-processing we preserve initialized logical states with a low error probability of 3% per cycle. The demonstration of repeated, fast and high-performance quantum error correction supports our understanding that fault-tolerant quantum computation will eventually be realizable. [1] S. Krinner, N. Lacroix, A. Remm, A. Di Paolo, E. Genois, C. Leroux, C. Hellings, S. Lazar, F. Swiadek, J. Herrmann, G. J. Norris, C K. Andersen, M. Müller, A. Blais, C. Eichler, and A. Wallraff, arxiv.org:2112.03708 (202
Keywords: wwwqudev

Repeated Quantum Error Correction in a Surface Code Using Superconducting Circuits - Eichler, Christopher (CMD 29, Superconducting Circuits for Quantum Technologies, 2022)
The ability to perform logical quantum operations fault-tolerantly by correcting unavoidable errors induced by control inaccuracies and decoherence, will be essential for building and operating large-scale quantum computers. In my talk, I present our recent demonstration of repeated quantum error correction using a surface code, which is known for it exceptionally high error threshold and its compatibility with planar qubit architectures featuring nearest-neighbor coupling. The code implemented in our experiments uses 17 physical qubits, nine of of which encode the logical information and eight of which perform repeated measurements of error syndromes. By decoding the syndrome data in post-processing we preserve initialized logical states with a low error probability of 3% per cycle. The demonstration of repeated, fast and high-performance quantum error correction supports our understanding that fault-tolerant quantum computation will eventually be realizable.
Keywords: wwwqudev

Repeated Quantum Error Correction in a Surface Code Using Superconducting Circuits - Eichler, Christopher (IST Austria : Vienna, Austria, 2022)
The ability to perform logical quantum operations fault-tolerantly by correcting unavoidable errors induced by control inaccuracies and decoherence, will be essential for building and operating large-scale quantum computers. In my talk, I present our recent demonstration of repeated quantum error correction using a surface code, which is known for it exceptionally high error threshold and its compatibility with planar qubit architectures featuring nearest-neighbor coupling. The code implemented in our experiments uses 17 physical qubits, nine of of which encode the logical information and eight of which perform repeated measurements of error syndromes. By decoding the syndrome data in post-processing we preserve initialized logical states with a low error probability of 3% per cycle. The demonstration of repeated, fast and high-performance quantum error correction supports our understanding that fault-tolerant quantum computation will eventually be realizable. [1] S. Krinner, N. Lacroix, A. Remm, A. Di Paolo, E. Genois, C. Leroux, C. Hellings, S. Lazar, F. Swiadek, J. Herrmann, G. J. Norris, C K. Andersen, M. Müller, A. Blais, C. Eichler, and A. Wallraff, arxiv.org:2112.03708 (2021)
Keywords: wwwqudev

Resonant electro-optic frequency comb - Rueda, Alfredo; Sedlmeir, Florian; Kumari, Madhuri; Leuchs, Gerd; Schwefel, Harald G. L. (Nature, 2019)
High-speed optical telecommunication is enabled by wavelength-division multiplexing, whereby hundreds of individually stabilized lasers encode information within a single-mode optical fibre. Higher bandwidths require higher total optical power, but the power sent into the fibre is limited by optical nonlinearities within the fibre, and energy consumption by the light sources starts to become a substantial cost factor 1 . Optical frequency combs have been suggested to remedy this problem by generating numerous discrete, equidistant laser lines within a monolithic device; however, at present their stability and coherence allow them to operate only within small parameter ranges 2–4 . Here we show that a broadband frequency comb realized through the electro-optic effect within a high-quality whispering-gallery-mode resonator can operate at low microwave and optical powers. Unlike the usual third-order Kerr nonlinear optical frequency combs, our combs rely on the second-order nonlinear effect, which is much more efficient. Our result uses a fixed microwave signal that is mixed with an optical-pump signal to generate a coherent frequency comb with a precisely determined carrier separation. The resonant enhancement enables us to work with microwave powers that are three orders of magnitude lower than those in commercially available devices. We emphasize the practical relevance of our results to high rates of data communication. To circumvent the limitations imposed by nonlinear effects in optical communication fibres, one has to solve two problems: to provide a compact and fully integrated, yet high-quality and coherent, frequency comb generator; and to calculate nonlinear signal propagation in real time 5 . We report a solution to the first problem.
CRIS-Team Scopus Importer:2019-05-02

Resonant electro-optic frequency comb generation in lithium niobate disk resonator inside a microwave cavity - Rueda, Alfredo; Sedlmeir, Florian; Leuchs, Gerd; Kumari, Madhuri; Schwefel, Harald (Optics InfoBase Conference Papers, 2019)
We demonstrate electro-optic frequency comb generation using a doubly resonant system comprising a whispering gallery mode disk resonator made of lithium niobate mounted inside a three dimensional copper cavity. We observe 180 sidebands centred at 1550 nm.
CRIS-Team Scopus Importer:2020-02-21

Resonant metamaterials for contrast enhancement in optical lithography - Dobmann, Sabine; Shyroki, Dzmitry; Banzer, Peter; Erdmann, Andreas; Peschel, Ulf (Optics Express, 2012)
The transmission through ultra-thin metal films is noticeable and thus limits their potential for the formation of lithographic masks. By sub-wavelength patterning of a metal film with a post structure, a resonant metamaterial is formed, which can effectively suppress the transmission. Measurements as well as calculations identify the width of the metal islands as a critical geometrical feature. Hence, the extraordinarily low transmission effect can be explained by the resonant response of single scatterers known as Localized Surface Plasmon Resonances (LSPR). A potential application of this suppressed transmission effect to thin metal masks in optical lithography is experimentally investigated.
EAM Import::2019-03-13

Resonant photo-ionization of Yb+ to Yb2+ - Heugel, Simon Tobias; Fischer, Martin; Elman, Vladimir; Maiwald, Robert; Sondermann, Markus; Leuchs, Gerd (Journal of Physics B: Atomic, Molecular and Optical Physics, 2016)
We demonstrate the controlled creation of a Yb ion by photo-ionizing Yb with weak continuous-wave lasers at ultraviolet wavelengths. The photo-ionization is performed by resonantly exciting transitions of the Yb ion in three steps. Starting from an ion crystal of two laser-cooled Yb ions localized in a radio-frequency trap, the verification of the ionization process is performed by characterizing the properties of the resulting mixed-species ion-crystal. The obtained results facilitate fundamental studies of physics involving Yb ions.
Keywords: light-matter interaction; photo-ionization; ytterbium

Reverse Engineering mit Hilfe optischer 3D-Sensoren - Häusler, Gerd; et al. (Optische 3D-Erfassung großer Objekte, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.revers

Reverse engineering using optical 3D sensors - Häusler, Gerd; et al. (Proceedings of SPIE, 1998)
Optical 3D sensors are used as tools for reverse engineering: First the shape of an object is digitized by acquisition of multiple range images from different view points. Then the range images are registered and the data is turned into a CAD description, e.g. tensor product surfaces, by surface modeling software. For many applications however it is sufficient to generate a polyhedral surface. We present a nearly automatic procedure covering the complete task of data acquisition, calibration, surface registration and surface reconstruction using a mesh of triangles. A couple of measurements, such as teeth, works of art and cutting tools are shown.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.revers
Keywords: 3D sensing; Calibration; Optical 3D sensor; Registration; Reverse engineering; Surface reconstruction; Triangulation

Reverse Engineering using Optical Range Sensors - Häusler, Gerd; et al. (Handbook of Computer Vision and Applications Vol. 3: Systems and Applications, 1999)
UnivIS-Import:2015-04-20:Pub.1999.nat.dphy.optik.1optik.revers

Ring-shaped molecules as split ring resonators of a molecular metamaterial - Lindlein, Norbert; et al. (Photonic Metamaterials: From Random to Periodic, META 2006, 2006)
We analytically analyse the magnetic response of ring shaped molecules. We find that circular symmetry must be broken and that transitions between higher order states have to be enabled to ob-tain a reasonable magnetic response. © 2006 Optical Society of America.

Risk analysis of Trojan-horse attacks on practical quantum key distribution systems - Jain, Nitin; Stiller, Birgit; Khan, Imran; Makarov, Vadim; Marquardt, Christoph; Leuchs, Gerd (IEEE Journal of Selected Topics in Quantum Electronics, 2015)
An eavesdropper Eve may probe a quantum key distribution (QKD) system by sending a bright pulse from the quantum channel into the system and analyzing the back-reflected pulses. Such Trojan-horse attacks can breach the security of the QKD system, if appropriate safeguards are not installed or if they can be fooled by the Eve. We present a risk analysis of such attacks based on extensive spectral measurements, such as transmittance, reflectivity, and detection sensitivity of some critical components used in a typical QKD systems. Our results indicate the existence of wavelength regimes, where the attacker gains considerable advantage as compared to launching an attack at 1550 nm. We also propose countermeasures to reduce the risk of such attacks.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Electrooptic modulators; Fiber optics; Infrared detectors; Infrared spectra; Optical pulses; Optical receivers; Photodetectors; Quantum cryptography; Quantum key distribution; Reflectometry; Supercontinuum; Transmittance; Trojan-horse attack

Satellite quantum communication via the alphasat laser communication terminal quantum signals from 36 thousand kilometers above earth - Elser, Dominique Alexander; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Marquardt, Christoph; Leuchs, Gerd; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (2015 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2015, 2016)
By harnessing quantum effects, we nowadays can use encryption that is in principle proven to withstand any conceivable attack. These fascinating quantum features have been implemented in metropolitan quantum networks around the world. In order to interconnect such networks over long distances, optical satellite communication is the method of choice. Standard telecommunication components allow one to efficiently implement quantum communication by measuring field quadratures (continuous variables). This opens the possibility to adapt our Laser Communication Terminals (LCTs) to quantum key distribution (QKD). First satellite measurement campaigns are currently validating our approach.
CRIS-Team Scopus Importer:2021-06-29
Keywords: free-space optical communication; quantum cryptography; quantum key distribution; satellite quantum communication; satellite-ground laser communication

Scattering of an exponential pulse by a single atom - Sondermann, Markus; Leuchs, Gerd (Romanian Reports in Physics, 2013)
We discuss the scattering of a light pulse by a single atom in free space using a purely semi-classical framework. The atom is treated as a linear elastic scatterer allowing to treat each spectral component of the incident pulse separately. For an increasing exponential pulse with a dipole radiation pattern incident from full solid angle the spectrum resulting from interference of incident and scattered components is a decreasing exponential pulse.

Scheme for the generation of entangeled solitons for quantum communication - Leuchs, Gerd; et al. (Journal of Modern Optics, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.optik.1optik.scheme

Search for a light sterile neutrino with 7.5 years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We present a search for an eV-scale sterile neutrino using 7.5 years of data from the IceCube DeepCore detector. The analysis uses a sample of 21,914 events with energies between 5 and 150 GeV to search for sterile neutrinos through atmospheric muon neutrino disappearance. Improvements in event selection and treatment of systematic uncertainties provide greater statistical power compared to previous DeepCore sterile neutrino searches. Our results are compatible with the absence of mixing between active and sterile neutrino states, and we place constraints on the mixing matrix elements |Uμ4|2<0.0534 and |Uτ4|2<0.0574 at 90% CL under the assumption that Δm412≥1 eV2. These null results add to the growing tension between anomalous appearance results and constraints from disappearance searches in the 3+1 sterile neutrino landscape.
CRIS-Team Scopus Importer:2024-11-01

Search for an eV-Scale Sterile Neutrino Using Improved High-Energy νμ Event Reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review Letters, 2024)
This Letter presents the result of a 3+1 sterile neutrino search using 10.7 yr of IceCube data. We analyze atmospheric muon neutrinos that traverse the Earth with energies ranging from 0.5 to 100 TeV, incorporating significant improvements in modeling neutrino flux and detector response compared to earlier studies. Notably, for the first time, we categorize data into starting and throughgoing events, distinguishing neutrino interactions with vertices inside or outside the instrumented volume, to improve energy resolution. The best-fit point for a 3+1 model is found to be at sin2(2θ24)=0.16 and Δm412=3.5 eV2, which agrees with previous iterations of this Letter. The result is consistent with the null hypothesis of no sterile neutrinos with a p value of 3.1%.
CRIS-Team Scopus Importer:2024-12-06

Search for Correlations of High-energy Neutrinos Detected in IceCube with Radio-bright AGN and Gamma-Ray Emission from Blazars - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2023)
The IceCube Neutrino Observatory sends realtime neutrino alerts with a high probability of being astrophysical in origin. We present a new method to correlate these events and possible candidate sources using 2089 blazars from the Fermi-LAT 4LAC-DR2 catalog and with 3413 active galactic nuclei (AGNs) from the Radio Fundamental Catalog. No statistically significant neutrino emission was found in any of the catalog searches. The result suggests that a small fraction, <1%, of the studied AGNs emit neutrinos that pass the alert criteria, and is compatible with prior evidence for neutrino emission presented by IceCube and other authors from sources such as TXS 0506 + 056 and PKS 1502 + 106. We also present cross-checks to other analyses that claim a significant correlation using similar data samples.
CRIS-Team Scopus Importer:2023-10-20

Search for decoherence from quantum gravity with atmospheric neutrinos - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Nature Physics, 2024)
Neutrino oscillations at the highest energies and longest baselines can be used to study the structure of spacetime and test the fundamental principles of quantum mechanics. If the metric of spacetime has a quantum mechanical description, its fluctuations at the Planck scale are expected to introduce non-unitary effects that are inconsistent with the standard unitary time evolution of quantum mechanics. Neutrinos interacting with such fluctuations would lose their quantum coherence, deviating from the expected oscillatory flavour composition at long distances and high energies. Here we use atmospheric neutrinos detected by the IceCube South Pole Neutrino Observatory in the energy range of 0.5–10.0 TeV to search for coherence loss in neutrino propagation. We find no evidence of anomalous neutrino decoherence and determine limits on neutrino–quantum gravity interactions. The constraint on the effective decoherence strength parameter within an energy-independent decoherence model improves on previous limits by a factor of 30. For decoherence effects scaling as E2, our limits are advanced by more than six orders of magnitude beyond past measurements compared with the state of the art.
CRIS-Team Scopus Importer:2024-06-14

Search for Galactic Core-collapse Supernovae in a Decade of Data Taken with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2024)
The IceCube Neutrino Observatory has been continuously taking data to search for O(0.5–10) s long neutrino bursts since 2007. Even if a Galactic core-collapse supernova is optically obscured or collapses to a black hole instead of exploding, it will be detectable via the O(10) MeV neutrino burst emitted during the collapse. We discuss a search for such events covering the time between 2008 April 17 and 2019 December 31. Considering the average data taking and analysis uptime of 91.7% after all selection cuts, this is equivalent to 10.735 yr of continuous data taking. In order to test the most conservative neutrino production scenario, the selection cuts were optimized for a model based on an 8.8 solar mass progenitor collapsing to an O–Ne–Mg core. Conservative assumptions on the effects of neutrino oscillations in the exploding star were made. The final selection cut was set to ensure that the probability to detect such a supernova within the Milky Way exceeds 99%. No such neutrino burst was found in the data after performing a blind analysis. Hence, a 90% C.L. upper limit on the rate of core-collapse supernovae out to distances of ≈25 kpc was determined to be 0.23 yr−1. For the more distant Magellanic Clouds, only high neutrino luminosity supernovae will be detectable by IceCube, unless external information on the burst time is available. We determined a model-independent limit by parameterizing the dependence on the neutrino luminosity and the energy spectrum.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Core-collapse supernovae (304); Neutrino telescopes (1105); Supernova neutrinos (1666)

Search for Joint Multimessenger Signals from Potential Galactic Cosmic-Ray Accelerators with HAWC and IceCube - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotti, U.; et al. (Astrophysical Journal, 2024)
The origin of high-energy galactic cosmic rays is yet to be understood, but some galactic cosmic-ray accelerators can accelerate cosmic rays up to PeV energies. The high-energy cosmic rays are expected to interact with the surrounding material or radiation, resulting in the production of gamma-rays and neutrinos. To optimize for the detection of such associated production of gamma-rays and neutrinos for a given source morphology and spectrum, a multimessenger analysis that combines gamma-rays and neutrinos is required. In this study, we use the MultiMission Maximum Likelihood framework with IceCube Maximum Likelihood Analysis software and HAWC Accelerated Likelihood to search for a correlation between 22 known gamma-ray sources from the third HAWC gamma-ray catalog and 14 yr of IceCube track-like data. No significant neutrino emission from the direction of the HAWC sources was found. We report the best-fit gamma-ray model and 90% CL neutrino flux limit from the 22 sources. From the neutrino flux limit, we conclude that, for five of the sources, the gamma-ray emission observed by HAWC cannot be produced purely from hadronic interactions. We report the limit for the fraction of gammarays produced by hadronic interactions for these five sources.
CRIS-Team Scopus Importer:2024-11-29

Search for Spatial Correlations of Neutrinos with Ultra-high-energy Cosmic Rays - Albert, A.; Domi, Alba; Alves, S.; Andre, M.; Anghinolfi, M.; Ardid, S.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2022)
For several decades, the origin of ultra-high-energy cosmic rays (UHECRs) has been an unsolved question of high-energy astrophysics. One approach for solving this puzzle is to correlate UHECRs with high-energy neutrinos, since neutrinos are a direct probe of hadronic interactions of cosmic rays and are not deflected by magnetic fields. In this paper, we present three different approaches for correlating the arrival directions of neutrinos with the arrival directions of UHECRs. The neutrino data are provided by the IceCube Neutrino Observatory and ANTARES, while the UHECR data with energies above similar to 50 EeV are provided by the Pierre Auger Observatory and the Telescope Array. All experiments provide increased statistics and improved reconstructions with respect to our previous results reported in 2015. The first analysis uses a high-statistics neutrino sample optimized for point-source searches to search for excesses of neutrino clustering in the vicinity of UHECR directions. The second analysis searches for an excess of UHECRs in the direction of the highest-energy neutrinos. The third analysis searches for an excess of pairs of UHECRs and highest-energy neutrinos on different angular scales. None of the analyses have found a significant excess, and previously reported overfluctuations are reduced in significance. Based on these results, we further constrain the neutrino flux spatially correlated with UHECRs.
CRIS-Team WoS Importer:2022-08-26

Search for the Prompt Atmospheric Neutrino Flux in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
For about a decade the IceCube Neutrino Observatory has been observing a high-energy diffuse astrophysical neutrino flux. At these energies, an important source of background are the prompt atmospheric neutrinos produced in decays of charmed mesons that are part of cosmic-ray-induced air showers. The production yield of charmed mesons in the very forward phase space of hadronic interactions, and thus the flux of prompt neutrinos, is not well known and has not yet been observed by IceCube. A measurement of the flux of prompt neutrinos will improve the modeling of hadronic interactions in cosmic-ray induced air showers at high energies. Additionally, in the context of astrophysical neutrino measurements, understanding this background flux will improve the measurement precision of the spectral shape in the future. In particular, the analysis of up-going muon neutrino-induced tracks in IceCube provides a large sample of atmospheric neutrinos which likely includes prompt neutrinos. However, the measurement of a subdominant prompt neutrino flux strongly depends on the hypothesis for the dominant astrophysical neutrino flux. This makes the estimation of upper limits on the prompt neutrino flux challenging. We discuss the extent of this model dependency on the astrophysical flux and propose a method to calculate robust upper limits. Furthermore, a possible dedicated search of the prompt neutrino flux using multiple IceCube detection channels is outlined.
CRIS-Team Scopus Importer:2025-02-04

Second Harmonic Generation from metallic and dielectric spherical nanoparticles - Peukert, Wolfgang; Wunderlich, Sarina; Zhuromskyy, Oleksandr; Schürer, Benedikt; Haderlein, Michael; Sauerbeck, Christian; Peschel, Ulf (2012 Conference on Lasers and Electro-Optics (CLEO), 2012)
Due to symmetry-breaking at an interface, Second Harmonic Generation (SHG) is an extremely surface sensitive process. Therefore it is a widely used tool to study surfaces. Applied to colloidal nanoparticles it offers efficient means to monitor growth and molecular adsorption processes in real time and in situ. This makes SHG a preferred method to study the formation of core-shell plasmonic nanoparticles, which recently became quite popular because of their strong and tunable plasmonic resonances.
Keywords: Symmetry; spherical; nanoparticle; second; harmonic; generation; plasmon; Optical; surface; wave; Harmonic analysis; Plasmons; Frequency conversion; Dielectrics

Second Harmonic Light Scattering from Spherical Polyelectrolyte Brushes - Peukert, Wolfgang; Schürer, Benedikt; Hoffmann, Martin; Wunderlich, Sarina; Peschel, Ulf; Harnau, Ludger; Ballauf, Matthias (Journal of Physical Chemistry C, 2011)
Optical second harmonic generation (SHG) was applied to study the shell layer of spherical polyelectrolyte brushes (SPB) as a function of ionic strength. The particles consist of a polystyrene core from which linear chains of a quenched polyelectrolyte are grafted. Compared to all systems studied by SHG previously, the shell layer in this study has a remarkable thickness of ca. 100 nm. Angle-resolved second harmonic (SH) scattering profiles were recorded and compared to simulations with different model geometries using a nonlinear Mie scattering model. The analysis reveals that the second harmonic signal is not generated by the polyelectrolyte molecules, but rather by oriented and polarized water molecules at the inner (polystyrene / polyelectrolyte) and at the outer (polyelectrolyte / solvent) interface of the polyelectrolyte shell. The results demonstrate that angle-resolved SH light scattering provides direct access to the structure of water and the screening of charges at the inner and outer interface of the polyelectrolyte shell. Correspondingly, this work sets the experimental and theoretical basis for the study of the extended interfacial layer of electrosterically stabilized particles by SH light scattering.
Keywords: optical; second; harmonic; generation; particle; polyelectrolyte

Seeded and unseeded high-order parametric down-conversion - Okoth, Cameron; Cavanna, Andrea; Joly, Nicolas; Chekhova, Maria (Physical Review A, 2019)
Spontaneous parametric down-conversion (SPDC) has been one of the foremost tools in quantum optics for over five decades. Over that time, it has been used to demonstrate some of the curious features that arise from quantum mechanics. Despite the success of SPDC, its higher-order analogs have never been observed, even though it has been suggested that they generate far more unique and exotic states than SPDC. An example of this is the emergence of non-Gaussian states without the need for postselection. Here we calculate the expected rate of emission for nth-order SPDC with and without external stimulation (seeding). Focusing primarily on third-order parametric down-conversion, we estimate the photon detection rates in a rutile crystal for both the unseeded and seeded regimes.
CRIS-Team WoS Importer:2019-04-18

Self-Catalyzed Growth of Vertically Aligned InN Nanorods by Metal-Organic Vapor Phase Epitaxy - Tessarek, C.; Fladischer, Stefanie; Dieker, Christel; Sarau, G.; Hoffmann, Björn; Bashouti, M.; Goebelt, M.; Heilmann, M.; Latzel, Michael; Butzen, E.; Figge, S.; Gust, A.; et al. (Nano Letters, 2016)
Vertically aligned hexagonal InN nanorods were grown mask-free by conventional metal organic vapor phase epitaxy without any foreign catalyst. The In droplets on top of the nanorod's indicate a self-catalytic vapor liquid solid growth mode. A systematic study on important growth parameters has been carried out for the optimization of nanorod morphology. The nanorod N-polarity, induced by high temperature nitridation of the sapphire substrate, IS necessary to achieve vertical growth. Hydrogen, usually inapplicable during InN growth due to formation of metallic indium, and silane are needed to enhance the aspect ratio and to reduce parasitic deposition beside the nanorods on the sapphire surface. The results reveal many similarities between InN and GaN nanorod growth showing that the process despite the large difference in growth temperature is similar. Transmission electron microscopy, spatially resolved energy-dispersive X-ray spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Raman spectroscopy have been performed to analyze the structural properties. Spatially resolved cathodoluminescence investigations are carried out to verify the optical activity of the InN nanorods. The InN nanorods are expected to be the material of choice for high-efficiency hot carrier solar cells.
Keywords: InN; nanorods; MOVPE; growth; vapor-liquid-solid; cathodoluminescence

Self-starting soliton modelocked femtosecond Chromium YAG laser using an antiresonant Fabry-Perot saturable absorber - Leuchs, Gerd; et al. (PDP oral presentation, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.selfst

Self-Starting Soliton-modelocked Femtosecond Cr(4+):YAG Laser Using an Antiresonant Fabry-Perot Saturable Absorber - Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 1997)
We set up a self-starting passively modelocked femtosecond Cr(4+):YAG laser using a low-finesse antiresonant Fabry-Pérot saturable absorber (A-FPSA). Stable transform-limited pulses were produced without the critical cavity alignment necessary for Kerr lens modelocking. We achieved 114-fs pulses with 94 mW output power at the telecommunication wavelength 1.5 μm. The pulse formation is demonstrated to be due to soliton modelocking. At higher intracavity energy multiple pulsing was observed and is explained by the saturation behaviour of the A-FPSA. In the multipulsing regime a pulse width as short as 95 fs and an averaged output power of up to 395 mW have been obtained. © Springer-Verlag 1997.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.selfst

Self-Switching Kerr Oscillations of Counterpropagating Light in Microresonators - Woodley, Michael T.M.; Hill, Lewis; Del Bino, Leonardo; Oppo, Gian Luca; Del'Haye, Pascal (Physical Review Letters, 2021)
We report the experimental and numerical observation of oscillatory antiphase switching between counterpropagating light beams in Kerr ring microresonators, where dominance between the intensities of the two beams is periodically or chaotically exchanged. Self-switching occurs in balanced regimes of operation and is well captured by a simple coupled dynamical system featuring only the self- and cross-phase Kerr nonlinearities. Switching phenomena are due to temporal instabilities of symmetry-broken states combined with attractor merging, which restores the broken symmetry on average. Self-switching of counterpropagating light is robust for realizing controllable, all-optical generation of waveforms, signal encoding, and chaotic cryptography.
CRIS-Team Scopus Importer:2021-02-12

Separated Schmidt modes in the angular spectrum of biphotons - Borshchevskaia, N. A.; Just, F.; Katamadze, K. G.; Cavanna, Andrea; Chekhova, Maria (Laser Physics Letters, 2019)
We prepared qudits based on angular multimode biphoton states by modulating the pump angular spectrum. The modes were prepared in the Schmidt basis and their intensity distributions did not overlap in space. This allows one to get rid of filtering losses while addressing single modes and to realize a single-shot qudit readout.
CRIS-Team WoS Importer:2019-07-26

Shaping Field Gradients for Nanolocalization - Nechayev, Sergey; Eismann, Jörg; Neugebauer, Martin; Banzer, Peter (ACS Photonics, 2020)
Deep subwavelength localization and displacement sensing of optical nanoantennas have emerged as extensively pursued objectives in nanometrology, where focused beams serve as high-precision optical rulers while the scattered light provides an optical readout. Here, we show that in these schemes using an optical excitation as a position gauge implies that the sensitivity to displacements of a nanoantenna depends on the spatial gradients of the excitation field. Specifically, we explore one of such novel localization schemes based on the appearance of transversely spinning fields in strongly confined optical beams, resulting in far-field segmentation of left- and right-hand circular polarizations of the scattered light, an effect known as the giant spin-Hall effect of light. We construct vector beams with an augmented transverse spin density gradient in the focal plane and experimentally confirm enhanced sensitivity of the far-field spin segmentation to lateral displacements of an electric-dipole nanoantenna. We conclude that sculpturing of electromagnetic field gradients and intelligent design of scatterers pave the way toward further improvements in displacement sensitivity.
CRIS-Team Scopus Importer:2020-04-14
Keywords: displacement sensing; localization; nanoantennas; tight focusing; transverse spin

Sharper Focus for a radially polarized light beam - Leuchs, Gerd; et al. (Physical Review Letters, 2003)
The influence of polarization on the shape of the focal spot was discussed. The focal intensity distribution for radially and azimuthally polarized input fields was compared to analyze the effect of vector properties of light. A radially polarization field led to a longitudinal electric field component for strong focusing. The results show that the radially polarized light beam was focused to a spot size significantly smaller than for linear polarization.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.sharpe

Shifting the phase of a coherent beam with a 174Yb+ ion: influence of the scattering cross section - Fischer, Martin; Srivathsan, Bharath; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2017)
We discuss and measure the phase shift imposed onto a radially polarized light beam when focusing it onto an Yb ion. In the derivation of the expected phase shifts, we include the properties of the involved atomic levels. Furthermore, we emphasize the importance of the scattering cross section and its relation to the efficiency for coupling the focused light to an atom. The phase shifts found in the experiment are compatible with the expected ones when accounting for known deficiencies of the focusing optics and the motion of the trapped ion at the Doppler limit of laser cooling (Hänsch and Schawlow in Opt Commun 13:68–69, 1975).

Silicon dual pillar structure with a distributed Bragg reflector for dielectric laser accelerators: Design and fabrication - Yousefi, Peyman; McNeur, Joshua; Kozak, Martin; Niedermayer, Uwe; Gannott, Florentina; Lohse, Olga; Boine-Frankenheim, Oliver; Hommelhoff, Peter (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
Dielectric laser accelerators (DLAs) have proven to be good candidates for miniaturized particle accelerators. They rely on micro-fabricated dielectrics which are able to modulate the kinetic energy of the incoming electron beam under a proper laser illumination. In this paper we demonstrate a dual pillar structure with a distributed Bragg reflector to mimic a double sided illumination to the electron path. The structure is fabricated by an electron beam lithography technique followed by a cryogenic reactive ion etching process. Such a structure can accelerate the injected 28 keV electrons by a gradient of approximately 150 MeV/m which can be further optimized towards the GeV/m regim
Keywords: Dielectric laser accelerators; Dual pillar structure; Distributed Bragg reflector; Electron beam lithography; Cryogenic reactive ion etching

Simplified theory for ellipsoidal melted microlenses - Lindlein, Norbert; et al. (EOS Topical Meetings Digest Series, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.optik.1optik.simpli

Simulating an interacting quantum gas with superconducting circuits - Eichler, Christopher (2014)
Simulating an Interacting Quantum Gas with Superconducting Circuits The high level of control achievable over quantized degrees of freedom have turned superconducting circuits into one of the prime physical architectures for quantum computing and simulation. While conventional approaches towards quantum information processing mostly rely on unitary time evolution, more recently open-system dynamics are considered for quantum simulations. In this talk, I will present experiments in which we use an open cavity QED system with tunable interactions to simulate the ground state of an interacting Bose gas confined in one dimension [1,2]. These experiments rely on the ability to efficiently measure higher order photon corrélations of the cavity output field. For this purpose we have developed a quantum limited amplifier achieving phase-preserving amplification at large bandwidth and high dynamic range [3]. Our results explore a different path towards the simulation of complex quantum many-body physics based on the controlled generation and detection of nonclassical radiation in an open quantum system. [1] S. Barrett et al., Phys. Rev. Lett. 110, 090501 (2013). [2] F. Verstraete and J. I. Cirac, Phys. Rev. Lett. 104, 190405 (2010). [3] C. Eichler et al., Phys. Rev. Lett. 113, 110502 (2014).
Keywords: wwwqudev

Simulating an Interacting Quantum Gas with Superconducting Circuits - Eichler, Christopher; et al. (APS March Meeting, 2015)
Keywords: wwwqudev

Simulating Dicke-like superradiance with classical light sources - Bhatti, Daniel; Oppel, Steffen; Wiegner, Ralph; Agarwal, Girish; von Zanthier, Joachim (Physical Review A, 2016)
In this paper we investigate the close relationship between Dicke superradiance, originally predicted for an ensemble of two-level atoms in entangled states, and the Hanbury Brown and Twiss effect, initially established in astronomy to determine the dimensions of classical light sources such as stars. By studying the state evolution of the fields produced by classical sources-defined by a positive Glauber-Sudarshan P function-when recording intensity correlations of higher order in a generalized Hanbury Brown and Twiss setup we find that the angular distribution of the last detected photon, apart from an offset, is identical to the superradiant emission pattern generated by an ensemble of two-level atoms in entangled symmetric Dicke states. We show that the phenomenon derives from projective measurements induced by the measurement of photons in the far field of the sources and the permutative superposition of quantum paths identical to those leading to superradiance in the case of single photon emitters. We thus point out an important similarity between classical sources and quantum emitters upon detection of photons if the particular photon source remains unknown. We finally present a compact result for the characteristic functional which generates intensity correlations of arbitrary order for any kind of light sourc

Simulating superradiance from higher-order-intensity-correlation measurements: Single atoms - Wiegner, Ralph; Oppel, Steffen; Bhatti, Daniel; von Zanthier, Joachim; Agarwal, G. S. (Physical Review A, 2015)
Superradiance typically requires preparation of atoms in highly entangled multiparticle states, the so-called Dicke states. In this paper we discuss an alternative route where we prepare such states from initially uncorrelated atoms by a measurement process. By measuring higher-order intensity-intensity correlations we demonstrate that we can simulate the emission characteristics of Dicke superradiance by starting with atoms in the fully excited state. We describe the essence of the scheme by first investigating two excited atoms. Here we demonstrate how via Hanbury Brown and Twiss type of measurements we can produce Dicke superradiance and subradiance displayed commonly with two atoms in the single excited symmetric and antisymmetric Dicke states, respectively. We thereafter generalize the scheme to arbitrary numbers of atoms and detectors, and explain in detail the mechanism which leads to this result. The approach shows that the Hanbury Brown and Twiss type of intensity interference and the phenomenon of Dicke superradiance can be regarded as two sides of the same coin. We also present a compact result for the characteristic functional which generates all order intensity-intensity correlation

Simulation der Vorläuferpulse bei Fokussierung ultrakurzer optischer Laserpulse - Dehne, Henry; Loosen, Florian; Iff, Wolfgang; Lindlein, Norbert (Proceeding, 115. Jahrestagung der DGaO, 2014)
Ultrakurze Laserpulse sind sowohl in Wissenschaft und Forschung als auch in der Industrie aufgrund ihrer extrem kurzen zeitlichen Breite und hohen Intensität vielseitig einsetzbar. Hierbei sind Pulsdauern, mit einer Hauptfrequenz innerhalb des sichtbaren Spektrums, in einem Bereich von wenigen Femtosekunden realisierbar. Bei der Fokussierung dieser Pulse durch Linsen mit kreisförmiger Apertur tritt ein sogenannter Vorläuferpuls auf, der sich hinter dem Fokuspunkt vom Hauptpuls separiert und mit scheinbar Überlichtgeschwindigkeit ausbreitet. Dies ist keine Verletzung der Kausalität, da der Vorläuferpuls nur eine Interferenzerscheinung ist und keine Energie ins Fernfeld trägt. Der Vorläuferpuls entsteht durch die Beugung des Pulses an der Apertur und verursacht eine „Verzerrung“ des elektrischen Feldes im Fokusbereich. Durch Simulation kann der Einfluss von Parametern wie Polarisation und numerischer Apertur (NA) auf die Geschwindigkeit, Form und Amplitude des Vorläuferpulses bestimmt werden. Hierfür wird das Debye-Integral unter Berücksichtigung der einzelnen Frequenzkomponenten des Pulses verwendet.

Simulationen zur Erfassung der Güte gedruckter Polymer Optischer Wellenleiter (POWs) bei Variation signiﬁkanter Charakteristika - Loosen, Florian; Backhaus, Carsten; Vögl, Christian; Lindlein, Norbert (Proceeding, 119. DGaO-Jahrestagung, 2018)
Die Forschergruppe OPTAVER (Optische Aufbau- und Verbindungstechnik für baugruppenintegrierte Bussysteme) beschäftigt sich seit ca. 3 Jahren mit dem Design, der Simulation und dem Druckprozess Polymer Optischer Wellenleiter (POWs). Durch den eingesetzten additiven 3D-Fertigungsprozess (Flexodruck und Aerosol Jet Druck) der Wellenleiterstrukturen wird eine optische Simulation vorab unumgänglich, um die Güte der Wellenleiter simulativ zu überprüfen. In den vergangenen DGaO-Jahrestagungen wurde neben der Erweiterung des Simulationsmodells um einen Streuansatz (Dämpfungsberechnung) [1] auch eine Erweiterung bezüglich der Signaldispersion [2] dem wissenschaftlichen Publikum vorgestellt. Dämpfung und Signaldispersion legen vor allem die Güte des Wellenleiters als wichtige Kenngrößen fest. Diese Güte ist abhängig von der Variation signifikanter Charakteristika, wie Wellenleiterform, -pfad und Materialeigenschaften, welche simulativ untersucht werden müssen, um daraus Kenngrößen für die Wellenleiter zu erhalten. [1] F. Loosen et al. DGaO Proceedings C5 (2016) [2] C. Backhaus et al. DGaO Proceedings P8 (201

Simulation of micro-optical array systems with RAYTRACE - Lindlein, Norbert; et al. (Optical Engineering, 1998)
The optical analysis and design program RAYTRACE, which was developed at our institute, enables the simulation of micro-optical systems containing arrays of microlenses or other optical components. The most important features of the program are briefly described to show its broad application areas. A special simulation example showing the spot diagram and the intensity distribution in the focal plane of a simple Shack-Hartmann sensor with a diffractive microlens array for an incident aspherical wave is given. ©1998 Society of Photo-Optical Instrumentation Engineers.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.simula
Keywords: Micro-optics; Microlens arrays; Optical design software; Ray tracing Shack-Hartmann wavefront sensor

Simulation of micro-optical systems including microlens arrays - Lindlein, Norbert (Journal of Optics A-Pure and Applied Optics, 2002)
The simulation of micro-optical systems, especially those including microlens arrays, is still a challenging task. There are of course traditional methods which can be applied under certain circumstances. This paper will discuss several geometrical optical and diffraction-based methods for the simulation of micro-optical systems. A simple paraxial geometrical optical matrix theory will be extended to the simulation of off-axis optical elements. Ray tracing will be used to model incoherent micro-optical systems. The propagation of Gaussian beams through off-axis optical systems using differential ray tracing will be discussed. The angular spectrum of plane waves will be used to propagate a scalar complex wave amplitude in free space simulating non-paraxial diffraction effects. Finally, a model will be proposed which combines ray tracing and wave propagation methods by converting a complex wave amplitude into rays and vice versa. In the case of wavefront warping a decomposition of the wave into elementary waves has to be performed. This combined model can take into account non-paraxial effects such as aberrations of optical elements and also diffraction effects.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.simula
Keywords: Optical system design; Wave propagation; Wavefronts and ray tracing

Simulations and experiments on polarization squeezing in optical fiber - Leuchs, Gerd; et al. (Physical Review A, 2008)
We investigate polarization squeezing of ultrashort pulses in optical fiber, over a wide range of input energies and fiber lengths. Comparisons are made between experimental data and quantum dynamical simulations to find good quantitative agreement. The numerical calculations, performed using both truncated Wigner and exact +P phase-space methods, include nonlinear and stochastic Raman effects, through coupling to phonon variables. The simulations reveal that excess phase noise, such as from depolarizing guided acoustic wave Brillouin scattering, affects squeezing at low input energies, while Raman effects cause a marked deterioration of squeezing at higher energies and longer fiber lengths. We also calculate the optimum fiber length for maximum squeezing. © 2008 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.simula

Simulations of the secondary maxima of highly focused ultrashort optical pulses in the focal plane - Fries, Sebastian; Loosen, Florian; Lindlein, Norbert (Proceeding, 116. Jahrestagung der DGaO, 2015)
Nowadays, ultrashort optical pulses have quite a few applications, e.g. in the measuring technology, in the processing of materials, and also in the medical science. Like in the stationary (continuous wave) case, secondary maxima appear in the focal plane, when optical pulses are focused by an aplanatic lens (without aberrations). These can be simulated by adding frequency dependent Debye integrals, where each of them can be considered as a superposition of plane waves travelling from the exit pupil to the focus. By changing the order of integrations this corresponds to a superposition of waves with plane wavefront, but time-dependent amplitude. The secondary maxima are highly dependent on the duration of the pulse. Depending on the parameters of the pulse and the lens, they have a maximum intensity at a certain duration, and seemingly vanish as the duration of the pulse grows shorter. The latter results from the fact, that at any non-axial point in the focal plane the amplitude of the envelope of some of these “plane waves” diminishes. Via simulations the effects of certain parameters, such as polarisation, numerical aperture, and initial amplitude profile can be analysed.

Simultaneous characterization of the quality and orientation of cylindrical lens surfaces - Mantel, Klaus Peter; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2005)
A diffractive grazing-incidence interferometer for the test of cylindrical lenses is described. Besides surface aberrations from the ideal shape, the interferometer allows for the simultaneous determination of the relative position and orientation of surfaces to another. The measurement principle as well as a classification of deviation types is given. Measurement results for planar concave lenses are presented. © 2005 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.simult

Simultaneous measurement of phase and local orientation of linearly polarized light: Implementation and measurement results - Rothau, Sergej; Kellermann, Christine; Nercissian, Vanusch; Berger, Andreas; Mantel, Klaus; Lindlein, Norbert; Lindlein, Norbert (Applied Optics, 2014)
Optical components manipulating both polarization and phase of wave fields find many applications in today's optical systems. With modern lithography methods it is possible to fabricate optical elements with nanostructured surfaces from different materials capable of generating spatially varying, locally linearly polarized-light distributions, tailored to the application in question. Since such elements in general also affect the phase of the light field, the characterization of the function of such elements consists in measuring the phase and the polarization of the generated light, preferably at the same time. Here, we will present first results of an interferometric approach for a simultaneous and spatially resolved measurement of both phase and polarization, as long as the local polarization at any point is linear (e.g., for radially or azimuthally polarized light).

Simultaneous measurement of phase transmission and birefringence of an object under test - Rothau, Sergej; Mantel, Klaus; Lindlein, Norbert (Applied Optics, 2018)
This paper presents a novel interferometric method for the simultaneous spatially resolved analysis of an object under test regarding the phase transmission function and the magnitude and orientation of the (uniaxial) birefringence. The measurement strategy is based on variations of the phase and polarization and processing the interference patterns so obtained. With this method, which is very similar to the classical phase-shifting interferometry, a complete analysis of birefringent properties of the object and its impact on the phase of the incoming light can be done in one measurement cycle. The theoretical description of the investigated methods and their experimental implementation are presented.
Keywords: Fringe analysis; Interferometry; Phase measurement; Polarimetry; Birefringence; Polarization; Phase measurement; Phase shift; Phase shifting interferometry; Polymer liquid crystals; Refractive index; Stress birefringence

Simultane Vermessung der Phase und der räumlich variierenden linearen Polarisation - Rothau, Sergej; Nercissian, Vanusch; Berger, Andreas; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Single Photons Emitted by Nanocrystals Optically Trapped in a Deep Parabolic Mirror - Salakhutdinov, Vsevolod; Sondermann, Markus; Carbone, Luigi; Giacobino, Elisabeth; Bramati, Alberto; Leuchs, Gerd (Physical Review Letters, 2020)

Single sideband microwave to optical photon conversion-an electro-optic realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2017)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator.
CRIS-Team Scopus Importer:2021-06-29

Single-Step Process for Titanium Surface Micro-and Nano-Structuring and In Situ Silver Nanoparticles Formation by Ultra-Short Laser Patterning - Aceti, Dante Maria; Filipov, Emil; Angelova, Liliya; Sotelo, Lamborghini; Fontanot, Tommaso; Yousefi, Peyman; Christiansen, Silke; Leuchs, Gerd; Stanimirov, Stanislav; Trifonov, Anton; Buchvarov, Ivan; Daskalova, Albena (Materials, 2022)
Ultra-short laser (USL)-induced surface structuring combined with nanoparticles synthesis by multiphoton photoreduction represents a novel single-step approach for commercially pure titanium (cp-Ti) surface enhancement. Such a combination leads to the formation of distinct topographical features covered by nanoparticles. The USL processing of cp-Ti in an aqueous solu-tion of silver nitrate (AgNO3) induces the formation of micron-sized spikes surmounted by silver nanoparticles (AgNPs). The proposed approach combines the structuring and oxidation of the Ti surface and the synthesis of AgNPs in a one-step process, without the use of additional chemicals or a complex apparatus. Such a process is easy to implement, versatile and sustainable compared to alternative methodologies capable of obtaining comparable results. Antimicrobial surfaces on medical devices (e.g., surgical tools or implants), for which titanium is widely used, can be realized due to the simultaneous presence of AgNPs and micro/nano-structured surface topography. The pro-cessed surfaces were examined by means of a scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM) and Raman spectroscopy. The surface morphology and the oxidation, quality and quantity of AgNPs were analyzed in relation to process parameters (laser scanning speed and AgNO3 concentration), as well as the effect of AgNPs on the Raman signal of Titanium oxide.
CRIS-Team Scopus Importer:2022-07-22
Keywords: laser ablation; multiphoton photo-reduction; silver nanoparticles; surface patterning; titanium; ultra-short laser processing

Slow waves on magnetic metamaterials and on chains of plasmonic nanoparticles: Driven solutions in the presence of retardation - Zhuromskyy, Oleksandr; Sydoruk, Oleksiy; Shamonina, E.; Solymar, L. (Journal of Applied Physics, 2009)
Slow waves on chains or lattices of resonant elements offer a unique tool for guiding and manipulating the electromagnetic radiation on a subwavelength scale. Applications range from radio waves to optics with two major classes of structures being used: (i) metamaterials made of coupled ring resonators supporting magnetoinductive waves and (ii) plasmonic crystals made of nanoparticles supporting waves of near-field coupling. We derive dispersion equations of both types of slow waves for the case when the interelement coupling is governed by retardation effects, and show how closely they are related. The current distribution is found from Kirchhoff's equation by inverting the impedance matrix. In contrast to previous treatments power conservation is demonstrated in a form relevant to a finite structure: the input power is shown to be equal to the radiated power plus the powers absorbed in the Ohmic resistance of the elements and the terminal impedance. The relations between frequency and wave number are determined for a 500-element line for two excitations using three different methods. Our approach of retrieval of the dispersion from driven solutions of finite lines is relevant for practical applications and may be used in the design of metamaterials and plasmonic crystals with desired properties.
EAM Import::2019-03-13

Soliton back-action evading measurement using spectral filtering - Leuchs, Gerd; et al. (Physical Review A, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.solito

Sparse Active Triangulation Grids for Respiratory Motion Management - Bauer, Sebastian; Ettl, Svenja; Wasza, Jakob; Willomitzer, Florian; Huber, Franz; Hornegger, Joachim; Häusler, Gerd (DGaO Proceedings 2012, 2012)

Spatial Herodyn-Spektrometer zur Temperaturmessung in der mittleren Atmosphäre - Wagner, Fritz; Mantel, Klaus; Loosen, Florian; Deiml, Michael; Olschewski, Friedhelm; Kaufmann, Martin (Proceeding, 118. DGaO-Jahrestagung, 2017)
Die Atmosphäre der Erde wird durch eine Vielzahl von chemischen und physikalischen Kopplungsvorgängen beeinflusst, deren Verständnis noch einige Lücken aufweist. Um die Dynamik der dort ablaufenden physikalischen Prozesse zu untersuchen und damit Wetter- und Klimamodelle testen und verbessern zu können, bedarf es der Messung atmosphärischer Daten auf einer globalen Skala und mit hoher zeitlicher und räumlicher Auflösung. Die „Initiative zur Entwicklung von Kleinsatelliten für die Erforschung von Klimaprozessen mittels Tomographie“ (DISSECT) hat sich zum Ziel gesetzt, die Zusammensetzung und Dynamik der mittleren Atmosphäre mittels Fernerkundung durchzuführen. In einem ersten Projekt werden Kleinsatelliten (CubeSats) mit sog. Spatialen Heterodyn-Spektrometern ausgerüstet, die die Temperaturverteilung der mittleren Atmosphäre spektroskopisch bestimmen sollen, indem die Intensitätsverhältnisse gewisser Linien im A-Band des Sauerstoffs gemessen werden. Der Beitrag beschreibt Design und Herstellung eines solchen Spektrometers sowie der verwendeten optischen Systeme des Kleinsatelliten. Ein erster Test des Systems erfolgt im März 2017 im Rahmen des REXUS-Projekts von DLR, SNSB und ESA.

Spatially-controlled laser-induced decoration of 2D and 3D substrates with plasmonic nanoparticles - Bashouti, M. Y.; Povolotckaia, A. V.; Povolotskiy, A. V.; Tunik, S. P.; Christiansen, S. H.; Leuchs, Gerd; Manshina, A. A. (RSC Advances, 2016)
We demonstrate a new approach which can be used for targeted imparting of plasmonic properties for a wide range of different substrates (transparent and non-transparent) which may have any 2D or 3D topological structure created independently in a prior step with some other technology.
EAM Import::2019-03-13

Spectral extension and synchronization of microcombs in a single microresonator - Zhang, Shuangyou; Silver, Jonathan M.; Bi, Toby; Del'Haye, Pascal (Nature Communications, 2020)
Broadband optical frequency combs are extremely versatile tools for precision spectroscopy, ultrafast ranging, as channel generators for telecom networks, and for many other metrology applications. Here, we demonstrate that the optical spectrum of a soliton microcomb generated in a microresonator can be extended by bichromatic pumping: one laser with a wavelength in the anomalous dispersion regime of the microresonator generates a bright soliton microcomb while another laser in the normal dispersion regime both compensates the thermal effect of the microresonator and generates a repetition-rate-synchronized second frequency comb. Numerical simulations agree well with experimental results and reveal that a bright optical pulse from the second pump is passively formed in the normal dispersion regime and trapped by the primary soliton. In addition, we demonstrate that a dispersive wave can be generated and influenced by cross-phase-modulation-mediated repetition-rate synchronization of the two combs. The demonstrated technique provides an alternative way to generate broadband microcombs and enables the selective enhancement of optical power in specific parts of a comb spectrum.
CRIS-Team Scopus Importer:2020-12-25

Spectral extension of microcombs with two seed lasers - Zhang, Shuangyou; Silver, Jonathan M.; Bi, Toby; Del'Haye, Pascal (Optics InfoBase Conference Papers, 2021)
We demonstrate the spectral extension of microcombs by bichromatic pumping of a single microresonator. One of the seed lasers generates a soliton that synchronizes with the repetition rate of the second frequency comb via cross-phase modulation.
CRIS-Team Scopus Importer:2021-12-03

Spectral properties of second, third and fourth harmonics generation from broadband multimode bright squeezed vacuum - Kopylov, Denis A.; Rasputnyi, Andrei; Murzina, Tatiana; Chekhova, Maria (Laser Physics Letters, 2020)
We study theoretically the spectra of second, third and fourth harmonics from multimode bright squeezed vacuum obtained by type-I broadband high-gain parametric down conversion. The different contributions to the spectra of harmonics are analyzed. A new method for the measurement of second-order correlation function g((2))(0) of parametric down conversion radiation is suggested.
CRIS-Team WoS Importer:2020-06-26

Spectral Radar: OCT in the Fourier Domain - Häusler, Gerd; et al. (Handbook of Optical Coherence Tomography, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dphy.optik.1optik.spectr

Spin-orbit coupling affecting the evolution of transverse spin - Eismann, Joerg S.; Banzer, Peter; Neugebauer, Martin (Physical Review Research, 2019)
We investigate the evolution of transverse spin in tightly focused circularly polarized beams of light, where spin-orbit coupling causes a local rotation of the polarization ellipses upon propagation through the focal volume. The effect can be explained as a relative Gouy-phase shift between the circularly polarized transverse field and the longitudinal field carrying orbital angular momentum. The corresponding rotation of the spatial distribution of the electric transverse spin density is observed experimentally by utilizing a recently developed reconstruction scheme, which relies on transverse-spin-dependent directional scattering of a nanoprobe.
CRIS-Team WoS Importer:2021-10-18

Spin-orbit interaction in nanofiber-based Brillouin scattering - Zerbib, Maxime; Romanet, Maxime; Sylvestre, Thibaut; Wolff, Christian; Stiller, Birgit; Beugnot, Jean Charles; Huy, Kien Phan (Optics Express, 2023)
Angular momentum is an important physical property that plays a key role in light-matter interactions, such as spin-orbit interaction. Here, we investigate theoretically and experimentally the spin-orbit interaction between a circularly polarized optical (spin) and a transverse vortex acoustic wave (orbital) using Brillouin backscattering in a silica optical nanofiber. We specifically explore the state of polarization of Brillouin backscattering induced by the TR21 torso-radial vortex acoustic mode that carries an orbital angular momentum. Using a full-vectorial theoretical model, we predict and observe two operating regimes for which the backscattered Brillouin signal is either depolarized or circularly polarized, depending on the input pump polarization. We demonstrate that when the pump is circularly polarized and thus carries a spin angular momentum, the backscattered signal undergoes a handedness reversal of circular polarization due to opto-acoustic spin-orbit interaction and the conservation of overall angular momentum.
CRIS-Team Scopus Importer:2023-07-21

Squeezed light and self-induced transparency in mercury-filled hollow core photonic crystal fibers - Vogl, Ulrich; Joly, Nicolas Y.; Russell, Philip St. J.; Marquardt, Christoph; Leuchs, Gerd (Proceedings 2015 European Conference on Lasers and Electro-Optics - European Quantum Electronics Conference, CLEO/Europe-EQEC 2015, 2015)
We successfully demonstrate squeezing of nanosecond pulses via self-induced transparency in a system of mercury vapor confined in a hollow core kagomé-style fiber.
CRIS-Team Scopus Importer:2022-06-05

Squeezed Light from Microstructured Fibres: Towards Free Space Quantum Cryptography - Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 2001)
Amplitude-squeezed pulsed light has been produced using a microstructured silica fibre. By spectrally filtering after the non-linear propagation in the fibre a squeezing value of - 1.7 dB has been measured. A quantum key distribution scheme based on squeezed light from such microstructured fibres is proposed.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.squeez

Squeezed-state purification with linear optics and feedforward - Leuchs, Gerd; et al. (Physical Review Letters, 2006)
A scheme for optimal and deterministic linear optical purification of mixed squeezed Gaussian states is proposed and experimentally demonstrated. The scheme requires only linear optical elements and homodyne detectors, and allows the balance between purification efficacy and squeezing degradation to be controlled. One particular choice of parameters gave a tenfold reduction of the thermal noise with a corresponding squeezing degradation of only 11%. We prove optimality of the protocol, and show that it can be used to enhance the performance of quantum informational protocols such as dense coding and entanglement generation. © 2006 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.squeez

Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Shafiee, Golnoush; Dirmeier, Thomas; Vogl, Ulrich; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald G.L.; Gehring, Tobias; Andersen, Ulrik L.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2018)
We demonstrate the generation of squeezed vacuum states of light in a crystalline whispering gallery mode resonator. We utilize a millimeter-sized lithium niobate resonator with strong optical second order nonlinearity. This system allows us to reach 1.2 dB of squeezing at a pump power of only 300 μW and offers hereby a compact and power efficient source of squeezed vacuum states of light.
CRIS-Team Scopus Importer:2022-06-05

Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Vogl, Ulrich; Dirmeier, Thomas; Shafiee, Golnoush; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald; Gehring, Tobias; Andersen, Ulrik Lund; Leuchs, Gerd; Marquardt, Christoph (Optica, 2019)
Squeezed vacuum states enable optical measurements below the quantum limit and hence are a valuable resource for applications in quantum metrology and also quantum communication. However, most available sources require high pump powers in the milliwatt range and large setups that hinder real-world applications. Furthermore, degenerate operation of such systems presents a challenge. Here, we use a compact crystalline whispering gallery mode resonator made of lithium niobate as a degenerate parametric oscillator. We demonstrate about 1.4 dB noise reduction below the shot-noise level for only 300 mu W of pump power in degenerate single-mode operation. Furthermore, we report a record pump threshold as low as 1.35 mu W. Our results show that the whispering gallery-based approach presents a promising platform for a compact and efficient source for nonclassical light. (c) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-12-06

Squeezing by self induced transparency in Rb filled hollow core fibers - Zhong, Wenjia; Marquardt, Christoph; Leuchs, Gerd; Andersen, U. L.; Light, P; Couny, F.; Benabid, F. (2007 European Conference on Lasers and Electro-Optics and the International Quantum Electronics Conference, 2007)
There is great interest in photonic crystal fibers (PCFs) because of their potential for hosting highly nonlinear material. Already with material of low nonlinearity such as silica for solid core PCFs, the nonlinear properties can be utilized since high intensities of light are guided within the core. To create squeezed states, we plan to exploit the high nonlinearity of resonant Rb vapor filled in the hollow fiber core and to use self-induced transparency (SIT) solitons to avoid resonant loss. High nonlinearity is induced from the self-phase modulation of a detuned 2pi soliton. Photon-phonon interactions, which cause a significant amount of excess noise in solid core fibers, will be highly reduced in our system.<br
Keywords: Resonance; Optical fiber theory; Photonics; Crystalline materials; Fiber nonlinear optics; Optical solitons; Solids; Atom optics; Physics; Optical materials

Stabilization of transmittance fluctuations caused by beam wandering in continuous-variable quantum communication over free-space atmospheric channels - Usenko, Vladyslav C.; Peuntinger, Christian; Heim, Bettina; Guenthner, Kevin; Derkach, Ivan; Elser, Dominique; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd (Optics Express, 2018)
Transmittance fluctuations in turbulent atmospheric channels result in quadrature excess noise which limits applicability of continuous-variable quantum communication. Such fluctuations are commonly caused by beam wandering around the receiving aperture. We study the possibility to stabilize the fluctuations by expanding the beam, and test this channel stabilization in regard of continuous-variable entanglement sharing and quantum key distribution. We perform transmittance measurements of a real free-space atmospheric channel for different beam widths and show that the beam expansion reduces the fluctuations of the channel transmittance by the cost of an increased overall loss. We also theoretically study the possibility to share an entangled state or to establish secure quantum key distribution over the turbulent atmospheric channels with varying beam widths. We show the positive effect of channel stabilization by beam expansion on continuous-variable quantum communication as well as the necessity to optimize the method in order to maximize the secret key rate or the amount of shared entanglement. Being autonomous and not requiring adaptive control of the source and detectors based on characterization of beam wandering, the method of beam expansion can be also combined with other methods aiming at stabilizing the fluctuating free-space atmospheric channels.
CRIS-Team Scopus Importer:2022-06-05

Stitching errors in diffractive nulltest elements - Berger, Andreas; Harder, Irina; Nercissian, Vanusch; Mantel, Klaus Peter; Lindlein, Norbert (DGaO Proceedings, 2012)

Structured quantum projectiles - Larocque, Hugo; Fickler, Robert; Cohen, Eliahu; Grillo, Vincenzo; Dunin-Borkowski, Rafal E.; Leuchs, Gerd; Karimi, Ebrahim (Physical Review A, 2019)
Matter wave interferometry is becoming an increasingly important technique in quantum metrology. However, unlike its photonic counterpart, this technique relies on the interference of particles possessing a nonzero rest mass and an electric charge. Matter waves can therefore experience alterations in their wavelike features while propagating through uniform fields to which a linear potential can be attributed, e.g., the Newtonian gravitational potential. Here, we derive the propagation kernel attributed to matter waves within such a potential. This kernel thereafter allows us to provide analytical formulations for structured matter waves subjected to a linear potential. Our formulations are in agreement with both the classical dynamics attributed to such waves and with previous interferometry experiments. Eigenbasis representations of structured matter waves are also introduced along with their application to enhanced interferometric measurements. Our results are not only relevant to matter wave interferometry, but also emphasize its fundamental differences with respect to photonic interferometry.
CRIS-Team WoS Importer:2019-03-15

Strukturierungsfehler diffraktiv optischer Elemente - Berger, Andreas; Harder, Irina; Lohse, Olga; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Study of broadband multimode light via non-phase-matched sum frequency generation - Kopylov, Denis A.; Spasibko, Kirill; Murzina, Tatiana; Chekhova, Maria (New Journal of Physics, 2019)
We propose non-phase-matched sum frequency generation (SFG) as a method for characterizing broadband multimode light. Both the central wavelength and the bandwidth are in this case not limited by the phase matching condition. As an example, we consider bright squeezed vacuum (BSV) generated through high-gain parametric down conversion (PDC). In the spectrum of SFG from BSV, we observe the coherent peak and the incoherent background. We show that the ratio of their widths is equal to the number of frequency modes in BSV, which in the case of low-gain PDC gives the degree of frequency entanglement for photon pairs. By generating the sum frequency in the near-surface region of a nonlinear crystal, we increase the SFG efficiency and get rid of the modulation caused by chromatic dispersion, known as Maker fringes. This allows one to use non-phasematched SFG as a wavelength-independent autocorrelator. Furthermore, we demonstrate efficient non-phase-matched three- and four-frequency summation of broadband multimode light, hardly possible under phase matching. We show that the latter contains the coherent peak while the former does not.
CRIS-Team WoS Importer:2019-04-12

Study of mass transfer in supercritical carbon dioxide (SCCO2) using optical methods - Hu, Miao; Benning, Rainer; Delgado, Antonio; Ertunc, Özgür; Nercissian, Vanusch; Berger, M. (Heat and Mass Transfer, 2017)
The purpose of this work is to design and develop a type of experiment setup that would enable the direct observation of steady diffusion process in situ. Two different optical methods - shadowgraph and shearing interferometry - were used for the first time to visualise and quantitatively analyse the diffusion around a droplet of organic substance in supercritical carbon dioxide (SCCO2) as well as in its direct vicinity. We constructed and tested a cylindrical high-pressure chamber and an experiment system with a high speed camera. The solute/solvent combination of DL-α-tocopherol/SCCO2 was applied using shadowgraph. The diffusion coefficients at temperatures of 40o C, 50o C and 60o C and pressures between 75 bar and 90 bar were calculated based on the displacement of the droplet contour in the captured images. The shearing interferometry with a Wollaston-prism was then applied not only for the combination of DL-α-tocopherol/SCCO2, but also for other substances in SCCO2, for example for a type of rose oil and lubricant oil as well as for acetone, benzene, toluene and naphthalene. The changes of the refractive index gradient were directly measured and evaluated with the interferograms; afterwards changes of the density gradients and the diffusion coefficients were determined. We propose then a multivariate regression model to capture the relationship between the diffusion coefficient, the pressure and the temperature. To minimize the influence of gravity-driven convections in the solvent during diffusion, the experiments were also carried out under microgravity condition, i.e. in two parabolic flight campaign
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.studyo

Study of turbulence induced orbital angular momentum channel crosstalk in a 1.6km free-space optical link - Lavery, Martin P.J.; Heim, Bettina; Peuntinger, Christian; Magaña-Loaiza, Omar S.; Karimi, Ebrahim; Bauer, Thomas; Banzer, Peter; Marquardt, Christoph; Willner, Alan E.; Boyd, Robert W.; Padgett, Miles J.; Leuchs, Gerd (CLEO: Science and Innovations, CLEO-SI 2015, 2015)
We experimentally study the turbulence induced crosstalk between orbital angular momentum channels transmitted over a 1.6 km optical link. Our presented results indicate that turbulence mitigation techniques will be required for links of this length. © OSA 2015.
CRIS-Team Scopus Importer:2022-06-05

Stylus ion trap for enhanced access and sensing - Leuchs, Gerd; et al. (Nature Physics, 2009)
Small, controllable, highly accessible quantum systems can serve as probes at the single-quantum level to study a number of physical effects, for example in quantum optics or for electric- and magnetic-field sensing. The applicability of trapped atomic ions as probes is highly dependent on the measurement situation at hand and thus calls for specialized traps. Previous approaches for ion traps with enhanced optical access included traps consisting of a single ring electrode or two opposing endcap electrodes. Other possibilities are planar trap geometries, which have been investigated for Penning traps and radiofrequency trap arrays. By not having the electrodes lie in a common plane, the optical access can be substantially increased. Here, we report the fabrication and experimental characterization of a novel radiofrequency ion trap geometry. It has a relatively simple structure and provides largely unrestricted optical and physical access to the ion, of up to 96% of the total 4 solid angle in one of the three traps tested. The trap might find applications in quantum optics and field sensing. As a force sensor, we estimate sensitivity to forces smaller than 1 yN Hz 1/2. © 2009 Macmillan Publishers Limited.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.stylus

Sub shot noise phase quadrature measurement of intense light beams - Leuchs, Gerd; et al. (Optics Letters, 2004)
We present a setup for performing sub-shot-noise measurements of the phase quadrature of intense pulsed light without the use of a separate local oscillator. A Mach-Zehnder interferometer with an unbalanced arm length is used to detect the fluctuations of the phase quadrature at a single sideband frequency. With this setup, the nonseparability of a pair of quadrature-entangled beams is demonstrated experimentally. © 2004 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.subsho

Substrate-Induced Chirality in an Individual Nanostructure - Nechayev, Sergey; Barczyk, Rene; Mick, Uwe; Banzer, Peter (ACS Photonics, 2019)
We experimentally investigate the chiral optical response of an individual nanostructure consisting of three equally sized spherical nanoparticles made of different materials and arranged in 90 degrees bent geometry. Placing the nanostructure on a substrate converts its morphology from achiral to chiral. Chirality leads to pronounced differential extinction (circular dichroism) and optical rotation (circular birefringence), which would be strictly forbidden in the absence of a substrate or heterogeneity. This first experimental observation of the substrate-induced break of symmetry in an individual heterogeneous nanostructure sheds new light on chiral light-matter interactions at substrate-nanostructure interfaces.
CRIS-Team WoS Importer:2019-09-13

SUCROSE TRANSPORTER 5 supplies Arabidopsis embryos with biotin and affects triacylglycerol accumulation - Pommerrenig, Benjamin; Popko, Jennifer; Heilmann, Martin; Schulmeister, Sylwia; Dietel, Katharina; Schmitt, Bianca; Stadler, Ruth; Feussner, Ivo; Sauer, Norbert (Plant Journal, 2013)
The Arabidopsis SUC5 protein represents a classical sucrose/H(+) symporter. Functional analyses previously revealed that SUC5 also transports biotin, an essential co-factor for fatty acid synthesis. However, evidence for a dual role in transport of the structurally unrelated compounds sucrose and biotin in plants was lacking. Here we show that SUC5 localizes to the plasma membrane, and that the SUC5 gene is expressed in developing embryos, confirming the role of the SUC5 protein as substrate carrier across apoplastic barriers in seeds. We show that transport of biotin but not of sucrose across these barriers is impaired in suc5 mutant embryos. In addition, we show that SUC5 is essential for the delivery of biotin into the embryo of biotin biosynthesis-defective mutants (bio1 and bio2). We compared embryo and seedling development as well as triacylglycerol accumulation and fatty acid composition in seeds of single mutants (suc5, bio1 or bio2), double mutants (suc5 bio1 and suc5 bio2) and wild-type plants. Although suc5 mutants were like the wild-type, bio1 and bio2 mutants showed developmental defects and reduced triacylglycerol contents. In suc5 bio1 and suc5 bio2 double mutants, developmental defects were severely increased and the triacylglycerol content was reduced to a greater extent in comparison to the single mutants. Supplementation with externally applied biotin helped to reduce symptoms in both single and double mutants, but the efficacy of supplementation was significantly lower in double than in single mutants, showing that transport of biotin into the embryo is lower in the absence of SUC5.

Superbunching and Nonclassicality as new Hallmarks of Superradiance - Bhatti, Daniel; von Zanthier, Joachim; Agarwal, Girish S. (Scientific Reports, 2015)
Superradiance, i.e., spontaneous emission of coherent radiation by an ensemble of two-level atoms in collective states introduced by Dicke in 1954, is one of the enigmatic problems of quantum optics. The startling gist is that even though the atoms have no dipole moment they radiate with increased intensity in particular directions. Following the advances in our understanding of superradiant emission by atoms in entangled W-states we examine the quantum statistical properties of superradiance. Such investigations require the system to have at least two excitations in order to explore the photon-photon correlations of the radiation emitted by such states. We present specifically results for the spatially resolved photon-photon correlations of systems prepared in doubly excited W-states and give conditions when the atomic system emits nonclassial light. Equally, we derive the conditions for the occurrence of bunching and even of superbunching, a rare phenomenon otherwise known only from nonclassical states of light like the squeezed vacuum. We finally investigate the photon-photon cross correlations of the spontaneously scattered light and highlight the nonclassicalty of such correlations. The theoretical findings can be implemented with current technology, e.g., using ions in a linear rf-trap, atoms in an optical lattice or quantum dots in a cavit

Superconducting circuits for quantum computing - Eichler, Christopher (QCHS SUMMER SCHOOL, 2022)
Keywords: wwwqudev

Superconducting Quantum Circuits - Eichler, Christopher (QSIT Meeting - Winter school, 2017)
Keywords: wwwqudev

Superlinear threshold detectors in quantum cryptography - Lydersen, Lars; Jain, Nitin; Wittmann, Christoffer; Maroy, Oystein; Skaar, Johannes; Marquardt, Christoph; Makarov, Vadim; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2011)
We introduce the concept of a superlinear threshold detector, a detector that has a higher probability to detect multiple photons if it receives them simultaneously rather than at separate times. Highly superlinear threshold detectors in quantum key distribution systems allow eavesdropping the full secret key without being revealed. Here, we generalize the detector control attack, and analyze how it performs against quantum key distribution systems with moderately superlinear detectors. We quantify the superlinearity in superconducting single-photon detectors based on earlier published data, and gated avalanche photodiode detectors based on our own measurements. The analysis shows that quantum key distribution systems using detector(s) of either type can be vulnerable to eavesdropping. The avalanche photodiode detector becomes superlinear toward the end of the gate. For systems expecting substantial loss, or for systems not monitoring loss, this would allow eavesdropping using trigger pulses containing less than 120 photons per pulse. Such an attack would be virtually impossible to catch with an optical power meter at the receiver entrance. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Superresolving Imaging of Arbitrary One-Dimensional Arrays of Thermal Light Sources Using Multiphoton Interference - Classen, Anton; Waldmann, Felix; Giebel, Sebastian; Schneider, Raimund; Bhatti, Daniel; Mehringer, Thomas; von Zanthier, Joachim (Physical Review Letters, 2016)
We propose to use multiphoton interferences of photons emitted fromstatistically independent thermal light sources in combination with linear optical detection techniques to reconstruct, i.e., image, arbitrary source geometries in one dimension with subclassical resolution. The scheme is an extension of earlier work [S. Oppel et al., Phys. Rev. Lett. 109, 233603 (2012)], where N regularly spaced sources in one dimension were imaged by use of the Nth-order intensity correlation function. Here, we generalize the scheme to reconstruct any number of independent thermal light sources at arbitrary separations in one dimension, exploiting intensity correlation functions of order m >= 3. We present experimental results confirming the imaging protocol and provide a rigorous mathematical proof for the obtained subclassical resolutio

Suppression of Nonlinear Phase Noise in a DPSK Transmission Using a Nonlinear Amplifying Loop Mirror - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Fiber Communication 2009, 2009)
Experimental and numerical investigations of phase-preserving amplitude regeneration in a DPSK transmission with a NALM have shown that a 3dB improvement of the Q-factor or alternatively a 3dB increase of fiber-launched power could be achieved. © 2009 IEEE.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.suppre

Suppression of the critical angle of diffraction in thin-film colloidal photonic crystals - Romanov, Sergei G.; Peschel, Ulf; Bardosova, Maria; Essig, Sabine; Busch, Kurt (Physical Review B, 2010)
We present an experimental and numerical investigation of the polarization anisotropy of the zero-order backdiffracted light from three-dimensional thin-film photonic crystals assembled from colloidal spheres. In particular, we compare simulations of reflectance spectra from perfectly ordered fcc lattice of spheres with measured reflectance data from self-organized opal films and forced-assembled Langmuir-Blodgett crystal films. We identify cross-polarization couplings and interactions between photonic crystal eigenmodes as the major physical mechanisms for resonance depolarization effects. Based on this, we find that a necessary condition for the observation of critical angles of diffraction in three-dimensional lattices is that the orientation of the light's plane of incidence coincides with a high-symmetry plane of the crystal lattice. We further show that for currently achievable colloidal photonic crystals with moderate refractive index contrast, this resonance depolarization mechanisms together with the destructive influence of lattice disorder effectively renders the meaning of a critical angle of diffraction obsolete.
EAM Import::2019-03-13

Surface structuring of β-TCP and transition to α-TCP induced by femtosecond laser processing - Aceti, D. M.; Filipov, E.; Sotelo, Lamborghini; Fontanot, T.; Christiansen, S.; Lasgorceix, M.; Leriche, A.; Buchvarov, I.; Daskalova, A. (Journal of Physics: Conference Series, 2023)
Tricalcium phosphate (Ca3(PO4)2, TCP), is one of the most studied and used as material for bioresorbable implants. The β phase has a slower dissolution dynamic and ensures mechanical support for a longer time in biological environment, while a faster release of ions characterize the α phase that trigger a stronger biological response. In this work a femtosecond laser system was used to process β-TCP pellets surface. The femtosecond laser processing results in surface morphology modification, by turning the flat mirror polished surface into a rough and opaque one. The morphological and phisycochemical characteristics of material surface were studied by means of SEM, AFM, Raman, XRD and contact angle measurement. The processed surface showed the formation of micro and nano roughness alongside, furthermore a partial phase transformation from β-TCP to α-TCP was detected. A significant improvement in surface wettability for three different liquids (i.e.water, ethylene glycol and diiodo-methane) is reported. This implies an increase in surface free energy as well. The combination of α and β phase, together with the increased roughness obtained by laser processing, could positively affect the cell adhesion and metabolic activity.
CRIS-Team Scopus Importer:2023-06-02

Systematic investigation of the effect of aberration on ultrashort optical pulses focused by an aplanatic lens - Fries, Sebastian; Loosen, Florian; Lindlein, Norbert (Proceeding, 5th doctoral students conference on optics (DoKDoK), 2016)

Systematic investigation of the principal and first secondary maxima of ultrashort optical pulses focused by a high numerical aperture aplanatic lens - Lindlein, Norbert; Loosen, Florian; Fries, Sebastian (Optical Systems Design 2015: Computational Optics, 2015)
The electromagnetic field in the focus of an ideal aplanatic lens with high numerical aperture, which is illuminated by an ultrashort optical pulse and plane wave front, is simulated by taking the vectorial Debye integral and the coherent superposition of a frequency spectrum of monochromatic waves. The behavior of the principal maxima and the first secondary maxima as function of the numerical aperture (NA) and the pulse duration T is investigated systematically for light incident with linear polarization. First, one would not expect remarkable deviations from the stationary case. But also this simple system of an ideal aplanatic lens without any chromatic or monochromatic aberrations (of course only simple from the point of theory, but not at all from the point of practical realization) shows some remarkable results. If the NA (in vacuum) tends to the limiting case of 1.0 the maximum value of |E| increases faster than expected from the scalar theory (Airy disc) with a maximum deviation of about 13%. The second effect really comes from very short pulses, i.e. very small values T. Then, the value of |E| compared to the expected linear increase with 1/T decreases slightly (only less than 2%), but systematically for all NAs. Even more interesting is the dependence of the height of the first secondary maxima along the x-axis and y-axis on the NA and 1/T. It can be seen that along both axes the first secondary maxima nearly vanish for very short pulses, i.e. large values 1/T.
Keywords: aplanatic lens; electric field distribution in the focus; focusing at high numerical aperture; optical simulation techniques; propagation of ultrashort optical pulses; Ultrashort optical pulses

Tailored polarization patterns for performance optimization of optical devices - Leuchs, Gerd; et al. (Journal of Modern Optics, 2006)
In the case of strong focusing the smallest possible focal spot can be reached, provided one uses a specially designed polarization pattern. Other optical set-ups also employing high numerical aperture imaging are likewise expected to improve performance under polarization optimization. We propose a strategy for calculating the polarization pattern required for system optimization. A single element modulating only the polarization and not amplitude and phase may lead to satisfactory performance in some cases.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.tailor

TE- and TM-polarization-resolved spectroscopy on quantum wells under normal incidence - Malzer, Stefan; Leuchs, Gerd; Schardt, Michael; et al. (Physica E-Low-Dimensional Systems & Nanostructures, 2006)
We present TE- and TM-polarization-resolved photocurrent measurements on quantum well pin diodes under normal incidence. Usually, optical experiments performed in such a geometry yield information only about transitions involving in-plane (p and p ) components of the hole wave functions because of the in-plane (TE) polarization of the light. Information on transitions sensitive to the p components can be obtained by focussing a radially polarized laser beam through a microscope objective with high numerical aperture ( NA = 0.9). With our setup, the electrical field vector at the focal tail has a significant component along the optical axis (TM-polarization!) which enables excitation of transitions sensitive to p components also. Additionally, the existence of a degenerate (azimuthally polarized) optical mode enables switching these p components on and off easily. Experimental evidence of these features has been achieved by exploiting the selection rules for e-hh and e-lh transitions in a quantum well structure. We present a comparison of our recorded spectra with theoretical predictions obtained from simple geometric optics assumptions. For our quantum wells the polarization effects are small because our measurement averages the intensity distribution of the whole focal plane. We plan to extend our measurements to polarization resolved single quantum dot spectroscopy. By restricting the detection region to the spatial extent of a single dot, one can exploit the almost pure TM-polarization on the optical axis for obtaining high contrast between heavy- and light-hole exciton absorption. © 2006.

Technical Modelling Approach for Spatial Integrated Optomechatronic Products - Zeitler, Jochen; Reitberger, Thomas; Reichle, Andreas; Backhaus, Carsten; Lindlein, Norbert; Franke, Jörg (Procedia CIRP, Volume 84, 2019)
In the age of digitalization, the amount of data generated and transferred continues to increase dramatically. To increase the usability of this data it must be accessible with sufficient transmission bandwidth. Optical signals are already being used for transmitting data over long distances and high bandwidths, as this enables fast and low-loss data transmission. This trend is now also continuing in smaller scales of data transmission. Consequently, even highly integrated electrical circuits must be supported with optical components. Therefore, completely new research approaches for the product development of spatially integrated optical waveguides are necessary. The polymer-based aerosol jet printing represents a promising method to print optical waveguides on 3D circuit carriers. For this reason, the Research Group for Module Integrated Bus Systems deals with topics related to product development and production of such systems. A focus is to customize the design and associated modelling tasks accordingly. Thus, it is essential to create methodical approaches for a digital representation of waveguides and their production processes in order to map the physical behavior and to predict their manufacturability. Current studies show that integrated engineering approaches with removed boundaries among engineering domains are preferable to traditional engineering approaches. Consequently, novel engineering tools are needed for modelling the geometric as well as the physical properties of optical waveguides with the possibility to integrate specific design rule checks. The presented modelling approach in this paper provides/supports the creation of exact digital models without discontinuities through unnecessary interfaces. This article presents a method for a powerful computer-aided modelling environment that enables the design of models that are capable of representing and validating logical relationships among optoelectronic networks, but also considers challenges resulting from spatial geometric characteristics as well as restrictions from manufacturing and physic
Keywords: Computer aided design (CAD); Product development; Optomechatronics

Telecentric line scanning system based on a ring surface mirror for inline processes - Loosen, Florian; Lindlein, Norbert; Donner, Klaus (Advanced Optical Technologies, 2016)
In many industrial applications, an inline measurement of a production process poses a difficult challenge for any optical system. Therefore, telecentric optical systems are being used to ensure an independence of the magnification of the object from the working distance. Usually, telecentric optical systems are impractical for inline applications with large objects due to the size of the telecentric optical system, which has to be larger than the object. Therefore, a new approach of telecentric line scanning systems was developed to gain access to this advantage.
Keywords: industrial applications; inline processes; measuring system; optical design and simulation; ring surface mirror; telecentric system.

Telezentrischer Linienscanner auf Basis eines Ringfächenspiegels zur Oberflächenanalyse von Bauteilen - Loosen, Florian; Iff, Wolfgang; Lindlein, Norbert; Donner, Klaus (Proceeding, 115. Jahrestagung der DGaO, 2014)
Telezentrische Objektive finden heutzutage in der Messtechnik Anwendung, damit auch bei Veränderung des Objektabstands der Abbildungsmaßstab des Systems nicht von der Tiefe des Objekts abhängt. Da jedoch telezentrische Objektive für das Abscannen großer Oberflächen zu groß und preisintensiv sind, wird hier für diese Anwendung ein modulares System vorgestellt, mit dessen Aufbau ein Objekt linienförmig abgescannt werden kann. Das Ziel dieser Arbeit ist, eine ringförmige Scanlinie auf eine Zeilenkamera abzubilden. Dabei werden die von jedem Objektpunkt ausgehenden Hauptstrahlen durch einen Ringflächenspiegel um 90° abgelenkt und das Objekt auf eine Kugelschale projiziert. Abhängig von der Geometrie der spiegelnden Fläche entsteht so ein reelles oder virtuelles Zwischenbild des Objekts, welches durch ein Abbildungssystem auf den Detektor abgebildet wird. Durch die optische Simulation der Systembestandteile sowie des Gesamtsystems können verschiedene Einflussgrößen genau bestimmt werden. Zur Analyse werden dafür die Punktbildfunktion (PSF) in lateraler sowie in axialer Richtung (Schärfentiefe im Objektraum) und die Wellenaberrationen (WA) der Strahlenbündel bestimmt.

Temporally Distilled High-Dimensional Biphotonic States from Thin Sources - Sultanov, Vitaliy; Chekhova, Maria (ACS Photonics, 2024)
Generation of entangled photons through spontaneous parametric down-conversion (SPDC) from micro- and nanoscale sources offers unprecedented freedom in quantum state engineering, including the ability to generate two-photon states with high-dimensional hyperentanglement. However, as the source of SPDC gets smaller, the role of photoluminescence increases, which leads to the contamination of two-photon states with a thermal background. Here we propose and implement a solution to this problem: by using pulsed SPDC and time distillation, we increase the purity and the heralding efficiency of the photon pairs. In the experiment, we increased the purity of the two-photon states generated in a 7 μm film of lithium niobate from 0.002 to 0.99. With the higher purity we were able to observe and characterize different polarization states of photon pairs generated simultaneously due to relaxed phase matching. In particular, we showed the presence of orthogonally polarized photons that are potentially usable for the generation of polarization entanglement.
CRIS-Team Scopus Importer:2024-02-09
Keywords: distillation; nanoscale; photon pairs; purity

Temporal shaping of heralded photons in a resonator-assisted parametric down-conversion with modulated pump pulses - Averchenko, V. A.; Förtsch, M.; Fischer, M.; Aiello, A.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2022-06-05

Temporal shaping of single photons enabled by entanglement - Averchenko, Valentin; Sych, Denis; Schunk, Gerhard; Vogl, Ulrich; Marquardt, Christoph; Leuchs, Gerd (Physical Review A, 2017)
We present a method to produce pure single photons with an arbitrary designed temporal shape in a heralded way. As an indispensable resource, the method uses pairs of time-energy entangled photons. One photon of a pair undergoes temporal amplitude-phase modulation according to the desired shape. Subsequent frequency-resolved detection of the modulated photon heralds its entangled counterpart in a pure quantum state. The temporal shape of the heralded photon is indirectly affected by the modulation in the heralding arm. We derive conditions for which the shape of the heralded photon is given by the modulation function. The method can be implemented with various sources of time-energy entangled photons. In particular, using entangled photons from parametric down-conversion the method provides a simple means to generate pure shaped photons with an unprecedented broad range of temporal durations, from tenths of femtoseconds to microseconds. This shaping of single photons will push forward the implementation of scalable multidimensional quantum information protocols, efficient photon-matter coupling, and quantum control at the level of single quanta.
CRIS-Team Scopus Importer:2022-06-05

TEMPUS, a Timepix4-based system for the event-based detection of X-rays - Correa, Jonathan; Ignatenko, Alexandr; Pennicard, David; Lange, Sabine; Fridman, Sergei; Karl, Sebastian; Lohse, Leon; Senfftleben, Björn; Sergeev, Ilya; Velten, Sven; Prajapat, Deepak; Bocklage, Lars; et al. (Journal of Synchrotron Radiation, 2024)
TEMPUS is a new detector system being developed for photon science. It is based on the Timepix4 chip and, thus, it can be operated in two distinct modes: a photon-counting mode, which allows for conventional full-frame readout at rates up to 40 kfps; and an event-driven time-stamping mode, which allows excellent time resolution in the nanosecond regime in measurements with moderate X-ray flux. In this paper, the initial prototype, a single-chip device, is introduced, and the readout system described. Moreover, and in order to evaluate its capabilities, some tests were performed at PETRA III and ESRF for which results are also presented.<br
Keywords: X-ray detector; photon science; event-driven; sparse-readout; Timepix4.

Testing acylindrical microlenses at grazing incidence - Lindlein, Norbert; et al. (Optik, 2000)
An interferometer is described which allows the fast test of acylindrical microlenses at grazing incidence. The interferometer uses two diffractive optical elements as beam splitters and beam shapers. For the test of cylinder lenses at grazing incidence a conical test wavefront is needed, which is generated by diffraction at a phase structure. One main feature is that the sensitivity only depends on the pitch of the diffractive elements. The interferometer, the fringe evaluation method, and the method to eliminate aberrations are described in detail and measurement results are presented.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.testin

Test of a remote sensing Michelson-interferometer for temperature Measurements in the Mesosphere on a REXUS Rocket - Deiml, Michael; Song, Rui; Fröhlich, Denis; Rottland, Björn; Wagner, Fritz; Liu, Jilin; Wroblowski, Oliver; Chen, Qiuyu; Loosen, Florian; Kaufmann, Martin; Rongen, Heinz; Neubert, Tom; et al. (23. ESA Symposium on European Rocket and Ballon Programmes and related Research, 2017)
The experiment AtmoHIT, the Atmospheric Heterodyne Interferometer Test, is a precursor mission with the goal to verify a small satellite remote sensing instrument under space conditions. The satellite instrument is developed to measure temperatures in the Mesosphere/Lower-Thermosphere. Temperature measurements allow the characterization of gravity waves, which have an increasing importance in the modelling of the climate system representing one of the larger uncertanties in this field. The instrument consists of a highly miniturized and rigid Spatial Heterodyne Spectrometer (SHS), which measures the oxygen atmospheric band emission in the Mesosphere. The instrument resolves individual rotational lines whose intensities follow a Boltzmann law allowing for the derivation of temperature from the relative structure of these lines. This instrument ich characterized by its high throughput at a small form factor to perform scientific remote sensing measurements with a CubeSat. The AtmoHIT experiment is part of the Rocket Experiment for University Students campaign (REXUS 22), realised under a bilateral Agency Agreement between the German Aerospace Centre (DLR) and the Swedish National Space Board (SNSB). This contribution focuses on the developed technologies, laboratory measurements and rocket campaign results.

The Asymmetric Fiber Sagnac Interferometer as a Possibility of Noise-Reduction and Puls-Shaping in Modern High Bitrate Telecommunication Systems - Wietfeld, André; Meißner, Markus; Schmauß, Bernhard; Korolkova, Natalia; Leuchs, Gerd (DPG-Frühjahrstagung, 2001)
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.LEH.theasy

The asymmetric fiber-Sagnac interferometer in a high bitrate telecommunication system - Leuchs, Gerd; et al. (CLEO/Europe Focus Meeting Conference Digest, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.theasy

The Direct Writing of Plasmonic Gold Nanostructures by Electron-Beam-Induced Deposition - Hoeflich, Katja; Yang, Ren Bin; Berger, Andreas; Leuchs, Gerd; Christiansen, Silke (Advanced Materials, 2011)
Various nanostructures are directly written by electron-beam-induced deposition using dimethyl-gold(III)-acetylacetonate as the precursor gas. After purification, their potential applications include plasmonic devices and metamaterials. Carbon contamination of the as-written structures can be completely removed by low-temperature ozone treatment, leaving polycrystalline pure gold structures (see figure). This treatment reduces the size of the nanostructures but does not substantially alter their functional shape.
EAM Import::2019-03-12

The Effect of Dissipation on Nonclassical States of the Radiation Field - Leuchs, Gerd; et al. (Laser Physics, 2005)
We point out similarities in the evolution of different types of nonclassical light fields. Generally, Fock and cat states are considered to decay much faster under dissipation than do squeezed states. We connect measurements of the intensity correlation function of nonclassical light to the second moment of the photon number distribution function. It is shown that all these nonclassical fields behave in a similar manner when one is looking at an appropriate property. Finally it is shown how the electronic-detection noise floor, typically present in measurements of the variance of a photocurrent, can be eliminated based upon a procedure that is well-established for intensity correlation measurements. Copyright © 2005 by MAIK "Nauka/ Interperiodica" (Russia).
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.theeff

The effect of the high surface roughness in a comparative process - Häusler, Gerd; et al. (Optics and Lasers in Engineering, 2002)
Comparative measurement methods are used to compare the behaviour of two macroscopically identical but microscopically different object surfaces. The roughness of these surfaces can have any value. The aim of this paper is to demonstrate theoretically as well as experimentally, the effect and the limitations of the high surface roughness on the visibility of the difference correlation fringes obtained in comparative processes. © 2001 Elsevier Science Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.theeff
Keywords: Comparative holography; Difference correlation fringes; Surface roughness; Visibility

The focus of light-linear polarization breaks the rotational symmetry of the focal spot - Leuchs, Gerd; et al. (Journal of Modern Optics, 2003)
We experimentally demonstrate for the first time that a linearly polarized beam is focused to an asymmetric spot when using a high-numerical aperture focusing system. This asymmetry was predicted by Richards and Wolf in 1959 and can only be measured when a polarization-insensitive sensor is placed in the focal region. We used a specially modified photodiode in a knife-edge-type set-up to obtain highly resolved images of the total electric energy density distribution at the focus. The results are in good agreement with the predictions of a vectorial focusing theory.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.thefoc

The focus of light - theoretical calculation and experimental tomographic reconstruction - Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 2001)
We present numerical calculations on the field distribution in the focus of an optical system with high numerical aperture. The diffraction integrals which are based on the Debye approximation are derived and evaluated for a radially polarized input field with a doughnut-shaped intensity distribution. It is shown that this mode focusses down to a spot size significantly smaller as compared to the case of linear polarization. An experimental setup to measure the three-dimensional intensity distribution in the focal region is presented, which is based on the knife-edge method and on tomographic reconstruction.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.thefoc

The Formation of Calcified Nanospherites during Micropetrosis Represents a Unique Mineralization Mechanism in Aged Human Bone - Milovanovic, Petar; Zimmermann, Elizabeth A.; Scheidt, Annika Vom; Hoffmann, Björn; Sarau, George; Yorgan, Timur; Schweizer, Michaela; Amling, Michael; Christiansen, Silke; Busse, Bjoern (Small, 2017)
Osteocytes—the central regulators of bone remodeling—are enclosed in a network of microcavities (lacunae) and nanocanals (canaliculi) pervading the mineralized bone. In a hitherto obscure process related to aging and disease, local plugs in the lacuno-canalicular network disrupt cellular communication and impede bone homeostasis. By utilizing a suite of high-resolution imaging and physics-based techniques, it is shown here that the local plugs develop by accumulation and fusion of calcified nanospherites in lacunae and canaliculi (micropetrosis). Two distinctive nanospherites phenotypes are found to originate from different osteocytic elements. A substantial deviation in the spherites' composition in comparison to mineralized bone further suggests a mineralization process unlike regular bone mineralization. Clearly, mineralization of osteocyte lacunae qualifies as a strong marker for degrading bone material quality in skeletal aging. The understanding of micropetrosis may guide future therapeutics toward preserving osteocyte viability to maintain mechanical competence and fracture resistance of bone in elderly individuals.
Keywords: biomineralization; bone cells; lacuno-canalicular network; nanospherites; osteocytes

The Optical Kerr Effect and Quantum Optics in Fibres - Leuchs, Gerd; et al. (Progress in Optics, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.optik.1optik.theopt

Theoretical description of a method for simultaneous measurement of phase and arbitrary polarization - Kellermann, Christine; Rothau, Sergej; Lindlein, Norbert (116. Jahrestagung der DGaO, 2015)

Theoretical-experimental study of the vectorial modal properties of polarization-stable multimode grating VCSELs - Debernardi, Pierluigi; Ostermann, Johannes-Michael; Sondermann, Markus; Ackemann, Thorsten; Bava, Gian Paolo; Michalzik, Rainer (IEEE Journal of Selected Topics in Quantum Electronics, 2007)
Vertical-cavity surface-emitting lasers (VCSELs) with a monolithically integrated grating in the outcoupling aperture have proven to generate a stable and predictable polarization of the emitted light. This paper provides further insight into the polarization anisotropies of grating-controlled highly multimode VCSELs by direct experimental measurements of crucial vectorial characteristics, i.e., modal dichroism and birefringence. This is achieved by a careful analysis of linewidths and peak positions of the dominant and the suppressed polarizations of the emission spectra recorded close to threshold. These experimental results allow us for the first time to compare the observed dichroism and birefringence directly with simulations performed with a fully vectorial, three-dimensional model. Large dichroisms exceeding 30 GHz, even for higher transverse modes, were found to agree very well with the simulations. Such high dichroisms clearly indicate the excellent capability of integrated surface gratings for reliable polarization control, even under extreme operation conditions. © 2007 IEEE.
Keywords: Electromagnetic modeling; Polarization control; Semiconductor laser; Surface grating; Vertical-cavity surface-emitting laser (VCSEL)

The phase shift induced by a single atom in free space - Sondermann, Markus; Leuchs, Gerd (Journal of the European Optical Society, 2013)
In this article we theoretically study the phase shift a single atom imprints onto a coherent state light beam in free space. The calculations are performed in a semiclassical framework. The key parameters governing the interaction and thus the measurable phase shift are the solid angle from which the light is focused onto the atom and the overlap of the incident radiation with the atomic dipole radiation pattern. The analysis includes saturation effects and discusses the associated Kerr-type non-linearity of a single atom.
Keywords: Atom-photon interaction; Free space; Kerr effect; Phase shift

The photonic wheel - demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2013)

The polarization properties of a tilted polarizer - Korger, Jan; Kolb, Tobias; Banzer, Peter; Aiello, Andrea; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2013)
Polarizers are key components in optical science and technology. Thus, understanding the action of a polarizer beyond oversimplifying approximations is crucial. In this work, we study the interaction of a polarizing interface with an obliquely incident wave experimentally. To this end, a set of Mueller matrices is acquired employing a novel procedure robust against experimental imperfections. We connect our observation to a geometric model, useful to predict the effect of polarizers on complex light fields. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

The quantum properties of multimode optical amplifiers revisited - Leuchs, Gerd; et al. (Advances in Atomic Molecular and Optical Physics, 2006)
There are a number of physically different realizations of an optical amplifier and yet they all share the same fundamental quantum limit as far as their noise characteristics are concerned. We review the underlying mathematical formalism without the restriction of a minimum number of modes being involved, its physical implications and relate it to the phenomenological models for the various amplifiers. © 2006 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.thequa

Thermodynamic Control of Nanoliter Volumes of CS2 via Stimulated Brillouin Scattering - Geilen, Andreas; Popp, Alexandra; Das, Debayan; Junaid, Saher; Poulton, Christopher; Chemnitz, Mario; Marquardt, Christoph; Schmidt, M. A.; Stiller, Birgit (Optics InfoBase Conference Papers, 2022)
We present Brillouin-Mandelstam measurements of hard-to-reach, thermodynamic regimes in fully-sealed, CS2-filled liquid-core optical fibers. We investigate the Brillouin response in the positive and negative pressure regimes for isochoric and isobaric processes.
CRIS-Team Scopus Importer:2023-04-20

The role of coherence in mode bistability of gas laser in inhomogenous medium - Leuchs, Gerd; et al. (Journal of Modern Optics, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.therol

The SkyLLH framework for IceCube point-source search - Kontrimas, Tomas; Wolf, Martin; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; et al. (Proceedings of Science, 2022)
Hypothesis tests based on unbinned log-likelihood (LLH) functions are a common technique used in multi-messenger astronomy, including IceCube’s neutrino point-source searches. We present the general Python-based tool "SkyLLH", which provides a modular framework for implementing and executing log-likelihood functions to perform data analyses with multi-messenger astronomy data. Specific SkyLLH framework features for a new and improved time-integrated IceCube point-source analysis are highlighted, including the support for kernel density estimation (KDE) based probability density functions. In addition, the support for a variety of point-source analysis types, such as stacked and time-variable searches, will be presented.
CRIS-Team Scopus Importer:2024-12-16

The standard quantum limit of coherent beam combining - Müller, Christian; Sedlmeir, F.; Martynov, V. O.; Marquardt, Christoph; Andrianov, A. V.; Leuchs, Gerd (New Journal of Physics, 2019)
Coherent beam combining refers to the process of generating a bright output beam by merging independent input beams of individually diffusing relative phases by locking them to each other. We report the first quantum mechanical noise limit calculations for coherent beam combining and compare our results to quantum-limited amplification. Our coherent beam combining scheme is based on an optical Fourier transformation which renders the scheme compatible with integrated optics combined with feed-back stabilization of the relative phases. The scheme can belayed out for an arbitrary number of input beams and approaches the shot noise limit for a large number of inputs.
CRIS-Team WoS Importer:2019-10-15

The Wavelength-Shifting Optical Module in Application to the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The Wavelength-shifting Optical Module (WOM) is a novel photosensor concept developed as part of the upcoming Upgrade for the IceCube Neutrino Observatory. It uses the technique of wavelength shifting and total internal reflection to increase the photon light yield in the UV-regime of the Cherenkov spectrum. The decoupling of the effective area from the size of light sensors enhances the signal-to-noise-ratio. Twelve WOM modules will be deployed in the IceCube Upgrade to increase the photon detection efficiency and thus enhance future low-energy analyses. The general concept can also be applied at the future IceCube-Gen2 detector, where passive light collecting extensions to the optical sensor modules locally increase the light collection efficiency. This technique would benefit the detection of supernova neutrinos or other particles with low light emissions. We report on new results in characterizing and optimizing the WOM concept, the production status of the modules to be deployed in 2025/26 as well as possible applications of the concept for IceCube-Gen2.
CRIS-Team Scopus Importer:2025-02-04

The Wigner flow on the sphere - Yang, Popo; Valtierra, Ivan F.; Klimov, Andrei B.; Wu, Shin-Tza; Lee, Ray-Kuang; Sanchez-Soto, Luis L.; Leuchs, Gerd (Physica Scripta, 2019)
We derive a continuity equation for the evolution of the SU(2) Wigner function under nonlinear Kerr evolution. We give explicit expressions for the resulting quantum Wigner current, and discuss the appearance of the classical limit. We show that the global structure of the quantum current significantly differs from the classical one, which is clearly reflected in the form of the corresponding stagnation lines.
CRIS-Team Scopus Importer:2019-05-07
Keywords: phase space; Wigner flow; Wigner function

Thio-oxalic Acid 2-Amide-1-hydrazide-2-hydrazone - Heinemann, Frank Wilhelm; Hartung, H; Dehne, Henry; Scheunemann, A. (Acta crystallographica. Section C, Crystal structure communications, 1995)

Three-dimensional photonic crystals with an active surface: Gold film terminated opals - Ding, Boyang; Pemble, Martyn E.; Korovin, Alexander V.; Peschel, Ulf; Romanov, Sergey (Physical Review B, 2010)
A hybrid metal-dielectric photonic crystal, a thin opal slab coated by a gold film, has been designed in order to exercise additional control upon the light propagation in a photonic band-gap material using extraordinary optical transmission in the corrugated gold film. The photonic and plasmonic components of the hybrid crystal are closely linked, because the photonic crystal lattice provides a spatial template for the gold film corrugation and modifies the electromagnetic vacuum in the vicinity of the gold film. Due to coupling of light diffracted in the opal lattice to surface plasmon polaritons in the metal film, the spectra and angle diagrams of transmission in hybrid structures deviate from the linear superposition of transmission functions of both hybrid components. In particular, the selective conversion of diffraction minima, and cavity mode and thickness dependence of the surface plasmon polariton-related properties have been observed. The synergy of three resonance mechanisms behind the functionality of hybrid photonic crystals provides a uniquely broad tunability of their optical properties.
EAM Import::2019-03-12

Three-Dimensional Sensors - Potentials and Limitations - Häusler, Gerd (Handbook of Computer Vision and Applications, Vol. 1: Sensors and Imaging, 1999)
UnivIS-Import:2015-04-20:Pub.1999.nat.dphy.optik.1optik.threed

Three-Dimensional Simulations of Optical Multimode Waveguides - Backhaus, Carsten; Loosen, Florian; Lindlein, Norbert (Springer International Publishing, 2022)
The waveguides fabricated in the project OPTAVER have a special shape with a circle segment cross section and are highly multimode due to the large extension of about 300 µm in diameter and about 40 µm in height. Therefore, specially adapted simulation methods have been developed. On the one side, due to the highly multimode nature, ray tracing can be used. Here, a quite efficient bisection algorithm has been investigated for the calculation of the intersection points with an arbitrarily curved waveguide during the propagation of light along its axis. On the other side, interference and diffraction effects can only be modeled by a wave-optical simulation. Here, the wave propagation method (WPM) is used which is also quite efficient compared to beam propagation methods. Especially, for a waveguide coupler (see chap. 6), this method gives more accurate results as a ray tracing simulation.
CRIS-Team Scopus Importer:2024-12-16

Three-year performance of the IceAct telescopes at the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
IceAct is an array of compact Imaging Air Cherenkov Telescopes at the ice surface as part of the IceCube Neutrino Observatory. The telescopes, featuring a camera of 61 silicon photomultipliers and fresnel-lens-based optics, are optimized to be operated in harsh environmental conditions, such as at the South Pole. Since 2019, the first two telescopes have been operating in a stereoscopic configuration in the center of IceCube’s surface detector IceTop. With an energy threshold of about 10 TeV and a wide field-of-view, the IceAct telescopes show promising capabilities of improving current cosmic-ray composition studies: measuring the Cherenkov light emissions in the atmosphere adds new information about the shower development not accessible with the current detectors. First simulations indicate that the added information of a single telescope leads, e.g., to an improved discrimination between flux contributions from different primary particle species in the sensitive energy range. We review the performance and detector operations of the telescopes during the past 3 years (2020-2022) and give an outlook on the future of IceAct.
CRIS-Team Scopus Importer:2025-02-04

Time evolution of a quantum soliton in a Kerr medium - Leuchs, Gerd; et al. (Journal of Modern Optics, 2001)
The Q-function of the quantum soliton in a fibre is derived in a new form suitable for the assessment of the possibilities for experimental observations of specific quantum-soliton effects. The characteristic effects of soliton evolution are associated with a cubic term in the nonlinear phase angle and appear at distances well beyond the attenuation length (long range). At the accessible distances, the nonlinear dynamics of a fundamental soliton follows essentially the single-mode dynamics (short and middle range). However, for the higher-order solitons, the form of the evolution parameter suggests strong deviations of soliton dynamics from the single-mode with a square of soliton number. The use of enhanced-nonlinearity fibres and higher-order solitons might make the experimental studies of the specific quantum-soliton features more viable.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.quatim

Time-frequency multiplexed single-photon source based on LiNbO3 modulators - Massaro, Marcello; Ansari, Vahid; Schlue, Fabian; Luo, Kai Hong; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine; Dirmeier, Thomas; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2020)
We present advances in the use of gigahertz LiNbO3 modulators enabling us programmable delays, which we will use to implement a multiplexed single-photon source, based on birefringent phase-matching in KTP waveguides.
CRIS-Team Scopus Importer:2020-11-13

Time-reversal symmetry in optics - Leuchs, Gerd; Sondermann, Markus (Physica Scripta, 2012)
The utilization of time-reversal symmetry in designing and implementing (quantum) optical experiments has become more and more frequent over the last few years. We review the basic idea underlying time-reversal methods, illustrate it with several examples and discuss a number of implications. © 2012 The Royal Swedish Academy of Sciences.

T-matrix analysis of dipole waves on chains of dielectric particles - Zhuromskyy, Oleksandr; Peschel, Ulf (7th International Congress on Advanced Electromagnetic Materials in Microwaves and Optics, 2013)
Loss less propagation of longitudinal magnetic-dipole waves is predicted for regular chains of rutile particles. Rigorous T-matrix simulation techniques are applied to deduce the dispersion characteristics of the dipole waves and to optimize the properties of the closing elements in the waveguide for maximum power transmission. The proposed technique can be used to optimize the interaction between light and particle ensembles.
EAM Import::2019-03-13

Tomography and Correlation Function Measurements of Itinerant Microwave Photons - Eichler, Christopher; et al. (Moriond 2011 - Quantum Mesoscopic Physics, 2011)
Keywords: wwwqudev

Tomography and Correlation Function Measurements of Itinerant Microwave Photons - Eichler, Christopher; et al. (2011)
Keywords: wwwqudev

Topology-dependent light transport in planar plasmonic-photonic architectures - Tuzakli, Refik; Vogel, Nicolas; Romanova, Alexandra; Romanov, Sergei G.; Peschel, Ulf (European Conference on Lasers and Electro-Optics, CLEO 2015, 2014)

Toward a Corrected Knife-Edge-Based Reconstruction of Tightly Focused Higher Order Beams - Orlov, Sergej; Huber, Christian; Marchenko, Pavel; Banzer, Peter; Leuchs, Gerd (Frontiers in Physics, 2020)
The knife-edge method is an established technique for profiling of even tightly focused light beams. However, the straightforward implementation of this method fails if the materials and geometry of the knife-edges are not chosen carefully or, in particular, if knife-edges are used that are made of pure materials. Artifacts are introduced in these cases in the shape and position of the reconstructed beam profile due to the interaction of the light beam under study with the knife. Hence, corrections to the standard knife-edge evaluation method are required. Here we investigate the knife-edge method for highly focused radially and azimuthally polarized beams and their linearly polarized constituents. We introduce relative shifts for those constituents and report on the consistency with the case of a linearly polarized fundamental Gaussian beam. An adapted knife-edge reconstruction technique is presented and proof-of-concept tests are shown, demonstrating the reconstruction of beam profiles.
CRIS-Team WoS Importer:2021-01-22

Toward High-Speed Nanoscopic Particle Tracking via Time-Resolved Detection of Directional Scattering - Beck, Paul; Neugebauer, Martin; Banzer, Peter (Laser & Photonics Reviews, 2020)
Owing to their immediate relevance for high precision position sensors, a variety of different sub-wavelength localization techniques has been developed in the past decades. However, many of these techniques suffer from low temporal resolution or require expensive detectors. Here, a method is presented that is based on the ultrafast detection of directionally scattered light with a quadrant photodetector operating at a large bandwidth, which exceeds the speed of most cameras. The directionality emerges due to the position dependent tailored excitation of a high-refractive index nanoparticle with a tightly focused vector beam. A spatial resolution of (Formula presented.) and a temporal resolution of (Formula presented.) is reached experimentally, which is not a fundamental but rather a technical limit. The detection scheme enables real-time particle tracking and sample stabilization in many optical setups sensitive to drifts and vibrations.
CRIS-Team Scopus Importer:2020-08-14
Keywords: directional scattering; tight focusing; ultrafast nanolocalization; vector beams

Towards Error-Corrected Quantum Computing with Superconducting Circuits - Eichler, Christopher (WE-Heraeus-Symposium: Recent Progress in Quantum Computing, 2022)
Keywords: wwwquantum

Towards fully integrated photonic displacement sensors - Bag, Ankan; Neugebauer, Martin; Mick, Uwe; Christiansen, Silke; Schulz, Sebastian A.; Banzer, Peter (Nature Communications, 2020)
The field of optical metrology with its high precision position, rotation and wavefront sensors represents the basis for lithography and high resolution microscopy. However, the on-chip integration—a task highly relevant for future nanotechnological devices—necessitates the reduction of the spatial footprint of sensing schemes by the deployment of novel concepts. A promising route towards this goal is predicated on the controllable directional emission of the fundamentally smallest emitters of light, i.e., dipoles, as an indicator. Here we realize an integrated displacement sensor based on the directional emission of Huygens dipoles excited in an individual dipolar antenna. The position of the antenna relative to the excitation field determines its directional coupling into a six-way crossing of photonic crystal waveguides. In our experimental study supported by theoretical calculations, we demonstrate the first prototype of an integrated displacement sensor with a standard deviation of the position accuracy below λ/300 at room temperature and ambient conditions.
CRIS-Team Scopus Importer:2020-06-16

Towards polarization-based excitation tailoring for extended Raman spectroscopy - Grosche, Simon; Hünermann, Richard; Sarau, George; Christiansen, Silke; Boyd, Robert W.; Leuchs, Gerd; Banzer, Peter (Optics Express, 2020)
Undoubtedly, Raman spectroscopy is one of the most elaborate spectroscopy tools in materials science, chemistry, medicine and optics. However, when it comes to the analysis of nanostructured specimens or individual sub-wavelength-sized systems, the access to Raman spectra resulting from different excitation schemes is usually very limited. For instance, the excitation with an electric field component oriented perpendicularly to the substrate plane is a difficult task. Conventionally, this can only be achieved by mechanically tilting the sample or by sophisticated sample preparation. Here, we propose a novel experimental method based on the utilization of polarization tailored light for Raman spectroscopy of individual nanostructures. As a proof of principle, we create three-dimensional electromagnetic field distributions at the nanoscale using tightly focused cylindrical vector beams impinging normally onto the specimen, hence keeping the traditional beam-path of commercial Raman systems. In order to demonstrate the convenience of this excitation scheme, we use a sub-wavelength diameter gallium-nitride nanostructure as a test platform and show experimentally that its Raman spectra depend sensitively on its location relative to the focal vector field. The observed Raman spectra can be attributed to the interaction with transverse and pure longitudinal electric field components. This novel technique may pave the way towards a characterization of Raman active nanosystems, granting direct access to growth-related parameters such as strain or defects in the material by using the full information of all Raman mode

Towards Quantum Noise Squeezing for 2-Micron Light with Tellurite and Chalcogenide Fibers with Large Kerr Nonlinearity - Sorokin, Arseny A.; Leuchs, Gerd; Corney, Joel F.; Kalinin, Nikolay A.; Anashkina, Elena A.; Andrianov, Alexey (Mathematics, 2022)
Squeezed light—nonclassical multiphoton states with fluctuations in one of the quadrature field components below the vacuum level—has found applications in quantum light spectroscopy, quantum telecommunications, quantum computing, precision quantum metrology, detecting gravitational waves, and biological measurements. At present, quantum noise squeezing with optical fiber systems operating in the range near 1.5 μm has been mastered relatively well, but there are no fiber sources of nonclassical squeezed light beyond this range. Silica fibers are not suitable for strong noise suppression for 2 µm continuous-wave (CW) light since their losses dramatically deteriorate the squeezed state of required lengths longer than 100 m. We propose the generation multiphoton states of 2-micron 10-W class CW light with squeezed quantum fluctuations stronger than −15 dB in chalcogenide and tellurite soft glass fibers with large Kerr nonlinearities. Using a realistic theoretical model, we numerically study squeezing for 2-micron light in step-index soft glass fibers by taking into account Kerr nonlinearity, distributed losses, and inelastic light scattering processes. Quantum noise squeezing stronger than −20 dB is numerically attained for a customized As2Se3 fibers with realistic parameters for the optimal fiber lengths shorter than 1 m. For commercial As2S3 and customized tellurite glass fibers, the expected squeezing in the −20–−15 dB range can be reached for fiber lengths of the order of 1 m.
CRIS-Team Scopus Importer:2022-10-28
Keywords: chalcogenide fibers; Kerr nonlinearity; quantum noise squeezing; stochastic nonlinear Schrödinger equation; tellurite fibers

Transverse Angular Momentum and Geometric Spin Hall Effect of Light - Aiello, Andrea; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2009)
We present a novel fundamental phenomenon occurring when a polarized beam of light is observed from a reference frame tilted with respect to the direction of propagation of the beam. This effect has a purely geometric nature and amounts to a polarization-dependent shift or split of the beam intensity distribution evaluated as the time-averaged flux of the Poynting vector across the plane of observation. We demonstrate that such a shift is unavoidable whenever the beam possesses a nonzero transverse angular momentum. This latter result has general validity and applies to arbitrary systems such as, e.g., electronic and atomic beams. © 2009 The American Physical Societ
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.transv

Transverse angular momentum of photons - Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2010)
We develop the quantum theory of transverse angular momentum of light beams. The theory applies to paraxial and quasiparaxial photon beams in vacuum and reproduces the known results for classical beams when applied to coherent states of the field. Both the Poynting vector, alias the linear momentum, and the angular-momentum quantum operators of a light beam are calculated including contributions from first-order transverse derivatives. This permits a correct description of the energy flow in the beam and the natural emergence of both the spin and the angular momentum of the photons. We show that for collimated beams of light, orbital angular-momentum operators do not satisfy the standard commutation rules. Finally, we discuss the application of our theory to some concrete cases. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Transverse spinning of unpolarized light - Eismann, Jörg; Nicholls, L. H.; Roth, D. J.; Alonso, M. A.; Banzer, Peter; Rodriguez-Fortuno, F. J.; Zayats, A.; Nori, Franco; Bliokh, K. Y. (Nature Photonics, 2020)
It is well known that the spin angular momentum of light, and therefore that of photons, is directly related to their circular polarization. Naturally, for totally unpolarized light, polarization is undefined and the spin vanishes. However, for non-paraxial light, the recently discovered transverse spin component, orthogonal to the main propagation direction, is largely independent of the polarization state of the wave. Here, we demonstrate, both theoretically and experimentally, that this transverse spin survives even in non-paraxial fields (for example, focused or evanescent) generated from totally unpolarized paraxial light. This counterintuitive phenomenon is closely related to the fundamental difference between the meanings of 'full depolarization' for two-dimensional (2D) paraxial and 3D non-paraxial fields. Our results open an avenue for studies of spin-related phenomena and optical manipulation using unpolarized light.
CRIS-Team WoS Importer:2021-01-15

Trojan-horse attacks threaten the security of practical quantum cryptography - Jain, Nitin; Anisimova, Elena; Khan, Imran; Makarov, Vadim; Marquardt, Christoph; Leuchs, Gerd (New Journal of Physics, 2014)
A quantum key distribution (QKD) system may be probed by an eavesdropper Eve by sending in bright light from the quantum channel and analyzing the back-reflections. We propose and experimentally demonstrate a setup for mounting such a Trojan-horse attack. We show it in operation against the quantum cryptosystem Clavis2 from ID Quantique, as a proof-of-principle. With just a few back-reflected photons, Eve discerns Bob's (secret) basis choice, and thus the raw key bit in the Scarani-Acín-Ribordy-Gisin 2004 protocol, with higher than 90% probability. This would clearly breach the security of the cryptosystem. Unfortunately, Eve's bright pulses have a side effect of causing a high level of afterpulsing in Bob's single-photon detectors, resulting in a large quantum bit error rate that effectively protects this system from our attack. However, in a Clavis2-like system equipped with detectors with less-noisy but realistic characteristics, an attack strategy with positive leakage of the key would exist. We confirm this by a numerical simulation. Both the eavesdropping setup and strategy can be generalized to attack most of the current QKD systems, especially if they lack proper safeguards. We also propose countermeasures to prevent such attacks.
CRIS-Team Scopus Importer:2022-06-05
Keywords: quantum cryptography; quantum hacking; quantum key distribution; reflectometry; security proofs; Trojan horse

Tunable coupler to fully decouple and maximally localize superconducting qubits - Heunisch, Lukas; Eichler, Christopher; Hartmann, Michael (Physical Review Applied, 2023)
Enhancing the capabilities of superconducting quantum hardware, requires higher gate fidelities and lower crosstalk, particularly in larger-scale devices, in which qubits are coupled to multiple neighbors. Progress towards both of these objectives would highly benefit from the ability to fully control all interactions between pairs of qubits. Here we propose an alternative coupler model that allows dispersively detuned transmon qubits to be fully decoupled from each other, i.e., ZZ crosstalk is completely suppressed while maintaining a maximal localization of the qubits' computational basis states. We further reason that, for a dispersively detuned transmon system, this can only be the case if the anharmonicity of the coupler is positive at the idling point. A simulation of a 40-ns CZ gate for a lumped-element model suggests that achievable process infidelity can be pushed below the limit imposed by state-of-the-art coherence times of transmon qubits. On the other hand, idle gates between qubits are no longer limited by parasitic interactions. We show that our scheme can be applied to large integrated qubit grids, where it allows a pair of qubits to be fully isolated, that undergoes a gate operation, from the rest of the chip while simultaneously pushing the fidelity of gates to the limit set by the coherence time of the individual qubits.
CRIS-Team Scopus Importer:2024-12-16

Tuning the chirality of a dipole moment in an achiral particle with structured light - Eismann, Jörg; Neugebauer, Martin; Banzer, Peter (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
In the last decade, the attention drawn towards electric and magnetic dipole moments induced in optical nanoantennas significantly increased because of their numerous potential applications. For example, certain combinations of electric and magnetic dipoles allow for controlling the polarization state and propagation direction of light at the nanoscale [1,2]. The underlying effects rely on specific orientations and phase relations between the individual electric and magnetic dipole moments. In a recent work [3] we presented a new addition to the toolbox of experimental nanophotonics, the so-called σ-dipole, consisting of parallel electric and magnetic dipole moments phase shifted by ±π/2. The name originates from its well-defined near- and far-field helicity of ±1 [4]. Utilizing a combination of in-phase radially and azimuthally polarized beams, tightly focused onto a silicon nanoparticle, a well-defined and controllable superposition of both σ-dipoles can be realized.
CRIS-Team Scopus Importer:2019-11-15

Tuning the Optical and Geometrical Properties of Hybrid Carbon Flakes by Fabrication Parameters - Butt, Muhammad; Mamonova, Daria; Manshina, Alina A.; Banzer, Peter; Leuchs, Gerd (Optics InfoBase Conference Papers, 2020)
We investigate the effects of fabrication parameters on the properties of a selfassembled crystalline carbon-metal hybrid. We show that attenuation and geometrical parameters can be tuned, while high birefringence is observed for all studied cases.
CRIS-Team Scopus Importer:2020-11-13

Über die kluge Auswahl und Anwendung optischer 3D-Sensoren - Häusler, Gerd; et al. (Photonik, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.berdie

Ubiquitous coherence - boon and bale of the optical metrologist - Häusler, Gerd (Proceedings of SPIE, 2003)
Commonly, optical systems are called coherent, if a laser is used (right), and incoherent if other sources come into play (wrong). Most opticists are not aware that parasitic spatial coherence is ubiquitous, even if it is unobvious. The pretended incoherent approach may lead to significant quantitative measuring errors of illumination or reflectivity, 3d shape, size or distance. On the other hand, a favourable property of spatial coherence is that among the "speckle noise" we may reveal useful information about the object, by white light interferometry. This report will discuss simple rules to estimate the occuring errors and how to reduce spatial coherence. We will further discuss the complex signal formation in white light interferometry and roughness measurements far beyond the bandwidth limit of the observing optics.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.ubiqui
Keywords: Coherence; Coherence radar; Measuring uncertainty; Roughness measurement; Speckle; Speckle noise; Superresolution; White light interferometry

Ultrafast spinning twisted ribbons of confined electric fields - Bauer, Thomas; Khonina, Svetlana N.; Golub, Ilya; Leuchs, Gerd; Banzer, Peter (Optica, 2020)
Topological properties of light attract tremendous attention in the optics communities and beyond. For instance, light beams gain robustness against certain deformations when carrying topological features, enabling intriguing applications. We report on the observation of a topological structure contained in an optical beam, i.e., a twisted ribbon formed by the electric field vector per se, in stark contrast to recently reported studies dealing with topological structures based on the distribution of the time averaged polarization ellipse. Moreover, our ribbons are spinning in time at a frequency given by the optical frequency divided by the total angular momentum of the incoming beam. The number of full twists of the ribbon is equal to the orbital angular momentum of the longitudinal component of the employed light beam upon tight focusing, which is a direct consequence of spin-to-orbit coupling. We study this angular-momentum-transfer-assisted generation of the twisted ribbon structures theoretically and experimentally for tightly focused circularly polarized beams of different vorticity, paving the way to tailored topologically robust excitations of novel coherent light-matter states.
CRIS-Team Scopus Importer:2020-10-23

Ultra-short laser surface properties optimization of biocompatibility characteristics of 3d poly-ε-caprolactone and hydroxyapatite composite scaffolds - Daskalova, Albena; Filipov, Emil; Angelova, Liliya; Stefanov, Radostin; Tatchev, Dragomir; Avdeev, Georgi; Sotelo, Lamborghini; Christiansen, Silke; Sarau, George; Leuchs, Gerd; Iordanova, Ekaterina; Buchvarov, Ivan (Materials, 2021)
The use of laser processing for the creation of diverse morphological patterns onto the surface of polymer scaffolds represents a method for overcoming bacterial biofilm formation and inducing enhanced cellular dynamics. We have investigated the influence of ultra-short laser pa-rameters on 3D-printed poly-ε-caprolactone (PCL) and poly-ε-caprolactone/hydroxyapatite (PCL/HA) scaffolds with the aim of creating submicron geometrical features to improve the matrix biocompatibility properties. Specifically, the present research was focused on monitoring the effect of the laser fluence (F) and the number of applied pulses (N) on the morphological, chemical and mechanical properties of the scaffolds. SEM analysis revealed that the femtosecond laser treatment of the scaffolds led to the formation of two distinct surface geometrical patterns, microchannels and single microprotrusions, without triggering collateral damage to the surrounding zones. We found that the microchannel structures favor the hydrophilicity properties. As demonstrated by the com-puter tomography results, surface roughness of the modified zones increases compared to the non-modified surface, without influencing the mechanical stability of the 3D matrices. The X-ray diffraction analysis confirmed that the laser structuring of the matrices did not lead to a change in the semi-crystalline phase of the PCL. The combinations of two types of geometrical designs—wood pile and snowflake—with laser-induced morphologies in the form of channels and columns are considered for optimizing the conditions for establishing an ideal scaffold, namely, precise dimensional form, mechanical stability, improved cytocompatibility and antibacterial behavior.
CRIS-Team Scopus Importer:2021-12-31
Keywords: Antibacterial structuring; Biodegradable polymers; Bone tissue engineering; Surface patterns; Ultra-short laser processing

Unconditional quantum cloning of coherent states with linear optics - Leuchs, Gerd; et al. (Physical Review Letters, 2005)
A scheme for optimal Gaussian cloning of optical coherent states is proposed and experimentally demonstrated. Its optical realization is based entirely on simple linear optical elements and homodyne detection. The optimality of the presented scheme is limited only by detection inefficiencies. Experimentally, we achieved a cloning fidelity of about 65%, which almost touches the optimal value of 2/3. © 2005 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.uncond

Understanding GaN/InGaN core-shell growth towards high quality factor whispering gallery modes from non-polar InGaN quantum wells on GaN rods. - Tessarek, Christian; Rechberger, Stefanie; Dieker, Christel; Heilmann, Martin; Spiecker, Erdmann; Christiansen, S. H. (Nanotechnology, 2017)
GaN microrods are used as a basis for subsequent InGaN quantum well (QW) and quantum dot deposition by metal-organic vapor phase epitaxy. The coverage of the shell along the sidewall of rods is dependent on the rod growth time and a complete coverage is obtained for shorter rod growth times. Transmission electron microscopy measurements are performed to reveal the structural properties of the InGaN layer on the sidewall facet and on the top facet. The presence of layers in the microrod and on the microrod surface will be discussed with respect to GaN and InGaN growth. A detailed model will be presented explaining the formation of multiple SiN layers and the partial and full coverage of the shell around the core. Cathodoluminescence measurements are performed to analyze the InGaN emission properties along the microrod and to study the microresonator properties of such hexagonal core-shell structures. High quality factor whispering gallery modes with [Formula: see text] are reported for the first time in a GaN microrod/InGaN non-polar QW core-shell geometry. The GaN/InGaN core-shell microrods are expected to be promising building blocks for low-threshold laser diodes and ultra-sensitive optical sensors.
Keywords: GaN; InGaN; SiN; rods; core–shell; quantum wells; whispering gallery modes

Universal optical amplification without nonlinearity - Leuchs, Gerd; et al. (Physical Review Letters, 2006)
We propose and realize a novel universal phase insensitive optical amplifier operating at the quantum limit in the low gain regime. The amplifier consists only of linear optics and detectors thus circumventing a nonlinear interaction. © 2006 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.univer

Universelles wellenoptisches Phasenprüfgerät - Lindlein, Norbert; et al. (FORMIKROSYS-Sonderteil von F&M, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dphy.optik.1optik.univer

Untersuchung der Abweichungen zwischen skalarer und rigoroser Rechnung an CGHs in Twyman-Green-Interferometern zur Linsenprüfung - Iff, Wolfgang; Glaubrecht, Stefan; Lindlein, Norbert; Schwider, Johannes (DGaO Proceedings 2010 – http://www.dgao-proceedings.de – ISSN: 1614-8436, 2010)

Untersuchungen zum Stofftransport ausgewählter Substanzen in überkritischem Kohlendioxid mittels Shearing-Intereferometrie - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Bielke, Thorsten; Delgado, Antonio; Neukam, Johannes; Nercissian, Vanusch; Berger, Andreas (Proceedings der 19. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.ITC.stmmec.unters

Untersuchung von Phasensingularitäten in der Umgebung kleiner Strukturen mit einem Linnik-Interferenzmikroskop - Leuchs, Gerd; et al. (Technisches Messen, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.unters

Untreated ´blow-in´ fracture of the orbital floor causing a mucocele: report of an unusual late complication - Nkenke, Emeka; Häusler, Gerd; et al. (Journal of Cranio-Maxillofacial Surgery, 2005)
Background: Several severe complications have been described with blow-in fractures. Therefore, immediate surgical treatment of these fractures has been recommended. To date, there is only minimal knowledge on long-term complications of blow-in fractures that have remained untreated. The present case report describes a late complication of an untreated blow-in fracture of the orbital floor. Case: A 37-year-old male was involved in a car accident 16 years before. At that time, a non-dislocated midfacial fracture was diagnosed and remained untreated because of the lack of clinical symptoms. Four months before surgery an exophthalmos of the left globe began to develop. CT examination revealed a consolidated blow-in fracture of the left orbital floor and an opaque mass around the dislocated bony fragments. By an infraorbital approach the bony fragments and the surrounding mass were removed. Histological examination of the removed material revealed a cystic structure lined with respiratory epithelium. Therefore, the diagnosis 'post-traumatic mucocele in the orbit caused by dislocated respiratory epithelium from the maxillary sinus' was made. Conclusion: Even if blow-in fractures do not cause complications immediately after trauma, late complications like mucoceles can occur after several symptom-free years. Therefore, early reconstruction should be intended even in asymptomatic cases of blow-in fractures with minimal displacement of the bony fragments. © 2005 European Association for Cranio-Maxillofacial Surgery.
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.untrea
Keywords: Alloplastic reconstruction of the orbital floor; Blow-in fracture; Exophthalmos; Mucocele; Untreated orbital floor fracture

Use of Fiber Nonlinearities for Signal Improvement in Optical Transmission Systems - Schmauß, Bernhard; Holtmannspötter, Michael; Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Leuchs, Gerd (Frequenz, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.useoff

Using a quantum well heterostructure to study the longitudinal and transverse electric field components of a strongly focused laser beam - Malzer, Stefan; Leuchs, Gerd; et al. (Journal of Applied Physics, 2006)
We report a method to measure the electric energy density of longitudinal and transverse electric field components of strongly focused polarized laser beams. We used a quantum well photodetector and exploited the polarization dependent optical transitions of light holes and heavy holes to probe the electric field distribution in the focal region. A comparison of the measured photocurrent spectra for radially and azimuthally polarized beams at the light and heavy hole absorption peaks provides a measure of the amount of the longitudinal electric field component. © 2006 American Institute of Physics.

Using saturation effects in a nonlinear amplifying loop mirror for multilevel phase-preserving amplitude regeneration - Roethlingshoefer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2011 13th International Conference on, 2011)
The influence of amplifier gain saturation in nonlinear amplifying loop mirror on simultaneous phase-preserving regeneration of two power states has been studied. Numeri cal simulations have shown an improvement of up to 4 dB for the first, low-power state and 8 dB for the se cond high-power state. Compar ed to the linear amplifier case an improvement of 3 dB for the se cond power state has been achieved.
lhft_intern.bib::Roethlingshoefer2011a
Keywords: 2R regeneration; quadrature amplitude modulation; NALM; NOLM

Using Supercritical Carbon Dioxide for Physical Foaming of Advanced Polymer Materials - Wolff, Friederich; Zirkel, Larissa; Sarah, Betzold; Jakob, Matthias; Verena, Maier; Nachtrab, Frank; Ceron Nicolat, Bruno; Fey, Tobias; Münstädt, Helmut (International Polymer Processing, 2011)
Foams from high performance polymers find more and more interest. The processes to generate them can be difficult, however. It is shown how physical foaming with CO2 can be used as a first step to assess the potentials of such materials. For investigations of such kind an autoclave on a laboratory scale which allows pressure variations up to 300 bars and temperatures up to 300 degrees C was set up. The samples are saturated with supercritical carbon dioxide (s.c. CO2) which acts as a foaming agent. Depending on the process and material parameters different foam characteristics and cell morphologies were obtained and characterised. The potential of this method is demonstrated for two different classes of advanced polymer materials, thermoplastic fluoropolymers (PEP), and a silicone resin. In the case of the fluoropolymer, previously prepared films were foamed and the effects of various process parameters on the foam characteristics were investigated. Besides the general potential of foams from fluoropolymers, they are candidates for polymeric piezoelectric materials with a relatively high temperature stability. Silicone polymers possess some properties superior to common organic polymers. First results on the foaming behaviour of a silicone resin are presented.

Vectorial vortex generation and phase singularities upon Brewster reflection - Barczyk, Rend; Nechayev, Sergey; Butt, Muhammad Abdullah; Leuchs, Gerd; Banzer, Peter (Physical Review A, 2019)
We experimentally demonstrate the emergence of an azimuthally polarized vectorial vortex beam with a phase singularity upon Brewster reflection of focused circularly polarized light from a dielectric substrate. The effect originates from the polarizing properties of the Fresnel reflection coefficients described in Brewster's law. An astonishing consequence of this effect is that the reflected field's Cartesian components acquire local phase singularities at Brewster's angle. Our observations are crucial for polarization microscopy and open avenues for the generation of exotic states of light based on spin-to-orbit coupling, without the need for sophisticated optical elements.
CRIS-Team WoS Importer:2019-07-02
Keywords: Angular momentum of light; Classical optics; Geometrical & wave optics; Imaging & optical processing; Light propagation; transmission & absorption; Optical vortices; Optics & lasers; Polarization of light

Verifying continuous variable entanglement of intense light pulses - Leuchs, Gerd; et al. (Physical Review A, 2006)
Three different methods have been discussed to verify continuous variable entanglement of intense light beams. We demonstrate all three methods using the same setup to facilitate the comparison. The nonlinearity used to generate entanglement is the Kerr effect in optical fibers. Due to the brightness of the entangled pulses, standard homodyne detection is not an appropriate tool for the verification. However, we show that by using large asymmetric interferometers on each beam individually, two noncommuting variables can be accessed and the presence of entanglement verified via joint measurements on the two beams. Alternatively, we witness entanglement by combining the two beams on a beam splitter that yields certain linear combinations of quadrature amplitudes which suffice to prove the presence of entanglement. © 2006 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.verify

Vertically Oriented Growth of GaN Nanorods on Si Using Graphene as an Atomically Thin Buffer Layer - Heilmann, Martin; Munshi, A. Mazid; Sarau, George; Göbelt, Manuela; Tessarek, Christian; Fauske, Vidar T.; van Helvoort, Antonius T. J.; Yang, Jianfeng; Latzel, Michael; Hoffmann, Bjoern; Conibeer, Gavin; Weman, Helge; et al. (Nano Letters, 2016)
The monolithic integration of wurtzite GaN on Si via metal-organic vapor phase epitaxy is strongly hampered by lattice and thermal mismatch as well as meltback etching. This study presents single-layer graphene as an atomically thin buffer layer for c-axis-oriented growth of vertically aligned GaN nanorods mediated by nanometer-sized AlGaN nucleation islands. Nanostructures of similar morphology are demonstrated on graphene-covered Si(111) as well as Si(100). High crystal and optical quality of the nanorods are evidenced through scanning transmission electron microscopy, micro-Raman, and cathodoluminescence measurements supported by finite-difference time-domain simulations. Current-voltage characteristics revealed high vertical conduction of the as-grown GaN nanorods through the Si substrates. These findings are substantial to advance the integration of GaN-based devices on any substrates of choice that sustains the GaN growth temperatures, thereby permitting novel designs of GaN-based heterojunction device concepts.
Keywords: GaN; GaN-on-Si; graphene; MOVPE; nanorods

Visualization and Detection of Small Defects on Car-Bodies - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visualization '99, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.visual

Wave aberration measurement using microlens arrays - Lindlein, Norbert; et al. (EOS Topical Meetings DigestSeries, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.waveab

Wave-front reconstruction with a Shack-Hartmann sensor with an iterative spline fitting method - Lindlein, Norbert; et al. (Applied Optics, 2000)
One limitation of the conventional Shack-Hartmann sensor is that the spots of each microlens have to remain in their respective subapertures. We present an algorithm that assigns the spots to their reference points unequivocally even if they are situated far outside their subaperture. For this assignment a spline function is extrapolated in successive steps of the iterative algorithm. The proposed method works in a single-shot technique and does not need any aid from mechanical devices. The reconstruction of a simulated steep aspherical wave front (∼100lλ/mm slope) is described as well as experimental results of the measurement of a spherical wave front with a huge peak-to-valley value (∼400l). The performance of the method is compared with the unwrapping method, which has been published before. © 2000 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.wavefr

Waveguide properties of single subwavelength holes demonstrated with radially and azimuthally polarized light - Banzer, Peter; Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 2007)
We investigate the transmission of focused beams through single subwavelength holes in a silver film. We use radially and azimuthally polarized light to excite higher-order waveguide modes as well as to match the radial symmetry of the aperture geometry. Remarkably, the transmission properties can be described by a classical waveguide model even for thicknesses of the silver film as thin as a quarter of a wavelength. © 2007 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.wavegu

Wavelength mismatch correcting elements for volume holograms written on a laser pattern generator - Lindlein, Norbert; et al. (Journal of Modern Optics, 1993)
Holographic optical lenses based on volume gratings commonly suffer from severe aberrations due to wavelength mismatch between recording (blue-sensitive material) and application (often employing diode lasers). Here, methods are described for the precompensation of the aberrations at the recording. Both, aberrations in the phase of the reconstructed wave from the desired wave ('wave aberration'), as well as aberrations in intensity resulting from deviations from the Bragg condition during reconstruction ('Bragg aberration') need to be compensated for. The design method for generating the computer generated holograms is described which are used as precompensating elements in the recording step of the interferometrically produced holographic optical elements. The computer generated holograms are written on a laser pattern generator. Test results of our laser pattern generator are shown to demonstrate its capability for this process. The measurement of the aberrations at the design wavelength in the near infrared is a very important step because it allows to eliminate in a second recording process misadjustment errors which will occur during the first recording step. By modification of at least one of the computer generated holograms the convergence of the procedure can be achieved. © 1993 Taylor & Francis Ltd.

Wave-optical simulation of a grating lateral shearing interferometer with a periodic incoherent light source - Lindlein, Norbert; et al. (Photon Management III, 2008)
A quite simple numerical model for the wave-optical simulation of the interference in a grating lateral shearing interferometer with a periodic light source and a large lateral shear is presented. Aberrations of the collimating lens will generate a spatially varying modulation in the interference pattern. The model assumes that the light source itself is completely spatially incoherent so that only the light from each point of the light source has to be propagated wave-optically through the optical system. Then, the intensity distributions of all light source points in the detector plane can just be added. The simulations are compared to theoretical calculations of partial coherence theory and also to experimental results.
Keywords: Coherence; Grating lateral shearing interferometer; Partial coherence; Periodic light source; Shearing interferometer; Wave-optical simulation

Wave Optics - Lindlein, Norbert; Leuchs, Gerd (Handbook of Lasers and Optics, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dphy.optik.1optik.waveop

Wave phenomena and wave equations - Leuchs, Gerd (Proceedings of the International School of Physics "Enrico Fermi", 2019)
For any kind of wave phenomenon one can find ways to derive the respective dispersion relation from experimental observations and measurements. This dispersion relation determines the structure of the wave equation and thus characterizes the dynamics of the respective wave. Different wave phenomena are thus governed by different differential equations. Here we want to emphasize the experimental approach to matter waves, but before doing so we will discuss and test the procedure for other types of waves, in particular water waves.
CRIS-Team Scopus Importer:2019-06-21

Weak Measurement Enhanced Spin Hall Effect of Light for Particle Displacement Sensing - Neugebauer, Martin; Nechayev, Sergey; Vorndran, Martin; Leuchs, Gerd; Banzer, Peter (Nano Letters, 2019)
A spherical nanoparticle can scatter tightly focused optical beams in a spin-segmented manner, meaning that the far field of the scattered light exhibits laterally separated left- and right-handed circularly polarized components. This effect, commonly referred to as giant spin Hall effect of light, strongly depends on the position of the scatterer in the focal volume. Here, a scheme that utilizes an optical weak measurement in a cylindrical polarization basis is put forward to drastically enhance the spin-segmentation and, therefore, the sensitivity to small displacements of a scatterer. In particular, we experimentally achieve a change of the spin-splitting signal of 5% per nanometer displacement.
CRIS-Team Scopus Importer:2019-05-07
Keywords: localization; scattering; spin Hall effect; structured light; Weak measurement

Wellenfrontsensor für den Optical Workshop - Lindlein, Norbert; et al. (Laser, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.optik.1optik.wellen

White-light interferometer with dispersion - an accurate fiber-optic sensor for the measurement of distance - Häusler, Gerd; et al. (Applied Optics, 2005)
We present a fiber-optical sensor for distance measurement of smooth and rough surfaces that is based on white-light interferometry; the sensor measures the distance from the sample surface to the sensor head. Because white light is used, the measurement is absolute. The measurement uncertainty depends not on the aperture of the optical system but only on the properties of the rough surface and is commonly ∼ 1 μm. The measurement range is approximately 1 mm. The sensor includes no mechanical moving parts; mechanical movement is replaced by the spectral decomposition of light at the interferometer output. The absence of mechanical moving parts enables a high measuring rate to be reached. © 2005 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.whitel

Wide-field SU(1,1) interferometer - Frascella, Gaetano; Mikhailov, E. E.; Takanashi, N.; Zakharov, R. V.; Tikhonova, O. V.; Chekhova, Maria (Optica, 2019)
An SU(1,1) interferometer uses a sequence of two optical parametric amplifiers for achieving sub-shot-noise sensitivity to a phase shift introduced in between. We present the first realization of a wide-field SU(1,1) interferometer, where the use of a focusing element enables spatially multimode operation within a broad angle. Over this angle, the interference phase is found to be flat. This property is important for the high sensitivity to the phase front disturbance. Further, -4.3 +/- 0.7 dB quadrature squeezing, an essential requirement to the high sensitivity, is experimentally demonstrated for plane-wave modes inside the interferometer. Such an interferometer is useful not only for quantum metrology, but also in remote sensing, enhanced sub-shot-noise imaging, and quantum information processing. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-10-11

Young's Double-Slit, Invisible Objects and the Role of Noise in an Optical Epsilon-near-Zero Experiment - Ploss, Daniel; Kriesch, Arian; Etrich, Christoph; Engheta, Nader; Peschel, Ulf (ACS Photonics, 2017)
Epsilon-near-zero (ENZ) media disclose the peculiarities of electrodynamics in the limit of infinite wavelength but nonzero frequency for experiments and applications. Theory suggests that wave interaction with obstacles and disturbances dramatically changes in this domain. To investigate the optics of those effects, we fabricated a nanostructured 2D optical ENZ multilayer waveguide that is probed with wavelength-tuned laser light via a nanoscale wave launch configuration. In this experimental framework, we directly optically measure wave propagation and diffraction in a realistic system with the level and scale of imperfection that is typical in nanooptics. As we scan the wavelength from 1.0 to 1.7 μm, we approach the ENZ regime and observe the interference pattern of a microscale Young's double slit to steeply diverge. By evaluating multiple diffraction orders we experimentally determine the effective refractive index neff and its zero-crossing as an intrinsic measured reference, which is in agreement with theoretical predictions. We further verify that the double-slit and specifically placed scattering objects become gradually invisible when approaching the ENZ regime. We also observe that light-matter interaction intensifies toward ENZ and quantify how speckle noise, caused by tiny random imperfections, increasingly dominates the optical response and blue-shifts the cutoff frequency.
CRIS-Team Scopus Importer:2023-04-20
Keywords: diffraction; double-slit; ENZ; epsilon-near-zero; noise; photonics

Effect of fabrication errors on the diffraction pattern produced by sawtooth gratings - Harder, Irina; Lindlein, Norbert; Torcall-Milla, Francisco Jose (Applied Optics, 2010)

Measuring the modulus of the spatial coherence function using an error tolerant phase shifting algorithm and a continuous lateral shearing interferometer - Harder, Irina; Eisner, Martin; Voelkel, Reinhard; Rothau, Sergej; Schwider, Johannes; Schwider, Peter Mario (Optics Express, 2016)
The modulus of the degree of coherence can be derived from interference patterns either by using fringes and next neighbour operations or by using several interferograms produced through phase shifting. Here the latter approach will be followed by using a lateral shearing interferometer exploiting a diffractive grating wedge providing a linearly progressive shear. Phase shifting methods offer pixel-oriented evaluations but suffer from instabilities and drifts which is the reason for the derivation of an error immune algorithm. This algorithm will use five π/2-steps of the reference phase also for the calculation of the modulus of the coherence function.

Multi-Pass Shack-Hartmann Ebenheits-Test: Monitoring von thermischen Deformationen - Schwider, Johannes (DGAO-Proceedings, 2010)